Introduction to the 3RsC's cross-platform microphysiological systems evaluation for drug-induced liver injury in collaboration with FDA-CDER - Megan R. LaFollette; Ksenia Blinova; Amber B. Daniel; Deidre A. Dalmas; Emily Richardson; Graham Marsh; James T. Shoemaker; Ji Hye Seo; Jelena Vukasinovic; Laura J. Word; Szczepan W. Baran; Tomasz Kostrzewski; et al. (Regulatory Toxicology and Pharmacology, 2026)

Environmental life cycle impacts of bioenergy and value-added bioproducts derived from macroalgae - Jingyi Zhang; Farah Naaz; Udayan Singh; Troy R. Hawkins; Stephen T. Crafton-Tempel; Scott J. Edmundson; Jeff Caminiti; Jacob D. Watkins; Peter J. Valdez; Michael Huesemann (Energy and Climate Change, 2026)

Technical mitigation measures to reduce the bycatch of sharks: there is no silver bullet - David A. D. Drynan; G. Barry Baker; Stephen T. Garnett; Peter M. Kyne (Reviews in Fish Biology and Fisheries, 2026)
Incidental catch (bycatch) of sharks in commercial fisheries is driving global population declines. In this review we assess the efficacy of a comprehensive list of technical bycatch mitigation measures for all major commercial fishing gears. We structured our review around the three stages of capture where opportunities exist to mitigate bycatch: preventing capture; increasing escape probability; and decreasing at-vessel/post-release mortality. Adding magnetic repellents in static gears, removing lightsticks from longlines, adding artificial lights in gillnets, optimising gillnet mesh size, and using non-entangling Fish Aggregating Devices are all effective (i.e., reduce bycatch mortality) without causing harm (i.e., increase in shark catch, or injuring sharks or other species) or reducing target catch, and were feasible to implement. To enable escape, the use of excluders with appropriately configured escape panels/hatches in trawls is effective and feasible. The use of nylon leaders in place of wire in longlines is also effective and feasible but can harm sharks. Post-release mortality decreases by cutting leaders at the hook. Use of circle hooks in longlines is effective at reducing bycatch mortality, but can increase catch rates of sharks. Overall, we found that few measures were supported by studies that reported empirical data. Of those that are effective, many are unlikely to be adopted by fishers because they can reduce target catch, have deleterious impacts on sharks or other species or still require significant investment to resolve technical issues. The variety of measures available and the high degree of interspecific and geographical variation in responses highlights the need for more trials under local conditions before deployment. Future research priorities should include development and incorporation of necromones into commercially viable artificial baits, production of active electrical repellents at scale to encourage uptake, investigating the impact of removal of lightsticks from longlines on shark catch rates, and refinement of circle hook design to reduce shark catch rates.

Combined Effects of Volatiles on Attraction of Beetles to Carrion (Silphinae) - Stephen T. Trumbo (Journal of Insect Behavior, 2026)

Superbugs exposed: The occurrence of antimicrobial-resistant bacteria in food-producing animals in Suriname - Carlotte M. Rozemond; Edmund F. Rozenblad; Engeline van Duijkeren; Eline J. Pierik; Paul D. Hengeveld; Cindy M. Dierikx; Sabine C. de Greeff; Stephen G. Vreden; Ed IJzerman; Terrence Mawie; Joost Hordijk; Jaap T. van Dissel (Next Research, 2026)

Clinical outcomes of patients with brain metastases from primary esophageal cancer - Bianca Nolde-Lopez; Christina K. Cramer; Scott Isom; Anthony Naquin; Caio M.S.P. Rocha Lima; Ravi K. Paluri; Jimmy Ruiz; Fei Xing; Christopher T. Whitlow; Stephen B. Tatter; Adrian W. Laxton; Jaclyn J. White; et al. (Next Research, 2026)

Bioinspired pullulan-based adhesive coacervate films for targeted buccal delivery of peptides - Margarida M.A. Sacramento; Nazanin Z. Ezazi; Eleftheria Pantazoglou; Philip Mark Lund; Marco van de Weert; Zhongyang Zhang; Rui Vitorino; Floriane Bahuon; Ragna Berthelsen; Stephen T. Buckley; Gavrielle R. Untracht; Peter Eskil Andersen; et al. (Carbohydrate Polymers, 2026)

Human and Porcine Marginal Chordal Forces in a Vacuum Based Physiological In Vitro Mitral Valve Model - Mads V. Ancker; Sam E. Stephens; Justin T. Jack; Neil B. Ingels; Jonathan F. Wenk; Søren N. Skov; Surendra K. Chawla; Ajit. P. Yoganathan; Morten O. Jensen (Cardiovascular Engineering and Technology, 2026)
Introduction This study aimed to quantitatively investigate the role of marginal chordae of the mitral valve during static closure by analyzing the force within these chordae and its potential correlation with the transvalvular pressure. Materials and Methods Porcine (n = 10) and human (n = 4) mitral valves were mounted in a saddle-shaped annulus clamp, while an in vitro system was utilized to replicate a physiological systolic blood pressure by vacuum pressure applied to the atrial side of the valve. A Millar pressure catheter and force transducers (“C-gauges”) were used to acquire the data. Strut chordal force was recorded simultaneously with the marginal chordal force, to serve as a verification of the employed equipment. Results The marginal chordal force in porcine and human averaged to 0.012 N ± 0.008 N and 0.006 N ± 0.008 N respectively at peak systolic pressure of 120 mmHg. Additionally, a simplified finite element study was conducted and supports low marginal forces relative to intermediary chords. Discussion & Conclusion This low force calls into question the traditionally-described role of the marginal chordae in preventing mitral prolapse at closure. The chords do, however, still show signs of assisting with the leaflets’ positioning. The relationship between marginal chordal forces and transvalvular pressure varies significantly across experiments, further obfuscating their role in normal valvular function.

Trends in fertiliser use and efficiency in the Great Barrier Reef catchment area - Stephen E. Lewis; Cassandra S. James; Zoe T. Bainbridge; Aaron M. Davis; Adam Northey; Emma Lawrence; Rebecca Bartley (Journal of Environmental Management, 2026)

A review of trends, outcomes and the reasons for acquittals of wildlife cases appealed in the higher courts of Tanzania - Juma J. Kegamba; Diana T. Butiku; Elias R. Mwita; Stephen T. Garnett; Magdalena S. Kaaya (Biological Conservation, 2026)

Goat productivity under smallholder farmer management in semi-arid and hot-humid parts of Zimbabwe: a useful step for building resilient goat production systems in marginalized communities - Anderson Munengwa; Emmanuel T. Nyahangare; Prosper Jambwa; Alban Mugoti; Stephen Mandara; Melody Dzviti; Nation Chikumba; Lyndy J. McGaw (Tropical Animal Health and Production, 2026)
Information about on-farm goat productivity patterns is crucial for building resilient production systems in marginalised communities. Goat flock dynamics, management practices and production constraints in selected smallholder farming systems of Zimbabwe were explored. A multistage sampling approach was adopted to recruit a total of 200 participants. The effect of environment on productive indices and constraints was analysed using the Mann-Whitney U test and either Ordinal or Nominal logistic regression, respectively, in IBM SPSS version 26. Results highlight the importance of goats to rural communities. On average, 10.01 ± 5.14 goats were maintained per capita and the largest proportion was found in hot-humid environments ( p > 0.05). However, reproductive performance in terms of average gestation length (4. 47 ± 0.59 months), age at first service (11.20 ± 2.24 months) and kidding (15.67 ± 2.30 months) was poorer in semi-arid environments than in the hot-humid areas ( p > 0.05). Moreover, optimum productivity is hampered by a multitude of factors, including selection of breeding animals mainly based on personal appraisal (Index = 0.120), dependence of animals primarily on natural forages for feed (Index = 0.213), sub-optimal housing conditions like irregular cleaning (Index = 0.123) and disease preponderance (Index = 0.129). Ailments were mainly controlled using ethnoveterinary medicines (Index = 0.103). Taken together, our results underline the crucial role of goats to rural livelihoods, which could be elevated even more through community-based capacity building on proper animal husbandry practices in terms of breeding, nutrition, health and housing management.

Mechanisms and trait controls of canopy thermal regulation across a tropical rainfall gradient - Matteo Detto; Brett T. Wolfe; Alfonso Zambrano; S. Joseph Wright; Stephen Pacala (Agricultural and Forest Meteorology, 2026)

Heat, Health and Holidays: Reported Heat Related Adjustments to Australian Tourist Behaviour - Kerstin K. Zander; Sohail Ali; Amila Kasun Sampath Udage Kankanamge; Ronju Ahammad; Jonatan Lassa; Matthew Abunyewah; Michael Odei Erdiaw‐Kwasie; Stephen T. Garnett (International Journal of Climatology, 2026)
Extreme heat is one of the fastest growing threats to human health, already causing tens of thousands of deaths annually and projected to affect hundreds of millions more people under continued warming. Australians are highly mobile and live in one of the most heat‐exposed countries, so rising temperatures create risks both at home and while travelling. Yet the implications of extreme heat for tourist health, behaviour and destination choice remain poorly understood. Using Protection Motivation Theory, we examined how heat risk perception and coping appraisal relate to reported travel adjustments due to weather, with implications for public health agencies, destination managers and policymakers responding to the growing burden of heat. We aimed to examine (1) how extreme heat, compared to other weather events, affects reported holiday behaviour, (2) whether tourists have decided against destinations perceived as too hot and (3) which individuals are most likely to make heat‐related adjustments to their travel. Data were collected through a national online survey ( n = 2292) and analysed using descriptive statistics (Chi‐square tests, ANOVA) and model estimation (multinomial logit and binary logit models). We found that 20% of respondents reported making changes to their most recent holiday because of the weather: 6% in response to heat, 6% to heavy rain and 8% to severe natural hazards. Most reported heat‐related changes involved timing (35%), activities (34%) or destinations (23%), reflecting substitution in time and place rather than cancellation. Age (−), education (+), income (−), perception of personal risk (+) and participation in nature‐based activities (+) were significantly associated with reported heat‐related adjustments. Awareness of weather forecasts and use of warning apps were strong predictors of reported behavioural change. One third of respondents reported they had previously decided against a destination because it was perceived as too hot, mostly for domestic trips.

Enhancing the search for potentially useful plant extracts with anthelmintic activity by combining traditional ethnoveterinary knowledge with wild type and stress reporter Caenorhabditis elegans in vitro screening tools - Anderson Munengwa; Emmanuel T. Nyahangare; Prosper Jambwa; Alban Mugoti; Stephen Mandara; Melody Dzviti; Nation Chikumba; Lyndy J. McGaw (South African Journal of Botany, 2026)

Metagenomic Profiling of Obesity-Associated Differences in Ex Vivo Intestinal Microbial Biotransformation of Sumac Gallotannins - A1344 - Susanne U. Talcott; Rodrigo U. San Cristobal Blanco; Elizabeth U. Culpepper; Tara U. Mahmood; Stephen T. Talcott (Journal of Nutrition Education and Behavior, 2026)

Water quality trends in river catchments draining to the Great Barrier Reef: an analysis of ∼40 years of data - Cassandra S. James; Petra M. Kuhnert; Stephen E. Lewis; Rebecca Bartley; Emma Lawrence; Jennifer Strauss; Reinier M. Mann; Ryan D.R. Turner; Zoe T. Bainbridge (Journal of Environmental Management, 2026)

Timing and drivers of Cenozoic marine phosphogenesis along the southeastern Pacific margin - Priscilla R. Martinez; Barbara Carrapa; Jason D. Kirk; Mark T. Clementz; Carolina S. Gutstein; Fabían A. Muñoz; Joao Gabriel Martínez-López; Whitney E. Worrell; Stephen T. Hasiotis; Jacob Q. Stevens (Chemical Geology, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Demography and Localized Reservoirs of Diversity Underlie Global Divergence in the Giant Kelp Macrocystis pyrifera - E. C. Giles; A. Zaiko; H. G. Hampton; P. Saenz‐Agudelo; M. Scriver; D. Crossett; A. Sim; X. B. Zhang; T. Jedrecka; C. O. Blain; L. Rauhina‐August; C. E. Cornwall; et al. (Molecular Ecology, 2026)
Accurate assessments of genetic diversity are crucial for effective management of natural resources. Numerous evolutionary mechanisms and genetic constraints can shape lineage divergence, challenging our quantification of biodiversity. Here, using whole genome resequencing of globally distributed giant kelp, Macrocystis pyrifera (Order: Laminariales), we show clear separation of genetic groups across the Pacific based on 99 genotyped individuals and 799,160 SNPs. Additionally, divergence across 88 genotyped individuals (53 derived in silico and 35 newly sequenced) considering 5,466,408 SNPs is attributed to both historical demographic processes and differential selection. Between Central California and the South Pacific (Chile, Tasmania, New Zealand), high divergence has occurred with very weak levels of gene flow, with concurrent timing of divergence. In parts of the South Pacific, kelp exhibited nucleotide diversity comparable to Central Californian populations but showed stronger signals of directional selection and excesses of rare alleles, with fewer genes showing signs of negative selection and some carbon‐related genes under positive selection. In contrast, Central Californian kelp had an excess of genes with synonymous mutations and showed evidence of a recent population contraction, as indicated by linkage disequilibrium and Tajima's D . In all populations, genome‐wide background divergence was paired with narrow genomic intervals of high nucleotide diversity and high linkage disequilibrium, which predominantly contained pervasive repetitive sequences. These repetitive regions were larger and more often shared among genetic groups in the South Pacific. They also appear to harbour genes of unknown function and alleles at intermediate frequency, suggesting that giant kelp maintain reservoirs of diversity within linked repeats, and this phenomenon is more pronounced in South Pacific M. pyrifera . Overall, the discovery of differential selection and structural variation as key drivers of divergence points to underappreciated genomic mechanisms of adaptation in kelp. These results will be useful for informing efforts to enhance climate resilience by identifying the evolutionary potential underlying kelp forest adaptation in the future.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Long-Term Patterns of Geographically Isolated Wetland Inundation and Hydroperiods from the Gulf Coastal Plain - Nicholas S. Marzolf; Brian A. Clayton; Stephen W. Golladay; Lora L. Smith; Steven T. Brantley (Wetlands, 2026)

Plasticity in the Function of Secretions in the Burying Beetle, Nicrophorus orbicollis - Stephen T. Trumbo; Justin D. Sardi (Journal of Insect Behavior, 2026)

A perfluoro-functionalised fluorescent maleimide probe for imaging of per- and polyfluoroalkyl substances - Jake E. Barker; Stephen D. P. Fielden; Richard H. Kempton; Calum T. J. Ferguson; Rachel K. O’Reilly; Grant B. Douglas (Environmental Chemistry Letters, 2026)
The persistence of per- and polyfluoroalkyl substances in the environment is becoming a major health concern, yet studying their fate and behaviour in complex media is limited due to the lack of suitable analytical methods. Here we proposed that a fluorescent polyfluoroalkyl probe could enable rapid tracing and negate drawbacks associated with current techniques. We synthesised a fluorescent probe containing a maleimide motif grafted to perfluorooctanoic acid. Using a conductivity assay, the critical micelle concentration was determined, and cryogenic transmission electron microscopy was further utilised to verify the presence of multilamellar vesicles. Titration of the fluorescent probe with a base enabled the determination of the acid dissociation constant, an important property of perfluorooctanoic acid. Results show that this fluorescent probe exhibits similar properties to perfluorooctanoic acid, and thus could reasonably act as an environmental proxy, with the benefit of strong, concentration-dependent and environmentally responsive fluorescence. This fluorescence offers a facile entry point for real-time tracing in various media. Further exploration of this tracer through plant, concrete, or soil studies could enable a better understanding of per- and polyfluoroalkyl substance behaviour in range of natural and artificial media.

Multifrequency Electrical Impedance Myography Enhanced with Machine Learning for Screening Patients with Neuromuscular Disorders - Buket Sonbas-Cobb; Seward B. Rutkove; Baoguo Wei; Sara Robicheau; W. David Arnold; Kaneshia Hives; Amy Bartlett; Peter Riley; Aleah Pagan; Stephen M. Chrzanowski; Basil T. Darras; Stephen J. Kolb (Annals of Biomedical Engineering, 2026)
Purpose We evaluated surface electrical impedance myography (EIM) enhanced with machine learning to serve as a new office-based screening tool for neuromuscular disease Methods EIM of nine muscles was successfully performed in 119 adults and 111 children (approximately half healthy and half diseased) for a total of 3158 individual muscle measurements. Multifrequency data were processed with feature engineering and classification. Nested cross-validation assessed performance, with muscle-based predictions aggregated to participant via majority voting Results Single-feature analyses showed moderate-to-good discrimination (area-under-ROC curve of 0.62–0.73). When multifrequency features were used, participant-based logistic regression and extra trees ensemble models achieved 84% accuracy with 88.1% sensitivity in adults and 93% accuracy and 94.6% sensitivity in children. Beyond classification, regression using EIM predicted muscle strength with R 2 = 0.49, outperforming single-frequency correlations Conclusion These results demonstrate that machine learning-enhanced EIM can successfully distinguish individuals with neuromuscular disease from healthy individuals. Nevertheless, further studies in larger populations of people would help advance this technology to the point that it could serve as a convenient, office-based screening tool for neuromuscular disease.

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Evaluating the use of taxonomy in the IUCN Red List - Stephen T. Garnett; Claire E. Johnston; Phil Bowles; Les Christidis; Stijn Conix; J. W. Duckworth; Aaron Lien; Frank E. Zachos; Joeri Witteveen (Conservation Biology, 2026)
Taxonomy defines the units that conservationists strive to preserve for future generations. However, the discovery of new species and the taxonomic revision of existing species affect conservation efforts. Despite the importance of taxonomy for a species’ conservation, there is currently no overview of how those leading species extinction risk assessments use taxonomy. To fill this gap, we asked the chairs of the International Union for Conservation of Nature's (IUCN) Species Survival Commission Specialist Groups and other IUCN expert groups that coordinate extinction risk assessments about the state of taxonomy within their taxonomic group of interest, their sources of information, and what taxonomy‐related challenges they encounter in conducting assessments. Most experts answered immediately and in detail, reflecting the importance of taxonomy. Approaches to taxonomy were diverse. Although most experts ignored debates about species definitions, for some groups, particularly mammals and birds, there were theoretical differences about what constitutes a species. Governance of species lists varied from individual experts making all decisions, to dedicated committees, to collective decisions for all taxonomic resolutions being made by others outside the group. The extent to which current taxonomy represents the views and consensus of the taxonomic community with an interest in that taxonomic group is not known. However, the taxonomies used in IUCN assessments differ from those used by other species conservation initiatives led by multilateral environmental agreements or the Catalogue of Life. Greater alignment is possible and could be beneficial, though it may constrain the flexibility and adaptability in taxonomic decision‐making that informs IUCN Red List assessments. We argue that regardless of the extent to which further alignment is sought, there is potential to enhance taxonomic list governance within the IUCN.

Strategic deep tillage of deep sand soils impacts the sorption and biological availability of trifluralin - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Michael T. Rose; Benedict Arthur; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2026)

Metabolic fate of montmorency tart cherry (Prunus cerasus L.) polyphenols and their association with short-chain fatty acids in humans: A secondary analysis - Muhammad Jawad; Stephen T. Talcott; Robert G. Brannan; Angela R. Hillman (Food Bioscience, 2026)

A Portable, Active Abdominal Compression Binder for Orthostatic Intolerance: Design and Evaluation in Healthy Subjects - Vishnu S. Emani; Andreas Escher; Stephen P. Juraschek; Ellen T. Roche (Annals of Biomedical Engineering, 2026)

Urbanization impacts on stream and lake water quality in a small watershed in central Massachusetts, USA - Laura C. Reynolds; Allison L. Dunn; William J. Hansen; Meghna Dilip; Diana M. T. Sharpe; Nathan A. Ahlgren; Jacquelyn Burmeister; Caitlin Dellert; Alyssa Hammond; Stephen Humphrey; Katie Liming; Emily Maynard; et al. (Environmental Monitoring and Assessment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Lessons learned from building Confluence: Cloud-based global river discharge estimation software for the SWOT satellite - Nicole Tebaldi; Colin J. Gleason; Michael T. Durand; Stephen Coss; Travis Simmons (Environmental Modelling & Software, 2026)

The future of Global Environmental Assessments: 20 years after the Millennium Ecosystem Assessment - Elena Michele Bennett; Walter Reid; Stephen Carpenter; Tom Dietz; Garry Peterson; Neville Ash; T Doug Beard; Silke Beck; Reinette Biggs; Noel Castree; John Ehrmann; Tim Forsyth; et al. (Current Opinion in Environmental Sustainability, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Ghanaian farmers' perspectives on pesticides: Balancing use and environmental sustainability - Francis Clottey Odonkor; Stephen T. Odonkor (Crop Protection, 2026)

Late glacial sedimentation in the Atchafalaya Basin of Louisiana and its link to overflow from glacial Lake Agassiz - James T. Teller; Stephen R. Moran (Quaternary Science Reviews, 2026)

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Water sparing versus sharing: Depolarising wetland management with novel environment-agriculture policy - Matthew W. Herring; Stephen T. Garnett; Kerstin K. Zander (Biological Conservation, 2026)

Nutrient Transfer Dynamics of Anadromous Alewives (Alosa pseudoharengus) in Freshwater Spawning and Nursery Habitats - Robert E. Vincent; John M. Logan; John J. Sheppard; Michael Power; Stephen T. Hurley; Kevin Bennett (Estuaries and Coasts, 2026)
River herring (alewife, Alosa pseudoharengus and blueback herring, A . aestivalis ) can act as vectors of nutrient transfer between marine and freshwater environments. Adult river herring can transfer marine-derived nutrients to freshwater ecosystems during spawning migrations through excretions and direct consumption of adults, eggs, and early phase juveniles by freshwater scavengers and predators. Adults and juveniles can transfer nutrients derived during freshwater residency back to the marine environment following emigration and the same excretion and consumption mechanisms. Potential nutrient transfers were assessed by applying carbon, nitrogen, and sulfur stable isotope analyses to a collection of juvenile and adult alewives, baseline food web components, and freshwater fish predators in three ponds in southeastern Massachusetts USA. Out-migrating adult alewife tissue stable isotope values were lower for both carbon and sulfur but higher for nitrogen than in-migrating conspecifics reflecting incorporation of freshwater-derived nutrients. Most juvenile alewife stable isotope values were at steady state with freshwater food webs at the time of sampling reflecting additional export of freshwater-derived nutrients with their eventual emigration to the marine environment. Stable isotope-based detection of marine-derived nutrients in freshwater predators was limited to catadromous elvers ( Anguilla rostrata ), anadromous white perch ( Morone americana ), and semi-anadromous yellow perch ( Perca flavescens ) with no marine-derived nutrients detected in resident freshwater fish predators. However, juvenile alewives were observed in stomachs of smallmouth ( Micropterus dolomieu ) and largemouth bass ( M . nigricans ). Results further inform current alewife ecosystem-level interactions with the marine and freshwater environments that they occupy during different life history phases for the many coastal watersheds in New England.

Resistance-based exercise restores muscle health in dialysis patients - Piush Srivastava; Sunil Kumar Singh; Rakesh Sathish Nair; Saket Jha; Navin Viswakarma; Deepti Srivastava; Greg Hachaj; Stephen T. Bartlett; Ilaria Santi; Aslam Ejaz; Robert W. Motl; Enrico Benedetti; et al. (Journal of Muscle Research and Cell Motility, 2026)
Chronic kidney disease (CKD) and end-stage renal disease (ESRD) are serious health concerns worldwide that require regular dialysis before a kidney transplant for a better quality of life. Due to aging and frailty, dialysis patients are often limited in physical activity, which can lead to multiple health complications and sometimes result in patient death. Therefore, maintaining muscle health is crucial for individuals undergoing dialysis. We recently reported that personalized resistance-based exercise can improve frailty in dialysis patients; however, the molecular mechanisms underlying its effects on muscle health remain unknown. RNA-Seq analysis revealed that exercise upregulates genes associated with muscle stemness, regeneration, and differentiation. Furthermore, our study demonstrated that exercise upregulates mitochondrial proteins involved in the oxidation of organic compounds and mitochondrial function in muscle. Moreover, we observed that exercise increased energy production via glucose uptake, glycogenesis, and fatty acid metabolism. These results suggest that personalized resistance-based muscle therapy in dialysis patients restores the expression of genes and proteins associated with muscle stemness, regeneration, differentiation, and energy generation.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Stochastic modelling of burden of livestock diseases on domestic ruminants in Ethiopia - Wudu T. Jemberu; Gemma Chaters; Theodore J.D. Knight-Jones; William Gilbert; Stephen Kwok; Mieghan Bruce; Benjamin Huntington; Jonathan Rushton (Preventive Veterinary Medicine, 2026)

Effects of Vairimorpha (Nosema) ceranae and Lotmaria passim on antimicrobial peptide expression in the digestive tract of honey bees (Apis mellifera L.) - Courtney I. MacInnis; Lien T. Luong; Stephen F. Pernal (Journal of Invertebrate Pathology, 2026)

Encapsulation of jabuticaba (Plinia cauliflora) peel extract with whey or pea protein in combination with gum arabic enhances anthocyanin bioaccessibility and metabolite production - Larissa Lorrane Rodrigues Borges; Valdeir Viana Freitas; Janaina Gonçalves Fernandes; Amanda Lais Alves Almeida Nascimento; Hélia de Barros Kobi; Evandro Martins; Pedro Henrique Campelo Felix; Stephen T. Talcottt; Paulo César Stringheta (Food Chemistry, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Dietary exposure to nitrate and nitrite of the Hong Kong population through a total diet study - Stephen W. C. Chung; Joey L. Y. Kwok; T. C. Chan; Waiky W. K. Wong; Gabriel Y. S. Chan; Tony C. Y. Chow; Terence Y. Y. Cheung (Food Additives & Contaminants: Part A, 2026)

Efficacy and Economic Viability of an Integrated Pest Management Strategy Against Phthorimaea absoluta in Open-Field Tomato Production in Northern Tanzania - Simon B. Boni; Stephen T. O. Othim; Nickson Mlowe; Ramasamy Srinivasan (Journal of Crop Health, 2026)

Radiological and elemental hazards of informal gold mining at OAU: health risk modelling with spectrometric and probabilistic indices - Felix S. Olise; Lasun T. Ogundele; Nurudeen O. Omowumi; Stephen F. Olukotun; Muyiwa M. Orosun (Environmental Geochemistry and Health, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Identification of antihypertensive peptides from Eudrilus eugeniae (Kinberg, 1867): in vitro ACE-I inhibition and peptide profiling - Roi Martin B. Pajimna; Omar A. Villalobos; Stephen B. Lirio; Hsi-Ya Huang; Chia-Her Lin; Allan Patrick Macabeo; Mary-Jho Anne T. Corpuz; Oliver B. Villaflores (Natural Product Research, 2026)

OECMs in China need to consider practical adaptability - Hai Ren; Richard T. Corlett; Zhiyun Ouyang; Stephen Blackmore (Trends in Ecology & Evolution, 2026)

Simulating climate change impacts on soil carbon storage in agroecosystems from Brazilian drylands - Lucas T. Greschuk; Stephen Ogle; Jorge L. Locatelli; Ram B. Gurung; Bruna E. Schiebelbein; Diana Signor; Rafael G. Tonucci; Leidivan A. Frazão; Maurício R. Cherubin (Journal of Environmental Management, 2026)

Different responses of African rice cultivars to alternate wetting and drying irrigation and anaerobic digestate application - Stephen Yeboah; Patricia Amankwaa-Yeboah; Jaime Puértolas; Francis B. Agyenim; Kirk T. Semple; Ian C. Dodd (Field Crops Research, 2026)

Ten questions concerning indoor dust - Erica M. Hartmann; Karen C. Dannemiller; Delphine K. Farmer; Rachel E. O'Brien; Joseph Berberich; Jenna C. Ditto; Olivia R. Farinas; Elliott T. Gall; Anindita Ganguly; Vicki H. Grassian; Rachel Greene; Bridget Hegarty; et al. (Building and Environment, 2026)

In poor taste: leaf palatability traits are not correlated with aboveground enemy release - Zoe A. Xirocostas; Eve Slavich; Susan E. Everingham; Juha-Pekka Salminen; Louis Booth; Roslyn Gleadow; Jeff Ollerton; Riin Tamme; Begoña Peco; Vincent Lesieur; S. Raghu; Robert R. Junker; et al. (Oecologia, 2026)

Resilience of small-Scale maize irrigation farmers to climate change stress in South Africa - Yonas T. Bahta; Stephen A. Nyaki; Henry Jordaan; Markus Monteiro; Edward Nesamvuni (Mitigation and Adaptation Strategies for Global Change, 2026)

Decoding bacterial extracellular vesicles: A review on isolation and characterization techniques - Malatesh S. Devati; Apoorva Jnana; Stephen P. Kidd; Slade O. Jensen; T. G. Satheesh Babu; Dinesh Upadhya; Thokur S. Murali (Archives of Microbiology, 2026)

An opalised mid-Cretaceous flora from the Griman Creek Formation at lightning ridge, eastern Australia - Stephen McLoughlin; Sherri Donaldson; Christian Pott; Elizabeth T. Smith (Review of Palaeobotany and Palynology, 2025)

Thresholds of visible light detection in hawksbill turtle (Eretmochelys imbricata) hatchlings - Robert T. Gammariello; Stephen G. Dunbar (Regional Studies in Marine Science, 2025)

Cholinergic dysfunction in occupational manganese exposure - T. Noah Hutson; Susan Searles Nielsen; Natalie Senini; John O’Donnell; Hubert P. Flores; Tamara Hershey; Joel S. Perlmutter; Anil Kumar Soda; Stephen M. Moerlein; Zhude Tu; Michael Kasper; Lianne Sheppard; et al. (NeuroToxicology, 2025)

Seismic imaging of mid-crustal heterogeneity beneath geothermal systems, central Taupō Volcanic Zone, New Zealand - Stephen Bannister; Edward A. Bertrand; Geoff Kilgour; T. Grant Caldwell; Isabelle Chambefort; Wiebke Heise; Sandra Bourguignon (Journal of Volcanology and Geothermal Research, 2025)

A bibliometric review of research on climate change in Africa - Obianuju Patience Ilo; Stephen Sunday Emmanuel; Ademidun Adeola Adesibikan; Odunayo T. Ore; Ajibola A. Bayode; Hamza Badamasi; Saheed O. Sanni; Mulala D. Simatele (Environmental Science & Policy, 2025)

Ten questions concerning wind-focused shape and structural optimization of tall buildings - Magdy Alanani; Ahmed Elshaer; Stephen Vasilopoulos; Seymour M.J. Spence; Girma T. Bitsuamlak; Ashraf El Damatty (Building and Environment, 2025)

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Population-level phylogenomic analysis yields insights into species cohesion and population substructure of Lobelia section Lobelia (Campanulaceae) - Grant T. Godden; Andrew A. Crowl; Stephen R. Patten; Princess Abu; Svea Hall; Mark O. Johnston; Douglas W. Schemske; T. Wayne Barger; Miguel A. Pérez-Pérez; Christopher R. Herlihy; Lynda F. Delph; Christopher B. Blackwood; et al. (Molecular Phylogenetics and Evolution, 2025)

Microbial community response to spent mushroom substrate composting methods by phospholipid fatty acid analysis - Siobhan N. Jordan; Michael P. Farrell; Caroline T. Gilleran Stephens (Biocatalysis and Agricultural Biotechnology, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Pre-Clinical Models of Heart Failure with Preserved Ejection Fraction: Advancing Knowledge for Device Based Therapies - Nina Langer; Andreas Escher; Caglar Ozturk; Andrew F. Stephens; Ellen T. Roche; Marcus Granegger; David M. Kaye; Shaun D. Gregory (Annals of Biomedical Engineering, 2025)
Heart failure with preserved ejection fraction (HFpEF) is a growing health problem worldwide, accounting for half of all heart failure cases. HFpEF patients present with diverse underlying causes and symptoms, making diagnosis and treatment challenging. Current pharmacological therapies are inadequate, while approved device-based therapies have shown limited success due to patient heterogeneity. This underscores the need for improved pre-clinical models, critical for guiding the design and development of effective therapeutic devices. This paper presents an overview of current pre-clinical HFpEF models, including in-silico, in-vitro, ex-vivo, and in-vivo approaches, aimed at advancing the understanding of HFpEF physiology and the development of device-based therapies. We examined each model's ability to replicate key HFpEF characteristics, discuss their respective strengths and limitations, and highlight their role in supporting the creation of clinically relevant solutions. Additionally, the potential of emerging advancements is explored.

Effects of Biodiversity Loss on Freshwater Ecosystem Functions Increase With the Number of Stressors - Ralf B. Schäfer; Daria Baikova; Helena S. Bayat; Arne J. Beermann; Stella A. Berger; Jens Boenigk; Mario Brauns; Andrea Burfeid‐Castellanos; Bradley J. Cardinale; Gwendoline M. David; Alexander Feckler; Christian K. Feld; et al. (Global Change Biology, 2025)
A multitude of anthropogenic stressors drive biodiversity loss and alter ecosystem functioning. Freshwaters, which contribute disproportionally to global biodiversity and biogeochemical cycles, are particularly threatened. Although the relationship between biodiversity and ecosystem functions (BEF) is generally well‐established, especially in terrestrial ecosystems, the role of multiple, co‐occurring stressors in modulating the relationship remains unclear. We conducted a meta‐analysis to address this knowledge gap by assessing the effect of multiple stressors on the relationship between taxon richness and four measures of ecosystem function. The relationship was generally positive, with the slope becoming steeper as the number of stressors increased, suggesting that exposure to multiple stressors exacerbates impacts of biodiversity loss on ecosystem function. Multiple stressor effects on both taxon richness and ecosystem functions were largely predictable from individual stressor effects, although antagonistic effects on ecosystem functions emerged in 14% of the considered cases. The type of stressor and ecosystem function, along with taxonomic group, exerted no influence on the BEF relationship, contrary to our expectations. Microbial production and biomass declined most strongly in response to stressors, despite notable variability. Overall, our findings imply that functional consequences of freshwater biodiversity loss are more severe under multifaceted environmental change than previously assumed.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Half of coastal aquaculture sites in Queensland are in close proximity to shorebird habitats - Caitlin D. Kuempel; Marina Christofidis; Richard A. Fuller; Robert Bush; Stephen T. Garnett; Micha V. Jackson (Ocean & Coastal Management, 2025)

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Drought, topography, and forest management shape wildfire occurrence and severity in montane Australian landscapes - Jeremy Johnson; Luke T. Kelly; Luke Collins; Stephen Stewart; Craig R. Nitschke (Science of The Total Environment, 2025)

Chemical investigation of the beetle Agrilus cyanescens (Buprestidae) - Isaiah I. Korostil; Jessica L. Pepe; Stephen T. Deyrup (Phytochemistry Letters, 2025)

Innovative planning for sustainable development: A win-win approach through conversion of negative into positive externalities - Lawrence W.C. Lai; Frank T. Lorne; Stephen N.G. Davies; K.W. Chau (Land Use Policy, 2025)

Occurrence and tissue distribution of per- and polyfluoroalkyl substances (PFAS) in fishes from waterbodies with point and non-point sources in Massachusetts, USA - Heather L. Walsh; Vicki S. Blazer; Emma Lord; Stephen T. Hurley; Denis R. LeBlanc (Aquatic Toxicology, 2025)

The effect of dietary nitrate supplementation on resistance exercise performance: A dose–response investigation - Rachel Tan; Isabella G. Lincoln; Keonabelle K. Paniagua; Justin M. Foster; Lauren E. Wideen; Raymond T. Gerardo; Nathan J. Ornelas; Isaac Tchaprazian; Jeffrey Li; Michael Egiazarian; Samantha N. Rowland; Stephen J. Bailey; et al. (European Journal of Applied Physiology, 2025)
Dietary nitrate (NO 3 − ) can enhance skeletal muscle contractile function and explosive-type exercise by modulating type II muscle fibers; however, limited attention has been directed at exploring the optimal dosing guidelines and potential performance-enhancing effects of NO 3 − supplementation during resistance-type exercise. The purpose of our investigation was to examine potential dose–response effects of concentrated NO 3 − -rich beetroot juice on neuromuscular performance during resistance exercise. Eighteen resistance-trained men were assigned in a double-blind, randomized, crossover design, to four conditions to consume beetroot juice containing: negligible NO 3 − (PL); ~ 6 mmol NO 3 − (BR-LOW); ~ 12 mmol NO 3 − (BR-MOD); and ~ 24 mmol NO 3 − (BR-HIGH). Participants completed 1 set of vertical countermovement jumps (CMJ), 2 sets × 3 repetitions of barbell back squats, and 2 sets × 3 repetitions of barbell bench press 2.5 h post-supplementation. Plasma [NO 3 − ] increased in a dose-dependent manner ( P < 0.01). Plasma [nitrite] ([NO 2 − ]) increased in all BR conditions compared to PL ( P < 0.05), such that BR-MOD vs. BR-LOW ( P < 0.01) and BR-LOW vs. PL ( P < 0.01), but BR-HIGH was not different compared to BR-MOD ( P > 0.05). Performance was not different between conditions in CMJ, 50% one-repetition maximum (1RM) and 75%1RM back squats, or 50%1RM and 75%1RM bench press ( P > 0.05). The change in plasma [NO 2 − ] was significantly correlated with peak power ( r = − 0.65, P = 0.003), mean power ( r = − 0.52, P = 0.03), and mean velocity ( r = − 0.48, P = 0.04) during 50%1RM back squats following BR-LOW vs. PL but not in other conditions ( P > 0.05). This study indicates that dietary NO 3 − does not impact resistance exercise performance at any of the doses assessed in the current study.

Clarifying the so‐called gull problem in the Gulf of Maine: Response to Taylor et al. (2024) - Antony W. Diamond; Linda Welch; Donald E. Lyons; Lauren C. Scopel; Brian Benedict; Heather L. Major; Stephen W. Kress; Stephanie Koch; Ian C. T. Nisbet (Conservation Biology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

How can China protect 30% of its land? - Hai Ren; Richard T. Corlett; Zhiyun Ouyang; Stephen Blackmore (Trends in Ecology & Evolution, 2025)

A comparison of three nutritional models for estimating total metabolisable energy requirements for a ewe, beef breeding cow, lamb, and a calf/yearling in New Zealand’s pasture-only system - Joseph A. Adjabui; Patrick H.C. Morel; Stephen T. Morris; Paul R. Kenyon; Peter R. Tozer (Livestock Science, 2025)

Sterol-modified plants reduce aphid performance by limiting sterol availability - Ivy W. Chen; Jiaxin Lei; Zekun Jin; Adriana E. Alvarez; Robert J. Grebenok; Stephen Fletcher; Spencer T. Behmer; Keyan Zhu-Salzman (Insect Biochemistry and Molecular Biology, 2025)

Calibration of the FullCAM model for Australian native vegetation - David I. Forrester; Jacqueline R. England; Chiara Pasut; Keryn I. Paul; Lauren T. Bennett; Chris Eastaugh; Thomas Fairman; Melissa Fedrigo; Carl R. Gosper; Sabine Kasel; Tom Lewis; Crispen Marunda; et al. (Ecological Modelling, 2025)

Extraction of Various Crude Oil Fractions from Water by Sorption: An Overview - Ebuka Chizitere Emenike; Joy Adetooke Adeleke; Stephen Sunday Emmanuel; Ifeoluwa Peter Oyekunle; Ozukwe Austin Eze; Chisom T. Umeh; Kingsley O. Iwuozor; Kanika Dulta; Yogesh Kumar Awasthi; Adewale George Adeniyi (Water, Air, & Soil Pollution, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The Mechanisms Through Which Fire Drives Population Change in Terrestrial Biota - Ella Plumanns‐Pouton; Julianna L. Santos; Cristina Aponte; Lluís Brotons; Luke T. Kelly; Stephen C. Mason; Kirsten Parris; Lauren Ponisio; David A. Keith (Global Change Biology, 2025)
Global fire regime change is threatening terrestrial biodiversity. Understanding how these changes affect biota is essential to protect biodiversity now and into the future. A targeted examination of the mechanisms through which fire influences populations will help achieve this by enabling comparisons and connections across taxa. Here, we develop a cross‐taxa framework that identifies mechanisms through which fire regimes influence terrestrial species populations over different time scales, and traits on which those mechanisms depend. We focus on amphibians, birds, fungi, insects, mammals, plants, and reptiles. First, we identify key mechanisms through which fire regimes influence species populations across different taxonomic groups. Second, we link these mechanisms to functional traits that influence the relevance to different species. Third, we identify traits that shape the vulnerability—or conversely, resilience—of species populations to frequent, high‐intensity, and large wildfires that are emerging as a threat in many parts of the world. Finally, we highlight how this integrative framework can be useful for understanding and identifying fire‐related threats common to different taxa across the globe and for guiding future research on fire‐related population change.

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Detection of multi-year ex-fast ice in the Weddell Sea, Antarctica, using ICESat-2 satellite altimeter data - Younghyun Koo; Hongjie Xie; Walter N. Meier; Stephen F. Ackley; Nathan T. Kurtz (Remote Sensing of Environment, 2025)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Systematic revision of the genus Orchidasma Looss, 1900 and description of Orchidasma orchilobata n. sp. from the loggerhead Caretta caretta (L.) and Kemp’s ridley Lepidochelys kempii (Garman) turtles - Thomas G. Rosser; Aiden Meaux; Ethan T. Woodyard; Justin M. Stilwell; Bradley M. Richardson; Logan R. S. Robison; Jill B. Hudnall; Kaylin McNulty; Jonah A. Nguyen; Divya Rose; Debra Moore; Beth Peterman; et al. (Systematic Parasitology, 2025)

AviList: a unified global bird checklist - Frank E. Rheindt; Paul F. Donald; David B. Donsker; Jeffrey A. Gerbracht; Marshall J. Iliff; Denis Lepage; Janette A. Norman; Pamela C. Rasmussen; Richard Schodde; Thomas S. Schulenberg; Juan I. Areta; Frederik P. Brammer; et al. (Biodiversity and Conservation, 2025)

Inversions Dominate Evolution in the European Sardine ( Sardina pilchardus ) Amid Strong Gene Flow - Stephen J. Sabatino; M. Pilar Cabezas; Paulo Pereira; Susana Garrido; António M. Santos; Miguel Carneiro; Paulo T. Santos; Bruno Louro; Cymon J. Cox; Adelino V. M. Canário; Ana Veríssimo (Molecular Ecology, 2025)
Inversions can play key roles in the genetic architecture of adaptation, but the scale of their effects across different species remains poorly understood. Here, we use whole‐genome sequencing and demographic modelling to investigate the influence of inversions on the population genomics of the r‐selected European sardine ( Sardina pilchardus ). Allele frequency differences from millions of SNPs across 34 populations spanning the species' range were analysed. Genomic scans identified several extreme outlier regions overlapping large inversions (29–52 Mbp), collectively representing over half the genome. Our findings suggest these inversions correlate with locally adapted life‐history strategies. First, SNPs within outlier regions containing inversions exhibited striking allele frequency differences between Atlantic and Mediterranean sardines, which differ in key adaptive life‐history traits. In the Atlantic, inversion allele frequencies varied latitudinally, while in the Mediterranean, they shifted longitudinally, aligning with temperature and oceanographic features that influence sardine life‐history strategies. Moreover, adjacent populations in contrasting environments exhibited pronounced differences in inversion allele frequencies, accompanied by a marked reduction in migration between them. In contrast, spatial patterns at neutral loci showed widespread gene flow, isolation by distance within basins, and population structure between Atlantic and Mediterranean basins (except for the Canary Islands). These results suggest that the inversions studied are under selection and demonstrate the capacity of large inversions to shape genome‐wide patterns of genetic diversity and population structure in species characterized by widespread gene flow. Our work also offers crucial insights for stock delimitation and management of this commercially valuable species in the face of climate change.

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

Relations of groundwater quality to long-term surface disposal of produced water near the Midway-Sunset and Buena Vista Oil Fields, California, USA - Riley S. Gannon; Matthew K. Landon; Justin T. Kulongoski; Michael J. Stephens; Lyndsay B. Ball; John G. Warden; Tracy A. Davis; Janice M. Gillespie; Isabelle M. Cozzarelli (Science of The Total Environment, 2025)

In utero exposure to a mixture of phthalates, parabens, and other phenols and menstrual cycle characteristics in adolescents - Olivia P. Stoddard; Kimberly Berger; Brenda Eskenazi; Katherine Kogut; Nina T. Holland; Stephen Rauch; Kim G. Harley (International Journal of Hygiene and Environmental Health, 2025)

Microbial ecology in hypersaline coastal lagoons: A model for climate-induced coastal salinisation and eutrophication - Christopher Keneally; Virginie Gaget; Daniel Chilton; Stephen P. Kidd; Luke Mosley; David T. Welsh; Yongqiang Zhou; Lei Zhou; Justin Brookes (Earth-Science Reviews, 2025)

The biocontrol paradox - Stephen P. Bonser; Violaine Gabriel; Karen Zeng; Angela T. Moles (Trends in Ecology & Evolution, 2025)

Hydrological and geochemical controls of surface water and suspended sediment toxic metal fluxes from nearshore large coal ash pond - Stephen Anderson; Natasha T. Dimova; Dini Adyasari (Science of The Total Environment, 2025)

The influence of artificial reef structural complexity on fish assemblage composition - Brooke T. Marshall; Sam R. Russell; James H. Florisson; Benjamin J. Saunders; Stephen J. Newman; Euan S. Harvey (Marine Environmental Research, 2025)

Exploring Neoproterozoic climate and biogeochemical evolution in the SCION model - Benjamin J.W. Mills; Guillaume le Hir; Andrew Merdith; Khushboo Gurung; Fred T. Bowyer; Alexander J. Krause; Patricia Sanchez-Baracaldo; Stephen J. Hunter; Yinggang Zhang (Global and Planetary Change, 2025)

Improving process-based modeling of crop production in the DayCent ecosystem model with solar-induced chlorophyll fluorescence - Wenguang Sun; Stephen M. Ogle; Yao Zhang; Andrew E. Schuh; Ian T Baker; Troy S. Magney; Francis Ulep; Shahriar S. Heydari (Ecological Modelling, 2025)

Post-release survival of marine gastropods: A review - Kathy Overton; Tim Dempster; Stephen E. Swearer; Luke T. Barrett (Biological Conservation, 2025)

Factors influencing landslide occurrence in low-relief formerly glaciated landscapes: landslide inventory and susceptibility analysis in Minnesota, USA - Laura D. Triplett; Morena N. Hammer; Stephen B. DeLong; Karen B. Gran; Carrie E. Jennings; Zachary T. Engle; Julie K. Bartley; Dylan J. Blumentritt; Andy J. Breckenridge; Stephanie Day; Melissa A. Kohout; Phil H. Larson; et al. (Natural Hazards, 2025)
In landscapes recently impacted by continental glaciation, landslides may occur where topographic relief has been generated by the drainage of glacial lakes and ensuing post-glacial fluvial network development into unconsolidated glacially derived sediments and exhumed bedrock. To investigate linkages among environmental variables, post-glacial landscape development, and landslides, we created a landslide inventory of nearly 10,000 landslides in five regions of the formerly glaciated low-relief state of Minnesota, United States. Multivariate logistic regression indicates the importance of slope angle, lithology, and the development of stream valleys to landslide distribution. Areas underlain by fine-grained glaciolacustrine and nearshore deposits that are incised by streams are particularly prone to shallow (< 1–2 m depth) landslides. Landslides also occur in a wide range of glacial and fluvial deposits, and as rockfall in layered Paleozoic sedimentary rocks in central and southern Minnesota and Precambrian igneous and sedimentary rocks in northeastern Minnesota. Although no more than 1–2% of the studied regions are susceptible to landslides, they can pose risk to life and safety, damage infrastructure, and impact water quality. The combination of recently generated low-relief steep slopes, extensive unconsolidated sediments, and layered sedimentary bedrock make this formerly glaciated landscape more susceptible to landslides than current national-scale models indicate.

STICr: An open-source package and workflow for stream temperature, intermittency, and conductivity (STIC) data - Sam Zipper; Christopher T. Wheeler; Delaney M. Peterson; Stephen C. Cook; Sarah E. Godsey; Ken Aho (Environmental Modelling & Software, 2025)

Corrigendum to “Role of NEIL1 in genome maintenance” [DNA Repair 148 (2025) 103820] - Amanda K. McCullough; Irina G. Minko; Michael M. Luzadder; Jamie T. Zuckerman; Vladimir L. Vartanian; Pawel Jaruga; Miral Dizdaroglu; R. Stephen Lloyd (DNA Repair, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Environmental monitoring for Ascaris egg remediation: a critical review - Nathaniel I. Strong; Jack T. Andraka; Sung-Geun Woo; Sahar H. El Abbadi; Aaron J. Lewis; Sindy K. Y. Tang; Stephen P. Luby; Craig S. Criddle (Environmental Science and Pollution Research, 2025)

Impact of phosphorus on the functional properties of extracellular polymeric substances recovered from sludge - Nouran T. Bahgat; Philipp Wilfert; Stephen J. Picken; Leo Sorin; Yuemei Lin; Leon Korving; Mark C.M. van Loosdrecht (Water Research, 2025)

Role of NEIL1 in genome maintenance - Amanda K. McCullough; Irina G. Minko; Michael M. Luzadder; Jamie T. Zuckerman; Vladimir L. Vartanian; Pawel Jaruga; Miral Dizdaroglu; R. Stephen Lloyd (DNA Repair, 2025)

Correction to: Improved GODAS reanalysis with MOM5 and impact of altimeter assimilation - Hasibur Rahaman; Samir Pokhrel; Subodh Saha; Raheema Rahman; Stephen Penny; Eric Hackert; James Carton; T. M. Balakrishnan Nair; T. Srinivasa Kumar; M. Ravichandran (Modeling Earth Systems and Environment, 2025)

Improved GODAS reanalysis with MOM5 and impact of altimeter assimilation - Hasibur Rahaman; Samir Pokhrel; Subodh Saha; Raheema Rahman; Stephen Penny; Eric Hackert; James Carton; T. M. Balakrishnan Nair; T. Srinivasa Kumar; M. Ravichandran (Modeling Earth Systems and Environment, 2025)

Subcellular localization of SARS-CoV-2 E and 3a proteins along the secretory pathway - Joshua J. Hinkle; Kathleen A. Trychta; Emily S. Wires; Raven M. Osborn; Justin R. Leach; Zoha F. Faraz; Reinis Svarcbahs; Christopher T. Richie; Stephen Dewhurst; Brandon K. Harvey (Journal of Molecular Histology, 2025)
SARS-CoV-2 E and 3a proteins are important for the assembly, budding, and release of viral particles. These two transmembrane proteins have been implicated in forming channels in the membrane that allow the transport of ions to favor viral replication. During an active infection, both proteins generally localize to the endoplasmic reticulum (ER), ER-Golgi intermediate compartment (ERGIC), and the Golgi where viral assembly occurs. The ER and Golgi are critical for the proper packaging and trafficking of cellular proteins along the secretory pathways which determine a protein’s final destination inside or outside of the cell. The SARS-CoV-2 virus primarily infects epithelial cells that are highly secretory in nature such as those in the lung and gut. Here we quantified the distribution of SARS-CoV-2 E and 3a proteins along the secretory pathways in a human intestinal epithelial cell line. We used NaturePatternMatch to demonstrate that epitope-tagged E and 3a proteins expressed alone via transient transfection have a similar immunoreactivity pattern as E and 3a proteins expressed by wild-type viral infection. While E and 3a proteins localized with all selected cellular markers to varying degrees, 3a protein displayed a higher correlation coefficient with the Golgi, early/late endosome, lysosome, and plasma membrane when compared to E protein. This work is the first to provide quantification of the subcellular distribution of E and 3a proteins along the multiple components of the secretory pathway and serves as a basis to develop models for examining how E and 3a alter proteostasis within these structures and affect their function.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Accelerated solvent extraction of dioxins sequestered in activated carbon: A response surface methodology-based optimization - P.S. Kirankumar; Lili Tian; Hui Li; Cliff T. Johnston; Stephen A. Boyd; Brian J. Teppen (Chemosphere, 2025)

Rapid, complex back barrier pedestal formation preconditions washover deposition on the southeast Indian coast - Chris Gouramanis; Seshachalam Srinivasalu; Andasabari Karthik; Dat T. Pham; Stephen Carson; Adam D. Switzer (Marine Geology, 2025)

Effects of microbial alteration of oceanic crust on sulfur cycling in hydrothermal systems - Sarah N. Moriarty; Emma Bertran; James W. Dottin; James Farquhar; David T. Johnston; Stephen J. Piercey; Dennis Sánchez-Mora; Michael G. Babechuk; Jason B. Sylvan; John W. Jamieson (Geochimica et Cosmochimica Acta, 2025)

Self-driving laboratory for emulsion polymerization - Peter M. Pittaway; Stephen T. Knox; Olivier J. Cayre; Nikil Kapur; Lisa Golden; Sophie Drillieres; Nicholas J. Warren (Chemical Engineering Journal, 2025)

Investigating the interactions between a poloxamer and TEMPO-oxidised cellulose nanocrystals - Alessandra Lavoratti; Onajite Abafe Diejomaoh; Annela M. Seddon; Todor T. Koev; Yaroslav Z. Khimyak; Robert L. Harniman; Katri S. Kontturi; Tekla Tammelin; Stephen J. Eichhorn (Carbohydrate Polymers, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Immunotherapy for leptomeningeal disease from solid tumors: current clinical outcomes and future opportunities - Eleanor C. Smith; Bryan T Mott; Emily Douglas; Stephen B. Tatter; Kounosuke Watabe (Cancer and Metastasis Reviews, 2025)
Leptomeningeal disease is a debilitating, late-stage form of metastatic cancer disseminated within the cerebrospinal fluid, subarachnoid space, and leptomeninges, leading to significant neurological morbidity and mortality. As systemic cancer treatments improve, rates of leptomeningeal disease have increased, yet prognosis remains exceedingly poor. A wide range of treatment modalities have been trialed; however, no standard of care has been established. Additionally, many clinical trials exclude patients with leptomeningeal disease, limiting available prospective data. In this review, we discuss the efficacy of immunotherapy for leptomeningeal disease from solid tumors including systemic and intrathecal therapies, as well as combined therapy regimens. Our review indicates a continued deficiency in the current prospective literature and highlights ongoing research regarding the leptomeningeal immune microenvironment, which will be critical in directing future study of leptomeningeal disease treatment. Currently, the efficacy of immunotherapies on leptomeningeal disease appears limited, and further prospective research is needed to draw significant conclusions. However, recent advancement in understanding the leptomeningeal microenvironment points to potential efficacy of novel immunotherapies targeting the innate immune system, and further study is warranted to evaluate the efficacy of these treatments in this subpopulation of patients.

Correction to: Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Effect of silvopasture, paddock trees and linear agroforestry systems on agricultural productivity: A global quantitative analysis - Thomas P. Baker; Jacqueline R. England; Shaun T. Brooks; Stephen B. Stewart; Daniel Mendham (Agricultural Systems, 2025)

Rapid subsidence as a driver of phosphate deposition in the later Ordovician: Case study from the Alabama Appalachians - John T. Haynes; Rafael A. Villanueva; Richard M. Robinet; Stephen A. Leslie; Achim D. Herrmann (Sedimentary Geology, 2025)

Controls on late Miocene marine vertebrate bonebed genesis in northern Chile - Priscilla R. Martinez; Barbara Carrapa; Mark T. Clementz; Carolina S. Gutstein; Whitney E. Worrell; Stephen T. Hasiotis; Joao Gabriel Martínez-López; Fabían A. Muñoz (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Integrated testing and modelling of substructures using full-field imaging and data fusion - Tobias Laux; Riccardo Cappello; Jack S. Callaghan; Geir Ólafsson; Stephen W. Boyd; Duncan A. Crump; Andrew F. Robinson; Ole T. Thomsen; Janice M. Dulieu-Barton (Engineering Structures, 2025)

Can strategic protected area expansion solve the insufficient representation of biodiversity in protected area networks? A case study from South Africa - Lize von Staden; Stephen D. Holness; Amanda T. Lombard (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Spatial distribution of the intertidal limpet Patella depressa Pennant, 1777: Patterns across wave exposure and season - Jón T. Magnússon; Ana Silva; Stephen J. Hawkins; José P.M. Paula; Tiago A. Marques; Diana Boaventura (Journal of Experimental Marine Biology and Ecology, 2025)

An experimental investigation on performance, emission and combustion characteristics of IC engine using liquid fuel produced through catalytic co-pyrolysis of pressed oil cake and mixed plastics with the addition of nanoparticles - T. Stephen Livingston; P. Madhu; C. Sowmya Dhanalakshmi; R. Vignesh Kumar (Fuel, 2025)

Evaluating P-Wave detection algorithms for earthquake early warning: insights from GeoNet data in Canterbury, Aotearoa New Zealand - Chanthujan Chandrakumar; Marion Lara Tan; Caroline Holden; Max T. Stephens; Raj Prasanna (Earth Science Informatics, 2025)

Energy-informed pathways: A fundamental approach to designing ballistic lunar transfers - Stephen T. Scheuerle; Kathleen C. Howell; Diane C. Davis (Advances in Space Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The actions of varenicline on alkaloids from Conium maculatum (poison hemlock), Lupinus sulphureus (sulphur lupine) and Nicotiana glauca (tree tobacco) - Benedict T. Green; Stephen T. Lee; Kevin D. Welch; Daniel Cook; Clinton A. Stonecipher (Toxicon, 2024)

The evaluation of earwax as a noninvasive specimen to determine livestock exposure to death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Kevin D. Welch; Daniel Cook (Toxicon, 2024)

Validating ex210Pb sediment dating methods applied to a large anthropogenically-impacted river basin - Stephen Anderson; Natasha T. Dimova; Scott Brande (Quaternary Geochronology, 2024)

Comprehensive model for predicting toxic equivalents (TEQ) reduction due to dechlorination of polychlorinated dibenzo-p-dioxin and dibenzofurans (PCDD/F congeners) - Dar Tafazul Islam; Maggie R. Williams; Brian J. Teppen; Cliff T. Johnston; Hui Li; Stephen A. Boyd; Gerben J. Zylstra; Donna E. Fennell; Alison M. Cupples; Syed A. Hashsham (Journal of Hazardous Materials, 2024)

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

A preliminary Coasian proposal for tree auditing via planning control of tree farms - Lawrence W.C. Lai; K.W. Chau; Stephen N.G. Davies; Hon Chim Chiu; Frank T. Lorne (Forest Policy and Economics, 2024)

Acute inorganic nitrate ingestion does not impact oral microbial composition, cognitive function, or high-intensity exercise performance in female team-sport athletes - Rachel Tan; Courtney Merrill; Chandler F. Riley; Maya A. Hammer; Ryan T. Kenney; Alyssa A. Riley; Jeffrey Li; Alexandra C. Zink; Sean T. Karl; Katherine M. Price; Luka K. Sharabidze; Samantha N. Rowland; et al. (European Journal of Applied Physiology, 2024)
The purpose of this study was to investigate the effects of acute nitrate (NO 3 − )-rich beetroot juice ingestion on explosive and high-intensity exercise performance, oral microbiota composition, and cognitive flexibility (i.e., function), before and after maximal intermittent running exercise. Fifteen women team-sport athletes were assigned in a randomized, double-blind, crossover design to consume concentrated NO 3 – -depleted beetroot juice (PL; 0.1 mmol NO 3 − ) and NO 3 − -rich beetroot juice (BR; 12.0 mmol NO 3 − ) 2.5 h prior to performing a battery of exercise performance tasks and cognitive testing before and after the Yo–Yo intermittent recovery level 1 (YYIR1) running test. Resting plasma [NO 3 − ] and plasma nitrite ([NO 2 − ]) were elevated following BR ( P < 0.001). BR did not impact global composition or relative abundance of taxa in the oral microbiome ( P > 0.05) or cognitive flexibility before or after exercise ( P > 0.05). There was no significant difference in performance during 20-m (PRE, PL: 4.38 ± 0.27 vs. BR: 4.38 ± 0.32 s; POST, PL: 4.45 ± 0.29 vs. BR: 4.43 ± 0.35 s) and 10-m sprints (PRE, PL 2.78 ± 0.15 vs. BR 2.79 ± 0.18 s; POST, PL: 2.82 ± 0.16 vs. BR: 2.81 ± 0.19 s), isokinetic handgrip dynamometry, medicine ball throw, horizontal countermovement jump, or YYIR1 (PL: 355 ± 163 m vs. BR: 368 ± 184 m) between BR and PL ( P > 0.05). These findings indicate that acute dietary NO 3 − may not influence the oral microbiome, explosive and high-intensity exercise performance, or cognitive function in women team-sport athletes.

Characterizing variability in geochemistry and mineralogy of western US dust sources - Abby L. Mangum; Gregory T. Carling; Barry R. Bickmore; Nicholas Webb; DeTiare L. Leifi; Janice Brahney; Diego P. Fernandez; Kevin A. Rey; Stephen T. Nelson; Landon Burgener; Joshua J. LeMonte; Alyssa N. Thompson; et al. (Aeolian Research, 2024)

Climate Change and the Emergence of No‐Analog Forest Assemblages in North America - Andrew V. Gougherty; Anantha M. Prasad; Matthew P. Peters; Stephen N. Matthews; Bryce T. Adams (Global Change Biology, 2024)
Future climate change is expected to result in tree species shifting their geographic distributions in ways that could reorganize species into assemblages with no contemporary analog. These projected no‐analog forests raise concern as their ecological function could similarly shift, which may challenge established conservation and management efforts. Here, we implement a community‐level modelling approach to identify the key climatic and topographic drivers of forest composition in North America, and then use these models to predict the distribution of “disappearing” and “novel” forest assemblages in future climate. We applied this modelling technique to both the taxonomic and phylogenetic composition of forest trees, to identify where species turnover may be greatest, and whether species are likely to be replaced with close relatives. Our work shows that approximately 11.9% of contemporary North American forests have low predicted similarity to future forests, and 26.2% of future forests could be compositionally novel compared with contemporary forests, but there was substantial geographic variability in the magnitude of these metrics across the continent. High‐elevation regions in the west tend to be nearest to their closest compositional analog, suggesting these regions may be most likely to realize the future predicted composition. This work provides a new approach to understanding how forest composition may shift in future climates in a way that avoids the need for individual species predictions and extends climate‐matching approaches with meaningful biological data.

Innovative techniques for combating a common enemy forever chemicals: A comprehensive approach to mitigating per- and polyfluoroalkyl substances (PFAS) contamination - Ajibola A. Bayode; Stephen Sunday Emmanuel; Amos O. Akinyemi; Odunayo T. Ore; Samson O. Akpotu; Daniel T. Koko; David E. Momodu; Eduardo Alberto López-Maldonado (Environmental Research, 2024)

Insights into the last 100 ky of geomagnetic field variability using numerical dynamo simulations - Stephen J. Mason; Christopher J. Davies; Andrew T. Clarke; Catherine G. Constable (Earth and Planetary Science Letters, 2024)

Surface modification of cellulose nanomaterials with amine functionalized fluorinated ionic liquids for hydrophobicity and high thermal stability - Onajite T. Abafe Diejomaoh; Alessandra Lavoratti; Jude Laverock; Todor T. Koev; Yaroslav Z. Khimyak; Tetsuo Kondo; Stephen J. Eichhorn (Carbohydrate Polymers, 2024)

Removal, mechanistic and kinetic studies of Cr(VI), Cd(II), and Pb(II) cations using Fe3O4 functionalized Schiff base chelating ligands - George S. Nyamato; Ian T. Kabogo; Siphosethu Maqinana; Rene Bachmann; Markus Schmitz; Joanne Ogunah; Wolfgang Kleist; Stephen O. Ojwach (Environmental Science and Pollution Research, 2024)

Nanoparticle transport in partially saturated porous media: Attachment at fluid interfaces - Youssra Rahham; Stephen Dauphinais; Jeff T. Gostick; Marios A. Ioannidis (Advances in Water Resources, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

A narrative review: 3D bioprinting of cultured muscle meat and seafood products and its potential for the food industry - Mediha Gurel; Nikheel Rathod; Laura Y. Cabrera; Stephen Voyton; Miji Yeo; Fatih Ozogul; Ibrahim T. Ozbolat (Trends in Food Science & Technology, 2024)

Sustainable crude oil desulfurization: A multi-objective fuzzy optimization for pollution prevention - Stephen S. Correa; Angel Nicole V. Arbilo; Kate Andre T. Alviar; Angelo Earvin Sy Choi (Process Safety and Environmental Protection, 2024)

Assessing good governance principles of renewable energy megaprojects - Kerstin K. Zander; Rabindra Nepal; Stephen T. Garnett (Journal of Cleaner Production, 2024)

A Tale of Two Tributaries: Source Delineation of Chloride in a Distressed Watershed (Grand Lake St. Marys, Ohio) - Douglas D. Kane; Nathan F. Manning; Stephen J. Jacquemin; Laura T. Johnson (Water, Air, & Soil Pollution, 2024)
Various sources of pollution have been assigned as contributing to the Freshwater Salinization Syndrome (FSS), by which water bodies are undergoing concurrent salinization and alkalinization. In many urban areas that receive substantial snowfall, road salt application has been ascribed as the main source of chloride driving the FSS. In rural areas, however, inorganic (e.g. chemical) and organic (e.g. manure) fertilizer applications have been found to be the most important sources of chloride. Herein, we compared daily mean concentrations of chloride over the past decade of time between Coldwater Creek and Chickasaw Creek, two tributaries of Grand Lake St. Marys, the largest reservoir in Ohio. We also used Weighted Regressions on Time, Discharge, and Season (WRTDS) analyses to visualize trends in chloride data and compared chloride vs. nitrate levels to delineate likely sources of chloride for the two streams. We found that road salt application increased over time in both subwatersheds and that 37% and 25% of the chloride could be apportioned to road salt as a source in Coldwater Creek and Chickasaw Creek, respectively. Additionally, in Coldwater Creek, 37% of the chloride was apportioned to animal or septic sources, while 25% was apportioned to inorganic fertilizers, in comparison with 30% and 42% for Chickasaw Creek. Monitoring and assessing salinized streams for both chemical and biological water quality is important, particularly since the FSS has become increasingly linked to declines in water quality (e.g. harmful algal blooms, including recent upticks in Prymnesium parvum blooms) and is expected to be exacerbated with global climate change (e.g. increased precipitation causing increased runoff of chloride from the land).

Mechanical and poroelastic behavior of porous tuff under drained and undrained conditions - Stephen J. Bauer; Scott T. Broome; William M. Kibikas; Jennifer E. Wilson (Bulletin of Engineering Geology and the Environment, 2024)
A series of drained and undrained water-saturated constant mean-stress tests were performed to investigate the strength, elasticity, and poroelastic response of a water-saturated high porosity nonwelded tuff. Drained strengths are found to increase with increasing effective confining pressures. Elastic moduli increase with increasing mean stress. Undrained strengths are small due to development of high pore pressures that generate low effective confining pressures. Skempton’s values are pressure dependent and appear to reflect the onset of inelastic deformation. Permeabilities decrease after deformation from ∼ 10 –14 to ∼ 10 –16 m 2 and are a function of the applied confining pressure. Deformation is dominated by pore collapse, compaction, and intense microfracturing, with the undrained tests favoring microfracture-dominant deformation and the drained tests favoring compaction-dominant deformation. These property determinations and observations are used to develop/parameterize physics-based models for underground explosives testing.

Are human activities or climate changes the main causes of soil erosion in the South African drylands?: A palaeo‐perspective from three sites in the interior - Richard Lyons; Stephen Tooth; Geoff A. T. Duller; Terence McCarthy (Journal of Quaternary Science, 2024)
Soil erosion across South Africa's drylands occurs widely in the form of gullies and badlands (locally termed dongas) that have developed in colluvium and in valley fills along incised rivers. This erosion has commonly been attributed to land mismanagement, particularly since European settlement, but natural factors such as soil properties, local base level fall and climate change have also been invoked. To disentangle human and natural factors, we use optically stimulated luminescence (OSL) dating, supported by documentary and archaeological evidence, to constrain the timing and causes of donga formation at three widely spaced sites across interior South Africa. At all three sites, the exposed stratigraphy indicates that hillslopes and floodplains underwent net sediment accumulation during most of the late Quaternary, and that present‐day deep erosion is of a magnitude unprecedented probably within at least the past 100 ka. OSL ages indicate that the onset of erosion at each site significantly pre‐dates European incursion and instead was broadly coincident with abrupt climatic changes that occurred during the Medieval Climatic Anomaly (MCA, ~ ad 900–1300) and Little Ice Age (LIA, ~ ad 1300–1800). Based on correlation with palaeoclimate proxy records, we propose that erosion was triggered by abrupt hydroclimatic oscillations during the MCA, and continued during the LIA in response to climate‐driven, large floods. At these sites, soil type and local base level falls exert secondary controls on the specific locations, processes, rates and depths of erosion. In other areas of South Africa, clear links between land mismanagement and soil erosion have been demonstrated, but for sites where detailed investigations have yet to be undertaken, these findings challenge an often default assumption that soil erosion is necessarily attributable to human factors. Our findings have significant implications for soil erosion control strategies and assessment of South African dryland landscape response to future climate changes.

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

Phosphorous speciation in EPS extracted from Aerobic Granular Sludge - Nouran T. Bahgat; Philipp Wilfert; Stephen J. Eustace; Leon Korving; Mark C.M. van Loosdrecht (Water Research, 2024)

The use of earwax to determine livestock exposure to teratogenic lupine - Clinton A. Stonecipher; Stephen T. Lee; Kevin D. Welch; Kristian R. Valles; Daniel Cook (Toxicon, 2024)

Comparison of the acute toxicity of zygacine versus zygadenine - Kevin D. Welch; Dale R. Gardner; Stephen T. Lee; Clint A. Stonecipher; Daniel Cook (Toxicon, 2024)

Gigaton commercial-scale carbon storage and mineralization potential in stacked Columbia River basalt reservoirs - Ruoshi Cao; Quin R.S. Miller; Casie L. Davidson; William Gallin; Stephen P. Reidel; Zunsheng Jiao; J. Fred McLaughlin; Emily T. Nienhuis; H. Todd Schaef (International Journal of Greenhouse Gas Control, 2024)

A first look at CRISM hyperspectral mapping mosaicked data: Results from Mawrth Vallis - Michael S. Phillips; Scott L. Murchie; Frank P. Seelos; Katie M. Hancock; Christina Selby; Ryan T. Poffenbarger; David C. Stephens; Maia Kawamura (Icarus, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Coupled atmosphere-ocean response of the southwest Pacific to deglacial changes in Atlantic meridional overturning circulation - Shaun R. Eaves; Andrew N. Mackintosh; Joel B. Pedro; Helen C. Bostock; Matthew T. Ryan; Kevin P. Norton; Bruce W. Hayward; Brian M. Anderson; Feng He; Richard S. Jones; Andrew M. Lorrey; Rewi M. Newnham; et al. (Earth and Planetary Science Letters, 2024)

Potassium permanganate–modified eggshell biosorbent for the removal of diclofenac from liquid environment: adsorption performance, isotherm, kinetic, and thermodynamic analyses - Abel A. Adeyi; Damilola O. Ogundola; Lekan T. Popoola; Esther Bernard; Stephen G. Udeagbara; Adebayo T. Ogunyemi; Idowu I. Olateju; Rahadian Zainul (Environmental Monitoring and Assessment, 2024)

The influence of conservation policies and legislations on communities in Tanzania - Juma J. Kegamba; Kamaljit K. Sangha; Penelope A.S. Wurm; Jafari R. Kideghesho; Stephen T. Garnett (Biodiversity and Conservation, 2024)
Benefit-sharing mechanisms have been instrumental in securing the support of local communities living on the edge of protected areas, and in resolving human-wildlife conflicts. Understanding how current conservation policies influence benefit-sharing and the management of human-wildlife conflicts is vital for designing strong mechanisms to achieve both conservation and ethical community outcomes. Here we examined how benefit-sharing and human-wildlife conflicts are acknowledged and addressed within the current conservation policies (wildlife policies, legislations, regulations and strategic plans) using the Greater Serengeti Ecosystem (GSE) as a case study. The fourteen policies focusing primarily on wildlife conservation in Tanzania are analysed. We also drew on the findings of three studies conducted during 2021 and 2022 documenting community interactions with wildlife and adjacent protected areas. These studies covered the types of benefit provided by various conservation institutions to local communities, the effectiveness of benefit-sharing mechanisms, and the conservation-related losses incurred by communities. The study uncovered a wide range of benefits provided to local communities in the form of social amenities, livelihood support and employment. However, the losses and costs experienced are far greater than these benefits. Integrating these findings with policy analysis, we identified that the main limitations reducing the impacts of benefits in motivating positive conservation behaviours to be: losses of livestock and crops were more than four times the value of benefits/compensation offered to communities; a lack of details and clarity of benefit-sharing mechanisms; benefit/conservation rates that have not been indexed against inflation and; shortcomings in implementation. To achieve conservation outcomes, we recommend revising the conservation policies and legislation across the country in collaboration with local communities who experience the impacts of conservation in their day-to-day life. We also propose a coordinated approach for all conservation institutions managing wildlife to address widespread human-wildlife conflicts across the country effectively and to achieve better conservation outcomes rather than leaving that task to a single organization (i.e. Tanzania Wildlife Management Authority).

Organic matter accumulation drives methylotrophic methanogenesis and microbial ecology in a hypersaline coastal lagoon - Christopher Keneally; Matilda Southgate; Daniel Chilton; Virginie Gaget; David T. Welsh; Luke Mosley; Dirk V. Erler; Stephen P. Kidd; Justin Brookes (Limnology and Oceanography, 2024)
Hypersalinity is common in coastal wetlands throughout warm, tropical, and arid regions. Climate‐induced changes in rainfall, sea level, and anthropogenic modification to basins and coastlines are likely to further increase salinization in these ecosystems. Yet, carbon cycling in hypersaline coastal wetlands is not well understood, and poorly constrained in climate models. In the Coorong, a eutrophic, hypersaline coastal lagoon, recognized as internationally important under the Ramsar convention, organic matter rapidly accumulates in deeper areas of the lagoon, through the settling of fine detrital particles, phytoplankton and suspended sediments. During initial surveys, elevated surface water methane (CH 4 ) concentrations were observed above these fine depositional sediments. To identify the drivers of CH 4 production, organic matter and sediment characteristics were assessed in surface sediments. Genetic markers (i.e., 16rDNA and the mcrA functional gene) were used to characterize microbial communities. With multiple lines of evidence, this study identifies organic matter, methanogen abundance, and salinity as important drivers of CH 4 production, which is concentrated in depositional zones. Archaea were also more abundant in depositional zones, including methylotrophic methanogens: Methanofastidiosales, Methanomasiliicoccales, Methermicoccaceae , and Methanococcoides . These methanogens were highly correlated to CH 4 in porewater, suggesting an influence of methylotrophic methanogenesis. To investigate further, metabolic genes were predicted from 16S rRNA with PICRUSt2. This represents the first effort to analyze CH 4 dynamics in the Coorong, underscoring the need to integrate these unique ecosystems into global climate models to enhance our understanding of greenhouse gas dynamics and emissions in a changing climate.

Japanese Yew (Taxus) poisoning of wild ungulates in Utah during the winter of 2022–2023 - Stephen T. Lee; Jane Kelly; Virginia Stout; Sydney Lamb; Thomas J. Baldwin; Daniel Cook (Toxicon, 2024)

An in vitro-in silico workflow for predicting renal clearance of PFAS - Hsing-Chieh Lin; Courtney Sakolish; Haley L. Moyer; Paul L. Carmichael; Maria T. Baltazar; Stephen S. Ferguson; Jason P. Stanko; Philip Hewitt; Ivan Rusyn; Weihsueh A. Chiu (Toxicology and Applied Pharmacology, 2024)

Public views about the world's largest proposed solar farm in remote Australia - Kerstin K. Zander; Deepika Mathur; Supriya Mathew; Stephen T. Garnett (Energy Policy, 2024)

Paralog switching facilitates diadromy: ontogenetic, microevolutionary and macroevolutionary evidence - Rebecca S. Colby; Stephen D. McCormick; Jonathan P. Velotta; Elizabeth Jockusch; Eric T. Schultz (Oecologia, 2024)

Shotgun Metagenomics Reveals Taxonomic and Functional Patterns of the Microbiome Associated with Barbour’s Seahorse (Hippocampus barbouri) - Rose Chinly Mae H. Ortega-Kindica; Chinee S. Padasas-Adalla; Sharon Rose M. Tabugo; Joey Genevieve T. Martinez; Olive A. Amparado; Carlo Stephen O. Moneva; Rodelyn Dalayap; Carlos O. Lomeli-Ortega; Jose Luis Balcazar (Marine Biotechnology, 2024)

The Arctic marine soundscape of the Amundsen Gulf, Western Canadian Arctic - Jacob T. Dingwall; William D. Halliday; Nikoletta Diogou; Andrea Niemi; Nadja Steiner; Stephen J. Insley (Marine Pollution Bulletin, 2024)

New records of early Paleocene (earliest Torrejonian) plesiadapiforms from northeastern Montana, USA, provide a window into the diversification of stem primates - Brody T. Hovatter; Stephen G.B. Chester; Gregory P. Wilson Mantilla (Journal of Human Evolution, 2024)

Functional characterization of single nucleotide polymorphic variants of DNA repair enzyme NEIL1 in South Asian populations - Jamie T. Zuckerman; Asia Sage Jackson; Irina G. Minko; Melis Kant; Pawel Jaruga; Michael P. Stone; Miral Dizdaroglu; Amanda K. McCullough; R. Stephen Lloyd (DNA Repair, 2024)

Correction: Evaluating Hydrogeomorphic Condition Across Ecosystem States in a Non-tidal, Brackish Peat Marsh of the Florida Coastal Everglades, USA - Lukas Lamb-Wotton; Tiffany G. Troxler; Carlos Coronado-Molina; Stephen E. Davis; Daniel Gann; Khandker S. Ishtiaq; Sparkle L. Malone; Paulo Olivas; David T. Rudnick; Fred H. Sklar (Estuaries and Coasts, 2024)

Evaluating Hydrogeomorphic Condition Across Ecosystem States in a Non-tidal, Brackish Peat Marsh of the Florida Coastal Everglades, USA - Lukas Lamb-Wotton; Tiffany G. Troxler; Carlos Coronado-Molina; Stephen E. Davis; Daniel Gann; Khandker S. Ishtiaq; Sparkle L. Malone; Paulo Olivas; David T. Rudnick; Fred H. Sklar (Estuaries and Coasts, 2024)
Emergent marsh and open water have been identified as alternate stable states in tidal marshes with large, relative differences in hydrogeomorphic conditions. In the Florida coastal Everglades, concern has been raised regarding the loss of non-tidal, coastal peat marsh via dieback of emergent vegetation and peat collapse. To aid in the identification of alternate stable states, our objective was to characterize the variability of hydrogeomorphic and biologic conditions using a field survey and long-term monitoring of hydrologic and geomorphic conditions across a range of vegetated (emergent, submerged) and unvegetated (open water) communities, which we refer to as “ecosystem states,” in a non-tidal, brackish peat marsh of the coastal Everglades. Results show (1) linear relationships among field-surveyed geomorphic, hydrologic, and biologic variables, with a 35-cm mean difference in soil surface elevation between emergent and open water states, (2) an overall decline in soil elevation in the submerged state that was related to cumulative dry days, and (3) a 2× increase in porewater salinity during the dry season in the emergent state that was also related to the number of dry days. Coupled with findings from previous experiments, we propose a conceptual model that describes how seasonal hydrologic variability may lead to ecosystem state transitions between emergent and open water alternate states. Since vegetative states are only moderately salt tolerant, as sea-level rise pushes the saltwater front inland, the importance of continued progress on Everglades restoration projects, with an aim to increase the volume of freshwater being delivered to coastal wetlands, is the primary management intervention available to mitigate salinization and slow ecosystem state shifts in non-tidal, brackish peat marshes.

Land-use interactions, Oil-Field infrastructure, and natural processes control hydrocarbon and arsenic concentrations in groundwater, Poso Creek Oil Field, California, USA - Peter B. McMahon; Matthew K. Landon; Michael J. Stephens; Kim A. Taylor; Michael T. Wright; Angela M. Hansen; Tamara E.C. Kraus; Isabelle M. Cozzarelli; David H. Shimabukuro; Theron A. Sowers; Justin T. Kulongoski; Andrew G. Hunt; et al. (Applied Geochemistry, 2024)

Determining recommended acceptable intake limits for N-nitrosamine impurities in pharmaceuticals: Development and application of the Carcinogenic Potency Categorization Approach (CPCA) - Naomi L. Kruhlak; Marianne Schmidt; Roland Froetschl; Stefan Graber; Bodo Haas; Irene Horne; Stephen Horne; Sruthi T. King; Iryna A. Koval; Govindaraj Kumaran; Anja Langenkamp; Timothy J. McGovern; et al. (Regulatory Toxicology and Pharmacology, 2024)

Recent advances in 3D printing for continuous flow chemistry - Mireia Benito Montaner; Stephen T. Hilton (Current Opinion in Green and Sustainable Chemistry, 2024)

Eggshell waste materials-supported metal oxide nanocomposites for the efficient photocatalytic degradation of organic dyes in water and wastewater: A review - Hamza Badamasi; Saheed O. Sanni; Odunayo T. Ore; Ajibola A. Bayode; Daniel T. Koko; Olaniran Kolawole Akeremale; Stephen Sunday Emmanuel (Bioresource Technology Reports, 2024)

A circumpolar study unveils a positive non‐linear effect of temperature on arctic arthropod availability that may reduce the risk of warming‐induced trophic mismatch for breeding shorebirds - Aurélie Chagnon‐Lafortune; Éliane Duchesne; Pierre Legagneux; Laura McKinnon; Jeroen Reneerkens; Nicolas Casajus; Kenneth F. Abraham; Élise Bolduc; Glen S. Brown; Stephen C. Brown; H. River Gates; Olivier Gilg; et al. (Global Change Biology, 2024)
Seasonally abundant arthropods are a crucial food source for many migratory birds that breed in the Arctic. In cold environments, the growth and emergence of arthropods are particularly tied to temperature. Thus, the phenology of arthropods is anticipated to undergo a rapid change in response to a warming climate, potentially leading to a trophic mismatch between migratory insectivorous birds and their prey. Using data from 19 sites spanning a wide temperature gradient from the Subarctic to the High Arctic, we investigated the effects of temperature on the phenology and biomass of arthropods available to shorebirds during their short breeding season at high latitudes. We hypothesized that prolonged exposure to warmer summer temperatures would generate earlier peaks in arthropod biomass, as well as higher peak and seasonal biomass. Across the temperature gradient encompassed by our study sites (>10°C in average summer temperatures), we found a 3‐day shift in average peak date for every increment of 80 cumulative thawing degree‐days. Interestingly, we found a linear relationship between temperature and arthropod biomass only below temperature thresholds. Higher temperatures were associated with higher peak and seasonal biomass below 106 and 177 cumulative thawing degree‐days, respectively, between June 5 and July 15. Beyond these thresholds, no relationship was observed between temperature and arthropod biomass. Our results suggest that prolonged exposure to elevated temperatures can positively influence prey availability for some arctic birds. This positive effect could, in part, stem from changes in arthropod assemblages and may reduce the risk of trophic mismatch.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Rates of tree cover loss in key biodiversity areas on Indigenous Peoples’ lands - Ashley Thomas Simkins; Paul F. Donald; Alison E. Beresford; Stuart H. M. Butchart; Julia E. Fa; Alvaro Onrubia Fernández‐Llamazares; Stephen T. Garnett; Graeme M. Buchanan (Conservation Biology, 2024)
Indigenous Peoples’ lands (IPL) cover at least 38 million km 2 (28.1%) of Earth's terrestrial surface. These lands can be important for biodiversity conservation. Around 20.7% of IPL intersect areas protected by government (PAs). Many sites of importance for biodiversity within IPL could make a substantial but hitherto unquantified contribution to global site‐based conservation targets. Key Biodiversity Areas (KBAs) represent the largest global network of systematically identified sites of high importance for biodiversity. We assessed the effectiveness of IPL in slowing biodiversity loss inside and outside PAs by quantifying tree cover loss from 2000 to 2019 in KBAs at international and national levels and comparing it with losses at equivalent sites outside mapped IPL. Based on a matched sample of 1‐km 2 cells in KBAs inside and outside mapped IPL, tree cover loss in KBAs outside PAs was lower inside IPL than outside IPL. By contrast, tree cover loss in KBAs inside PAs was lower outside IPL than inside IPL (although the difference was far smaller). National rates of tree cover loss in KBAs varied greatly in relation to their IPL and PA status. In one half of the 44 countries we examined individually, there was no significant difference in the rate of tree cover loss in KBAs inside and outside mapped IPL. The reasons for this intercountry variation could illuminate the importance of IPL in meeting the Convention on Biological Diversity's ambition of conserving 30% of land by 2030. Critical to this will be coordinated action by governments to strengthen and enforce Indigenous Peoples’ rights, secure their collective systems of tenure and governance, and recognize their aspirations for their lands and futures.

Social valuation of biodiversity relative to other types of assets at risk in wildfire - John C. Z. Woinarski; Stephen T. Garnett; Kerstin K. Zander (Conservation Biology, 2024)
Environmental crises, such as wildfires, can cause major losses of human life, infrastructure, biodiversity, and cultural values. In many such situations, incident controllers must make fateful choices about what to protect—and hence what to abandon. With an online representative survey of >2000 adult Australians, we investigated social attitudes to this dilemma. We used best–worst scaling to assess preferences across a set of 11 assets representing human life, infrastructure, biodiversity, and cultural values. Survey respondents overwhelmingly prioritized a single human life (best–worst score of 6647 out of possible score ranging from −10695 to 10695), even if that choice resulted in extinction of other species. Inanimate (replaceable) objects were accorded lowest priority (best–worst scores of −4655 for a shed and −3242 for a house). Among biodiversity assets, respondents prioritized protecting a population of the iconic koala ( Phascolarctos cinereus ) (best–worst score of 1913) ahead of preventing the extinction of a snail (score −329) and a plant species (−226). These results variably support current policy in that they emphasize the importance the community places on protection of human life, but results diverged from conventional practice in rating some biodiversity assets ahead of infrastructure. The preference for protecting a population of koalas ahead of action taken to prevent the extinction of an invertebrate and plant species corroborates previous research reporting biases in the way people value nature. If noncharismatic species are not to be treated as expendable, then the case for preventing their extinction needs to be better made to the community. Given the increasing global incidence of high‐severity wildfires, further sampling of societal preferences among diverse asset types is needed to inform planning, policy, and practice relating to wildfire. Other preemptive targeted management actions (such as translocations) are needed to conserve biodiversity, especially noniconic species, likely to be imperiled by catastrophic events.

Acute death as a result of poisoning tropical (Bos taurus indicus) but not temperate (Bos taurus taurus) cattle after oral dosing with Lupinus leucophyllus (velvet lupine) - Benedict T. Green; Kevin D. Welch; Stephen T. Lee; T. Zane Davis; Clinton A. Stonecipher; Bryan L. Stegelmeier; Daniel Cook (Toxicon, 2024)

Speculations on the Paleozoic legacy of Gondwana amalgamation - J. Brendan Murphy; R. Damian Nance; Stephen T. Johnston; Josep M. Casas; Peter A. Cawood; Edward J. Matheson; Peir K. Pufahl; Wei Dan; J. Javier Álvaro; Philip J. Heron; Rob A. Strachan (Gondwana Research, 2024)

An actor-centered, scalable land system typology for addressing biodiversity loss in the world’s tropical dry woodlands - Marie Pratzer; Patrick Meyfroidt; Marina Antongiovanni; Roxana Aragon; Germán Baldi; Stasiek Czaplicki Cabezas; Cristina A. de la Vega-Leinert; Shalini Dhyani; Jean-Christophe Diepart; Pedro David Fernandez; Stephen T. Garnett; Gregorio I. Gavier Pizarro; et al. (Global Environmental Change, 2024)

Migratory Shorebird Gut Microbes are not Associated with Bivalve Prey in Monsoon Tropical Australia - Chava L. Weitzman; Zarah Tinning; Kimberley A. Day; Stephen T. Garnett; Keith Christian; Karen Gibb (Current Microbiology, 2024)
Migratory animals can carry symbionts over long distances. While well-studied for parasite and pathogen transmission, less is known about use of this route by other symbiotic taxa, particularly those non-pathogenic. Here we ask the question of whether gut bacteria can be spread between continents by long-distance bird migration, although gut microbiomes in birds may not be as stable or persistent as those of non-volant animals. We used amplicon sequencing of both bacterial 16S rRNA gene and Vibrio -centric hsp60 gene to determine whether the faecal bacteria of migratory great knots ( Calidris tenuirostris ) also occur in their main food source in Northern Australia or in nearby sand, comparing samples before and after the birds’ long-distance migration. Our data suggest that there is little connectivity among the bacterial microbiomes, except in the bivalve prey. Our results are consistent with previous studies finding that bird faecal microbiomes were not host-specific and contrast with those showing an influence of diet on bird faecal bacteria. We also found little connectivity among Vibrio spp. However, although faecal sample sizes were small, the dominance of different individual Vibrio spp. suggests that they may have been well-established in knot guts and thus capable of moving with them on migration. We suggest that the physiological impacts of a long-distance migration may have caused shifts in the phyla comprising great knot faecal communities.

Why do avian responses to change in Arctic green‐up vary? - Eveling A. Tavera; David B. Lank; David C. Douglas; Brett K. Sandercock; Richard B. Lanctot; Niels M. Schmidt; Jeroen Reneerkens; David H. Ward; Joël Bêty; Eunbi Kwon; Nicolas Lecomte; Cheri Gratto‐Trevor; et al. (Global Change Biology, 2024)
Global climate change has altered the timing of seasonal events (i.e., phenology) for a diverse range of biota. Within and among species, however, the degree to which alterations in phenology match climate variability differ substantially. To better understand factors driving these differences, we evaluated variation in timing of nesting of eight Arctic‐breeding shorebird species at 18 sites over a 23‐year period. We used the Normalized Difference Vegetation Index as a proxy to determine the start of spring (SOS) growing season and quantified relationships between SOS and nest initiation dates as a measure of phenological responsiveness. Among species, we tested four life history traits (migration distance, seasonal timing of breeding, female body mass, expected female reproductive effort) as species‐level predictors of responsiveness. For one species (Semipalmated Sandpiper), we also evaluated whether responsiveness varied across sites. Although no species in our study completely tracked annual variation in SOS, phenological responses were strongest for Western Sandpipers, Pectoral Sandpipers, and Red Phalaropes. Migration distance was the strongest additional predictor of responsiveness, with longer‐distance migrant species generally tracking variation in SOS more closely than species that migrate shorter distances. Semipalmated Sandpipers are a widely distributed species, but adjustments in timing of nesting relative to variability in SOS did not vary across sites, suggesting that different breeding populations of this species were equally responsive to climate cues despite differing migration strategies. Our results unexpectedly show that long‐distance migrants are more sensitive to local environmental conditions, which may help them to adapt to ongoing changes in climate.

Consequences of pollen defense compounds for pollinators and antagonists in a pollen‐rewarding plant - Sébastien Rivest; Stephen T. Lee; Daniel Cook; Jessica R. K. Forrest (Ecology, 2024)
Plants produce an array of defensive compounds with toxic or deterrent effects on insect herbivores. Pollen can contain relatively high concentrations of such defense compounds, but the causes and consequences of this enigmatic phenomenon remain mostly unknown. These compounds could potentially protect pollen against antagonists but could also reduce flower attractiveness to pollinators. We combined field observations of the pollen‐rewarding Lupinus argenteus with chemical analysis and laboratory assays to test three hypotheses for the presence of pollen defense compounds: (1) these compounds are the result of spillover from adjacent tissues, (2) they protect against pollen thieves, and (3) they act as antimicrobial compounds. We also tested whether pollen defense compounds affect pollinator behavior. We found a positive relationship between alkaloid concentrations in pollen and petals, supporting the idea that pollen defense compounds partly originate from spillover. However, pollen and petals exhibited quantitatively (but not qualitatively) distinct alkaloid profiles, suggesting that plants can adjust pollen alkaloid composition independently from that of adjacent tissues. We found no relationship between pollen alkaloid concentration and the abundance of pollen thieves in Lupinus flowers. However, pollen alkaloids were negatively associated with bacterial abundance. Finally, plants with more alkaloids in their pollen received more pollinator visits, but these visits were shorter, resulting in no change in the overall number of flowers visited. We propose that pollen defense compounds are partly the result of spillover from other tissues, while they also play an antimicrobial role. The absence of negative effects of these compounds on pollinator visitation likely allows their maintenance in pollen at relatively high concentrations. Taken together, our results suggest that pollen alkaloids affect and are mediated by the interplay of multiple interactions.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Associations of walkability, regional and transit accessibility around home and workplace with active and sedentary travel - Behram Wali; Lawrence D. Frank; Brian E. Saelens; Deborah R. Young; Richard T. Meenan; John F. Dickerson; Erin M. Keast; Stephen P. Fortmann (Journal of Transport Geography, 2024)

Correction to: Do unpublished data help to redraw distributions? The case of the spectacled bear in Peru - Nereyda Falconi; John T. Finn; Todd K. Fuller; Stephen DeStefano; John F. Organ (Mammal Research, 2024)

Correction: Population structure and history of North Atlantic Blue whales (Balaenoptera musculus musculus) inferred from whole genome sequence analysis - Sushma Jossey; Oliver Haddrath; Livia Loureiro; Jason T. Weir; Burton K. Lim; Jacqueline Miller; Stephen W. Scherer; Anders Goksøyr; Roger Lille-Langøy; Kit M. Kovacs; Christian Lydersen; Heli Routti; et al. (Conservation Genetics, 2024)

Population structure and history of North Atlantic Blue whales (Balaenoptera musculus musculus) inferred from whole genome sequence analysis - Sushma Jossey; Oliver Haddrath; Livia Loureiro; Jason T. Weir; Burton K. Lim; Jacqueline Miller; Stephen W. Scherer; Anders Goksøyr; Roger Lille-Langøy; Kit M. Kovacs; Christian Lydersen; Heli Routti; et al. (Conservation Genetics, 2024)
Knowledge of genetic diversity and structure is essential for developing conservation strategies for endangered species. Blue whales were hunted to near extinction in the mid-twentieth century. Not-withstanding almost 380,000 animals killed globally, much remains unknown about their population structure and migration patterns. Herein, we use whole genome sequencing to elucidate the poorly understood population genetics of North Atlantic (NA) blue whales. We generated a de novo genome assembly for a NA blue whale to analyze 19 other whole genomic sequences and 31 complete mitochondrial genomes. Present-day and historical samples (earliest from 1876) from the Atlantic and Antarctic Oceans were included to understand the impact of whaling on the genetic diversity of this species. We found low but statistically significant population structuring and high genetic diversity. Demographic modeling using fastsimcoal2 rejected an absence of gene flow between eastern and western NA blue whales and suggested an asymmetric west to east gene flow. Introgression estimated using D-statistics between blue and fin whales ( Balaenoptera physalus ), was observed in all present-day samples. This gene flow was found to be unidirectional from fin whales to blue whales and accounts for ~ 3.5% of the NA blue whale’s genome. Our sequencing and population structure analyses provide a genomic baseline to inform ongoing conservation strategies for this iconic species.

Associations of plasma proteomics and age-related outcomes with brain age in a diverse cohort - Ramon Casanova; Keenan A. Walker; Jamie N. Justice; Andrea Anderson; Michael R. Duggan; Jenifer Cordon; Ryan T. Barnard; Lingyi Lu; Fang-Chi Hsu; Sanaz Sedaghat; Anna Prizment; Stephen B. Kritchevsky; et al. (GeroScience, 2024)
Machine learning models are increasingly being used to estimate “brain age” from neuroimaging data. The gap between chronological age and the estimated brain age gap (BAG) is potentially a measure of accelerated and resilient brain aging. Brain age calculated in this fashion has been shown to be associated with mortality, measures of physical function, health, and disease. Here, we estimate the BAG using a voxel-based elastic net regression approach, and then, we investigate its associations with mortality, cognitive status, and measures of health and disease in participants from Atherosclerosis Risk in Communities (ARIC) study who had a brain MRI at visit 5 of the study. Finally, we used the SOMAscan assay containing 4877 proteins to examine the proteomic associations with the MRI-defined BAG. Among N = 1849 participants (age, 76.4 (SD 5.6)), we found that increased values of BAG were strongly associated with increased mortality and increased severity of the cognitive status. Strong associations with mortality persisted when the analyses were performed in cognitively normal participants. In addition, it was strongly associated with BMI, diabetes, measures of physical function, hypertension, prevalent heart disease, and stroke. Finally, we found 33 proteins associated with BAG after a correction for multiple comparisons. The top proteins with positive associations to brain age were growth/differentiation factor 15 (GDF-15), Sushi, von Willebrand factor type A, EGF, and pentraxin domain-containing protein 1 (SEVP 1), matrilysin (MMP7), ADAMTS-like protein 2 (ADAMTS), and heat shock 70 kDa protein 1B (HSPA1B) while EGF-receptor (EGFR), mast/stem-cell-growth-factor-receptor (KIT), coagulation-factor-VII, and cGMP-dependent-protein-kinase-1 (PRKG1) were negatively associated to brain age. Several of these proteins were previously associated with dementia in ARIC. These results suggest that circulating proteins implicated in biological aging, cellular senescence, angiogenesis, and coagulation are associated with a neuroimaging measure of brain aging.

Ruminant metabolism of zygacine, the major toxic alkaloid in foothill death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Benedict T. Green; Kevin D. Welch; Dale R. Gardner; Daniel Cook (Toxicon, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Rationalising development of classification systems describing livestock production systems for disease burden analysis within the Global Burden of Animal Diseases programme - Yin Li; K. Marie McIntyre; Philip Rasmussen; William Gilbert; Gemma Chaters; Kassy Raymond; Wudu T. Jemberu; Andrew Larkins; Grace T. Patterson; Stephen Kwok; Alexander James Kappes; Dianne Mayberry; et al. (Research in Veterinary Science, 2024)

Characterization of the modulatory effect of zeaxanthin isolated from maize kernels on cellular signaling pathways associated with hyperglycemia-induced HepG2 cell proliferation - T. Maradagi; N.M. Stephen; R. Kumar; K.N. Ramudu; G. Ponesakki (PharmaNutrition, 2024)

Regional seismic response assessment using indicator buildings - Amin Ghasemi; Max T. Stephens; Kenneth J. Elwood (Bulletin of Earthquake Engineering, 2024)

Quantifying the combined impacts of anthropogenic CO2 emissions and watershed alteration on estuary acidification at biologically-relevant time scales: a case study from Tillamook Bay, OR, USA - Stephen R. Pacella; Cheryl A. Brown; James E. Kaldy; Rochelle G. Labiosa; Burke Hales; T Chris Mochon Collura; George G. Waldbusser (Frontiers in Marine Science, 2024)
The impacts of ocean acidification (OA) on coastal water quality have been subject to intensive research in the past decade, but how emissions-driven OA combines with human modifications of coastal river inputs to affect estuarine acidification dynamics is less well understood. This study presents a methodology for quantifying the synergistic water quality impacts of OA and riverine acidification on biologically-relevant timescales through a case study from a small, temperate estuary influenced by coastal upwelling and watershed development. We characterized the dynamics and drivers of carbonate chemistry in Tillamook Bay, OR (USA), along with its coastal ocean and riverine end-members, through a series of synoptic samplings and continuous water quality monitoring from July 2017 to July 2018. Synoptic river sampling showed acidification and increased CO 2 content in areas with higher proportions of watershed anthropogenic land use. We propagated the impacts of 1). the observed riverine acidification, and 2). modeled OA changes to incoming coastal ocean waters across the full estuarine salinity spectrum and quantified changes in estuarine carbonate chemistry at a 15-minute temporal resolution. The largest magnitude of acidification (-1.4 pH T units) was found in oligo- and mesohaline portions of the estuary due to the poor buffering characteristics of these waters, and was primarily driven by acidified riverine inputs. Despite this, emissions-driven OA is responsible for over 94% of anthropogenic carbon loading to Tillamook Bay and the dominant driver of acidification across most of the estuary due to its large tidal prism and relatively small river discharges. This dominance of ocean-sourced anthropogenic carbon challenges the efficacy of local management actions to ameliorate estuarine acidification impacts. Despite the relatively large acidification effects experienced in Tillamook Bay (-0.16 to -0.23 pH T units) as compared with typical open ocean change (approximately -0.1 pH T units), observations of estuarine pH T would meet existing state standards for pH T . Our analytical framework addresses pressing needs for water quality assessment and coastal resilience strategies to differentiate the impacts of anthropogenic acidification from natural variability in dynamic estuarine systems.

In-situ comparison of high-order detonations and low-order deflagration methodologies for underwater unexploded ordnance (UXO) disposal - Paul A. Lepper; Sei-Him Cheong; Stephen P. Robinson; Lian Wang; Jakob Tougaard; Emily T. Griffiths; John P. Hartley (Marine Pollution Bulletin, 2024)

Towards richer knowledge partnerships between ecology and ethnoecology - Zsolt Molnár; Yildiz Aumeeruddy-Thomas; Dániel Babai; Sandra Díaz; Stephen T. Garnett; Rosemary Hill; Peter Bates; Eduardo S. Brondízio; Joji Cariño; László Demeter; Álvaro Fernández-Llamazares; Maximilien Guèze; et al. (Trends in Ecology & Evolution, 2024)

Applications of perovskite oxides for the cleanup and mechanism of action of emerging contaminants/steroid hormones in water - Ajibola A. Bayode; Stephen Sunday Emmanuel; Andrea Osti; Chidinma G. Olorunnisola; Abisola O. Egbedina; Daniel T. Koko; Demilade T. Adedipe; Brigitte Helmreich; Martins O. Omorogie (Journal of Water Process Engineering, 2024)

Enviromic prediction enables the characterization and mapping of Eucalyptus globulus Labill breeding zones - Andrew N. Callister; Germano Costa-Neto; Ben P. Bradshaw; Stephen Elms; Jose Crossa; Jeremy T. Brawner (Tree Genetics & Genomes, 2024)
Genotype-environment interaction is pervasive in forest genetics. Delineation of spatial breeding zones (BZs) is fundamental for accommodating genotype-environment interaction. Here we developed a BZ classification pipeline for the forest tree Eucalyptus globulus in 2 Australian regions based on phenotypic, genomic, and pedigree data, as well on a detailed environmental characterization (“envirotyping”) and spatial mapping of BZs. First, the factor analytic method was used to model additive genetic variance and site–site genetic correlations ( r B ) in stem volume across 48 trials of 126,467 full-sib progeny from 2 separate breeding programs. Thirty-three trials were envirotyped using 145 environmental variables (EVs), involving soil and landscape (71), climate (73), and management (1) EVs. Next, sparse partial least squares-discriminant analysis was used to identify EVs that were required to predict classification of sites into 5 non-exclusive BZ classes based on r B . Finally, these BZs were spatially mapped across the West Australian and “Green Triangle” commercial estates by enviromic prediction using EVs for 80 locations and 15 sets of observed climate data to represent temporal variation. The factor analytic model explained 85.9% of estimated additive variance. Our environmental classification system produced within-zone mean r B between 0.76 and 0.84, which improves upon the existing values of 0.62 for Western Australia and 0.67 for Green Triangle as regional BZs. The delineation of 5 BZ classes provides a powerful framework for increasing genetic gain by matching genotypes to current and predicted future environments.

Trace element chemistry and strontium isotope ratios of atmospheric particulate matter reveal air quality impacts from mineral dust, urban pollution, and fireworks in the Wasatch Front, Utah, USA - Micah J. Marcy; Gregory T. Carling; Alyssa N. Thompson; Barry R. Bickmore; Stephen T. Nelson; Kevin A. Rey; Diego P. Fernandez; Matthew Heiner; Bradley R. Adams (Applied Geochemistry, 2024)

A tale of two islands: tectonic and orbital controls on marine terrace reoccupation, Channel Islands National Park, California, USA - Daniel R. Muhs; Lindsey T. Groves; Kathleen R. Simmons; R. Randall Schumann; Stephen B. DeVogel (Journal of Quaternary Science, 2024)
In areas of low uplift rate on the Pacific Coast of North America, reoccupation of emergent marine terraces by later high sea‐stands has been hypothesised to explain the existence of thermally anomalous fauna (mixtures of warm and cool species) of last interglacial age. If uplift rates have been low for much of the Quaternary, it follows that higher (older) terraces should also show evidence of reoccupation. Strontium isotope analyses of fossils from a high‐elevation marine terrace on Anacapa Island, California, yield ages ranging from ~2.4–2.3 Ma to ~1.4–1.5 Ma. These results indicate that terrace reoccupation and fossil mixing on Anacapa Island could have taken place over several interglacial periods in the early Pleistocene. Terrace reoccupation over this time period is likely a function of both a low uplift rate and the timing of orbital forcing of glacial–interglacial cycles. Climate change in the early Pleistocene was modulated by the 41 ka obliquity cycle, and glacial–interglacial cycles were much shorter than later in the Pleistocene. Nearby San Miguel Island also has evidence of terrace reoccupation, with Sr isotope ages of shells from several high‐elevation terraces ranging from ~1.21–1.25 Ma to ~0.43–0.50 Ma. However, the frequency of terrace reoccupation was lower than on Anacapa Island. The uplift rate of San Miguel Island is higher than that of Anacapa Island and terraces formed when glacial–interglacial cycles were longer. The frequency of marine terrace reoccupation is controlled by the rate of tectonic uplift and the timing of orbital forcing of sea level change during glacial–interglacial cycles.

Achieving conservation and restoration outcomes through ecologically beneficial aquaculture - Kathy Overton; Tim Dempster; Stephen E. Swearer; Rebecca L. Morris; Luke T. Barrett (Conservation Biology, 2024)
A range of conservation and restoration tools are needed to safeguard the structure and function of aquatic ecosystems. Aquaculture, the culturing of aquatic organisms, often contributes to the numerous stressors that aquatic ecosystems face, yet some aquaculture activities can also deliver ecological benefits. We reviewed the literature on aquaculture activities that may contribute to conservation and restoration outcomes, either by enhancing the persistence or recovery of one or more target species or by moving aquatic ecosystems toward a target state. We identified 12 ecologically beneficial outcomes achievable via aquaculture: species recovery, habitat restoration, habitat rehabilitation, habitat protection, bioremediation, assisted evolution, climate change mitigation, wild harvest replacement, coastal defense, removal of overabundant species, biological control, and ex situ conservation. This list may be expanded as new applications are discovered. Positive intentions do not guarantee positive ecological outcomes, so it is critical that potentially ecologically beneficial aquaculture activities be evaluated via clear and measurable indicators of success to reduce potential abuse by greenwashing. Unanimity on outcomes, indicators, and related terminology will bring the field of aquaculture–environment interactions into line with consensus standards in conservation and restoration ecology. Broad consensus will also aid the development of future certification schemes for ecologically beneficial aquaculture.

Few havens for threatened Australian animal taxa that are highly susceptible to introduced and problematic native species - John C. Z. Woinarski; David G. Chapple; Stephen T. Garnett; Sarah M. Legge; Mark Lintermans; Ben C. Scheele (Biodiversity and Conservation, 2024)

Indigenous Peoples' Lands are critical for safeguarding vertebrate diversity across the tropics - Jocelyne S. Sze; Dylan Z. Childs; L. Roman Carrasco; Álvaro Fernández‐Llamazares; Stephen T. Garnett; David P. Edwards (Global Change Biology, 2024)
Indigenous Peoples are long‐term custodians of their lands, but only recently are their contributions to conservation starting to be recognized in biodiversity policy and practice. Tropical forest loss and degradation are lower in Indigenous lands than unprotected areas, yet the role of Indigenous Peoples' Lands (IPL) in biodiversity conservation has not been properly assessed from regional to global scales. Using species distribution ranges of 11,872 tropical forest‐dependent vertebrates to create area of habitat maps, we identified the overlap of these species ranges with IPL and then compared values inside and outside of IPL for species richness, extinction vulnerability, and range‐size rarity. Of assessed vertebrates, at least 76.8% had range overlaps with IPL, on average overlapping ~25% of their ranges; at least 120 species were found only within IPL. Species richness within IPL was highest in South America, while IPL in Southeast Asia had highest extinction vulnerability, and IPL in Dominica and New Caledonia were important for range‐size rarity. Most countries in the Americas had higher species richness within IPL than outside, whereas most countries in Asia had lower extinction vulnerability scores inside IPL and more countries in Africa and Asia had slightly higher range‐size rarity in IPL. Our findings suggest that IPL provide critical support for tropical forest‐dependent vertebrates, highlighting the need for greater inclusion of Indigenous Peoples in conservation target‐setting and program implementation, and stronger upholding of Indigenous Peoples' rights in conservation policy.

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

Life cycle assessment of a decoupled biofloc aquaponics facility across seasons - Rohit Kalvakaalva; Mollie Smith; Stephen A. Prior; G. Brett Runion; Emmanuel Ayipio; Caroline Blanchard; Daniel Wells; David Blersch; Sushil Adhikari; Rishi Prasad; Terril R. Hanson; Brendan T. Higgins (Journal of Cleaner Production, 2023)

Coyotes eat flies at carrion - David S. Mason; Abby K. Jones; Brandon T. Barton; Mike Proctor; Stephen L. Webb; Marcus A. Lashley (Food Webs, 2023)

A comparative study of the physicochemical and structural properties of legumin and globulin extracted from Lagenaria siceraria seed - Eunice M. Ogunbusola; Opeyemi O. Alabi; Kudirat T. Araoye; Stephen O. Arinola; Mary B. Oyewale (Food and Humanity, 2023)

Survival of lactic acid bacteria species in Filipino donor milk subjected to different heating temperatures - Richard Paolo M. Aba; Cecile Leah T. Bayaga; Justin Godfred B. Peralta; Stephen Jan M. Agravante; Judith J. Cauilan; Alonzo A. Gabriel (Food and Humanity, 2023)

Recent approach in the application of nanoadsorbents for malachite green (MG) dye uptake from contaminated water: A critical review - Chisom T. Umeh; Abimbola B. Akinyele; Nkechi H. Okoye; Stephen S. Emmanuel; Kingsley O. Iwuozor; Ifeoluwa P. Oyekunle; Joshua O. Ocheje; Joshua O. Ighalo (Environmental Nanotechnology, Monitoring & Management, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Lower muscle mitochondrial energetics is associated with greater phenotypic frailty in older women and men: the Study of Muscle, Mobility and Aging - Theresa Mau; Haley N. Barnes; Terri L. Blackwell; Philip A. Kramer; Scott R. Bauer; David J. Marcinek; Sofhia V. Ramos; Daniel E. Forman; Frederico G. S. Toledo; Russell T. Hepple; Stephen B. Kritchevsky; Steven R. Cummings; et al. (GeroScience, 2023)

Group size and the resolution of insider–outsider conflict in animal societies - Sheng-Feng Shen; H. Kern Reeve; Stephen T. Emlen; Ming Liu; Dustin Rubenstein (Animal Behaviour, 2023)

Strategies to reduce environmental impacts from textiles: Extending clothing wear life compared to fibre displacement assessed using consequential LCA - Stephen G. Wiedemann; Simon J. Clarke; Quan V. Nguyen; Zhong Xiang Cheah; Aaron T. Simmons (Resources, Conservation and Recycling, 2023)

Parsing progress in conservation management of Australian mammals – A reply to - John C.Z. Woinarski; Stephen T. Garnett; Graeme Gillespie; Sarah M. Legge; Mark Lintermans; Libby Rumpff (Biological Conservation, 2023)

Are associations between obesity and prostate cancer outcomes following radical prostatectomy the same in smokers and non-smokers? Results from the SEARCH Cohort - Ivy T. Liu; Lin Gu; Amanda M. De Hoedt; Matthew R. Cooperberg; Christopher L. Amling; Christopher J. Kane; Zachary Klaassen; Martha K. Terris; Lourdes Guerrios-Rivera; Adriana C. Vidal; William J. Aronson; Stephen J. Freedland; et al. (Cancer Causes & Control, 2023)

Sea ice surface type classification of ICESat-2 ATL07 data by using data-driven machine learning model: Ross Sea, Antarctic as an example - Younghyun Koo; Hongjie Xie; Nathan T. Kurtz; Stephen F. Ackley; Wei Wang (Remote Sensing of Environment, 2023)

Terrestrial carbon isotope stratigraphy of the Eocene–Oligocene transition, Petrockstowe and Bovey basins, Devon, UK - Mohammed S. Chaanda; Stephen T. Grimes; Rhodri M. Jerrett; Mark Anderson; Melanie J. Leng; Meriel E. Fitzpatrick; Gregory D. Price (Proceedings of the Geologists' Association, 2023)

Chronic mandibular osteomyelitis associated with a novel probable Kocuria sp in a sugar glider (Petaurus breviceps) - Alan T. Mulder; Megan Partyka; Stephen J. Divers; April Childress; James F.X. Wellehan; Justin M. Stilwell (Journal of Comparative Pathology, 2023)

Trends in bushfire related tweets during the Australian ‘Black Summer’ of 2019/20 - Kerstin K. Zander; Stephen T. Garnett; Robert Ogie; Mamoun Alazab; Duy Nguyen (Forest Ecology and Management, 2023)

Release of mercury during contact metamorphism of shale: Implications for understanding the impacts of large igneous province volcanism - Henrik H. Svensen; Morgan T. Jones; Lawrence M.E. Percival; Stephen E. Grasby; Tamsin A. Mather (Earth and Planetary Science Letters, 2023)

Even after armed conflict, the environmental quality of Indigenous Peoples' lands in biodiversity hotspots surpasses that of non-Indigenous lands - Madeline Beattie; Julia E. Fa; Ian Leiper; Álvaro Fernández-Llamazares; Kerstin K. Zander; Stephen T. Garnett (Biological Conservation, 2023)

Factors influencing mercury exposure in Arctic-breeding shorebirds - Marie Perkins; Iain J. Stenhouse; Richard B. Lanctot; Stephen Brown; Joël Bêty; Megan Boldenow; Jenny Cunningham; Willow English; River Gates; H. Grant Gilchrist; Marie-Andrée Giroux; Kirsten Grond; et al. (Ecotoxicology, 2023)

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Jansen Smith; Marina C. Rillo; Ádám T. Kocsis; Maria Dornelas; David Fastovich; Huai‐Hsuan M. Huang; Lukas Jonkers; Wolfgang Kiessling; Qijian Li; Lee Hsiang Liow; Miranda Margulis‐Ohnuma; Stephen Meyers; et al. (Global Ecology and Biogeography, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present‐day to millions of years ago. Main Types of Variables Included BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm 2 to grid cells of ~100 km 2 . Time Period and Grain BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format SQLite, Comma‐separated values.

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Living comfortably with heat in Australia – preferred indoor temperatures and climate zones - Kerstin K. Zander; Joost van Hoof; Sarah Carter; Stephen T. Garnett (Sustainable Cities and Society, 2023)

Functional analyses of single nucleotide polymorphic variants of the DNA glycosylase NEIL1 in sub-Saharan African populations - Jamie T. Zuckerman; Irina G. Minko; Melis Kant; Pawel Jaruga; Michael P. Stone; Miral Dizdaroglu; Amanda K. McCullough; R. Stephen Lloyd (DNA Repair, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Tropical dry woodland loss occurs disproportionately in areas of highest conservation value - Ana Buchadas; Martin Jung; Mercedes Bustamante; Álvaro Fernández‐Llamazares; Stephen T. Garnett; Ana Sofía Nanni; Natasha Ribeiro; Patrick Meyfroidt; Tobias Kuemmerle (Global Change Biology, 2023)
Tropical and subtropical dry woodlands are rich in biodiversity and carbon. Yet, many of these woodlands are under high deforestation pressure and remain weakly protected. Here, we assessed how deforestation dynamics relate to areas of woodland protection and to conservation priorities across the world's tropical dry woodlands. Specifically, we characterized different types of deforestation frontier from 2000 to 2020 and compared them to protected areas (PAs), Indigenous Peoples' lands and conservation areas for biodiversity, carbon and water. We found that global conservation priorities were always overrepresented in tropical dry woodlands compared to the rest of the globe (between 4% and 96% more than expected, depending on the type of conservation priority). Moreover, about 41% of all dry woodlands were characterized as deforestation frontiers, and these frontiers have been falling disproportionately in areas with important regional (i.e. tropical dry woodland) conservation assets. While deforestation frontiers were identified within all tropical dry woodland classes of woodland protection, they were lower than the average within protected areas coinciding with Indigenous Peoples' lands (23%), and within other PAs (28%). However, within PAs, deforestation frontiers have also been disproportionately affecting regional conservation assets. Many emerging deforestation frontiers were identified outside but close to PAs, highlighting a growing threat that the conserved areas of dry woodland will become isolated. Understanding how deforestation frontiers coincide with major types of current woodland protection can help target context‐specific conservation policies and interventions to tropical dry woodland conservation assets (e.g. PAs in which deforestation is rampant require stronger enforcement, inactive deforestation frontiers could benefit from restoration). Our analyses also identify recurring patterns that can be used to test the transferability of governance approaches and promote learning across social–ecological contexts.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Effect of planning policies on land use dynamics and livelihood opportunities under global environmental change: Evidence from the Mekong Delta - Tristan Berchoux; Craig W. Hutton; Oliver Hensengerth; Hal E. Voepel; Van P.D. Tri; Pham T. Vu; Nghia N. Hung; Dan Parsons; Stephen E. Darby (Land Use Policy, 2023)

Cretaceous long-distance lithospheric extension and surface response in South China - Jianhua Li; Shuwen Dong; Peter A. Cawood; Hans Thybo; Peter D. Clift; Stephen T. Johnston; Guochun Zhao; Yueqiao Zhang (Earth-Science Reviews, 2023)

Frogs still in a dark place?: Reply to - John C.Z. Woinarski; Stephen T. Garnett; Graeme Gillespie; Sarah M. Legge; Mark Lintermans; Libby Rumpff (Biological Conservation, 2023)

Effects of acute cigarette smoke concentrate exposure on mitochondrial energy transfer in fast- and slow-twitch skeletal muscle - Stephen T. Decker; Nadia Alexandrou-Majaj; Gwenael Layec (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Growth, carcass and meat quality characteristics of Charolais-sired steers and heifers born to Angus-cross-dairy and Angus breeding cows - Lucy W. Coleman; Nicola M. Schreurs; Paul R. Kenyon; Stephen T. Morris; Rebecca E. Hickson (Meat Science, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Lead change of a HIF-2α antagonist guided by multiparameter optimization and utilization of an Olp→π*Ar interaction - Paul M. Wehn; Song Yang; Jonas A. Grina; James P. Rizzi; Stephen T. Schlachter; Bin Wang; Rui Xu; Hanbiao Yang; Xinlin Du; Guangzhou Han; Keshi Wang; Robert M. Czerwinski; et al. (Medicinal Chemistry Research, 2023)

Incorporating potential environmental impacts in building seismic design decisions - Rosa E. Gonzalez; Max T. Stephens; Charlotte Toma; David Dowdell (Bulletin of Earthquake Engineering, 2023)
Seismic losses due to earthquakes have been shown to have significant economic, social and environmental consequences. Over recent years, research to predict potential economic and social impact due to seismic risk has been increasing. Recognizing that the traditional philosophy of life safety design can lead to extensive damage and demolition which has a large environmental cost, incorporating environmental impacts associated with the expected seismic damage over a building’s life is a key step as the building industry moves towards both sustainable and seismically resilient design. This paper introduces a framework that uses environmental indicators quantifying losses from seismic response that can then be used to advocate for a change in seismic performance objectives. First, existing literature and previously developed approaches for quantifying potential environmental impact due to seismic damage are summarized. Next, performance based earthquake engineering concepts are used to demonstrate a probabilistic approach to quantify potential environmental impacts using a range of environmental and resource use indicators over the life span of a case study building. In addition, a case study is presented to compare different environmental indicators between a Code Minimum building and the same building redesigned for a higher seismic performance. The majority of the composition of the environmental indicator values are from the inclusion of the non-repairable scenario, and from the repair activities, the majority of the impacts are from damage to drift sensitive components including curtains walls, partitions and elevators. For the Code Minimum building the non-repairable scenario contributes to between 8 to 11% the total seismic cost. For the Stronger Stiffer building, the non-repairable scenario contributes around 3% of the initial impact. Neglecting non-repairable scenarios does significantly reduce the potential environmental impacts when analyzing buildings designed for current code minimum structural standards.

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

Abnormal Wall Shear Stress Area is Correlated to Coronary Artery Bypass Graft Remodeling 1 Year After Surgery - Nhien Tran-Nguyen; Andrew T. Yan; Stephen Fremes; Piero Triverio; Laura Jimenez-Juan (Annals of Biomedical Engineering, 2023)

High interannual surface p CO 2 variability in the southern Canadian Arctic Archipelago's Kitikmeot Sea - Richard P. Sims; Mohamed M. M. Ahmed; Brian J. Butterworth; Patrick J. Duke; Stephen F. Gonski; Samantha F. Jones; Kristina A. Brown; Christopher J. Mundy; William J. Williams; Brent G. T. Else (Ocean Science, 2023)
Warming of the Arctic due to climate change means the Arctic Ocean is now free from ice for longer, as sea ice melts earlier and refreezes later. Yet, it remains unclear how this extended ice-free period will impact carbon dioxide (CO2) fluxes due to scarcity of surface ocean CO2 measurements. Baseline measurements are urgently needed to understand spatial and temporal air–sea CO2 flux variability in the changing Arctic Ocean. There is also uncertainty as to whether the previous basin-wide surveys are representative of the many smaller bays and inlets that make up the Canadian Arctic Archipelago (CAA). By using a research vessel that is based in the remote Inuit community of Ikaluqtuutiak (Cambridge Bay, Nunavut), we have been able to reliably survey pCO2 shortly after ice melt and access previously unsampled bays and inlets in the nearby region. Here we present 4 years of consecutive summertime pCO2 measurements collected in the Kitikmeot Sea in the southern CAA. Overall, we found that this region is a sink for atmospheric CO2 in August (average of all calculated fluxes over the four cruises was −4.64 mmol m−2 d−1), but the magnitude of this sink varies substantially between years and locations (average calculated fluxes of +3.58, −2.96, −16.79 and −0.57 mmol m−2 d−1 during the 2016, 2017, 2018 and 2019 cruises, respectively). Surface ocean pCO2 varied by up to 156 µatm between years, highlighting the importance of repeat observations in this region, as this high interannual variability would not have been captured by sparse and infrequent measurements. We find that the surface ocean pCO2 value at the time of ice melt is extremely important in constraining the magnitude of the air–sea CO2 flux throughout the ice-free season. However, further constraining the air–sea CO2 flux in the Kitikmeot Sea will require a better understanding of how pCO2 changes outside of the summer season. Surface ocean pCO2 measurements made in small bays and inlets of the Kitikmeot Sea were ∼ 20–40 µatm lower than in the main channels. Surface ocean pCO2 measurements made close in time to ice breakup (i.e. within 2 weeks) were ∼ 50 µatm lower than measurements made > 4 weeks after breakup. As previous basin-wide surveys of the CAA have focused on the deep shipping channels and rarely measure close to the ice breakup date, we hypothesize that there may be an observational bias in previous studies, leading to an underestimate of the CO2 sink in the CAA. These high-resolution measurements constitute an important new baseline for gaining a better understanding of the role this region plays in the uptake of atmospheric CO2.

Effects of projected end-of-century temperature on the muscle development of neonate epaulette sharks, Hemiscyllium ocellatum - Peyton A. Thomas; Emily E. Peele; Carolyn R. Wheeler; Kara Yopak; Jodie L. Rummer; John W. Mandelman; Stephen T. Kinsey (Marine Biology, 2023)

Digital Storytelling Through the European Commission’s Africa Knowledge Platform to Bridge the Science-Policy Interface for Raw Materials - Falko T. Buschke; Christine Estreguil; Lucia Mancini; Fabrice Mathieux; Hugh Eva; Luca Battistella; Stephen Peedell (Circular Economy and Sustainability, 2023)

Elevated Galectin-9 across the human brain correlates with HIV neuropathology and detrimental cognitive states - Thomas A. Premeaux; Stephen T. Yeung; Satish K. Pillai; Lishomwa C. Ndhlovu (Journal of NeuroVirology, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Intraplate lithospheric extension revealed by seismic reflection profiling of South China - Shuwen Dong; Jianhua Li; Rui Gao; Peter A. Cawood; Hans Thybo; Stephen T. Johnston; Liqing Jiao; Yueqiao Zhang; Jinming Wang (Earth and Planetary Science Letters, 2023)

Conservation benefit-sharing mechanisms and their effectiveness in the Greater Serengeti Ecosystem: local communities’ perspectives - Juma J. Kegamba; Kamaljit K. Sangha; Penelope A.S. Wurm; Stephen T. Garnett (Biodiversity and Conservation, 2023)
Benefit-sharing mechanisms have been instrumental in securing the support of local communities living on the edge of protected areas to implement protected area goals and enhance biodiversity conservation outcomes. Understanding the acceptability of the types of benefit provided among diverse communities is crucial for co-designing benefit-sharing approaches that accommodate local perspectives. Here, we used quasi-structured questionnaires and focus group discussions (FGD) to assess the acceptance of the types of benefit received by the communities in the Greater Serengeti Ecosystem (GSE) in Tanzania and the effectiveness of the benefits in securing community support for conservation reserves. We found that the categories of social service provision, livelihood support, and employment described all the benefits provided across conservation institutions operating in the GSE. However, the types of benefit within these categories varied significantly among conservation institutions, in terms of level and frequency of benefits received by communities. Overall, student scholarships were highly rated by respondents as the most satisfying benefit received. Respondents who were dissatisfied with the benefits received thought that the benefits did not compensate for the high costs arising from wildlife incursions onto their land. Communities’ acceptance of the benefits received varied greatly among villages, but only a small proportion of pooled respondents (22%) were willing to support the existence of a protected area without benefit. This study suggests that local people are willing to support conservation outcomes but require conservation institutions to give greater consideration to the costs incurred by communities, their livelihood needs, and access to natural resources or other benefits. We recommend that benefit-sharing be tailored to the local circumstances and cultures of people living close to protected areas, particularly communities expressing more negative views, to ensure adequate and appropriate compensation is provided.

Factors that shape large‐scale gradients in clonality - Hongxiang Zhang; Si‐Chong Chen; Stephen P. Bonser; Timothy Hitchcock; Angela T. Moles (Journal of Biogeography, 2023)
Aim Many plant species reproduce clonally. However, ecologists still have much to learn about the factors that shape large‐scale patterns in plant clonal growth and reproduction, especially in the southern hemisphere. We addressed this knowledge gap by quantifying relationships between reproductive mode and a suite of plant characteristics and environmental variables. Location Australia. Taxon Spermatophytes. Methods We used data for 914,456 species‐site combinations (including 4116 unique species) in Australia to quantify the bivariate relationships between the probability of species having clonal reproduction and four plant characteristics and 16 environmental variables, using phylogenetic logistic regressions. We also compared the relative effects across plant characteristics and environmental variables groups through principal component analysis and phylogenetic logistic regressions. Results The probability of species having clonal reproduction was much more strongly related to plant characteristics than to environmental variables. Short, herbaceous plants and monocots were more likely to have clonal reproduction and were more common in environments with low temperatures, low solar radiation, high moisture availability, high net primary productivity (NPP) and high soil organic carbon and nitrogen contents. Tall, woody plants and eudicots tended to have only sexual reproduction, and were more common in dry and soil impoverished environments. Main conclusions Our results advance the understanding of the factors that shape large‐scale patterns in plant reproduction strategy. For example, the fact that clonality is more common in shorter, herbaceous species suggests that clonality can be added to the suite of traits that align species on the fast‐slow continuum. The fact that clonal reproduction is more tightly correlated with moisture availability, NPP and soil nutrients than climatic extremes and variations suggests that clonal reproduction may be better understood as a strategy for population expansion in resource abundant sites than as a strategy for reproductive assurance under environmental stress.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Bigger lambs or more lambs: The conundrum for New Zealand lamb producers - Adam J. Moloney; Peter R. Tozer; Stephen T. Morris; Paul R. Kenyon (Livestock Science, 2023)

MOO-GAPS: A multi-objective optimization model for global animal production and sustainability - Adam C. Castonguay; Stephen Polasky; Matthew H. Holden; Mario Herrero; Jinfeng Chang; Daniel Mason-D’Croz; Cecile Godde; Katie Lee; Brett A. Bryan; James Gerber; Edward T. Game; Eve McDonald-Madden (Journal of Cleaner Production, 2023)

Subjective response to alcohol in young adults with bipolar disorder and recent alcohol use: a within-subject randomized placebo-controlled alcohol administration study - Elizabeth T. C. Lippard; Dylan E. Kirsch; Raquel Kosted; Vanessa Le; Jorge R. C. Almeida; Kim Fromme; Stephen M. Strakowski (Psychopharmacology, 2023)

Terrestrial locomotor behaviors of the big brown bat (Vespertilionidae: Eptesicus fuscus) - Matthew F. Jones; Stephen T. Hasiotis (Mammal Research, 2023)

Do unpublished data help to redraw distributions? The case of the spectacled bear in Peru - Nereyda Falconi; John T. Finn; Todd K. Fuller; Stephen DeStefano; John F. Organ (Mammal Research, 2023)

Topic modelling the mobility response to heat and drought - Kerstin K. Zander; Hunter S. Baggen; Stephen T. Garnett (Climatic Change, 2023)
We conducted a systematic literature review of peer-reviewed full text articles on the nexus between human mobility and drought or heat published between 2001 and 2021, inclusive. We identified 387 relevant articles, all of which were analysed descriptively using a dictionary-based approach and by using an unsupervised machine learning–based Latent Dirichlet Allocation (LDA) model. Most articles were in response to droughts (71%), but heat and extreme temperature became more prominent after 2015. The drought-related literature focuses geographically on African and Southern Asian countries, while heat-related research has mainly been conducted in developed countries (mostly in the USA and Australia). For both hazards, European countries are under-represented. The LDA model identified 46 topics which were clustered into five major themes. One cluster (14% of all articles) included literature on heat-related mobility, mostly data-driven models, including amenity migration. The other four clusters included literature on drought, primarily on farming societies and the agricultural sector with three of those clusters making up 63% of all articles, with the common overarching focus on climate migration and food security. One of the four drought clusters focused on social dysfunction in relation to droughts. A sentiment analysis showed articles focusing on voluntary mobility as part of adaptation to drought and heat were more positive than articles focusing on migration triggered by droughts and heat. Based on the topics and the article characterisation, we identified various research gaps, including migration in relation to urban droughts, heat in farming societies and in urban societies of developing countries, planned retreat from hot to cooler places, and the inability or barriers to doing so. More research is also needed to understand the compound effect of drought and heat, and the social and psychological processes that lead to a mobility decision.

Warming and hypoxia reduce the performance and survival of northern bay scallops ( Argopecten irradians irradians ) amid a fishery collapse - Stephen J. Tomasetti; Brendan D. Hallinan; Stephen T. Tettelbach; Nils Volkenborn; Owen W. Doherty; Bassem Allam; Christopher J. Gobler (Global Change Biology, 2023)
Warming temperatures and diminishing dissolved oxygen (DO) concentrations are among the most pervasive drivers of global coastal change. While regions of the Northwest Atlantic Ocean are experiencing greater than average warming, the combined effects of thermal and hypoxic stress on marine life in this region are poorly understood. Populations of the northern bay scallop, Argopecten irradians irradians across the northeast United States have experienced severe declines in recent decades. This study used a combination of high‐resolution (~1 km) satellite‐based temperature records, long‐term temperature and DO records, field and laboratory experiments, and high‐frequency measures of scallop cardiac activity in an ecosystem setting to quantify decadal summer warming and assess the vulnerability of northern bay scallops to thermal and hypoxic stress across their geographic distribution. From 2003 to 2020, significant summer warming (up to ~0.2°C year −1 ) occurred across most of the bay scallop range. At a New York field site in 2020, all individuals perished during an 8‐day estuarine heatwave that coincided with severe diel‐cycling hypoxia. Yet at a Massachusetts site with comparable DO levels but lower daily mean temperatures, mortality was not observed. A 96‐h laboratory experiment recreating observed daily temperatures of 25 or 29°C, and normoxia or hypoxia (22.2% air saturation), revealed a 120‐fold increased likelihood of mortality in the 29°C‐hypoxic treatment compared with control conditions, with scallop clearance rates also reduced by 97%. Cardiac activity measurements during a field deployment indicated that low DO and elevated daily temperatures modulate oxygen consumption rates and likely impact aerobic scope. Collectively, these findings suggest that concomitant thermal and hypoxic stress can have detrimental effects on scallop physiology and survival and potentially disrupt entire fisheries. Recovery of hypoxic systems may benefit vulnerable fisheries under continued warming.

Marine invertebrates and noise - Marta Solé; Kenzo Kaifu; T. Aran Mooney; Sophie L. Nedelec; Frédéric Olivier; Andrew N. Radford; Mirella Vazzana; Matthew A. Wale; Jayson M. Semmens; Stephen D. Simpson; Giuseppa Buscaino; Anthony Hawkins; et al. (Frontiers in Marine Science, 2023)
Within the set of risk factors that compromise the conservation of marine biodiversity, one of the least understood concerns is the noise produced by human operations at sea and from land. Many aspects of how noise and other forms of energy may impact the natural balance of the oceans are still unstudied. Substantial attention has been devoted in the last decades to determine the sensitivity to noise of marine mammals—especially cetaceans and pinnipeds—and fish because they are known to possess hearing organs. Recent studies have revealed that a wide diversity of invertebrates are also sensitive to sounds, especially via sensory organs whose original function is to allow maintaining equilibrium in the water column and to sense gravity. Marine invertebrates not only represent the largest proportion of marine biomass and are indicators of ocean health but many species also have important socio-economic values. This review presents the current scientific knowledge on invertebrate bioacoustics (sound production, reception, sensitivity), as well as on how marine invertebrates are affected by anthropogenic noises. It also critically revisits the literature to identify gaps that will frame future research investigating the tolerance to noise of marine ecosystems.

Volcanism and carbon cycle perturbations in the High Arctic during the Late Jurassic – Early Cretaceous - Madeleine L. Vickers; Mads E. Jelby; Kasia K. Śliwińska; Lawrence M.E. Percival; Feiyue Wang; Hamed Sanei; Gregory D. Price; Clemens V. Ullmann; Stephen E. Grasby; Lutz Reinhardt; Tamsin A. Mather; Joost Frieling; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Seismic mapping of shallow bedrock shelves in the hanging wall of the Wasatch fault - Stephen T. Nelson; John H. McBride (Journal of Applied Geophysics, 2023)

Lights at the end of the tunnel: The incidence and characteristics of recovery for Australian threatened animals - John C.Z. Woinarski; Stephen T. Garnett; Graeme Gillespie; Sarah M. Legge; Mark Lintermans; Libby Rumpff (Biological Conservation, 2023)

Moving the corpse to hide the evidence: horizontal as well as vertical movement is important when burying beetles cache a carcass - Stephen T. Trumbo (Journal of Insect Behavior, 2023)

Towards building resilient cities to pandemics: A review of COVID-19 literature - Melika Amirzadeh; Saeideh Sobhaninia; Stephen T. Buckman; Ayyoob Sharifi (Sustainable Cities and Society, 2023)

Exploring long-term trends in microcystin toxin values associated with persistent harmful algal blooms in Grand Lake St Marys - Stephen J. Jacquemin; Jason C. Doll; Laura T. Johnson; Silvia E. Newell (Harmful Algae, 2023)

Spatial modeling of Sarus Crane nest site suitability in Cambodia to help target conservation of breeding areas - Robert N. van Zalinge; Jeb Barzen; Stephen T. Garnett (Forest Ecology and Management, 2023)

Is an MRI-derived anatomical measure of dementia risk also a measure of brain aging? - Ramon Casanova; Andrea M. Anderson; Ryan T. Barnard; Jamie N. Justice; Anna Kucharska-Newton; Beverly Gwen Windham; Priya Palta; Rebecca F. Gottesman; Thomas H. Mosley; Timothy M. Hughes; Lynne E. Wagenknecht; Stephen B. Kritchevsky (GeroScience, 2023)

Spiral Laminar Flow is Associated with a Reduction in Disturbed Shear in Patient-Specific Models of an Arteriovenous Fistula - Connor V. Cunnane; J. Graeme Houston; Daniel T. Moran; Stephen P. Broderick; Rose A. Ross; Michael T. Walsh (Cardiovascular Engineering and Technology, 2023)

Genetic and morphological comparisons of lesser celandine (Ficaria verna) invasions suggest regionally widespread sexual reproduction - Kali Z. Mattingly; Charles T. C. Day; Emily S. J. Rauschert; Aaron Tayal; Stephen M. Hovick (Biological Invasions, 2023)

Longer duration of seasonal stratification contributes to widespread increases in lake hypoxia and anoxia - Stephen F. Jane; Joshua L. Mincer; Maximilian P. Lau; Abigail S. L. Lewis; Jonathan T. Stetler; Kevin C. Rose (Global Change Biology, 2023)
The concentration of dissolved oxygen (DO) is an important attribute of aquatic ecosystems, influencing habitat, drinking water quality, biodiversity, nutrient biogeochemistry, and greenhouse gas emissions. While average summer DO concentrations are declining in lakes across the temperate zone, much remains unknown about seasonal factors contributing to deepwater DO losses. It is unclear whether declines are related to increasing rates of seasonal DO depletion or changes in seasonal stratification that limit re‐oxygenation of deep waters. Furthermore, despite the presence of important biological and ecological DO thresholds, there has been no large‐scale assessment of changes in the amount of habitat crossing these thresholds, limiting the ability to understand the consequences of observed DO losses. We used a dataset from >400 widely distributed lakes to identify the drivers of DO losses and quantify the frequency and volume of lake water crossing biologically and ecologically important threshold concentrations ranging from 5 to 0.5 mg/L. Our results show that while there were no consistent changes over time in seasonal DO depletion rates, over three‐quarters of lakes exhibited an increase in the duration of stratification, providing more time for seasonal deepwater DO depletion to occur. As a result, most lakes have experienced summertime increases in the amount of water below all examined thresholds in deepwater DO concentration, with increases in the proportion of the water column below thresholds ranging between 0.9% and 1.7% per decade. In the 30‐day period preceding the end of stratification, increases were greater at >2.2% per decade and >70% of analyzed lakes experienced increases in the amount of oxygen‐depleted water. These results indicate ongoing climate‐induced increases in the duration of stratification have already contributed to reduction of habitat for many species, likely increased internal nutrient loading, and otherwise altered lake chemistry. Future warming is likely to exacerbate these trends.

Applying landscape metrics to species distribution model predictions to characterize internal range structure and associated changes - Amelia Curd; Mathieu Chevalier; Mickaël Vasquez; Aurélien Boyé; Louise B. Firth; Martin P. Marzloff; Lucy M. Bricheno; Michael T. Burrows; Laura E. Bush; Céline Cordier; Andrew J. Davies; J. A. Mattias Green; et al. (Global Change Biology, 2023)
Distributional shifts in species ranges provide critical evidence of ecological responses to climate change. Assessments of climate‐driven changes typically focus on broad‐scale range shifts (e.g. poleward or upward), with ecological consequences at regional and local scales commonly overlooked. While these changes are informative for species presenting continuous geographic ranges, many species have discontinuous distributions—both natural (e.g. mountain or coastal species) or human‐induced (e.g. species inhabiting fragmented landscapes)—where within‐range changes can be significant. Here, we use an ecosystem engineer species ( Sabellaria alveolata ) with a naturally fragmented distribution as a case study to assess climate‐driven changes in within‐range occupancy across its entire global distribution. To this end, we applied landscape ecology metrics to outputs from species distribution modelling (SDM) in a novel unified framework. SDM predicted a 27.5% overall increase in the area of potentially suitable habitat under RCP 4.5 by 2050, which taken in isolation would have led to the classification of the species as a climate change winner. SDM further revealed that the latitudinal range is predicted to shrink because of decreased habitat suitability in the equatorward part of the range, not compensated by a poleward expansion. The use of landscape ecology metrics provided additional insights by identifying regions that are predicted to become increasingly fragmented in the future, potentially increasing extirpation risk by jeopardising metapopulation dynamics. This increased range fragmentation could have dramatic consequences for ecosystem structure and functioning. Importantly, the proposed framework—which brings together SDM and landscape metrics—can be widely used to study currently overlooked climate‐driven changes in species internal range structure, without requiring detailed empirical knowledge of the modelled species. This approach represents an important advancement beyond predictive envelope approaches and could reveal itself as paramount for managers whose spatial scale of action usually ranges from local to regional.

A deep investigation into the mechanisms and factors producing mud pumping of railway track - Stephen T. Wilk; Dingqing Li (Transportation Geotechnics, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Whiskers provide time-series of toxic and essential trace elements, Se:Hg molar ratios, and stable isotope values of an apex Antarctic predator, the leopard seal - Patrick Charapata; Casey T. Clark; Nathan Miller; Sarah S. Kienle; Daniel P. Costa; Michael E. Goebel; Heather Gunn; Emily S. Sperou; Shane B. Kanatous; Daniel E. Crocker; Renato Borras-Chavez; Stephen J. Trumble (Science of The Total Environment, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

Evaluation of the effects of abattoir effluent on the physicochemical and bacteriological quality of River Benue, Nigeria - Victor T. Omoni; Paul O. Bankole; Ojobo Omoche; Christopher Obida; Colonel Igben; Okekporo E. Stephen; Ekeoma I. Ogwo; Doosuur N. Torjir (Environmental Monitoring and Assessment, 2023)

Shoreline sentinels of global change show the consequences of extreme events - Stephen J. Hawkins; Michael T. Burrows; Nova Mieszkowska (Global Change Biology, 2023)

Exploring the perceptions of Malaysian Gen Z towards the impact of COVID-19 on sustainable development - Stephen T. Homer; Kuan Siew Khor (Environmental Science and Pollution Research, 2022)

Electron microscopy holdings of the Protein Data Bank: the impact of the resolution revolution, new validation tools, and implications for the future - Stephen K. Burley; Helen M. Berman; Wah Chiu; Wei Dai; Justin W. Flatt; Brian P. Hudson; Jason T. Kaelber; Sagar D. Khare; Arkadiusz W. Kulczyk; Catherine L. Lawson; Grigore D. Pintilie; Andrej Sali; et al. (Biophysical Reviews, 2022)
As a discipline, structural biology has been transformed by the three-dimensional electron microscopy (3DEM) “Resolution Revolution” made possible by convergence of robust cryo-preservation of vitrified biological materials, sample handling systems, and measurement stages operating a liquid nitrogen temperature, improvements in electron optics that preserve phase information at the atomic level, direct electron detectors (DEDs), high-speed computing with graphics processing units, and rapid advances in data acquisition and processing software. 3DEM structure information (atomic coordinates and related metadata) are archived in the open-access Protein Data Bank (PDB), which currently holds more than 11,000 3DEM structures of proteins and nucleic acids, and their complexes with one another and small-molecule ligands (~ 6% of the archive). Underlying experimental data (3DEM density maps and related metadata) are stored in the Electron Microscopy Data Bank (EMDB), which currently holds more than 21,000 3DEM density maps. After describing the history of the PDB and the Worldwide Protein Data Bank (wwPDB) partnership, which jointly manages both the PDB and EMDB archives, this review examines the origins of the resolution revolution and analyzes its impact on structural biology viewed through the lens of PDB holdings. Six areas of focus exemplifying the impact of 3DEM across the biosciences are discussed in detail (icosahedral viruses, ribosomes, integral membrane proteins, SARS-CoV-2 spike proteins, cryogenic electron tomography, and integrative structure determination combining 3DEM with complementary biophysical measurement techniques), followed by a review of 3DEM structure validation by the wwPDB that underscores the importance of community engagement.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Spread, Vector Flight Behavior, and Impact of Laurel Wilt in Sassafras Beyond the Gulf-Atlantic Coastal Plain - Albert E Mayfield; Rabiu O Olatinwo; Jaesoon Hwang; Bryan T Mudder; Alexandra Blevins; Stephen W Fraedrich (Journal of Forestry, 2022)
Laurel wilt is a destructive vascular disease of trees in the laurel family (Lauraceae) caused by a nonnative insect/pathogen complex. This study monitored the recent spread and impact of laurel wilt in sassafras (Sassafras albidum [Nutt.] Nees) from the Gulf-Atlantic Coastal Plain region of the southeastern United States (US) into the adjacent Piedmont/Sandhills and Mountain regions. Laurel wilt was detected at thirteen of forty-six sassafras sites including seven outside the Coastal Plain. Compared to nondiseased sites, sassafras mortality due to laurel wilt increased rapidly from 2018 to 2020 and occurred in all diameter classes monitored (≥ 5 cm diameter at breast height, dbh). Flight trapping for the laurel wilt vector, the redbay ambrosia beetle (RAB, Xyleborus glabratus Eichhoff), with α-copaene lures did not enhance early detection of latent laurel wilt infections. Seasonal flight activity of the RAB in the Piedmont and Mountains suggested two generations per year with little to no flight from December through March. Study Implications Sassafras is the most widely-distributed lauraceous tree species in the US and is valued for its ecological functions, durable wood, and numerous cultural uses. Our results strongly suggest the potential for substantial loss of the existing sassafras resource as laurel wilt continues spreading through the eastern US. Survey traps baited with current lures for the primary insect vector are unlikely to improve early detection of new laurel wilt infections. The georeferenced network of plots established for this project provides baseline data for future monitoring efforts and could be revisited to look for evidence of sassafras resistance to the laurel wilt pathogen.

A globally relevant change taxonomy and evidence‐based change framework for land monitoring - Richard M. Lucas; Sophia German; Graciela Metternicht; Rebecca K. Schmidt; Christopher J. Owers; Suzanne M. Prober; Anna E. Richards; Sally Tetreault‐Campbell; Kristen J. Williams; Norman Mueller; Belle Tissott; Sean M. T. Chua; et al. (Global Change Biology, 2022)
A globally relevant and standardized taxonomy and framework for consistently describing land cover change based on evidence is presented, which makes use of structured land cover taxonomies and is underpinned by the Driver‐Pressure‐State‐Impact‐Response (DPSIR) framework. The Global Change Taxonomy currently lists 246 classes based on the notation ‘impact (pressure)’, with this encompassing the consequence of observed change and associated reason(s), and uses scale‐independent terms that factor in time. Evidence for different impacts is gathered through temporal comparison (e.g., days, decades apart) of land cover classes constructed and described from Environmental Descriptors (EDs; state indicators) with pre‐defined measurement units (e.g., m, %) or categories (e.g., species type). Evidence for pressures, whether abiotic, biotic or human‐influenced, is similarly accumulated, but EDs often differ from those used to determine impacts. Each impact and pressure term is defined separately, allowing flexible combination into ‘impact (pressure)’ categories, and all are listed in an openly accessible glossary to ensure consistent use and common understanding. The taxonomy and framework are globally relevant and can reference EDs quantified on the ground, retrieved/classified remotely (from ground‐based, airborne or spaceborne sensors) or predicted through modelling. By providing capacity to more consistently describe change processes—including land degradation, desertification and ecosystem restoration—the overall framework addresses a wide and diverse range of local to international needs including those relevant to policy, socioeconomics and land management. Actions in response to impacts and pressures and monitoring towards targets are also supported to assist future planning, including impact mitigation actions.

Benzonatate Overdose Presenting as Cardiac Arrest with Rapidly Narrowing QRS Interval - Robert J. Stephens; Ari B. Filip; Kevin T. Baumgartner; Evan S. Schwarz; David B. Liss (Journal of Medical Toxicology, 2022)

Eight things you should never do in a monitoring program: an Australian perspective - David B. Lindenmayer; John Woinarski; Sarah Legge; Martine Maron; Stephen T. Garnett; Tyrone Lavery; Jaana Dielenberg; Brendan A. Wintle (Environmental Monitoring and Assessment, 2022)
Monitoring is critical to gauge the effect of environmental management interventions as well as to measure the effects of human disturbances such as climate change. Recognition of the critical need for monitoring means that, at irregular intervals, recommendations are made for new government-instigated programs or to revamp existing ones. Using insights from past well-intentioned (but sadly also often failed) attempts to establish and maintain government-instigated monitoring programs in Australia, we outline eight things that should never be done in environmental monitoring programs (if they aim to be useful). These are the following: (1) Never commence a new environmental management initiative without also committing to a monitoring program. (2) Never start a monitoring program without clear questions. (3) Never implement a monitoring program without first doing a proper experimental design. (4) Never ignore the importance of matching the purpose and objectives of a monitoring program to the design of that program. (5) Never change the way you monitor something without ensuring new methods can be calibrated with the old ones. (6) Never try to monitor everything. (7) Never collect data without planning to curate and report on it. (8) If possible, avoid starting a monitoring program without the necessary resources secured. To balance our “nevers”, we provide a checklist of actions that will increase the chances a monitoring program will actually measure the effectiveness of environmental management. Scientists and resource management practitioners need to be part of a stronger narrative for, and key participants in, well-designed, implemented, and maintained government-led monitoring programs. We argue that monitoring programs should be mandated in threatened species conservation programs and all new environmental management initiatives.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Microvascular anatomy suggests varying aerobic activity levels in the adipose tissues of diving tetrapods - Molly K. Gabler-Smith; Amy J. Berger; D. Mark Gay; Stephen T. Kinsey; Andrew J. Westgate; Heather N. Koopman (Journal of Comparative Physiology B, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Experimental habitat fragmentation disrupts host–parasite interaction over decades via life‐cycle bottlenecks - Matthew E. Bitters; Jacqui Meyers; Julian Resasco; Stephen D. Sarre; Kika T. Tuff; Kendi F. Davies (Ecology, 2022)
Habitat loss and fragmentation are likely to seriously impact parasites, a less studied but critical component of ecosystems, yet we lack long‐term experimental evidence. Parasites structure communities, increase connectivity in food webs, and account for a large proportion of an ecosystem's total biomass. Food web models predict that parasites with multiple obligate hosts are at greater risk of extinction because the local extinction, or reduction in abundance, of any host will result in a life‐cycle bottleneck for the parasite. We examine the response of a parasite and its multiple hosts to forest fragmentation over 26 years in the Wog Wog Habitat Fragmentation Experiment in southeastern Australia. The parasite is the nematode Hedruris wogwogensis , its intermediate host is the amphipod, Arcitalitrus sylvaticus , and its definitive host is the skink, Lampropholis guichenoti . In the first decade after fragmentation, nematodes completely disappeared from the matrix (plantation forestry) and all but disappeared from their definitive host (skinks) in fragments, and by the third decade after fragmentation had not appreciably recovered anywhere in the fragmented landscape compared to continuous forest. The low prevalence of the nematode in the fragmented landscape was associated with the low abundance of one or the other host in different decades: low abundance of the intermediate host (amphipod) in the first decade and low abundance of the definitive host (skink) in the third decade. In turn, the low abundance of each host was associated with changes to the abiotic environment over time due largely to the dynamically changing matrix as the plantation trees grew. Our study provides rare long‐term experimental evidence of how disturbance can cause local extinction in parasites with life cycles dependent on more than one host species through population bottlenecks at any life stage. Mismatches in the abundance of multiple hosts over time are likely to be common following disturbance, thus causing parasites with complex life cycles to be particularly susceptible to habitat fragmentation and other disturbances. The integrity of food webs, communities, and ecosystems in fragmented landscapes may be more compromised than presently appreciated due to the sensitivity of parasites to habitat fragmentation.

Climate change-mediated heat stress vulnerability and adaptation strategies among outdoor workers - Stephen T. Odonkor; Samuel Adams (Climate and Development, 2022)

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Measurement of pore volume, connectivity and clogging of pervious concrete reactive barrier used to treat acid mine drainage - Stephen O. Ekolu; Fitsum Solomon; Frikkie de Beer; Louisette Bitandi; Rais N. Kilula; Khaya T. Maseko; Fatty G. Mahlangu (Environmental Science and Pollution Research, 2022)

Proceedings of the fifth international Molecular Pathological Epidemiology (MPE) meeting - Song Yao; Peter T. Campbell; Tomotaka Ugai; Gretchen Gierach; Mustapha Abubakar; Viktor Adalsteinsson; Jonas Almeida; Paul Brennan; Stephen Chanock; Todd Golub; Samir Hanash; Curtis Harris; et al. (Cancer Causes & Control, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

A roadmap to integrating resilience into the practice of coral reef restoration - Elizabeth C. Shaver; Elizabeth McLeod; Margaux Y. Hein; Stephen R. Palumbi; Kate Quigley; Tali Vardi; Peter J. Mumby; David Smith; Phanor Montoya‐Maya; Erinn M. Muller; Anastazia T. Banaszak; Ian M. McLeod; et al. (Global Change Biology, 2022)
Recent warm temperatures driven by climate change have caused mass coral bleaching and mortality across the world, prompting managers, policymakers, and conservation practitioners to embrace restoration as a strategy to sustain coral reefs. Despite a proliferation of new coral reef restoration efforts globally and increasing scientific recognition and research on interventions aimed at supporting reef resilience to climate impacts, few restoration programs are currently incorporating climate change and resilience in project design. As climate change will continue to degrade coral reefs for decades to come, guidance is needed to support managers and restoration practitioners to conduct restoration that promotes resilience through enhanced coral reef recovery, resistance, and adaptation. Here, we address this critical implementation gap by providing recommendations that integrate resilience principles into restoration design and practice, including for project planning and design, coral selection, site selection, and broader ecosystem context. We also discuss future opportunities to improve restoration methods to support enhanced outcomes for coral reefs in response to climate change. As coral reefs are one of the most vulnerable ecosystems to climate change, interventions that enhance reef resilience will help to ensure restoration efforts have a greater chance of success in a warming world. They are also more likely to provide essential contributions to global targets to protect natural biodiversity and the human communities that rely on reefs.

Resisting ecosystem transformation through an intensive whole‐lake fish removal experiment - Holly S. Embke; Stephen R. Carpenter; Daniel A. Isermann; Giancarlo Coppola; Douglas T. Beard; Abigail J. Lynch; Greg G. Sass; Zachary S. Feiner; M. Jake Vander Zanden (Fisheries Management and Ecology, 2022)
Lake ecosystems are shifting due to many drivers including climate change and landscape‐scale habitat disturbance, diminishing their potential to support some fisheries. Walleye Sander vitreus (Mitchill) populations, which support recreational and tribal fisheries across North America, have declined in some lakes. Climate change, harvest, invasive species and concurrent increases in warm‐water fishes (e.g. Centrarchidae) may have contributed to declines. To test the utility of an intensive management action to resist walleye loss, an experimental removal of ~285,000 centrarchids from a 33‐ha lake over 4 years was conducted while monitoring the fish community response. Centrarchid abundance declined and yellow perch Perca flavescens (Mitchill) increased, yet no evidence of walleye recruitment was observed. These findings explore the feasibility of intensive resistance as a management strategy in supporting walleye facing environmental change and provide a platform for management discussions to move beyond resist strategies in the Resist‐Accept‐Direct (RAD) framework to navigate ecosystem change.

Wilderness forms and their implications for global environmental policy and conservation - Katharina‐Victoria Pérez‐Hämmerle; Katie Moon; Rubén Venegas‐Li; Sean Maxwell; Jeremy S. Simmonds; Oscar Venter; Stephen T. Garnett; Hugh P. Possingham; James E. M. Watson (Conservation Biology, 2022)
With the intention of securing industry‐free land and seascapes, protecting wilderness entered international policy as a formal target for the first time in the zero draft of the Post‐2020 Global Biodiversity Framework under the Convention on Biological Diversity. Given this increased prominence in international policy, it is timely to consider the extent to which the construct of wilderness supports global conservation objectives. We evaluated the construct by overlaying recently updated cumulative human pressure maps that offer a global‐scale delineation of industry‐free land as wilderness with maps of carbon stock, species richness, and ground travel time from urban centers. Wilderness areas took variable forms in relation to carbon stock, species richness, and proximity to urban centers, where 10% of wilderness areas represented high carbon and species richness, 20% low carbon and species richness, and 3% high levels of remoteness (>48 h), carbon, and species richness. Approximately 35% of all remaining wilderness in 2013 was accessible in

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Unbound Brain-to-Plasma Partition Coefficient, Kp,uu,brain—a Game Changing Parameter for CNS Drug Discovery and Development - Irena Loryan; Andreas Reichel; Bo Feng; Christoffer Bundgaard; Christopher Shaffer; Cory Kalvass; Dallas Bednarczyk; Denise Morrison; Dominique Lesuisse; Edmund Hoppe; Georg C. Terstappen; Holger Fischer; et al. (Pharmaceutical Research, 2022)
Purpose More than 15 years have passed since the first description of the unbound brain-to-plasma partition coefficient (K p,uu,brain ) by Prof. Margareta Hammarlund-Udenaes, which was enabled by advancements in experimental methodologies including cerebral microdialysis. Since then, growing knowledge and data continue to support the notion that the unbound (free) concentration of a drug at the site of action, such as the brain, is the driving force for pharmacological responses. Towards this end, K p,uu,brain is the key parameter to obtain unbound brain concentrations from unbound plasma concentrations. Methods To understand the importance and impact of the K p,uu,brain concept in contemporary drug discovery and development, a survey has been conducted amongst major pharmaceutical companies based in Europe and the USA. Here, we present the results from this survey which consisted of 47 questions addressing: 1) Background information of the companies, 2) Implementation, 3) Application areas, 4) Methodology, 5) Impact and 6) Future perspectives. Results and conclusions From the responses, it is clear that the majority of the companies (93%) has established a common understanding across disciplines of the concept and utility of K p,uu,brain as compared to other parameters related to brain exposure. Adoption of the K p,uu,brain concept has been mainly driven by individual scientists advocating its application in the various companies rather than by a top-down approach. Remarkably, 79% of all responders describe the portfolio impact of K p,uu,brain implementation in their companies as ‘game-changing’. Although most companies (74%) consider the current toolbox for K p,uu,brain assessment and its validation satisfactory for drug discovery and early development, areas of improvement and future research to better understand human brain pharmacokinetics/pharmacodynamics translation have been identified.

Governance of forest resource use in western Nepal: Current state and community preferences - Manoj Bhatta; Kerstin K. Zander; Stephen T. Garnett (Ambio, 2022)

Terrestrial ecosystem restoration increases biodiversity and reduces its variability, but not to reference levels: A global meta‐analysis - Joe Atkinson; Lars A. Brudvig; Max Mallen‐Cooper; Shinichi Nakagawa; Angela T. Moles; Stephen P. Bonser (Ecology Letters, 2022)
Ecological restoration projects often have variable and unpredictable outcomes, and these can limit the overall impact on biodiversity. Previous syntheses have investigated restoration effectiveness by comparing average restored conditions to average conditions in unrestored or reference systems. Here, we provide the first quantification of the extent to which restoration affects both the mean and variability of biodiversity outcomes, through a global meta‐analysis of 83 terrestrial restoration studies. We found that, relative to unrestored (degraded) sites, restoration actions increased biodiversity by an average of 20%, while decreasing the variability of biodiversity (quantified by the coefficient of variation) by an average of 14%. As restorations aged, mean biodiversity increased and variability decreased relative to unrestored sites. However, restoration sites remained, on average, 13% below the biodiversity of reference (target) ecosystems, and were characterised by higher (20%) variability. The lower mean and higher variability in biodiversity at restored sites relative to reference sites remained consistent over time, suggesting that sources of variation (e.g. prior land use, restoration practices) have an enduring influence on restoration outcomes. Our results point to the need for new research confronting the causes of variability in restoration outcomes, and close variability and biodiversity gaps between restored and reference conditions.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Vessel-Based, Shallow Water Mapping with a Phase-Measuring Sidescan Sonar - Mark Borrelli; Theresa L. Smith; Stephen T. Mague (Estuaries and Coasts, 2022)

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Analog experiments in volcanology: towards multimethod, upscaled, and integrated models - Sam Poppe; Johan T. Gilchrist; Eric Christophe Pascal Breard; Alison Graettinger; Stephen Pansino (Bulletin of Volcanology, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

A review of the impacts of invasive wild pigs on native vertebrates - Matthew T. McDonough; Stephen S. Ditchkoff; Mark D. Smith; Kurt C. Vercauteren (Mammalian Biology, 2022)

Correction to: Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)

Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)
The rs2802292, rs2764264 and rs13217795 variants of FOXO3 have been associated with extreme longevity in multiple human populations, but the mechanisms underpinning this remain unclear. We aimed to characterise potential effects of longevity-associated variation on the expression and mRNA processing of the FOXO3 gene. We performed a comprehensive assessment of FOXO3 isoform usage across a wide variety of human tissues and carried out a bioinformatic analysis of the potential for longevity-associated variants to disrupt regulatory regions involved in isoform choice. We then related the expression of full length and 5′ truncated FOXO3 isoforms to rs13217795 genotype in peripheral blood and skeletal muscle from individuals of different rs13217795 genotypes. FOXO3 isoforms displayed considerable tissue specificity. We determined that rs13231195 and its tightly aligned proxy variant rs9400239 may lie in regulatory regions involved in isoform choice. The longevity allele at rs13217795 was associated with increased levels of full length FOXO3 isoforms in peripheral blood and a decrease in truncated FOXO3 isoforms in skeletal muscle RNA. We suggest that the longevity effect of FOXO3 SNPs may in part derive from a shift in isoform usage in skeletal muscle away from the production of 5′ truncated FOXO3 isoforms lacking a complete forkhead DNA binding domain, which may have compromised functionality.

Strategic foraging: Understanding hawksbill ( Eretmochelys imbricata ) prey item energy values and distribution within a marine protected area - Dustin S. Baumbach; Renwu Zhang; Christian T. Hayes; Marsha K. Wright; Stephen G. Dunbar (Marine Ecology, 2022)
Anthropogenic disturbances affect the health of coral reefs worldwide and may also impact hawksbill ( Eretmochelys imbricata ) foraging areas, potentially decreasing sponge numbers, while increasing macroalgae. Few studies have been conducted to understand energy content of hawksbill prey. We investigated observed ( Geodia neptuni and Kallymenia limminghii ) and potential ( Xestospongia muta and Halimeda opuntia ) hawksbill prey abundances and their energy contents in the Sandy Bay West End Marine Reserve, and related prey distribution to hawksbill distribution within the reserve. We analysed prey abundances by conducting in‐water habitat transects followed by point count analyses. In‐water hawksbill observations were recorded to provide total times turtles foraged on prey. We then measured energy content of prey types using microbomb calorimetry. Habitat assessments indicated sponges were most abundant in West Bay and West End, whereas macroalgae were most abundant in West End. Foraging observations indicated juvenile hawksbills spent more time foraging on G. neptuni (x̅ = 236.5 s) than K. limminghii (x̅ = 98.0 s) and no time foraging on either X. muta or H. opuntia . Energy content was higher for G. neptuni (4.09 kJ g −1 ) and K. limminghii (12.88 kJ g −1 ) than X. muta (2.48 kJ g −1 ) and H. opuntia (1.27 kJ g −1 ). Hawksbills were frequently observed feeding in West Bay where sponges were abundant and were also observed foraging on K. limminghii throughout this area. Fewer hawksbills were observed in West End and Sandy Bay than in West Bay, and these areas had fewer sponges compared with West Bay. Hawksbills benefit from foraging on the abundant observed sponge and macroalgae within their home ranges, allowing them to conserve energy and increase potential net energy gains from high energy prey.

Plant-derived lignans as potential antiviral agents: a systematic review - Xin-Ya Xu; Dong-Ying Wang; Yi-Ping Li; Stephen T. Deyrup; Hong-Jie Zhang (Phytochemistry Reviews, 2022)

Climate policy conflict in the U.S. states: a critical review and way forward - Joshua A. Basseches; Rebecca Bromley-Trujillo; Maxwell T. Boykoff; Trevor Culhane; Galen Hall; Noel Healy; David J. Hess; David Hsu; Rachel M. Krause; Harland Prechel; J. Timmons Roberts; Jennie C. Stephens (Climatic Change, 2022)
Many U.S. states have taken significant action on climate change in recent years, demonstrating their commitment despite federal policy gridlock and rollbacks. Yet, there is still much we do not know about the agents, discourses, and strategies of those seeking to delay or obstruct state-level climate action. We first ask, what are the obstacles to strong and effective climate policy within U.S. states? We review the political structures and interest groups that slow action, and we examine emerging tensions between climate justice and the technocratic and/or market-oriented approaches traditionally taken by many mainstream environmental groups. Second, what are potential solutions for overcoming these obstacles? We suggest strategies for overcoming opposition to climate action that may advance more effective and inclusive state policy, focusing on political strategies, media framing, collaboration, and leveraging the efforts of ambitious local governments.

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Essential outcomes for COP26 - Pete Smith; Linda Beaumont; Carl J. Bernacchi; Maria Byrne; William Cheung; Richard T. Conant; Francesca Cotrufo; Xiaojuan Feng; Ivan Janssens; Hefin Jones; Miko U. F. Kirschbaum; Kazuhiko Kobayashi; et al. (Global Change Biology, 2022)

Towards a global list of accepted species V. The devil is in the detail - Richard L. Pyle; Saroj K. Barik; Les Christidis; Stijn Conix; Mark John Costello; Peter Paul van Dijk; Stephen T. Garnett; Donald Hobern; Paul M. Kirk; Aaron M. Lien; Thomas M. Orrell; David Remsen; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species II. Consequences of inadequate taxonomic list governance - Scott A. Thomson; Kevin Thiele; Stijn Conix; Les Christidis; Mark John Costello; Donald Hobern; Svetlana Nikolaeva; Richard L. Pyle; Peter Paul van Dijk; Haylee Weaver; Frank E. Zachos; Zhi-Qiang Zhang; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species IV: Overcoming fragmentation in the governance of taxonomic lists - Aaron M. Lien; Stijn Conix; Frank E. Zachos; Les Christidis; Peter Paul van Dijk; Olaf S. Bánki; Saroj K. Barik; John S. Buckeridge; Mark John Costello; Donald Hobern; Narelle Montgomery; Svetlana Nikolaeva; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species III. Independence and stakeholder inclusion - Stijn Conix; Stephen T. Garnett; Kevin R. Thiele; Les Christidis; Peter Paul van Dijk; Olaf S. Bánki; Saroj K. Barik; John S. Buckeridge; Mark J. Costello; Donald Hobern; Paul M. Kirk; Aaron Lien; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species I. Why taxonomists sometimes disagree, and why this matters - Kevin R. Thiele; Stijn Conix; Richard L. Pyle; Saroj K. Barik; Les Christidis; Mark John Costello; Peter Paul van Dijk; Paul Kirk; Aaron Lien; Scott A. Thomson; Frank E. Zachos; Zhi-Qiang Zhang; et al. (Organisms Diversity & Evolution, 2021)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Natural Intertidal Oyster Reef Growth Across Two Landscape Settings and Tidal Ranges - Molly C. Bost; Antonio B. Rodriguez; Justin T. Ridge; Carson B. Miller; Stephen R. Fegley (Estuaries and Coasts, 2021)

Stream Water Chemistry in Mixed-Conifer Headwater Basins: Role of Water Sources, Seasonality, Watershed Characteristics, and Disturbances - Yang Yang; Stephen C. Hart; Emma P. McCorkle; Erin M. Stacy; Morgan E. Barnes; Carolyn T. Hunsaker; Dale W. Johnson; Asmeret Asefaw Berhe (Ecosystems, 2021)

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

A new secoiridoid glycoside and other constituents from the roots and flowers of Fagraea fragrans Roxb. (Gentianaceae) - Watchara Sangsopha; Ratsami Lekphrom; Florian T. Schevenels; Brendan Byatt; Stephen G. Pyne; Nattakarn Sridadom; Kanlayanee Sawanyawisuth (Natural Product Research, 2021)

Heavy metals concentrations and naturally occurring radionuclides in soils affected by and around a solid waste dumpsite in Osogbo metropolis, Nigeria - Olubusayo F. Oladejo; Lasun T. Ogundele; Samuel O. Inuyomi; Stephen F. Olukotun; Mutiu A. Fakunle; Olusegun O. Alabi (Environmental Monitoring and Assessment, 2021)

Altered structure of bat–prey interaction networks in logged tropical forests revealed by metabarcoding - David R. Hemprich‐Bennett; Victoria A. Kemp; Joshua Blackman; Matthew J. Struebig; Owen T. Lewis; Stephen J. Rossiter; Elizabeth L. Clare (Molecular Ecology, 2021)
Habitat degradation is pervasive across the tropics and is particularly acute in Southeast Asia, with major implications for biodiversity. Much research has addressed the impact of degradation on species diversity; however, little is known about how ecological interactions are altered, including those that constitute important ecosystem functions such as consumption of herbivores. To examine how rainforest degradation alters trophic interaction networks, we applied DNA metabarcoding to construct interaction networks linking forest‐dwelling insectivorous bat species and their prey, comparing old‐growth forest and forest degraded by logging in Sabah, Borneo. Individual bats in logged rainforest consumed a lower richness of prey than those in old‐growth forest. As a result, interaction networks in logged forests had a less nested structure. These network structures were associated with reduced network redundancy and thus increased vulnerability to perturbations in logged forests. Our results show how ecological interactions change between old‐growth and logged forests, with potentially negative implications for ecosystem function and network stability.

The use of an unoccupied aerial vehicle to survey shark species over sand and rocky‐reef habitats in a marine protected area - Kathryn A. Ayres; James T. Ketchum; Rogelio González‐Armas; Felipe Galván‐Magaña; Alex Hearn; Fernando R. Elorriaga‐Verplancken; Edgar M. Hoyos‐Padilla; Stephen M. Kajiura (Journal of Fish Biology, 2021)
Cabo Pulmo National Park was established in 1995 and has since seen a large increase in fish biomass. An unoccupied aerial vehicle (UAV) was used to survey shallow coastal habitat in which lemon sharks ( Negaprion brevirostris ), bull sharks ( Carcharhinus leucas ) and Pacific nurse sharks ( Ginglymostoma unami ) were recorded. Sharks were more common in the afternoon, potentially using warmer shallow areas to behaviourally thermoregulate. This study highlights UAV surveying to be a viable tool for species identification, a limitation of previous terrestrial surveys conducted in the area.

Direct and size‐mediated effects of temperature and ration‐dependent growth rates on energy reserves in juvenile anadromous alewives ( Alosa pseudoharengus ) - Lian W. Guo; Stephen D. McCormick; Eric T. Schultz; Adrian Jordaan (Journal of Fish Biology, 2021)
Growth rate and energy reserves are important determinants of fitness and are governed by endogenous and exogenous factors. Thus, examining the influence of individual and multiple stressors on growth and energy reserves can help estimate population health under current and future conditions. In young anadromous fishes, freshwater habitat quality determines physiological state and fitness of juveniles emigrating to marine habitats. In this study, the authors tested how temperature and food availability affect survival, growth and energy reserves in juvenile anadromous alewives ( Alosa pseudoharengus ), a forage fish distributed along the eastern North American continent. Field‐collected juvenile anadromous A. pseudoharengus were exposed for 21 days to one of two temperatures (21°C and 25°C) and one of two levels of food rations (1% or 2% tank biomass daily) and compared for differences in final size, fat mass‐at‐length, lean mass‐at‐length and energy density. Increased temperature and reduced ration both led to lower growth rates, and the effect of reduced ration was greater at higher temperature. Fat mass‐at‐length decreased with dry mass, and energy density increased with total length, suggesting size‐based endogenous influences on energy reserves. Lower ration also directly decreased fat mass‐at‐length, lean mass‐at‐length and energy density. Given the fitness implications of size and energy reserves, temperature and food availability should be considered important indicators of nursery habitat quality and incorporated in A. pseudoharengus life‐history models to improve forecasting of population health under climate change.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Australian stingless bees detect odours left at food sources by nestmates, conspecifics and honey bees - R. Gloag; J. P. Smith; R. E. Stephens; T. A. Heard; M. Beekman (Insectes Sociaux, 2021)

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Occurrence of environmental contaminants (pesticides, herbicides, PAHs) in Australian/Queensland Apis mellifera honey - Natasha L. Hungerford; Mary T. Fletcher; Heng Hang Tsai; Darina Hnatko; Lorinda J. Swann; Cassandra L. Kelly; Shalona R. Anuj; Ujang Tinggi; Dennis C. Webber; Stephen T. Were; Benjamin L. L. Tan (Food Additives & Contaminants Part B-Surveillance, 2021)

A Co-Crystallised Cobalt(II) Cluster of Pyridinedicarboxylic Acid (PDC) as a Luminescent Material for Selective Sensing of Methanol - Victoria T. Olayemi; Adedibu C. Tella; Folahan A. Adekola; Hadley S. Clayton; Adetola C. Oladipo; Gift Mehlana; Adeniyi S. Ogunlaja; Oluwatobi S. Oluwafemi; Joseph O. Ogar; Stephen P. Argent; Robert Mokaya (Journal of Fluorescence, 2021)

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

Leech blood‐meal invertebrate‐derived DNA reveals differences in Bornean mammal diversity across habitats - Rosie Drinkwater; Tommaso Jucker; Joshua H. T. Potter; Tom Swinfield; David A. Coomes; Eleanor M. Slade; M. Thomas P. Gilbert; Owen T. Lewis; Henry Bernard; Matthew J. Struebig; Elizabeth L. Clare; Stephen J. Rossiter (Molecular Ecology, 2021)
The application of metabarcoding to environmental and invertebrate‐derived DNA (eDNA and iDNA) is a new and increasingly applied method for monitoring biodiversity across a diverse range of habitats. This approach is particularly promising for sampling in the biodiverse humid tropics, where rapid land‐use change for agriculture means there is a growing need to understand the conservation value of the remaining mosaic and degraded landscapes. Here we use iDNA from blood‐feeding leeches ( Haemadipsa picta ) to assess differences in mammalian diversity across a gradient of forest degradation in Sabah, Malaysian Borneo. We screened 557 individual leeches for mammal DNA by targeting fragments of the 16S rRNA gene and detected 14 mammalian genera. We recorded lower mammal diversity in the most heavily degraded forest compared to higher quality twice logged forest. Although the accumulation curves of diversity estimates were comparable across these habitat types, diversity was higher in twice logged forest, with more taxa of conservation concern. In addition, our analysis revealed differences between the community recorded in the heavily logged forest and that of the twice logged forest. By revealing differences in mammal diversity across a human‐modified tropical landscape, our study demonstrates the value of iDNA as a noninvasive biomonitoring approach in conservation assessments.

Timing and pace of ice‐sheet withdrawal across the marine–terrestrial transition west of Ireland during the last glaciation - Colm Ó Cofaigh; S. Louise Callard; David H. Roberts; Richard C. Chiverrell; C. K. Ballantyne; David J. A. Evans; Margot Saher; Katrien J. J. Van Landeghem; Rachel Smedley; Sara Benetti; Matthew Burke; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
Understanding the pace and drivers of marine‐based ice‐sheet retreat relies upon the integration of numerical ice‐sheet models with observations from contemporary polar ice sheets and well‐constrained palaeo‐glaciological reconstructions. This paper provides a reconstruction of the retreat of the last British–Irish Ice Sheet (BIIS) from the Atlantic shelf west of Ireland during and following the Last Glacial Maximum (LGM). It uses marine‐geophysical data and sediment cores dated by radiocarbon, combined with terrestrial cosmogenic nuclide and optically stimulated luminescence dating of onshore ice‐marginal landforms, to reconstruct the timing and rate of ice‐sheet retreat from the continental shelf and across the adjoining coastline of Ireland, thus including the switch from a marine‐ to a terrestrially‐based ice‐sheet margin. Seafloor bathymetric data in the form of moraines and grounding‐zone wedges on the continental shelf record an extensive ice sheet west of Ireland during the LGM which advanced to the outer shelf. This interpretation is supported by the presence of dated subglacial tills and overridden glacimarine sediments from across the Porcupine Bank, a westwards extension of the Irish continental shelf. The ice sheet was grounded on the outer shelf at ~26.8 ka cal bp with initial retreat underway by 25.9 ka cal bp. Retreat was not a continuous process but was punctuated by marginal oscillations until ~24.3 ka cal bp. The ice sheet thereafter retreated to the mid‐shelf where it formed a large grounding‐zone complex at ~23.7 ka cal bp. This retreat occurred in a glacimarine environment. The Aran Islands on the inner continental shelf were ice‐free by ~19.5 ka bp and the ice sheet had become largely terrestrially based by 17.3 ka bp. This suggests that the Aran Islands acted to stabilize and slow overall ice‐sheet retreat once the BIIS margin had reached the inner shelf. Our results constrain the timing of initial retreat of the BIIS from the outer shelf west of Ireland to the period of minimum global eustatic sea level. Initial retreat was driven, at least in part, by glacio‐isostatically induced, high relative sea level. Net rates of ice‐sheet retreat across the shelf were slow (62–19 m a −1 ) and reduced (8 m a −1 ) as the ice sheet vacated the inner shelf and moved onshore. A picture therefore emerges of an extensive BIIS on the Atlantic shelf west of Ireland, in which early, oscillatory retreat was followed by slow episodic retreat which decelerated further as the ice margin became terrestrially based. More broadly, this demonstrates the importance of localized controls, in particular bed topography, on modulating the retreat of marine‐based sectors of ice sheets.

The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation - Richard Christopher Chiverrell; Geoff Stephen Powell Thomas; Matthew Burke; Alicia Medialdea; Rachel Smedley; Mark Bateman; Chris Clark; Geoffrey A. T. Duller; Derek Fabel; Geraint Jenkins; Xianjiao Ou; Helen Marie Roberts; et al. (Journal of Quaternary Science, 2021)
Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.

Controls on Nutrient Cycling in Estuarine Mangrove Lake Sediments - Michael S. Owens; Stephen P. Kelly; Thomas A. Frankovich; David T. Rudnick; James W. Fourqurean; Jeffrey C. Cornwell (Journal of Marine Science and Engineering, 2021)
We estimated the net exchange of nitrogen and phosphorus species using core incubations under light and dark conditions in estuarine lakes that are the aquatic interface between the freshwater Everglades and marine Florida Bay. These lakes and adjacent shallow water Florida Bay environments are sites where the restoration of hydrological flows will likely have the largest impact on salinity. Sediment respiration, measured by oxygen uptake, averaged (±S.D.) −2400 ± 1300, −300 ± 1000, and 1900 ± 1400 μmol m−2 h−1 for dark incubations, light incubations, and gross photosynthesis estimates, respectively, with dark incubations consistent with oxygen uptake measured by microelectrode profiles. Although most fluxes of soluble reactive phosphorus, nitrate, and N2–N were low under both light and dark incubation conditions, we observed a number of very high efflux events of NH4+ during dark incubations. A significant decrease in NH4+flux was observed in the light. The largest differences between light and dark effluxes of NH4+ occurred in lakes during periods of low coverage of the aquatic macrophyte Chara hornemannii Wallman, with NH4+ effluxes > 200 μmol m−2 h−1. Increasing freshwater flow from the Everglades is expected to expand lower salinity environments suitable for Chara, and therefore, diminish the sediment NH4+ effluxes that may fuel algal blooms.

Endophyte-produced antimicrobials: a review of potential lead compounds with a focus on quorum-sensing disruptors - Hwang-Soo Joo; Stephen T. Deyrup; Sang Hee Shim (Phytochemistry Reviews, 2021)

A practical guide to selecting models for exploration, inference, and prediction in ecology - Andrew T. Tredennick; Giles Hooker; Stephen P. Ellner; Peter B. Adler (Ecology, 2021)
Selecting among competing statistical models is a core challenge in science. However, the many possible approaches and techniques for model selection, and the conflicting recommendations for their use, can be confusing. We contend that much confusion surrounding statistical model selection results from failing to first clearly specify the purpose of the analysis. We argue that there are three distinct goals for statistical modeling in ecology: data exploration, inference, and prediction. Once the modeling goal is clearly articulated, an appropriate model selection procedure is easier to identify. We review model selection approaches and highlight their strengths and weaknesses relative to each of the three modeling goals. We then present examples of modeling for exploration, inference, and prediction using a time series of butterfly population counts. These show how a model selection approach flows naturally from the modeling goal, leading to different models selected for different purposes, even with exactly the same data set. This review illustrates best practices for ecologists and should serve as a reminder that statistical recipes cannot substitute for critical thinking or for the use of independent data to test hypotheses and validate predictions.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

The importance of Indigenous Peoples’ lands for the conservation of terrestrial mammals - Christopher J. O'Bryan; Stephen T. Garnett; Julia E. Fa; Ian Leiper; Jose A. Rehbein; Álvaro Fernández‐Llamazares; Micha V. Jackson; Harry D. Jonas; Eduardo S. Brondizio; Neil D. Burgess; Catherine J. Robinson; Kerstin K. Zander; et al. (Conservation Biology, 2021)
Indigenous Peoples’ lands cover over one‐quarter of Earth's surface, a significant proportion of which is still free from industrial‐level human impacts. As a result, Indigenous Peoples and their lands are crucial for the long‐term persistence of Earth's biodiversity and ecosystem services. Yet, information on species composition on these lands globally remains largely unknown. We conducted the first comprehensive analysis of terrestrial mammal composition across mapped Indigenous lands based on data on area of habitat (AOH) for 4460 mammal species assessed by the International Union for Conservation of Nature. We overlaid each species’ AOH on a current map of Indigenous lands and found that 2695 species (60% of assessed mammals) had ≥10% of their ranges on Indigenous Peoples’ lands and 1009 species (23%) had >50% of their ranges on these lands. For threatened species, 473 (47%) occurred on Indigenous lands with 26% having >50% of their habitat on these lands. We also found that 935 mammal species (131 categorized as threatened) had ≥ 10% of their range on Indigenous Peoples’ lands that had low human pressure. Our results show how important Indigenous Peoples’ lands are to the successful implementation of conservation and sustainable development agendas worldwide.

Impacts of Pervasive Climate Change and Extreme Events on Rocky Intertidal Communities: Evidence From Long-Term Data - Nova Mieszkowska; Michael T. Burrows; Stephen J. Hawkins; Heather Sugden (Frontiers in Marine Science, 2021)
Annual surveys of the abundance of intertidal invertebrates and macroalgae have been made at between 70 and 100 rocky intertidal time-series sites around the United Kingdom coastline since 2002 under the MarClim project. The data provide a unique opportunity to investigate the impacts of both pervasive climate change and their punctuation by extreme events on intertidal species. After the extreme storm events in the 2013/2014 winter season and the record heatwaves in the summers of 2018 and 2020, MarClim surveys recorded both physical and biological changes to rocky shore habitats. Subsequent surveys reassessed the effects on community structure via analysis of those species that resisted storm damage, those species that returned after the extreme storm events, and species that opportunistically occupied vacant habitat after storm-induced species loss. In addition, biannual storm damage surveys documenting communities recovery were carried out in the spring and winter of each year from 2014 to 2020 at three MarClim sites in north Cornwall (Crackington Haven, Trevone, and St. Ives), which experienced different types of abiotic and biotic damage resulting from these storms. Impacts of heatwaves and cold spells on the abundance of species were determined by regression on frequencies of event per year. Species of invertebrates and macroalgae generally declined in years of more frequent winter cold spells and summer heatwaves, while winter heatwaves and summer cold spells had similar numbers of positive and negative effects across species. Winter warm spells tended to have a more negative effect on cold-affinity species than on warm-affinity species. No abrupt shift was recorded after the 2013/2014 storms. Whilst a short-term change in some species was recorded in quantitative quadrat surveys, the biological communities returned to the long-term species composition and abundance within 2 years. The heatwave events caused sublethal heat damage in macroalgae, evidenced as dried areas of tissue on many individuals, with mortality-induced reductions in the abundance of only a few invertebrate species, recorded in Scotland and southwest England after the heatwave events in 2018 and 2020. MarClim and storm-damage surveys indicate that there have been no sustained impacts from either extreme thermal or storm events across the rocky intertidal communities, and biodiversity has not been significantly altered as a result. The abundance and biogeographical distributions of rocky intertidal species and communities around the United Kingdom are being driven by longer-term, large scale, pervasive change in environmental conditions, with a gradual shift towards dominance of Lusitanian species from the early 2000s in responses to warming of the marine climate.

Independent and combined impact of hypoxia and acute inorganic nitrate ingestion on thermoregulatory responses to the cold - Josh T. Arnold; Stephen J. Bailey; Simon G. Hodder; Naoto Fujii; Alex B. Lloyd (European Journal of Applied Physiology, 2021)
Purpose This study assessed the impact of normobaric hypoxia and acute nitrate ingestion on shivering thermogenesis, cutaneous vascular control, and thermometrics in response to cold stress. Method Eleven male volunteers underwent passive cooling at 10 °C air temperature across four conditions: (1) normoxia with placebo ingestion, (2) hypoxia (0.130 F i O 2 ) with placebo ingestion, (3) normoxia with 13 mmol nitrate ingestion, and (4) hypoxia with nitrate ingestion. Physiological metrics were assessed as a rate of change over 45 min to determine heat loss, and at the point of shivering onset to determine the thermogenic thermoeffector threshold. Result Independently, hypoxia expedited shivering onset time ( p = 0.05) due to a faster cooling rate as opposed to a change in central thermoeffector thresholds. Specifically, compared to normoxia, hypoxia increased skin blood flow ( p = 0.02), leading to an increased core-cooling rate ( p = 0.04) and delta change in rectal temperature ( p = 0.03) over 45 min, yet the same rectal temperature at shivering onset ( p = 0.9). Independently, nitrate ingestion delayed shivering onset time ( p = 0.01), mediated by a change in central thermoeffector thresholds, independent of changes in peripheral heat exchange. Specifically, compared to placebo ingestion, no difference was observed in skin blood flow ( p = 0.5), core-cooling rate ( p = 0.5), or delta change in rectal temperature ( p = 0.7) over 45 min, while nitrate reduced rectal temperature at shivering onset ( p = 0.04). No interaction was observed between hypoxia and nitrate ingestion. Conclusion These data improve our understanding of how hypoxia and nitric oxide modulate cold thermoregulation.

Increasing maximum lake surface temperature under climate change - Martin T. Dokulil; Elvira de Eyto; Stephen C. Maberly; Linda May; Gesa A. Weyhenmeyer; R. Iestyn Woolway (Climatic Change, 2021)
Annual maximum lake surface temperature influences ecosystem structure and function and, in particular, the rates of metabolic activities, species survival and biogeography. Here, we evaluated 50 years of observational data, from 1966 to 2015, for ten European lakes to quantify changes in the annual maximum surface temperature and the duration above a potentially critical temperature of 20 °C. Our results show that annual maximum lake surface temperature has increased at an average rate of +0.58 °C decade −1 (95% confidence interval 0.18), which is similar to the observed increase in annual maximum air temperature of +0.42 °C decade −1 (95% confidence interval 0.28) over the same period. Increments in lake maximum temperature among the ten lakes range from +0.1 in the west to +1.9 °C decade −1 in the east. Absolute maximum lake surface water temperatures were reached in Wörthersee, 27.5 °C, and Neusiedler See, 31.7 °C. Periods exceeding a critical temperature of 20 °C each year became two to six times longer than the respective average (6 to 93). The depth at which water temperature exceeded 20 °C increased from less than 1 to more than 6 m in Mondsee, Austria, over the 50 years studied. As a consequence, the habitable environment became increasingly restricted for many organisms that are adapted to historic conditions.

The role of intraperitoneal chemotherapy in the surgical management of pancreatic ductal adenocarcinoma: a systematic review - Alexandre Brind’Amour; Mitchell Webb; Marina Parapini; Lucas Sidéris; Maja Segedi; Stephen W. Chung; Stéphanie Chartier-Plante; Pierre Dubé; Charles H. Scudamore; Peter T. W. Kim (Clinical & Experimental Metastasis, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

New microsatellite markers for Ellipse, Venustaconcha ellipsiformis (Bivalvia: Unionidae), with notes on optimal sample size and cross-species amplification - Kentaro Inoue; Bernard E. Sietman; Stephen E. McMurray; J. Scott Faiman; David T. Zanatta (Molecular Biology Reports, 2021)

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity - Christine R. Rollinson; Andria Dawson; Ann M. Raiho; John W. Williams; Michael C. Dietze; Thomas Hickler; Stephen T. Jackson; Jason McLachlan; David JP Moore; Benjamin Poulter; Tristan Quaife; Jörg Steinkamp; et al. (Ecology Letters, 2021)
Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem responses to hydroclimate variability are strongly governed by ecosystem sensitivity rather than climate exposure. Ecosystem sensitivity was higher in models than observations and highest in simpler models. Model‐data comparisons suggest that interactions among biodiversity, demography and ecophysiology processes dampen the sensitivity of forest composition and biomass to climate variability and change. Integrating ecosystem models with observations from timescales extending beyond the instrumental record can better understand and forecast the mechanisms regulating forest sensitivity to climate variability in a complex and changing world.

The impact of three weeks of pre-quit varenicline on reinforcing value and craving for cigarettes in a laboratory choice procedure - Schuyler C. Lawson; Julie C. Gass; Robert K. Cooper; Sarah S. Tonkin; Craig R. Colder; Martin C. Mahoney; Stephen T. Tiffany; Larry W. Hawk (Psychopharmacology, 2021)

Predictors of invertebrate biomass and rate of advancement of invertebrate phenology across eight sites in the North American Arctic - Rebecca Shaftel; Daniel J. Rinella; Eunbi Kwon; Stephen C. Brown; H. River Gates; Steve Kendall; David B. Lank; Joseph R. Liebezeit; David C. Payer; Jennie Rausch; Sarah T. Saalfeld; Brett K. Sandercock; et al. (Polar Biology, 2021)
Average annual temperatures in the Arctic increased by 2–3 °C during the second half of the twentieth century. Because shorebirds initiate northward migration to Arctic nesting sites based on cues at distant wintering grounds, climate-driven changes in the phenology of Arctic invertebrates may lead to a mismatch between the nutritional demands of shorebirds and the invertebrate prey essential for egg formation and subsequent chick survival. To explore the environmental drivers affecting invertebrate availability, we modeled the biomass of invertebrates captured in modified Malaise-pitfall traps over three summers at eight Arctic Shorebird Demographics Network sites as a function of accumulated degree-days and other weather variables. To assess climate-driven changes in invertebrate phenology, we used data from the nearest long-term weather stations to hindcast invertebrate availability over 63 summers, 1950–2012. Our results confirmed the importance of both accumulated and daily temperatures as predictors of invertebrate availability while also showing that wind speed negatively affected invertebrate availability at the majority of sites. Additionally, our results suggest that seasonal prey availability for Arctic shorebirds is occurring earlier and that the potential for trophic mismatch is greatest at the northernmost sites, where hindcast invertebrate phenology advanced by approximately 1–2.5 days per decade. Phenological mismatch could have long-term population-level effects on shorebird species that are unable to adjust their breeding schedules to the increasingly earlier invertebrate phenologies.

Persistent COVID-19-associated neurocognitive symptoms in non-hospitalized patients - Joanna Hellmuth; T. Allen Barnett; Breton M. Asken; J. Daniel Kelly; Leonel Torres; Melanie L. Stephens; Bryan Greenhouse; Jeffrey N. Martin; Felicia C. Chow; Steven G. Deeks; Meredith Greene; Bruce L. Miller; et al. (Journal of NeuroVirology, 2021)
As cases of coronavirus disease 2019 (COVID-19) mount worldwide, attention is needed on potential long-term neurologic impacts for the majority of patients who experience mild to moderate illness managed as outpatients. To date, there has not been discussion of persistent neurocognitive deficits in patients with milder COVID-19. We present two cases of non-hospitalized patients recovering from COVID-19 with persistent neurocognitive symptoms. Commonly used cognitive screens were normal, while more detailed testing revealed working memory and executive functioning deficits. An observational cohort study of individuals recovering from COVID-19 (14 or more days following symptom onset) identified that among the first 100 individuals enrolled, 14 were non-hospitalized patients reporting persistent cognitive issues. These 14 participants had a median age of 39 years (interquartile range: 35–56), and cognitive symptoms were present for at least a median of 98 days (interquartile range: 71–120 following acute COVID-19 symptoms); no participants with follow-up evaluation reported symptom resolution. We discuss potential mechanisms to be explored in future studies, including direct viral effects, indirect consequences of immune activation, and immune dysregulation causing auto-antibody production.

A Synthesis of the Biology and Ecology of Sculpin Species in the Laurentian Great Lakes and Implications for the Adaptive Capacity of the Benthic Ecosystem - Kelly F. Robinson; Charles R. Bronte; David B. Bunnell; Peter T. Euclide; Darryl W. Hondorp; John A. Janssen; Matthew S. Kornis; Derek H. Ogle; Will Otte; Stephen C. Riley; Mark R. Vinson; Shea L. Volkel; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Hemolymph Proteomics and Gut Microbiota of Horseshoe Crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda - Zhe Qu; Thomas C. N. Leung; Wenyan Nong; Ho Yin Yip; Ivy H. T. Lee; Siu Gin Cheung; Ngai Sai Ming; Wai Lok So; William G. Bendena; Stephen S. Tobe; Jerome H. L. Hui (Frontiers in Marine Science, 2020)
Horseshoe crabs are a group of marine chelicerates that contain only four extant species, some of which are endangered. Their hemolymph has been widely used in medical applications for endotoxin detection. Nevertheless, there is limited information on the profiles of their hemolymph proteins and their gut microbial diversity. In this study, we performed the first detailed investigation of the hemolymph proteomics and gut microbiota of two Asian horseshoe crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda . Among the identified proteins being cataloged in the juvenile and adult hemolymph, unexpectedly, sesquiterpenoid signaling pathway proteins including Heat shock protein 83 (HSP83), Chd64, and a juvenile hormone binding protein (JHBP) were revealed. This provides evidence for the presence of functional sesquiterpenoid hormonal systems in these marine chelicerates. consumption of certain horseshoe crab species often leads to tetrodotoxin poisoning and the horseshoe crab is thought to possess a tetrodotoxin resistance mechanism. As such, sodium channels were analyzed and found to have critical amino acid residues that are similar to the toxin resistant pufferfish sodium channels. The source of the toxin is unknown so we investigated the gut microbiota, and found that Clostridium and Vibrio were the most dominant bacteria in T. tridentatus and C. rotundicauda , respectively. Together, this study provides a framework for further understanding of sesquiterpenoids and gut microbiota of these marine chelicerates.

Development of a method for treating lower-eyelid carcinomas using superficial high dose rate brachytherapy - H. Stephens; C. Deans; D. Schlect; T. Kairn (Physical and Engineering Sciences in Medicine, 2020)

The clinical and genetic features of hereditary haemorrhagic telangiectasia (HHT) in central South Africa—three novel pathogenic variants - Tendaishe T. Mutize; Riaz Y. Seedat; Johannes K. Ploos van Amstel; Johannes J. Mager; Stephen C. Brown; Fekade Gebremariam; Marius J. Coetzee (Molecular Biology Reports, 2020)

Shallow groundwater flow and inverted fresh/saline-water interface in a hypersaline endorheic basin (Great Basin, USA) - Alan L. Mayo; David G. Tingey; Kevin A. Rey; Tony D. Winkel; John H. McBride; Stephen T. Nelson; Gregory T. Carling; Jiri Bruthans; Erik C. Petersen (Hydrogeology Journal, 2020)
Pilot Valley is an 828-km 2 arid-region endorheic basin in western USA. Bounding mountain ranges rise as much as 1,900 m above the nearly flat 379-km 2 playa floor. Up to 3.8 m of Pleistocene Lake Bonneville mud and thin oolitic sand layers form the surface layer of the basin floor. Groundwater conditions were evaluated using data from shallow monitoring wells and borings, springs, infiltrometer measurements, slug and dilution tests, geophysical transects, and precision elevation surveys. Alluvial fan groundwater discharges at fan/playa interface springs and underflows to the shallow basin sediments along the western side of the basin; the groundwater only underflows along the eastern side. Precision surveying established a Lake Bonneville shore-line break in slope as the cause of the spring discharges. Tectonic tilting causes groundwater to flow from east to west and to the topographic low. Monthly measured and pressure transducer data established seasonal pressure responses and upward groundwater gradients. All basin groundwater is lost to evapotranspiration at the topographic low, where a thin salt pan has developed. Groundwater evolves from fresh to hypersaline near the alluvial fan/playa interface where there is an inverted salinity gradient and a groundwater pressure ridge. The pressure ridge and inverted salinity interface are due to: (1) osmotic pressure established between the oolitic sand of high hydraulic conductivity and the overlying low-hydraulic-conductivity lake mud at the fan/playa interface, and (2) the collision between fresh groundwater flow driven by a steep hydraulic head and hypersaline groundwater flow driven by a nearly flat hydraulic head.

Forest Vegetation Change and Its Impacts on Soil Water Following 47 Years of Managed Wildfire - Jens T. Stevens; Gabrielle F. S. Boisramé; Ekaterina Rakhmatulina; Sally E. Thompson; Brandon M. Collins; Scott L. Stephens (Ecosystems, 2020)

Large-scale control on the frequency of tropical cyclones and seeds: a consistent relationship across a hierarchy of global atmospheric models - Tsung-Lin Hsieh; Gabriel A. Vecchi; Wenchang Yang; Isaac M. Held; Stephen T. Garner (Climate Dynamics, 2020)
A diagnostic framework is developed to explain the response of tropical cyclones (TCs) to climate in high-resolution global atmospheric models having different complexity of boundary conditions. The framework uses vortex dynamics to identify the large-scale control on the evolution of TC precursors—first non-rotating convective clusters and then weakly rotating seeds. In experiments with perturbed sea surface temperature (SST) and $$\hbox {CO}_2$$ CO 2 concentration from the historical values, the response of TCs follows the response of seeds. The distribution of seeds is explained by the distribution of the non-rotating convective clusters multiplied by a probability that they transition to seeds. The distribution of convective clusters is constrained by the large-scale vertical velocity and is verified in aquaplanet experiments with shifting Inter tropical Convergence Zones. The probability of transition to seeds is constrained by the large-scale vorticity via an analytical function, representing the relative importance between vortex stretching and vorticity advection, and is verified in aquaplanet experiments with uniform SST. The consistency between seed and TC responses breaks down substantially when the realistic SST is perturbed such that the spatial gradient is significantly enhanced or reduced. In such cases, the difference between the responses is explained by a change in the ventilation index, which influences the fraction of seeds that develop into TCs. The proposed TC-climate relationship serves as a framework to explain the diversity of TC projection across models and forcing scenarios.

Science and Risked-Based Stability Testing Strategies—a Test Case on the Global Implementation and Regulatory Reception - Dorys Argelia Diaz; Michael Lynch; Megan McMahon; Raquel Oblessuc; Stephen T. Colgan (The AAPS Journal, 2020)

Longitudinal associations between amygdala reactivity and cannabis use in a large sample of adolescents - Philip A. Spechler; Bader Chaarani; Catherine Orr; Matthew D. Albaugh; Nicholas R. Fontaine; Stephen T. Higgins; Tobias Banaschewski; Arun L. W. Bokde; Erin Burke Quinlan; Sylvane Desrivières; Herta Flor; Antoine Grigis; et al. (Psychopharmacology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Coastal carbon cycle changes following mangrove loss - James Z. Sippo; Christian J. Sanders; Isaac R. Santos; Luke C. Jeffrey; Mitchell Call; Yota Harada; Kylie Maguire; Dylan Brown; Stephen R. Conrad; Damien T. Maher (Limnology and Oceanography, 2020)
Global mangrove loss is occurring from deforestation and extreme climatic events, but changes to the coastal carbon cycle following mangrove mortality and/or loss are not well understood. In 2015/2016, a massive climate‐driven mangrove dieback event occurred over ~ 1000 km of Australian coastline. To assess carbon loss following mortality, carbon fluxes in adjacent living and dead forest areas were compared 8 and 20 months postforest dieback. Dead areas experienced an increase in soil CO 2 efflux by ~ 189%, and a decrease in oceanic dissolved inorganic carbon (DIC) outwelling of ~ 50% relative to living areas. DIC outwelling (predominantly carbonate alkalinity) and soil CO 2 efflux accounted for 81% and 16% of losses from the living forest, in comparison to 51% and 47%, respectively, from the dead forest. The dieback drove a shift from a dominance of oceanic carbon outwelling to increased atmospheric CO 2 emissions and decreased alkalinity exports. This shift was likely driven by increased oxygen sediment permeation and the loss of mangrove net primary productivity. Combining our new observations with literature data, we found a logarithmic relationship between soil carbon loss and time since mangrove loss. Using this relationship, we estimate ongoing global carbon losses from historical mangrove deforestation and dieback could be 13.7 ± 9.4 Tg C yr −1 , which is eightfold higher than previous estimates and offsets global mangrove carbon burial by ~ 60%. Even if no future deforestation occurred, we estimate ongoing carbon losses to the atmosphere and ocean from current global mangrove losses of 27 Tg C over the next 30 yr.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Knowledge Gaps and Management Priorities for Recreational Fisheries in the Developing World - Shannon D. Bower; Øystein Aas; Robert Arlinghaus; T. Douglas Beard; Ian G. Cowx; Andy J. Danylchuk; Kátia M. F. Freire; Warren M. Potts; Stephen G. Sutton; Steven J. Cooke (Reviews in Fisheries Science & Aquaculture, 2020)

Agricultural intensification is causing rapid habitat change in the Tonle Sap Floodplain, Cambodia - Simon P. Mahood; Colin M. Poole; James E. M. Watson; Richard A. MacKenzie; Sahadev Sharma; Stephen T. Garnett (Wetlands Ecology and Management, 2020)

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Generation lengths of the world's birds and their implications for extinction risk - Jeremy P. Bird; Robert Martin; H. Reşit Akçakaya; James Gilroy; Ian J. Burfield; Stephen T. Garnett; Andy Symes; Joseph Taylor; Çağan H. Şekercioğlu; Stuart H. M. Butchart (Conservation Biology, 2020)
Birds have been comprehensively assessed on the International Union for Conservation of Nature (IUCN) Red List more times than any other taxonomic group. However, to date, generation lengths have not been systematically estimated to scale population trends when undertaking assessments, as required by the criteria of the IUCN Red List. We compiled information from major databases of published life‐history and trait data for all birds and imputed missing life‐history data as a function of species traits with generalized linear mixed models. Generation lengths were derived for all species, based on our modeled values of age at first breeding, maximum longevity, and annual adult survival. The resulting generation lengths varied from 1.42 to 27.87 years (median 2.99). Most species (61%) had generation lengths

Catalyzing sustainable fisheries management through behavior change interventions - Gavin McDonald; Molly Wilson; Diogo Veríssimo; Rebecca Twohey; Michaela Clemence; Dean Apistar; Stephen Box; Paul Butler; Fel Cesar Cadiz; Stuart J. Campbell; Courtney Cox; Micah Effron; et al. (Conservation Biology, 2020)
Small‐scale fisheries are an important livelihood and primary protein source for coastal communities in many of the poorest regions in the world, yet many are overfished and thus require effective and scalable management solutions. Positive ecological and socioeconomic responses to management typically lag behind immediate costs borne by fishers from fishing pressure reductions necessary for fisheries recovery. These short‐term costs challenge the long‐term success of these interventions. However, social marketing may increase perceptions of management benefits before ecological and socioeconomic benefits are fully realized, driving new social norms and ultimately long‐term sustainable behavior change. By conducting underwater visual surveys to quantify ecological conditions and by conducting household surveys with community members to quantify their perceptions of management support and socioeconomic conditions, we assessed the impact of a standardized small‐scale fisheries management intervention that was implemented across 41 sites in Brazil, Indonesia, and the Philippines. The intervention combines TURF reserves (community‐based territorial use rights for fishing coupled with no‐take marine reserves) with locally tailored social‐marketing behavior change campaigns. Leveraging data across 22 indicators and 4 survey types, along with data from 3 control sites, we found that ecological and socioeconomic impacts varied and that communities supported the intervention and were already changing their fishing practices. These results suggest that communities were developing new social norms and fishing more sustainably before long‐term ecological and socioeconomic benefits of fisheries management materialized.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Evaluation of repeated or acute treatment with cannabidiol (CBD), cannabidiolic acid (CBDA) or CBDA methyl ester (HU-580) on nausea and/or vomiting in rats and shrews - Erin M. Rock; Megan T. Sullivan; Stephen A. Collins; Hannah Goodman; Cheryl L. Limebeer; Raphael Mechoulam; Linda A. Parker (Psychopharmacology, 2020)

Morphological Diversification under High Integration in a Hyper Diverse Mammal Clade - Brandon P. Hedrick; Gregory L. Mutumi; V. David Munteanu; Alexa Sadier; Kalina T. J. Davies; Stephen J. Rossiter; Karen E. Sears; Liliana M. Dávalos; Elizabeth Dumont (Journal of Mammalian Evolution, 2020)

β-guanidinopropionic acid and metformin differentially impact autophagy, mitochondria and cellular morphology in developing C2C12 muscle cells - Chelsea L. Crocker; Bradley L. Baumgarner; Stephen T. Kinsey (Journal of Muscle Research and Cell Motility, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Sampling, extraction and incidence of redberry mites (Acalitus essigi) on blackberries in Australia - Hui Meng Law; Geoff R. Allen; Jamie T. Davies; Ross Corkrey; Michele Buntain; Stephen R. Quarrell (Experimental and Applied Acarology, 2020)

Critical land change information enhances the understanding of carbon balance in the United States - Jinxun Liu; Benjamin M. Sleeter; Zhiliang Zhu; Thomas R. Loveland; Terry Sohl; Stephen M. Howard; Carl H. Key; Todd Hawbaker; Shuguang Liu; Bradley Reed; Mark A. Cochrane; Linda S. Heath; et al. (Global Change Biology, 2020)
Large‐scale terrestrial carbon (C) estimating studies using methods such as atmospheric inversion, biogeochemical modeling, and field inventories have produced different results. The goal of this study was to integrate fine‐scale processes including land use and land cover change into a large‐scale ecosystem framework. We analyzed the terrestrial C budget of the conterminous United States from 1971 to 2015 at 1‐km resolution using an enhanced dynamic global vegetation model and comprehensive land cover change data. Effects of atmospheric CO 2 fertilization, nitrogen deposition, climate, wildland fire, harvest, and land use/land cover change (LUCC) were considered. We estimate annual C losses from cropland harvest, forest clearcut and thinning, fire, and LUCC were 436.8, 117.9, 10.5, and 10.4 TgC/year, respectively. C stored in ecosystems increased from 119,494 to 127,157 TgC between 1971 and 2015, indicating a mean annual net C sink of 170.3 TgC/year. Although ecosystem net primary production increased by approximately 12.3 TgC/year, most of it was offset by increased C loss from harvest and natural disturbance and increased ecosystem respiration related to forest aging. As a result, the strength of the overall ecosystem C sink did not increase over time. Our modeled results indicate the conterminous US C sink was about 30% smaller than previous modeling studies, but converged more closely with inventory data.

Sleep Disordered Breathing in Hypertrophic Cardiomyopathy - Salma I. Patel; Fadi E. Shamoun; Heidi Esser; Sairam Parthasarathy; Michael J. Ackerman; Jeffrey B. Geske; Steve R. Ommen; William T. Love; Virend K. Somers; Anwar A. Chahal; Johan M. Bos; Stephen S. Cha; et al. (Sleep and Vigilance, 2020)

Foraging shifts and visual preadaptation in ecologically diverse bats - Kalina T. J. Davies; Laurel R. Yohe; Jesus Almonte; Miluska K. R. Sánchez; Edgardo M. Rengifo; Elizabeth R. Dumont; Karen E. Sears; Liliana M. Dávalos; Stephen J. Rossiter (Molecular Ecology, 2020)
Changes in behaviour may initiate shifts to new adaptive zones, with physical adaptations for novel environments evolving later. While new mutations are commonly considered engines of adaptive change, sensory evolution enabling access to new resources might also arise from standing genetic diversity, and even gene loss. We examine the relative contribution of molecular adaptations, measured by positive and relaxed selection, acting on eye‐expressed genes associated with shifts to new adaptive zones in ecologically diverse bats from the superfamily Noctilionoidea. Collectively, noctilionoids display remarkable ecological breadth, from highly divergent echolocation to flight strategies linked to specialized insectivory, the parallel evolution of diverse plant‐based diets (e.g., nectar, pollen and fruit) from ancestral insectivory, and—unusually for echolocating bats—often have large, well‐developed eyes. We report contrasting levels of positive selection in genes associated with the development, maintenance and scope of visual function, tracing back to the origins of noctilionoids and Phyllostomidae (the bat family with most dietary diversity), instead of during shifts to novel diets. Generalized plant visiting was not associated with exceptional molecular adaptation, and exploration of these novel niches took place in an ancestral phyllostomid genetic background. In contrast, evidence for positive selection in vision genes was found at subsequent shifts to either nectarivory or frugivory. Thus, neotropical noctilionoids that use visual cues for identifying food and roosts, as well as for orientation, were effectively preadapted, with subsequent molecular adaptations in nectar‐feeding lineages and the subfamily Stenodermatinae of fig‐eating bats fine‐tuning pre‐existing visual adaptations for specialized purposes.

Storm impacts on phytoplankton community dynamics in lakes - Jason D. Stockwell; Jonathan P. Doubek; Rita Adrian; Orlane Anneville; Cayelan C. Carey; Laurence Carvalho; Lisette N. De Senerpont Domis; Gaël Dur; Marieke A. Frassl; Hans‐Peter Grossart; Bas W. Ibelings; Marc J. Lajeunesse; et al. (Global Change Biology, 2020)
In many regions across the globe, extreme weather events such as storms have increased in frequency, intensity, and duration due to climate change. Ecological theory predicts that such extreme events should have large impacts on ecosystem structure and function. High winds and precipitation associated with storms can affect lakes via short‐term runoff events from watersheds and physical mixing of the water column. In addition, lakes connected to rivers and streams will also experience flushing due to high flow rates. Although we have a well‐developed understanding of how wind and precipitation events can alter lake physical processes and some aspects of biogeochemical cycling, our mechanistic understanding of the emergent responses of phytoplankton communities is poor. Here we provide a comprehensive synthesis that identifies how storms interact with lake and watershed attributes and their antecedent conditions to generate changes in lake physical and chemical environments. Such changes can restructure phytoplankton communities and their dynamics, as well as result in altered ecological function (e.g., carbon, nutrient and energy cycling) in the short‐ and long‐term. We summarize the current understanding of storm‐induced phytoplankton dynamics, identify knowledge gaps with a systematic review of the literature, and suggest future research directions across a gradient of lake types and environmental conditions.

Macroscale drivers of Atlantic and Gulf Menhaden growth - Stephen R. Midway; Amy M. Schueller; Robert T. Leaf; Geneviève M. Nesslage; Raymond M. Mroch (Fisheries Oceanography, 2020)
The identification of anthropogenic and environmental drivers on length‐at‐age of fish stocks is important to understanding ecosystem dynamics and harvest intensity. We evaluated coastwide annual growth of n = 187,115 Atlantic Menhaden ( Brevoortia tyrannus ) and n = 299,185 Gulf Menhaden ( B. patronus ), using samples collected from the North, Mid‐, and South Atlantic from 1961 to 2016 and across the Gulf of Mexico from 1977 to 2016. Using hierarchical models of age 1 growth and age 2 growth, we evaluated a suite of candidate predictors including fishery landings, easterly (U) and northerly (V) wind velocity, river discharge, juvenile abundance, and the Atlantic Multi‐decadal Oscillation (AMO). We found age 2 growth rates were smaller than age 1 growth rates for both species and that Atlantic Menhaden growth rates were 3–4 times greater than Gulf Menhaden. Age 1 growth rate of Atlantic Menhaden was positively affected by landings lagged by one year, indicating a density‐dependent mechanism. In addition, AMO (negative effect), and wind U (positive effect) and wind V (negative effect) in the North Atlantic region were significant factors influencing coastwide age 1 Menhaden growth. Wind V (negative effect) and AMO (positive effect) influenced age 1 Gulf Menhaden growth. No environmental factors were found to have an effect on age 2 Atlantic Menhaden growth, and AMO was the only significant predictor (weak negative effect) of age 2 Gulf Menhaden growth. Fishing pressure was the primary influence on age 1 Atlantic Menhaden growth, whereas age 1 Gulf Menhaden growth was primarily influenced by environmental conditions.

Better off dead: assessment of aquatic disinfectants and thermal shock treatments to prevent the spread of invasive freshwater bivalves - Neil E. Coughlan; Stephanie J. Bradbeer; Ross N. Cuthbert; Eoghan M. Cunningham; Kate Crane; Stephen Potts; Joe M. Caffrey; Frances E. Lucy; Alison M. Dunn; Eithne Davis; Trevor Renals; Claire Quinn; et al. (Wetlands Ecology and Management, 2020)
Biosecurity protocols designed to prevent further spread of invasive alien species have become a key component of invader management strategies. Yet, the species-specific efficacy of many biosecurity treatments are frequently unclear or unknown. Invasive quagga, Dreissena bugensis , and zebra mussels, D. polymorpha , are a serious threat to freshwater ecosystems worldwide. Here, we examine the effectiveness of immersion (≤ 90 min) within 2% or 4% solutions for two commonly used disinfectants (Virasure® Aquatic and Virkon® Aquatic) to cause mortality of adult Dreissena bivalves . Further, we assessed the effectiveness of thermal treatments: steam spray (≥ 100 °C; ≤ 120 s); hot air (− 500 °C; ≤ 60 s); and dry ice exposure (− 78 °C; ≤ 300 g; 15 min). Complete mortality of D. polymorpha was observed following exposure to both disinfectants for 90 min, at both concentrations. However, high but incomplete mortality (40–90%) was recorded for D. bugensis across disinfectant treatments. For both species, complete mortality was achieved following 30 s of steam. In addition, 10 s of hot air and 15 min exposure to 300 g of dry ice can both completely killed groups of D. polymorpha . Overall, although the disinfectants did not cause complete mortality, it appears that relatively brief exposure to thermal treatments could be used to curtail the further spread of Dreissena species.

Cohort antler size signals environmental stress in a moderate climate - Bronson K. Strickland; P. Grady Dixon; Phillip D. Jones; Stephen Demarais; Nathan O. Owen; David A. Cox; Katie Landry-Guyton; W. Mark Baldwin; William T. McKinley (International Journal of Biometeorology, 2020)

Physical Barrier Type Abuse-Deterrent Formulations: Mechanistic Understanding of Sintering-Induced Microstructural Changes in Polyethylene Oxide Placebo Tablets - Heather J. Boyce; Vivek S. Dave; Myke Scoggins; Vadim J. Gurvich; Daniel T. Smith; Stephen R. Byrn; Stephen W. Hoag (AAPS PharmSciTech, 2020)

Global‐scale species distributions predict temperature‐related changes in species composition of rocky shore communities in Britain - Michael T. Burrows; Stephen J. Hawkins; J. Jon Moore; Leoni Adams; Heather Sugden; Louise Firth; Nova Mieszkowska (Global Change Biology, 2020)
Changes in rocky shore community composition as responses to climatic fluctuations and anthropogenic warming can be shown by changes in average species thermal affinities. In this study, we derived thermal affinities for European Atlantic rocky intertidal species by matching their known distributions to patterns in average annual sea surface temperature. Average thermal affinities (the Community Temperature Index, CTI) tracked patterns in sea surface temperature from Portugal to Norway, but CTI for communities of macroalgae and plant species changed less than those composed of animal species. This reduced response was in line with the expectation that communities with a smaller range of thermal affinities among species would change less in composition along thermal gradients and over time. Local‐scale patterns in CTI over wave exposure gradients suggested that canopy macroalgae allow species with ranges centred in cooler than local temperatures (‘cold‐affinity’) to persist in otherwise too‐warm conditions. In annual surveys of rocky shores, communities of animal species in Shetland showed a shift in dominance towards warm‐affinity species (‘thermophilization’) with local warming from 1980 to 2018 but the community of plant and macroalgal species did not. From 2002 to 2018, communities in southwest Britain showed the reverse trend in CTI: declining average thermal affinities over a period of modest temperature decline. Despite the cooling, trends in species abundance were in line with the general mechanism of direction and magnitude of long‐term trends depending on the difference between species thermal affinities and local temperatures. Cold‐affinity species increased during cooling and warm‐affinity ones decreased. The consistency of responses across different communities and with general expectations based on species thermal characteristics suggests strong predictive accuracy of responses of community composition to anthropogenic warming.

Immunogenicity Risk Assessment for PEGylated Therapeutics - Johanna R. Mora; Joleen T. White; Stephen L. DeWall (The AAPS Journal, 2020)

Foraging ecology of Mediterranean juvenile loggerhead turtles: insights from C and N stable isotope ratios - Julia C. Haywood; Paolo Casale; Daniela Freggi; Wayne J. Fuller; Brendan J. Godley; Bojan Lazar; Dimitris Margaritoulis; ALan F. Rees; Jamie D. Shutler; Robin T. Snape; Nathalie R. Swain-Diaz; Stephen Widdicombe; et al. (Marine Biology, 2020)
Bycatch is one of the key threats to juvenile marine turtles in the Mediterranean Sea. As fishing methods are regional or habitat specific, the susceptibility of marine turtles may differ according to inter- and intra-population variations in foraging ecology. An understanding of these variations is necessary to assess bycatch susceptibility and to implement region-specific management. To determine if foraging ecology differs with region, sex, and size of juvenile loggerhead turtles ( Caretta caretta ), stable isotope analysis of carbon and nitrogen was performed on 171 juveniles from a range of foraging regions across the central and eastern Mediterranean Sea. Isotope ratios differed with geographical region, likely due to baseline variations in δ 13 C and δ 15 N values. The absence of sex-specific differences suggests that within an area, all comparably sized animals likely exploit similar foraging strategies, and therefore, their susceptibility to fisheries threats will likely be similar. The isotope ratios of juveniles occupying the North East Adriatic and North Levantine basin increased with size, potentially due to increased consumption of more prey items at higher trophic levels from a more neritic source. Isotope ratios of juveniles with access to both neritic and oceanic habitats did not differ with size which is consistent with them consuming prey items from both habitats interchangeably. With foraging habitats exploited differently among size classes in a population, the susceptibility to fisheries interactions will likely differ with size; therefore, region-specific management approaches will be needed.

Circumpolar terrestrial arthropod monitoring: A review of ongoing activities, opportunities and challenges, with a focus on spiders - Mark A. K. Gillespie; Matthias Alfredsson; Isabel C. Barrio; Joe Bowden; Peter Convey; Stephen J. Coulson; Lauren E. Culler; Martin T. Dahl; Kathryn M. Daly; Seppo Koponen; Sarah Loboda; Yuri Marusik; et al. (Ambio, 2020)

Status and trends of terrestrial arthropod abundance and diversity in the North Atlantic region of the Arctic - Mark A. K. Gillespie; Matthias Alfredsson; Isabel C. Barrio; Joseph J. Bowden; Peter Convey; Lauren E. Culler; Stephen J. Coulson; Paul Henning Krogh; Amanda M. Koltz; Seppo Koponen; Sarah Loboda; Yuri Marusik; et al. (Ambio, 2020)

eDNA metabarcoding survey reveals fine‐scale coral reef community variation across a remote, tropical island ecosystem - Katrina M. West; Michael Stat; Euan S. Harvey; Craig L. Skepper; Joseph D. DiBattista; Zoe T. Richards; Michael J. Travers; Stephen J. Newman; Michael Bunce (Molecular Ecology, 2020)
Environmental DNA (eDNA) metabarcoding, a technique for retrieving multispecies DNA from environmental samples, can detect a diverse array of marine species from filtered seawater samples. There is a growing potential to integrate eDNA alongside existing monitoring methods in order to establish or improve the assessment of species diversity. Remote island reefs are increasingly vulnerable to climate‐related threats and as such there is a pressing need for cost‐effective whole‐ecosystem surveying to baseline biodiversity, study assemblage changes and ultimately develop sustainable management plans. We investigated the utility of eDNA metabarcoding as a high‐resolution, multitrophic biomonitoring tool at the Cocos (Keeling) Islands, Australia (CKI)—a remote tropical coral reef atoll situated within the eastern Indian Ocean. Metabarcoding assays targeting the mitochondrial 16S rRNA and CO1 genes, as well as the 18S rRNA nuclear gene, were applied to 252 surface seawater samples collected from 42 sites within a 140 km 2 area. Our assays successfully detected a wide range of bony fish and elasmobranchs (244 taxa), crustaceans (88), molluscs (37) and echinoderms (7). Assemblage composition varied significantly between sites, reflecting habitat partitioning across the island ecosystem and demonstrating the localisation of eDNA signals, despite extensive tidal and oceanic movements. In addition, we document putative new occurrence records for 46 taxa and compare the efficiency of our eDNA approach to visual survey techniques at CKI. Our study demonstrates the utility of a multimarker metabarcoding approach in capturing multitrophic biodiversity across an entire coral reef atoll and sets an important baseline for ongoing monitoring and management.

Prevalence, intensity and pathology of the nasal parasite Nasicola hogansi in Atlantic bluefin tuna ( Thunnus thynnus ) - Zoemma T. Warshafsky; Stephen A. Bullard; Wolfgang K. Vogelbein; Emily A. Chandler; Molly E. Lutcavage (Journal of Fish Diseases, 2020)
Ectoparasitic flatworms of Nasicola (Monogenoidea: Capsalidae), which infect nasal epithelium of true tunas ( Thunnus spp.), are not well studied, nor have their impacts on the host's olfactory organ been evaluated. Infections of Nasicola hogansi on Atlantic bluefin tuna, Thunnus thynnus , were investigated with emphasis on the relationship between infection prevalence, abundance and mean intensity with bluefin tuna size, sex, body condition and capture month, as well as histopathological effects. Commercially caught Atlantic bluefin tuna ( n = 161, 185–305 cm curved fork length) from the Gulf of Maine were sampled during June through August 2009 for infections by N. hogansi . A total of 247 specimens of N. hogansi were collected, with a prevalence of 45.3%, mean abundance of 1.57 (CI: 1.21–2.03) and mean intensity of 3.45 (CI: 2.91–4.22). Neither fish sex nor landing month had a significant effect on parasite parameters. Larger and better‐conditioned Atlantic bluefin tuna had a higher mean intensity of infection. Pathology associated with infection by N. hogansi included extensive necrosis, sloughing of the nasal epithelium and associated inflammation of underlying connective tissues. Further epidemiological and pathological study of this host–parasite system is warranted since impaired olfaction, if present, could adversely affect spawning and migration of this top ocean predator.

Civil disobedience movements such as School Strike for the Climate are raising public awareness of the climate change emergency - Stephen J. Thackeray; Sharon A. Robinson; Pete Smith; Rhea Bruno; Miko U. F. Kirschbaum; Carl Bernacchi; Maria Byrne; William Cheung; M. Francesca Cotrufo; Phillip Gienapp; Sue Hartley; Ivan Janssens; et al. (Global Change Biology, 2020)

β-secretase 1 inhibitory activity and AMP-activated protein kinase activation of Callyspongia samarensis extracts - Danica L. Resuello; Stephen B. Lirio; Analin E. Porto; Allan Patrick G. Macabeo; Hsi-Ya Huang; Mary Jho-Anne T. Corpuz; Oliver B. Villaflores (Natural Product Research, 2020)

Development and validation of an analytical method for the analysis of Sterigmatocystin in roasted coffee beans and black pepper using liquid chromatography-tandem mass spectrometry - Stephen W. C. Chung; Andy H. T. Wu (Food Additives & Contaminants: Part A, 2020)

Development of a multi-assay approach for monitoring coral diversity using eDNA metabarcoding - Jason B. Alexander; Michael Bunce; Nicole White; Shaun P. Wilkinson; Arne A. S. Adam; Tina Berry; Michael Stat; Luke Thomas; Stephen J. Newman; Laurence Dugal; Zoe T. Richards (Coral Reefs, 2020)

Alcohol intake, tobacco smoking, and esophageal adenocarcinoma survival: a molecular pathology epidemiology cohort study - R. Stephen McCain; Damian T. McManus; Stephen McQuaid; Jacqueline A. James; Manuel Salto-Tellez; Nathan B. Reid; Stephanie Craig; Chintapuza Chisambo; Victoria Bingham; Eamon McCarron; Eileen Parkes; Richard C. Turkington; et al. (Cancer Causes & Control, 2020)
Purpose To investigate the association between cigarette smoking, alcohol consumption, and esophageal adenocarcinoma survival, including stratified analysis by selected prognostic biomarkers. Methods A population-representative sample of 130 esophageal adenocarcinoma patients (n = 130) treated at the Northern Ireland Cancer Centre between 2004 and 2012. Cox proportional hazards models were applied to evaluate associations between smoking status, alcohol intake, and survival. Secondary analyses investigated these associations across categories of p53, HER2, CD8, and GLUT-1 biomarker expression. Results In esophageal adenocarcinoma patients, there was a significantly increased risk of cancer-specific mortality in ever, compared to never, alcohol drinkers in unadjusted (HR 1.96 95% CI 1.13–3.38) but not adjusted (HR 1.70 95% CI 0.95–3.04) analysis. This increased risk of death observed for alcohol consumers was more evident in patients with normal p53 expression, GLUT-1 positive or CD-8 positive tumors. There were no significant associations between survival and smoking status in esophageal adenocarcinoma patients. Conclusions In esophageal adenocarcinoma patients, cigarette smoking or alcohol consumption was not associated with a significant difference in survival in comparison with never smokers and never drinkers in fully adjusted analysis. However, in some biomarker-selected subgroups, ever-alcohol consumption was associated with a worsened survival in comparison with never drinkers. Larger studies are needed to investigate these findings, as these lifestyle habits may not only be linked to cancer risk but also cancer survival.

Current climate, isolation and history drive global patterns of tree phylogenetic endemism - Brody Sandel; Patrick Weigelt; Holger Kreft; Gunnar Keppel; Masha T. van der Sande; Sam Levin; Stephen Smith; Dylan Craven; Tiffany M. Knight (Global Ecology and Biogeography, 2020)
Aim We mapped global patterns of tree phylogenetic endemism (PE) to identify hotspots and test hypotheses about possible drivers. Specifically, we tested hypotheses related to current climate, geographical characteristics and historical conditions and assessed their relative importance in shaping PE patterns. Location Global. Time period We used the present distribution of trees, and predictors covering conditions from the mid‐Miocene to present. Major taxa studied All seed‐bearing trees. Methods We compiled distributions for 58,542 tree species across 463 regions worldwide, matched these to a recent phylogeny of seed plants and calculated PE for each region. We used a suite of predictor variables describing current climate (e.g., mean annual temperature), geographical characteristics (e.g., isolation) and historical conditions (e.g., tree cover at the Last Glacial Maximum) in a spatial regression model to explain variation in PE. Results Tree PE was highest on islands, and was higher closer to the equator. All three groups of predictor variables contributed substantially to the PE pattern. Isolation and topographic heterogeneity promoted high PE, as did high current tree cover. Among mainland regions, temperature seasonality was strongly negatively related to PE, while mean annual temperature was positively related to PE on islands. Some relationships differed among the major floristic regions. For example, tree cover at the Last Glacial Maximum was a positive predictor of PE in the Palaeotropics, while tree cover at the Miocene was a negative predictor of PE in the Neotropics. Main conclusions Globally, PE can be explained by a combination of geographical, historical and current factors. Some geographical variables appear to be key predictors of PE. However, the impact of historic and current climate variables differs considerably among the major floristic regions, reflecting their unique histories. Hence, the current distribution of trees is the result of globally relevant geographical drivers and regional climatic histories.

Biomarkers of leaky gut are related to inflammation and reduced physical function in older adults with cardiometabolic disease and mobility limitations - Kylie Kavanagh; Fang-Chi Hsu; Ashley T. Davis; Stephen B. Kritchevsky; W. Jack Rejeski; Sunghye Kim (GeroScience, 2019)

Geophagy among East African Chimpanzees: consumed soils provide protection from plant secondary compounds and bioavailable iron - Paula A. Pebsworth; Stephen Hillier; Renate Wendler; Ray Glahn; Chieu Anh Kim Ta; John T. Arnason; Sera L. Young (Environmental Geochemistry and Health, 2019)

Individual differences in neonatal white matter are associated with executive function at 3 years of age - Sarah J. Short; Michael T. Willoughby; Marie Camerota; Rebecca L. Stephens; Rachel J. Steiner; Martin Styner; John H. Gilmore (Brain Structure and Function, 2019)

Spider monkeys, the misunderstood assumptions of distance sampling and the pitfalls of poor field design - Antonio Christian de Andrade; Tiago A. Marques; Stephen T. Buckland (Biodiversity and Conservation, 2019)

Quantifying trends and uncertainty in prehistoric forest composition in the upper Midwestern United States - Andria Dawson; Christopher J. Paciorek; Simon J. Goring; Stephen T. Jackson; Jason S. McLachlan; John W. Williams (Ecology, 2019)
Forest ecosystems in eastern North America have been in flux for the last several thousand years, well before Euro‐American land clearance and the 20th‐century onset of anthropogenic climate change. However, the magnitude and uncertainty of prehistoric vegetation change have been difficult to quantify because of the multiple ecological, dispersal, and sedimentary processes that govern the relationship between forest composition and fossil pollen assemblages. Here we extend STEPPS, a Bayesian hierarchical spatiotemporal pollen–vegetation model, to estimate changes in forest composition in the upper Midwestern United States from about 2,100 to 300 yr ago. Using this approach, we find evidence for large changes in the relative abundance of some species, and significant changes in community composition. However, these changes took place against a regional background of changes that were small in magnitude or not statistically significant, suggesting complexity in the spatiotemporal patterns of forest dynamics. The single largest change is the infilling of Tsuga canadensis in northern Wisconsin over the past 2,000 yr. Despite range infilling, the range limit of T. canadensis was largely stable, with modest expansion westward. The regional ecotone between temperate hardwood forests and northern mixed hardwood/conifer forests shifted southwestward by 15–20 km in Minnesota and northwestern Wisconsin. Fraxinus , Ulmus , and other mesic hardwoods expanded in the Big Woods region of southern Minnesota. The increasing density of paleoecological data networks and advances in statistical modeling approaches now enables the confident detection of subtle but significant changes in forest composition over the last 2,000 yr.

Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Brittany T. Trew; Hedley S. Grantham; Christian Barrientos; Tim Collins; Philip D. Doherty; Angela Formia; Brendan J. Godley; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Dominic Tilley; Matthew J. Witt; et al. (Frontiers in Marine Science, 2019)

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Impacts of marine and freshwater aquaculture on wildlife: a global meta‐analysis - Luke T. Barrett; Stephen E. Swearer; Tim Dempster (Reviews in Aquaculture, 2019)
The global expansion of aquaculture has raised concerns about its environmental impacts, including effects on wildlife. Aquaculture farms are thought to repel some species and function as either attractive population sinks (‘ecological traps’) or population sources for others. We conducted a systematic review and meta‐analysis of empirical studies documenting interactions between aquaculture operations and vertebrate wildlife. Farms were associated with elevated local abundance and diversity of wildlife, although this overall effect was strongly driven by aggregations of wild fish at sea cages and shellfish farms (abundance: 72×; species richness: 2.0×). Birds were also more diverse at farms (1.1×), but other taxa showed variable and comparatively small effects. Larger effects were reported when researchers selected featureless or unstructured habitats as reference sites. Evidence for aggregation ‘hotspots’ is clear in some systems, but we cannot determine whether farms act as ecological traps for most taxa, as few studies assess either habitat preference or fitness in wildlife. Fish collected near farms were larger and heavier with no change in body condition, but also faced higher risk of disease and parasitism. Birds and mammals were frequently reported preying on stock, but little data exist on the outcomes of such interactions for birds and mammals – farms are likely to function as ecological traps for many species. We recommend researchers measure survival and reproduction in farm‐associated wildlife to make direct, causal links between aquaculture and its effects on wildlife populations.

Phylogenetic Analyses of pheS, dnaA and atpA Genes for Identification of Weissella confusa and Weissella cibaria Isolated from a South African Sugarcane Processing Factory - Sanet Nel; Stephen B. Davis; Akihito Endo; Leon M. T. Dicks (Current Microbiology, 2019)

White matter hyperintensities are associated with falls in older people with dementia - Morag E. Taylor; Stephen R. Lord; Kim Delbaere; Wei Wen; Jiyang Jiang; Henry Brodaty; Susan E. Kurrle; A. Stefanie Mikolaizak; Jacqueline C. T. Close (Brain Imaging and Behavior, 2019)

Differences in chemical thickness of grain and phase boundaries: an atom probe tomography study of experimentally deformed wehrlite - Joseph T. Cukjati; Reid F. Cooper; Stephen W. Parman; Ningli Zhao; Austin J. Akey; Fernando A. T. P. Laiginhas (Physics and Chemistry of Minerals, 2019)

Modern pollen‐assemblage data from small lakes paired with local forest‐composition data in northeastern United States - Stephen T. Jackson (Ecology, 2019)
Understanding and modeling of how forest composition and pattern are recorded by sedimentary pollen assemblages requires data sets in which modern pollen assemblages are paired with forest‐composition data across a range of spatial scales. Pollen data from 33 small lakes (

Bambara groundnut: an exemplar underutilised legume for resilience under climate change - Sean Mayes; Wai Kuan Ho; Hui Hui Chai; Xiuqing Gao; Aloyce C. Kundy; Kumbirai I. Mateva; Muhammad Zahrulakmal; Mohd Khairul Izwan Mohd Hahiree; Presidor Kendabie; Luis C. S. Licea; Festo Massawe; Tafadzwanashe Mabhaudhi; et al. (Planta, 2019)

Morphometric analysis and characterization of the nutritional quality in African yam bean accessions - Charity O. Aremu; Omena B. Ojuederie; Folake Ayo-Vaughan; Olatunde Dahunsi; Aruna Olasekan Adekiya; Adeniyi Olayanju; Ojo T. Adebiyi; Ige Sunday; Henry Inegbedion; Abiola John Asaleye; Stephen Abolusoro; Christopher M. Aboyeji; et al. (Plant Physiology Reports, 2019)

Divergent long‐term trends and interannual variation in ecosystem resource use efficiencies of a southern boreal old black spruce forest 1999–2017 - Peng Liu; T. Andrew Black; Rachhpal S. Jassal; Tianshan Zha; Zoran Nesic; Alan G. Barr; Warren D. Helgason; Xin Jia; Yun Tian; Jilmarie J. Stephens; Jingyong Ma (Global Change Biology, 2019)
Long‐term trends in ecosystem resource use efficiencies (RUEs) and their controlling factors are key pieces of information for understanding how an ecosystem responds to climate change. We used continuous eddy covariance and microclimate data over the period 1999–2017 from a 120‐year‐old black spruce stand in central Saskatchewan, Canada, to assess interannual variability, long‐term trends, and key controlling factors of gross ecosystem production (GEP) and the RUEs of carbon (CUE = net primary production [NPP]/GEP), light (LUE = GEP/absorbed photosynthetic radiation [APAR]), and water (WUE = GEP/evapotranspiration [ E ]). At this site, annual GEP has shown an increasing trend over the 19 years ( p 2 concentration. Interannual variability in GEP, aside from its increasing trend, was most strongly related to spring temperatures. Associated with the significant increase in annual GEP were relatively small changes in NPP, APAR, and E , so that annual CUE showed a decreasing trend and annual LUE and WUE showed increasing trends over the 19 years. The long‐term trends in the RUEs were related to the increasing CO 2 concentration. Further analysis of detrended RUEs showed that their interannual variation was impacted most strongly by air temperature. Two‐factor linear models combining CO 2 concentration and air temperature performed well ( R 2 ~0.60) in simulating annual RUEs. LUE and WUE were positively correlated both annually and seasonally, while LUE and CUE were mostly negatively correlated. Our results showed divergent long‐term trends among CUE, LUE, and WUE and highlighted the need to account for the combined effects of climatic controls and the ‘CO 2 fertilization effect’ on long‐term variations in RUEs. Since most RUE‐based models rely primarily on one resource limitation, the observed patterns of relative change among the three RUEs may have important implications for RUE‐based modeling of C fluxes.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Henry C. Bittig; Tanya L. Maurer; Joshua N. Plant; Catherine Schmechtig; Annie P. S. Wong; Hervé Claustre; Thomas W. Trull; T. V. S. Udaya Bhaskar; Emmanuel Boss; Giorgio Dall’Olmo; Emanuele Organelli; Antoine Poteau; et al. (Frontiers in Marine Science, 2019)

Ocean Observations to Improve Our Understanding, Modeling, and Forecasting of Subseasonal-to-Seasonal Variability - Aneesh C. Subramanian; Magdalena A. Balmaseda; Luca Centurioni; Rajib Chattopadhyay; Bruce D. Cornuelle; Charlotte DeMott; Maria Flatau; Yosuke Fujii; Donata Giglio; Sarah T. Gille; Thomas M. Hamill; Harry Hendon; et al. (Frontiers in Marine Science, 2019)

Anti-angiogenic activity of Gracilaria coronopifolia J.G. Agardh extract by lowering the levels of trace metals (iron, zinc and copper) in duck chorioallantoic membrane and in vitro activation of AMP-kinase - Oliver B. Villaflores; Katrin Mae M. Ortega; Analin Empaynado-Porto; Stephen Lirio; Hwa-Kwang Yak; Dharmatov Rahula Albano; Mary Jho-Anne T. Corpuz (Molecular Biology Reports, 2019)

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Spatial distribution and ecological risk assessment of trace metals in surface sediments of Lake Qaroun, Egypt - Ahmed A. El-Kady; Terry L. Wade; Stephen T. Sweet; Andrew G. Klein (Environmental Monitoring and Assessment, 2019)

Substantial increase in minimum lake surface temperatures under climate change - R. Iestyn Woolway; Gesa A. Weyhenmeyer; Martin Schmid; Martin T. Dokulil; Elvira de Eyto; Stephen C. Maberly; Linda May; Christopher J. Merchant (Climatic Change, 2019)

Outbreak of growth anomalies in Isopora palifera at Cocos (Keeling) Islands - Zoe T. Richards; Stephen J. Newman (Marine Biodiversity, 2019)

Microbial Diversity Profiling of Polysaccharide (gum)-Producing Bacteria Isolated from a South African Sugarcane Processing Factory - Sanet Nel; Stephen B. Davis; Akihito Endo; Leon M. T. Dicks (Current Microbiology, 2019)

Diabetes and differences in detection of incident invasive breast cancer - Gregory S. Calip; Onchee Yu; Denise M. Boudreau; Huibo Shao; Ruth Oratz; Stephen B. Richardson; Heather T. Gold (Cancer Causes & Control, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Reliability Evaluation of Hydraulic Conductivity Characteristics of Waste Wood Ash Treated Lateritic Soil - Johnson R. Oluremi; Stephen T. Ijimdiya; Adrian O. Eberemu; Kolawole J. Osinubi (Geotechnical and Geological Engineering, 2019)

Conserving the abundance of nonthreatened species - David J. Baker; Stephen T. Garnett; James O'Connor; Glenn Ehmke; Rohan H. Clarke; John C.Z. Woinarski; Melodie A. McGeoch (Conservation Biology, 2019)
Human modification of the environment is driving declines in population size and distributional extent of much of the world's biota. These declines extend to many of the most abundant and widespread species, for which proportionally small declines can result in the loss of vast numbers of individuals, biomass, and interactions. These losses could have major localized effects on ecological and cultural processes and services without elevating a species’ global extinction risk. Although most conservation effort is directed at species threatened with extinction in the very near term, the value of retaining abundance regardless of global extinction risk is justifiable based on many biodiversity or ecosystem service metrics, including cultural services, at scales from local to global. The challenges of identifying conservation priorities for widespread and abundant species include quantifying the effects of species’ abundance on services and understanding how these effects are realized as populations decline. Negative effects of population declines may be disconnected from the threat processes driving declines because of species movements and environment flows (e.g., hydrology). Conservation prioritization for these species shares greater similarity with invasive species risk assessments than extinction risk assessments because of the importance of local context and per capita effects of abundance on other species. Because conservation priorities usually focus on preventing the extinction of threatened species, the rationale and objectives for incorporating declines of nonthreatened species must be clearly articulated, going beyond extinction risk to encompass the range of likely harmful effects (e.g., secondary extinctions, loss of ecosystem services) if declines persist or are not reversed. Research should focus on characterizing the effects of local declines in species that are not threatened globally across a range of ecosystem services and quantifying the spatial distribution of these effects through the distribution of abundance. The case for conserving abundance in nonthreatened species can be made most powerfully when the costs of losing this abundance are better understood.

Changing station coverage impacts temperature trends in the Upper Colorado River basin - Stephanie A. McAfee; Gregory J. McCabe; Stephen T. Gray; Gregory T. Pederson (International Journal of Climatology, 2019)
Over the Upper Colorado River basin (UCRB), temperatures in widely used gridded data products do not warm as much as mean temperatures from a stable set of U.S. Historical Climatology Network (USHCN) stations, located at generally lower elevations, in most months of the year. This is contrary to expectations of elevation‐dependent warming, which suggests that warming increases with elevation. These findings could reflect (a) a genuine absence of elevation‐dependent warming in the region, (b) systematic non‐climatic influences on either the USHCN stations or high‐elevation stations, including known inhomogeneities related to changes in the time of observation and instrumentation, or (c) suppression of an elevation‐dependent warming signal introduced by changes in the station network. While we cannot categorically dismiss the first two possibilities, we show here that over portions of the 20th century, gridded temperatures warm less than USHCN temperatures, and the difference cannot be explained by accounting for known inhomogeneities. These analyses suggest that changing station coverage in the UCRB has influenced trends in gridded temperature estimates that incorporate changing suites of stations over time. Specifically, increases in the number of high‐elevation stations in the UCRB may have led to an underestimation of elevation‐dependent warming, particularly during the spring. This phenomenon is unlikely limited to this specific basin and may be present in other high‐elevation watersheds across the western United States

Elucidating the Mechanism of Absorption of Fast-Acting Insulin Aspart: The Role of Niacinamide - Jonas Kildegaard; Stephen T. Buckley; Rasmus H. Nielsen; Gro K. Povlsen; Torben Seested; Ulla Ribel; Helle B. Olsen; Svend Ludvigsen; Claus B. Jeppesen; Hanne H. F. Refsgaard; Kristian M. Bendtsen; Niels R. Kristensen; et al. (Pharmaceutical Research, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

Contrasting genetic structure of sympatric congeneric gastropods: Do differences in habitat preference, abundance and distribution matter? - Edward J. G. Wort; Mark A. Chapman; Stephen J. Hawkins; Lucy Henshall; Alfonso Pita; Marc Rius; Suzanne T. Williams; Phillip B. Fenberg (Journal of Biogeography, 2019)
Aim The relationship of population genetics with the ecology and biogeography of species may be explored by comparing phenotypically similar but ecologically different congeners with overlapping ranges. We compared genetic differentiation between two congeneric rocky intertidal gastropods across a major portion of their sympatric range. We hypothesized that the habitat generalist with high abundance and continuous distribution would exhibit comparatively less genetic differentiation than the habitat specialist with low abundance and a fragmented distribution. Location North‐east Atlantic from the north‐west Iberian Peninsula to southern British coastline. Taxon Gastropoda, Trochidae, Steromphala (formerly Gibbula ). Methods Field surveys were conducted to assess the presence/absence and the abundance of Steromphala umbilicalis (generalist) and S. pennanti (specialist) at 23 localities along ~1,800 km coastline. We isolated polymorphic microsatellite markers for both species (seven loci for S. umbilicalis and eight for S. pennanti ) and used these to genotype 187 S. umbilicalis and 157 S. pennanti individuals. We used standard population genetic analyses to compare patterns of genetic differentiation between species in relation to the field surveys. Results Steromphala pennanti showed a more fragmented distribution, significantly lower abundance, and greater genetic differentiation than S. umbilicalis . One S. umbilicalis population towards the north of the range (southern Britain) was genetically distinct from all other sampled populations. Steromphala pennanti showed greater genetic differentiation between three southern localities, which may be attributable to its fragmented distribution and lower abundance because of limited availability of its preferred fucoid habitat in this region. We also suggest that oceanographic currents could be associated with regional genetic structure. Main conclusions The habitat generalist showed high‐local abundances, continuous distribution and low regional genetic differentiation. We found the opposite pattern for the habitat specialist. Our study highlights the importance of considering ecological (e.g. abundance, habitat preferences) and abiotic variables (e.g. ocean currents and temperature) for understanding differences in genetic structure of sympatrically distributed congeners.

Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Stephen Conrad; Dylan R. Brown; Paula Gomez Alvarez; Bronte Bates; Nizam Ibrahim; Alex Reid; Luciana Silva Monteiro; Daniela A. Silva; Lea T. Mamo; Jacob R. Bowtell; Huang An Lin; Nathaniel L. Tolentino; et al. (Frontiers in Marine Science, 2019)

Time-trial performance is not impaired in either competitive athletes or untrained individuals following a prolonged cognitive task - Ida E. Clark; Richie P. Goulding; Fred J. DiMenna; Stephen J. Bailey; Martin I. Jones; Jonathan Fulford; Sinead T. J. McDonagh; Andrew M. Jones; Anni Vanhatalo (European Journal of Applied Physiology, 2019)

Size‐by‐environment interactions: a neglected dimension of species' responses to environmental variation - Andrew T. Tredennick; Brittany J. Teller; Peter B. Adler; Giles Hooker; Stephen P. Ellner (Ecology Letters, 2018)
In both plant and animal systems, size can determine whether an individual survives and grows under different environmental conditions. However, it is unclear whether and when size‐dependent responses to exogenous environmental fluctuations affect population dynamics. Size‐by‐environment interactions create pathways for environmental fluctuations to influence population dynamics by allowing for negative covariation between sizes within vital rates (e.g. small and large individuals have negatively covarying survival rates) and/or size‐dependent variability in a vital rate (e.g. survival of large individuals varies less than small individuals through time). Whether these phenomena affect population dynamics depends on how they are mediated by elasticities (they must affect the sizes and vital rates that matter) and their projected impacts will depend on model functional form (the impact of reduced variance depends on the relationship between the environment and vital rate). We demonstrate these ideas with an analysis of fifteen species from five semiarid plant communities. We find that size‐by‐environment interactions are common but do not impact long‐term population dynamics. Size‐by‐environment interactions may yet be important for other species. Our approach can be applied to species in other ecosystems to determine if and how size‐by‐environment interactions allow them to cope with, or exploit, fluctuating environments.

Functional and Compositional Responses of Periphyton Mats to Simulated Saltwater Intrusion in the Southern Everglades - Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Benjamin J. Wilson; Shelby Servais; Laura Bauman; Stephen E. Davis; Steve Kelly; Fred H. Sklar; David T. Rudnick; Jemma Stachelek; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Canopy structure and topography jointly constrain the microclimate of human‐modified tropical landscapes - Tommaso Jucker; Stephen R. Hardwick; Sabine Both; Dafydd M.O. Elias; Robert M. Ewers; David T. Milodowski; Tom Swinfield; David A. Coomes (Global Change Biology, 2018)
Local‐scale microclimatic conditions in forest understoreys play a key role in shaping the composition, diversity and function of these ecosystems. Consequently, understanding what drives variation in forest microclimate is critical to forecasting ecosystem responses to global change, particularly in the tropics where many species already operate close to their thermal limits and rapid land‐use transformation is profoundly altering local environments. Yet our ability to characterize forest microclimate at ecologically meaningful scales remains limited, as understorey conditions cannot be directly measured from outside the canopy. To address this challenge, we established a network of microclimate sensors across a land‐use intensity gradient spanning from old‐growth forests to oil‐palm plantations in Borneo. We then combined these observations with high‐resolution airborne laser scanning data to characterize how topography and canopy structure shape variation in microclimate both locally and across the landscape. In the processes, we generated high‐resolution microclimate surfaces spanning over 350 km 2 , which we used to explore the potential impacts of habitat degradation on forest regeneration under both current and future climate scenarios. We found that topography and vegetation structure were strong predictors of local microclimate, with elevation and terrain curvature primarily constraining daily mean temperatures and vapour pressure deficit (VPD), whereas canopy height had a clear dampening effect on microclimate extremes. This buffering effect was particularly pronounced on wind‐exposed slopes but tended to saturate once canopy height exceeded 20 m—suggesting that despite intensive logging, secondary forests remain largely thermally buffered. Nonetheless, at a landscape‐scale microclimate was highly heterogeneous, with maximum daily temperatures ranging between 24.2 and 37.2°C and VPD spanning two orders of magnitude. Based on this, we estimate that by the end of the century forest regeneration could be hampered in degraded secondary forests that characterize much of Borneo's lowlands if temperatures continue to rise following projected trends.

Effects of program scale-up on time to resolution for patients with abnormal screening mammography results - Simon Craddock Lee; Robin T. Higashi; Joanne M. Sanders; Hong Zhu; Stephen J. Inrig; Caroline Mejias; Keith E. Argenbright; Jasmin A. Tiro (Cancer Causes & Control, 2018)

Quantifying current and potential contributions of Australian indigenous peoples to threatened species management - Ian Leiper; Kerstin K. Zander; Cathy J. Robinson; Josie Carwadine; Bradley J. Moggridge; Stephen T. Garnett (Conservation Biology, 2018)
Formal engagement of indigenous peoples in conservation is increasing globally and leads to multiple benefits to communities while contributing to national and international biodiversity goals and obligations. This and ongoing declines in biodiversity have led to calls to increase opportunities for indigenous people to engage in managing their estates. However, there is no overarching understanding of indigenous peoples’ involvement in conservation, which limits the identification of new opportunities. We amalgamated information across governments and large nongovernmental organizations in the megadiverse country of Australia to quantify the involvement of indigenous people in management of threatened species. We identified 153 Australian‐based projects undertaken by different indigenous groups around the nation in 2015 and 2016 that included explicit funds for management of threatened species or threatened ecosystems. Most were in remote parts of western and northern Australia. Almost one‐quarter of all threatened animals and 2% of threatened plants were the subject of some formal conservation action by indigenous people. Occurrence records for 1574 threatened species showed that 823 (89.2%) of 923 species recorded on indigenous peoples’ lands were not listed in management projects. This gap may represent new opportunities for conservation initiatives. Because at least 59.5% of Australia's threatened species occur on indigenous peoples’ lands, efforts to build appropriate and effective indigenous conservation alliances are vital. However, it is also important to recognize that threatened species are part of complex social, ecological, economic and cultural systems, and to achieve successful outcomes requires consideration of indigenous peoples’ priorities, rights, and obligations and relationships with their traditionally owned land and sea.

What are the Conditions of Riparian Ecosystems? Identifying Impaired Floodplain Ecosystems across the Western U.S. Using the Riparian Condition Assessment (RCA) Tool - William W. Macfarlane; Jordan T. Gilbert; Joshua D. Gilbert; William C. Saunders; Nate Hough-Snee; Chalese Hafen; Joseph M. Wheaton; Stephen N. Bennett (Environmental Management, 2018)

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.

Dipentylammonium Binds to the Sigma-1 Receptor and Protects Against Glutamate Toxicity, Attenuates Dopamine Toxicity and Potentiates Neurite Outgrowth in Various Cultured Cell Lines - James M. Brimson; Stephen T. Safrany; Heider Qassam; Tewin Tencomnao (Neurotoxicity Research, 2018)

The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Steve D. M. Brown; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Martin Hrabě de Angelis; Jong Kyoung Kim; K. C. Kent Lloyd; et al. (Conservation Genetics, 2018)
The International Mouse Phenotyping Consortium (IMPC) is building a catalogue of mammalian gene function by producing and phenotyping a knockout mouse line for every protein-coding gene. To date, the IMPC has generated and characterised 5186 mutant lines. One-third of the lines have been found to be non-viable and over 300 new mouse models of human disease have been identified thus far. While current bioinformatics efforts are focused on translating results to better understand human disease processes, IMPC data also aids understanding genetic function and processes in other species. Here we show, using gorilla genomic data, how genes essential to development in mice can be used to help assess the potentially deleterious impact of gene variants in other species. This type of analyses could be used to select optimal breeders in endangered species to maintain or increase fitness and avoid variants associated to impaired-health phenotypes or loss-of-function mutations in genes of critical importance. We also show, using selected examples from various mammal species, how IMPC data can aid in the identification of candidate genes for studying a condition of interest, deliver information about the mechanisms involved, or support predictions for the function of genes that may play a role in adaptation. With genotyping costs decreasing and the continued improvements of bioinformatics tools, the analyses we demonstrate can be routinely applied.

Processes That Contribute to Decreased Dimethyl Sulfide Production in Response to Ocean Acidification in Subtropical Waters - Stephen D. Archer; Kerstin Suffrian; Kevin M. Posman; Lennart T. Bach; Patricia A. Matrai; Peter D. Countway; Andrea Ludwig; Ulf Riebesell (Frontiers in Marine Science, 2018)

A Resilience Framework for Chronic Exposures: Water Quality and Ecosystem Services in Coastal Social-Ecological Systems - Nathaniel H. Merrill; Kate K. Mulvaney; David M. Martin; Marnita M. Chintala; Walter Berry; Timothy R. Gleason; Stephen Balogh; Austin T. Humphries (Coastal Management, 2018)

The modern pollen–vegetation relationships of a tropical forest–savannah mosaic landscape, Ghana, West Africa - Adele C.M. Julier; Phillip E. Jardine; Stephen Adu-Bredu; Angela L. Coe; Akwasi Duah-Gyamfi; Wesley T. Fraser; Barry H. Lomax; Yadvinder Malhi; Sam Moore; Kennedy Owusu-Afriyie; William D. Gosling (Palynology, 2018)

Momentary changes in craving predict smoking lapse behavior: a laboratory study - Courtney A. Motschman; Lisa J. Germeroth; Stephen T. Tiffany (Psychopharmacology, 2018)

Investigation of the effects of slow-release fertilizer and struvite in biodegradation in filter drains and potential application of treated water in irrigation of road verges - Stephen C. Theophilus; Fredrick U. Mbanaso; Ernest O. Nnadi; Kingsley T. Onyedeke (Environmental Science and Pollution Research, 2018)

Phenotypic and genotypic heterogeneity of Lynch syndrome: a complex diagnostic challenge - Henry T. Lynch; Stephen Lanspa; Trudy Shaw; Murray Joseph Casey; Marc Rendell; Mark Stacey; Theresa Townley; Carrie Snyder; Megan Hitchins; Joan Bailey-Wilson (Familial Cancer, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Woody plants optimise stomatal behaviour relative to hydraulic risk - William R. L. Anderegg; Adam Wolf; Adriana Arango‐Velez; Brendan Choat; Daniel J. Chmura; Steven Jansen; Thomas Kolb; Shan Li; Frederick C. Meinzer; Pilar Pita; Víctor Resco de Dios; John S. Sperry; et al. (Ecology Letters, 2018)
Stomatal response to environmental conditions forms the backbone of all ecosystem and carbon cycle models, but is largely based on empirical relationships. Evolutionary theories of stomatal behaviour are critical for guarding against prediction errors of empirical models under future climates. Longstanding theory holds that stomata maximise fitness by acting to maintain constant marginal water use efficiency over a given time horizon, but a recent evolutionary theory proposes that stomata instead maximise carbon gain minus carbon costs/risk of hydraulic damage. Using data from 34 species that span global forest biomes, we find that the recent carbon‐maximisation optimisation theory is widely supported, revealing that the evolution of stomatal regulation has not been primarily driven by attainment of constant marginal water use efficiency. Optimal control of stomata to manage hydraulic risk is likely to have significant consequences for ecosystem fluxes during drought, which is critical given projected intensification of the global hydrological cycle.

A model for assessing iceberg hazard - Grant R. Bigg; T. E. Cropper; Clare K. O’Neill; Alex K. Arnold; A. H. Fleming; R. Marsh; V. Ivchenko; Nicolas Fournier; Mike Osborne; Robin Stephens (Natural Hazards, 2018)

Social license as an emergent property of political interactions: response to Kendal and Ford 2017 - Stephen T. Garnett; Kerstin K. Zander; Catherine J. Robinson (Conservation Biology, 2018)
Article impact statement : Recognition that conservation, like mining, needs a social license to operate can help avoid dangerous assumptions of approval.

The Araneae of Svalbard: the relationships between specific environmental factors and spider assemblages in the High Arctic - Martin T. Dahl; Nigel G. Yoccoz; Kjetil Aakra; Stephen J. Coulson (Polar Biology, 2018)

Waterbird Use of Sheetwater Wetlands in Iowa’s Prairie Pothole Region - Kevin T. Murphy; Stephen J. Dinsmore (Wetlands, 2018)

Unresolved Complexity in Assessments of Mineral Resource Depletion and Availability - Stephen A. Northey; Gavin M. Mudd; T. T. Werner (Natural Resources Research, 2018)

Evaluation of triazole and isoxazole derivatives as potential anti-infective agents - Amer H. Tarawneh; Lo′ay A. Al-Momani; Francisco León; Surenda K. Jain; Anastassiya V. Gadetskaya; Sultan T. Abu-Orabi; Babu L. Tekwani; Stephen J. Cutler (Medicinal Chemistry Research, 2018)

Soil eaten by chacma baboons adsorbs polar plant secondary metabolites representative of those found in their diet - Chieu Anh Kim Ta; Paula A. Pebsworth; Rui Liu; Stephen Hillier; Nia Gray; John T. Arnason; Sera L. Young (Environmental Geochemistry and Health, 2018)

Culture environment and the odorous volatile compounds present in pond-raised channel catfish (Ictalurus punctatus) - Stephen T. McCrummen; Yifen Wang; Terrill R. Hanson; Lisa Bott; Shaoyang Liu (Aquaculture International, 2018)

Tree cover shows strong sensitivity to precipitation variability across the global tropics - Xiangtao Xu; David Medvigy; Anna T. Trugman; Kaiyu Guan; Stephen P. Good; Ignacio Rodriguez‐Iturbe (Global Ecology and Biogeography, 2018)
Aim Vegetation is sensitive to mean annual precipitation (MAP), but the sensitivity of vegetation to precipitation variability (PV) is less clear. Tropical ecosystems are likely to experience increased PV in the future. Here we assessed the importance, magnitude and mechanism of PV effects on tree cover in the context of covarying environmental drivers such as fire, temperature and soil properties. Location Tropical land. Time period 2000–2010. Major taxa studied Trees. Methods We compiled climate, soil and remotely‐sensed tree cover data over tropical land. We then comprehensively assessed the contribution of PV at different time‐scales to tropical tree cover variations and estimated the sensitivity of tree cover to PV changes by conducting rolling‐window regression and variance decomposition analyses. We further adopted a mechanistic modelling approach to test whether water competition between trees and grasses can explain the observed effect of PV. Results We find that PV contributes 33–56% to the total explained spatial variation (65–79%) in tree cover. The contribution of PV depends on MAP and is highest under intermediate MAP (500–1,500 mm). Tree cover generally increases with rainy day frequency and wet season length but shows mixed responses to inter‐annual PV. Based on the estimated sensitivity, tropical tree cover can decrease by 3–5% overall and by up to 20% in Amazonia under a 20% decrease in rainy days. Mechanistic modelling analysis reproduced the continental differences in tree cover along an MAP gradient. Main conclusions Under intermediate rainfall regimes (500–1,500 mm), PV can be a more important determinant of tropical tree cover than conventionally proposed drivers such as MAP and fire. The effect of PV likely results from the sensitivity of tree–grass competition to the temporal distribution of water resources. These results show that climate variability can strongly shape the biosphere.

Pollen-vegetation richness and diversity relationships in the tropics - William D. Gosling; Adele C. M. Julier; Stephen Adu-Bredu; Gloria D. Djagbletey; Wesley T. Fraser; Phillip E. Jardine; Barry H. Lomax; Yadvinder Malhi; Emmanuel A. Manu; Francis E. Mayle; Sam Moore (Vegetation History and Archaeobotany, 2018)

Acute acetaminophen ingestion improves performance and muscle activation during maximal intermittent knee extensor exercise - Paul T. Morgan; Joanna L. Bowtell; Anni Vanhatalo; Andrew M. Jones; Stephen J. Bailey (European Journal of Applied Physiology, 2018)

A new genus and species of turtle blood fluke (Digenea: Schistosomatoidea) from the Mekong snail-eating turtle, Malayemys subtrijuga (Schlegel & Müller) (Testudines: Geoemydidae) in Vietnam, with a reassessment of related Asiatic turtle blood flukes and molecular phylogeny - Jackson R. Roberts; Cova R. Arias; Kenneth M. Halanych; Binh T. Dang; Stephen A. Bullard (Systematic Parasitology, 2018)

Differential declines in Alaskan boreal forest vitality related to climate and competition - Anna T. Trugman; David Medvigy; William R. L. Anderegg; Stephen W. Pacala (Global Change Biology, 2018)
Rapid warming and changes in water availability at high latitudes alter resource abundance, tree competition, and disturbance regimes. While these changes are expected to disrupt the functioning of boreal forests, their ultimate implications for forest composition are uncertain. In particular, recent site‐level studies of the Alaskan boreal forest have reported both increases and decreases in productivity over the past few decades. Here, we test the idea that variations in Alaskan forest growth and mortality rates are contingent on species composition. Using forest inventory measurements and climate data from plots located throughout interior and south‐central Alaska, we show significant growth and mortality responses associated with competition, midsummer vapor pressure deficit, and increased growing season length. The governing climate and competition processes differed substantially across species. Surprisingly, the most dramatic climate response occurred in the drought tolerant angiosperm species, trembling aspen, and linked high midsummer vapor pressure deficits to decreased growth and increased insect‐related mortality. Given that species composition in the Alaskan and western Canadian boreal forests is projected to shift toward early‐successional angiosperm species due to fire regime, these results underscore the potential for a reduction in boreal productivity stemming from increases in midsummer evaporative demand.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Bayesian estimation and use of high-throughput remote sensing indices for quantitative genetic analyses of leaf growth - Robert L. Baker; Wen Fung Leong; Nan An; Marcus T. Brock; Matthew J. Rubin; Stephen Welch; Cynthia Weinig (Theoretical and Applied Genetics, 2018)

The culture of bird conservation: Australian stakeholder values regarding iconic, flagship and rare birds - Gillian B. Ainsworth; James A. Fitzsimons; Michael A. Weston; Stephen T. Garnett (Biodiversity and Conservation, 2018)

Forest biomass, productivity and carbon cycling along a rainfall gradient in West Africa - Sam Moore; Stephen Adu‐Bredu; Akwasi Duah‐Gyamfi; Shalom D. Addo‐Danso; Forzia Ibrahim; Armel T. Mbou; Agnès de Grandcourt; Riccardo Valentini; Giacomo Nicolini; Gloria Djagbletey; Kennedy Owusu‐Afriyie; Agne Gvozdevaite; et al. (Global Change Biology, 2018)
Net Primary Productivity ( NPP ) is one of the most important parameters in describing the functioning of any ecosystem and yet it arguably remains a poorly quantified and understood component of carbon cycling in tropical forests, especially outside of the Americas. We provide the first comprehensive analysis of NPP and its carbon allocation to woody, canopy and root growth components at contrasting lowland West African forests spanning a rainfall gradient. Using a standardized methodology to study evergreen ( EF ), semi‐deciduous ( SDF ), dry forests ( DF ) and woody savanna ( WS ), we find that (i) climate is more closely related with above and belowground C stocks than with NPP (ii) total NPP is highest in the SDF site, then the EF followed by the DF and WS and that (iii) different forest types have distinct carbon allocation patterns whereby SDF allocate in excess of 50% to canopy production and the DF and WS sites allocate 40%–50% to woody production. Furthermore, we find that (iv) compared with canopy and root growth rates the woody growth rate of these forests is a poor proxy for their overall productivity and that (v) residence time is the primary driver in the productivity‐allocation‐turnover chain for the observed spatial differences in woody, leaf and root biomass across the rainfall gradient. Through a systematic assessment of forest productivity we demonstrate the importance of directly measuring the main components of above and belowground NPP and encourage the establishment of more permanent carbon intensive monitoring plots across the tropics.

Measurements and Observations in the XXI century (MOXXI): innovation and multi-disciplinarity to sense the hydrological cycle - Flavia Tauro; John Selker; Nick van de Giesen; Tommaso Abrate; Remko Uijlenhoet; Maurizio Porfiri; Salvatore Manfreda; Kelly Caylor; Tommaso Moramarco; Jerome Benveniste; Giuseppe Ciraolo; Lyndon Estes; et al. (Hydrological Sciences Journal, 2018)

The First Hop: Use of Beaufort Sea Deltas by Hatch-Year Semipalmated Sandpipers - Roy T. Churchwell; Steve Kendall; Stephen C. Brown; Arny L. Blanchard; Tuula E. Hollmen; Abby N. Powell (Estuaries and Coasts, 2018)

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Immune competence assessment in marine medaka (Orzyias melastigma)—a holistic approach for immunotoxicology - Roy R. Ye; Drew R. Peterson; Frauke Seemann; Shin-Ichi Kitamura; J. S. Lee; Terrance C. K. Lau; Stephen K. W. Tsui; Doris W. T. Au (Environmental Science and Pollution Research, 2017)

Multiple hypotheses explain variation in extra‐pair paternity at different levels in a single bird family - Lyanne Brouwer; Martijn van de Pol; Nataly Hidalgo Aranzamendi; Glen Bain; Daniel T. Baldassarre; Lesley C. Brooker; Michael G. Brooker; Diane Colombelli‐Négrel; Erik Enbody; Kurt Gielow; Michelle L. Hall; Allison E. Johnson; et al. (Molecular Ecology, 2017)
Extra‐pair paternity ( EPP ), where offspring are sired by a male other than the social male, varies enormously both within and among species. Trying to explain this variation has proved difficult because the majority of the interspecific variation is phylogenetically based. Ideally, variation in EPP should be investigated in closely related species, but clades with sufficient variation are rare. We present a comprehensive multifactorial test to explain variation in EPP among individuals in 20 populations of nine species over 89 years from a single bird family (Maluridae). Females had higher EPP in the presence of more helpers, more neighbours or if paired incestuously. Furthermore, higher EPP occurred in years with many incestuous pairs, populations with many helpers and species with high male density or in which males provide less care. Altogether, these variables accounted for 48% of the total and 89% of the interspecific and interpopulation variation in EPP . These findings indicate why consistent patterns in EPP have been so challenging to detect and suggest that a single predictor is unlikely to account for the enormous variation in EPP across levels of analysis. Nevertheless, it also shows that existing hypotheses can explain the variation in EPP well and that the density of males in particular is a good predictor to explain variation in EPP among species when a large part of the confounding effect of phylogeny is excluded.

Microbial succession dynamics along glacier forefield chronosequences in Tierra del Fuego (Chile) - Miguel Angel Fernández-Martínez; Sergio Pérez-Ortega; Stephen B. Pointing; T. G. Allan Green; Ana Pintado; Ricardo Rozzi; Leopoldo G. Sancho; Asunción de los Ríos (Polar Biology, 2017)

The impact of the expansion of shrimp aquaculture on livelihoods in coastal Bangladesh - Abu Nasar Abdullah; Bronwyn Myers; Natasha Stacey; Kerstin K. Zander; Stephen T. Garnett (Environment, Development and Sustainability, 2017)

Invasive plants decrease microbial capacity to nitrify and denitrify compared to native California grassland communities - Chelsea J. Carey; Joseph C. Blankinship; Valerie T. Eviner; Carolyn M. Malmstrom; Stephen C. Hart (Biological Invasions, 2017)

Circadian rhythms vary over the growing season and correlate with fitness components - Matthew J. Rubin; Marcus T. Brock; Amanda M. Davis; Zachary M. German; Mary Knapp; Stephen M. Welch; Stacey L. Harmer; Julin N. Maloof; Seth J. Davis; Cynthia Weinig (Molecular Ecology, 2017)
Circadian clocks have evolved independently in all three domains of life, suggesting that internal mechanisms of time‐keeping are adaptive in contemporary populations. However, the performance consequences of either discrete or quantitative clock variation have rarely been tested in field settings. Clock sensitivity of diverse segregating lines to the environment remains uncharacterized as do the statistical genetic parameters that determine evolutionary potential. In field studies with Arabidopsis thaliana , we found that major perturbations to circadian cycle length (referred to as clock period) via mutation reduce both survival and fecundity. Subtler adjustments via genomic introgression of naturally occurring alleles indicated that clock periods slightly >24 hr were adaptive, consistent with prior models describing how well the timing of biological processes is adjusted within a diurnal cycle (referred to as phase). In segregating recombinant inbred lines ( RIL s), circadian phase varied up to 2 hr across months of the growing season, and both period and phase expressed significant genetic variances. Performance metrics including developmental rate, size and fruit set were described by principal components ( PC ) analyses and circadian parameters correlated with the first PC , such that period lengths slightly >24 hr were associated with improved performance in multiple RIL sets. These experiments translate functional analyses of clock behaviour performed in controlled settings to natural ones, demonstrating that quantitative variation in circadian phase is highly responsive to seasonally variable abiotic factors. The results expand upon prior studies in controlled settings, showing that discrete and quantitative variation in clock phenotypes correlates with performance in nature.

Decreased spontaneous activity and altered evoked nociceptive response of rat thalamic submedius neurons to lumbar vertebra thrust - William R. Reed; Jamie T. Cranston; Stephen M. Onifer; Joshua W. Little; Randall S. Sozio (Experimental Brain Research, 2017)

Erratum to: Monazite trumps zircon: applying SHRIMP U–Pb geochronology to systematically evaluate emplacement ages of leucocratic, low-temperature granites in a complex Precambrian orogen - Agnieszka M. Piechocka; Courtney J. Gregory; Jian-Wei Zi; Stephen Sheppard; Michael T. D. Wingate; Birger Rasmussen (Contributions to Mineralogy and Petrology, 2017)

The Influence of Hydrologic Residence Time on Lake Carbon Cycling Dynamics Following Extreme Precipitation Events - Jacob A. Zwart; Stephen D. Sebestyen; Christopher T. Solomon; Stuart E. Jones (Ecosystems, 2017)

Monazite trumps zircon: applying SHRIMP U–Pb geochronology to systematically evaluate emplacement ages of leucocratic, low-temperature granites in a complex Precambrian orogen - Agnieszka M. Piechocka; Courtney J. Gregory; Jian-Wei Zi; Stephen Sheppard; Michael T. D. Wingate; Birger Rasmussen (Contributions to Mineralogy and Petrology, 2017)

Does milk intake promote prostate cancer initiation or progression via effects on insulin-like growth factors (IGFs)? A systematic review and meta-analysis - Sean Harrison; Rosie Lennon; Jeff Holly; Julian P. T. Higgins; Mike Gardner; Claire Perks; Tom Gaunt; Vanessa Tan; Cath Borwick; Pauline Emmet; Mona Jeffreys; Kate Northstone; et al. (Cancer Causes & Control, 2017)

A nocturnal atmospheric loss of CH2I2 in the remote marine boundary layer - Lucy J. Carpenter; Stephen J. Andrews; Richard T. Lidster; Alfonso Saiz-Lopez; Miguel Fernandez-Sanchez; William J. Bloss; Bin Ouyang; Roderic L. Jones (Journal of Atmospheric Chemistry, 2017)

The ecology of cooperative breeding behaviour - Sheng‐Feng Shen; Stephen T. Emlen; Walter D. Koenig; Dustin R. Rubenstein (Ecology Letters, 2017)
Ecology is a fundamental driving force for the evolutionary transition from solitary living to breeding cooperatively in groups. However, the fact that both benign and harsh, as well as stable and fluctuating, environments can favour the evolution of cooperative breeding behaviour constitutes a paradox of environmental quality and sociality. Here, we propose a new model – the dual benefits framework – for resolving this paradox. Our framework distinguishes between two categories of grouping benefits – resource defence benefits that derive from group‐defended critical resources and collective action benefits that result from social cooperation among group members – and uses insider–outsider conflict theory to simultaneously consider the interests of current group members (insiders) and potential joiners (outsiders) in determining optimal group size. We argue that the different grouping benefits realised from resource defence and collective action profoundly affect insider–outsider conflict resolution, resulting in predictable differences in the per capita productivity, stable group size, kin structure and stability of the social group. We also suggest that different types of environmental variation (spatial vs. temporal) select for societies that form because of the different grouping benefits, thus helping to resolve the paradox of why cooperative breeding evolves in such different types of environments.

Abundance and distribution of sturgeon feeding pits in a Washington estuary - Mary L. Moser; Kim Patten; Stephen C. Corbett; Blake E. Feist; Steven T. Lindley (Environmental Biology of Fishes, 2017)

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

Genetic dissection of sorghum grain quality traits using diverse and segregating populations - Richard E. Boyles; Brian K. Pfeiffer; Elizabeth A. Cooper; Bradley L. Rauh; Kelsey J. Zielinski; Matthew T. Myers; Zachary Brenton; William L. Rooney; Stephen Kresovich (Theoretical and Applied Genetics, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Distribution and residue profile of organochlorine pesticides and polychlorinated biphenyls in sediment and fish of Lake Manzala, Egypt - Ahmed A. El-Kady; Terry L. Wade; Stephen T. Sweet; José L. Sericano (Environmental Science and Pollution Research, 2017)

Alcohol consumption as a predictor of reactivity to smoking and stress cues presented in the natural environment of smokers - Rachel L. Tomko; Michael E. Saladin; Erin A. McClure; Lindsay M. Squeglia; Matthew J. Carpenter; Stephen T. Tiffany; Nathaniel L. Baker; Kevin M. Gray (Psychopharmacology, 2017)

Exploration of volatile compounds causing off-flavor in farm-raised channel catfish (Ictalurus punctatus) fillet - Shaoyang Liu; Tao Liao; Stephen T. McCrummen; Terrill R. Hanson; Yifen Wang (Aquaculture International, 2017)

Transcriptomic imprints of adaptation to fresh water: parallel evolution of osmoregulatory gene expression in the Alewife - Jonathan P. Velotta; Jill L. Wegrzyn; Samuel Ginzburg; Lin Kang; Sergiusz Czesny; Rachel J. O'Neill; Stephen D. McCormick; Pawel Michalak; Eric T. Schultz (Molecular Ecology, 2017)
Comparative approaches in physiological genomics offer an opportunity to understand the functional importance of genes involved in niche exploitation. We used populations of Alewife ( Alosa pseudoharengus ) to explore the transcriptional mechanisms that underlie adaptation to fresh water. Ancestrally anadromous Alewives have recently formed multiple, independently derived, landlocked populations, which exhibit reduced tolerance of saltwater and enhanced tolerance of fresh water. Using RNA ‐seq, we compared transcriptional responses of an anadromous Alewife population to two landlocked populations after acclimation to fresh (0 ppt) and saltwater (35 ppt). Our results suggest that the gill transcriptome has evolved in primarily discordant ways between independent landlocked populations and their anadromous ancestor. By contrast, evolved shifts in the transcription of a small suite of well‐characterized osmoregulatory genes exhibited a strong degree of parallelism. In particular, transcription of genes that regulate gill ion exchange has diverged in accordance with functional predictions: freshwater ion‐uptake genes (most notably, the ‘freshwater paralog’ of Na + /K + ‐ ATP ase α‐subunit) were more highly expressed in landlocked forms, whereas genes that regulate saltwater ion secretion (e.g. the ‘saltwater paralog’ of NKA α) exhibited a blunted response to saltwater. Parallel divergence of ion transport gene expression is associated with shifts in salinity tolerance limits among landlocked forms, suggesting that changes to the gill's transcriptional response to salinity facilitate freshwater adaptation.

Ecosystem fluxes of hydrogen in a mid‐latitude forest driven by soil microorganisms and plants - Laura K. Meredith; Róisín Commane; Trevor F. Keenan; Stephen T. Klosterman; J. William Munger; Pamela H. Templer; Jianwu Tang; Steven C. Wofsy; Ronald G. Prinn (Global Change Biology, 2017)
Molecular hydrogen (H 2 ) is an atmospheric trace gas with a large microbe‐mediated soil sink, yet cycling of this compound throughout ecosystems is poorly understood. Measurements of the sources and sinks of H 2 in various ecosystems are sparse, resulting in large uncertainties in the global H 2 budget. Constraining the H 2 cycle is critical to understanding its role in atmospheric chemistry and climate. We measured H 2 fluxes at high frequency in a temperate mixed deciduous forest for 15 months using a tower‐based flux‐gradient approach to determine both the soil‐atmosphere and the net ecosystem flux of H 2 . We found that Harvard Forest is a net H 2 sink (−1.4 ± 1.1 kg H 2 ha −1 ) with soils as the dominant H 2 sink (−2.0 ± 1.0 kg H 2 ha −1 ) and aboveground canopy emissions as the dominant H 2 source (+0.6 ± 0.8 kg H 2 ha −1 ). Aboveground emissions of H 2 were an unexpected and substantial component of the ecosystem H 2 flux, reducing net ecosystem uptake by 30% of that calculated from soil uptake alone. Soil uptake was highly seasonal (July maximum, February minimum), positively correlated with soil temperature and negatively correlated with environmental variables relevant to diffusion into soils (i.e., soil moisture, snow depth, snow density). Soil microbial H 2 uptake was correlated with rhizosphere respiration rates ( r = 0.8, P 2 metabolism yielded up to 2% of the energy gleaned by microbes from carbon substrate respiration. Here, we elucidate key processes controlling the biosphere–atmosphere exchange of H 2 and raise new questions regarding the role of aboveground biomass as a source of atmospheric H 2 and mechanisms linking soil H 2 and carbon cycling. Results from this study should be incorporated into modeling efforts to predict the response of the H 2 soil sink to changes in anthropogenic H 2 emissions and shifting soil conditions with climate and land‐use change.

The contribution of policy, law, management, research, and advocacy failings to the recent extinctions of three Australian vertebrate species - John C.Z. Woinarski; Stephen T. Garnett; Sarah M. Legge; David B. Lindenmayer (Conservation Biology, 2017)
Extinctions typically have ecological drivers, such as habitat loss. However, extinction events are also influenced by policy and management settings that may be antithetical to biodiversity conservation, inadequate to prevent extinction, insufficiently resourced, or poorly implemented. Three endemic Australian vertebrate species—the Christmas Island pipistrelle ( Pipistrellus murrayi ), Bramble Cay melomys ( Melomys rubicola ), and Christmas Island forest skink ( Emoia nativitatis )—became extinct from 2009 to 2014. All 3 extinctions were predictable and probably preventable. We sought to identify the policy, management, research, and other shortcomings that contributed to their extinctions or failed to prevent them. These included a lack within national environmental legislation and policy of explicit commitment to the prevention of avoidable extinctions, lack of explicit accountability, inadequate resources for conservation (particularly for species not considered charismatic or not of high taxonomic distinctiveness), inadequate biosecurity, a slow and inadequate process for listing species as threatened, recovery planning that failed to consider the need for emergency response, inability of researchers to identify major threatening factors, lack of public engagement and involvement in conservation decisions, and limited advocacy. From these 3 cases, we recommend: environmental policy explicitly seeks to prevent extinction of any species and provides a clear chain of accountability and an explicit requirement for public inquiry following any extinction; implementation of a timely and comprehensive process for listing species as threatened and for recovery planning; reservation alone not be assumed sufficient to maintain species; enhancement of biosecurity measures; allocation of sufficient resources to undertake actions necessary to prevent extinction; monitoring be considered a pivotal component of the conservation response; research provides timely identification of factors responsible for decline and of the risk of extinction; effective dissemination of research results; advocacy by an informed public for the recovery of threatened species; and public involvement in governance of the recovery process. These recommendations should be applicable broadly to reduce the likelihood and incidence of extinctions.

Response to varying the nicotine content of cigarettes in vulnerable populations: an initial experimental examination of acute effects - Stephen T. Higgins; Sarah H. Heil; Stacey C. Sigmon; Jennifer W. Tidey; Diann E. Gaalema; Maxine L. Stitzer; Hanna Durand; Janice Y. Bunn; Jeff S. Priest; Christopher A. Arger; Mollie E. Miller; Cecilia L. Bergeria; et al. (Psychopharmacology, 2017)

Decadal predictions with the HiGEM high resolution global coupled climate model: description and basic evaluation - L. C. Shaffrey; D. Hodson; J. Robson; D. P. Stevens; E. Hawkins; I. Polo; I. Stevens; R. T. Sutton; G. Lister; A. Iwi; D. Smith; A. Stephens (Climate Dynamics, 2017)

Biodiversity and ecosystem services require IPBES to take novel approach to scenarios - Marcel T. J. Kok; Kasper Kok; Garry D. Peterson; Rosemary Hill; John Agard; Stephen R. Carpenter (Sustainability Science, 2017)

Examining the historical and present energy metabolism of a Rust Belt City: Syracuse, NY 1840–2005 - Stephen Balogh; Charles A. S. Hall; Drew V. Gamils; Alexander M. Popov; Ryan T. Rose (Urban Ecosystems, 2016)

Genetic structure of Pyrenophora teres f. teres and P. teres f. maculata populations from western Canada - Alireza Akhavan; T. Kelly Turkington; Berisso Kebede; Kequan Xi; Krishan Kumar; Andy Tekauz; H. Randy Kutcher; James R. Tucker; Stephen E. Strelkov (European Journal of Plant Pathology, 2016)

Exploring the effect of heat on stated intentions to move - Kerstin K. Zander; Akhilesh Surjan; Stephen T. Garnett (Climatic Change, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Early Passage Dependence of Mesenchymal Stem Cell Mechanics Influences Cellular Invasion and Migration - Stephen T. Spagnol; Wei-Chun Lin; Elizabeth A. Booth; Benoit Ladoux; Hillard M. Lazarus; Kris Noel Dahl (Annals of Biomedical Engineering, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Single-locus enrichment without amplification for sequencing and direct detection of epigenetic modifications - Thang T. Pham; Jun Yin; John S. Eid; Evan Adams; Regina Lam; Stephen W. Turner; Erick W. Loomis; Jun Yi Wang; Paul J. Hagerman; Jeremiah W. Hanes (Molecular Genetics and Genomics, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Erratum to: Dissolution Similarity Requirements: How Similar or Dissimilar Are the Global Regulatory Expectations? - Dorys Argelia Diaz; Stephen T. Colgan; Connie S. Langer; Nagesh Bandi; Michael D. Likar; Leslie Van Alstine (The AAPS Journal, 2016)

Kisspeptin signaling in the amygdala modulates reproductive hormone secretion - Alexander N. Comninos; Jelena Anastasovska; Meliz Sahuri-Arisoylu; Xiaofeng Li; Shengyun Li; Minghan Hu; Channa N. Jayasena; Mohammad A. Ghatei; Stephen R. Bloom; Paul M. Matthews; Kevin T. O’Byrne; Jimmy D. Bell; et al. (Brain Structure and Function, 2016)

An ecoclimatic framework for evaluating the resilience of vegetation to water deficit - Patrick J. Mitchell; Anthony P. O'Grady; Elizabeth A. Pinkard; Timothy J. Brodribb; Stefan K. Arndt; Chris J. Blackman; Remko A. Duursma; Rod J. Fensham; David W. Hilbert; Craig R. Nitschke; Jaymie Norris; Stephen H. Roxburgh; et al. (Global Change Biology, 2016)
The surge in global efforts to understand the causes and consequences of drought on forest ecosystems has tended to focus on specific impacts such as mortality. We propose an ecoclimatic framework that takes a broader view of the ecological relevance of water deficits, linking elements of exposure and resilience to cumulative impacts on a range of ecosystem processes. This ecoclimatic framework is underpinned by two hypotheses: (i) exposure to water deficit can be represented probabilistically and used to estimate exposure thresholds across different vegetation types or ecosystems; and (ii) the cumulative impact of a series of water deficit events is defined by attributes governing the resistance and recovery of the affected processes. We present case studies comprising Pinus edulis and Eucalyptus globulus , tree species with contrasting ecological strategies, which demonstrate how links between exposure and resilience can be examined within our proposed framework. These examples reveal how climatic thresholds can be defined along a continuum of vegetation functional responses to water deficit regimes. The strength of this framework lies in identifying climatic thresholds on vegetation function in the absence of more complete mechanistic understanding, thereby guiding the formulation, application and benchmarking of more detailed modelling.

The differential effects of metronomic gemcitabine and antiangiogenic treatment in patient-derived xenografts of pancreatic cancer: treatment effects on metabolism, vascular function, cell proliferation, and tumor growth - Donald T. Yapp; May Q. Wong; Alastair H. Kyle; Shannon M. Valdez; Jenny Tso; Andrew Yung; Piotr Kozlowski; David A. Owen; Andrzej K. Buczkowski; Stephen W. Chung; Charles H. Scudamore; Andrew I. Minchinton; et al. (Angiogenesis, 2016)

Late Holocene expansion of ponderosa pine ( Pinus ponderosa ) in the Central Rocky Mountains, USA - Jodi R. Norris; Julio L. Betancourt; Stephen T. Jackson (Journal of Biogeography, 2016)
Aim Ponderosa pine ( Pinus ponderosa ) experienced one of the most extensive and rapid post‐glacial plant migrations in western North America. We used plant macrofossils from woodrat ( Neotoma ) middens to reconstruct its spread in the Central Rocky Mountains, identify other vegetation changes coinciding with P. ponderosa expansion at the same sites, and relate P. ponderosa migrational history to both its modern phylogeography and to a parallel expansion by Utah juniper ( Juniperus osteosperma ). Location Central Rocky Mountains, Wyoming and Montana, and Black Hills, Wyoming and South Dakota, USA . Methods Plant macrofossils were analysed in 90 middens collected at 14 widely separated sites in the northern part of the range of P. ponderosa var. scopulorum . Middens with and without P. ponderosa were 14 C dated to pinpoint time of appearance at each site. Sensitivity experiments using a bioclimatic model were used to evaluate potential climatic drivers of late Holocene expansion. Results Pinus ponderosa colonized the Black Hills region by at least 3850 yr bp (all ages given in calendar years before present). It expanded into the eastern Bighorn Mountains of northern Wyoming by 2630 yr bp , quickly spreading north in the western Bighorns from 1400 to 1000 yr bp . Concurrent with the latter expansion, P. ponderosa spread c . 350 km to the Little Belt and Big Belt Mountains in western Montana, establishing its northern limit and the modern introgression zone between var. scopulorum and var. ponderosa . Expansion in the Central Rockies of P. ponderosa involved two known haplotypes. Main conclusions Pinus ponderosa expanded its range across large parts of northern Wyoming and central Montana during the late Holocene, probably in response to both northward and westward increases in summer temperature and rainfall. The underlying climatic driver may be the same as for the contemporaneous expansion of J. osteosperma , but will remain undetermined without focused development and integration of independent palaeoclimate records in the region.

Quantifying the relative irreplaceability of important bird and biodiversity areas - Moreno Di Marco; Thomas Brooks; Annabelle Cuttelod; Lincoln D.C. Fishpool; Carlo Rondinini; Robert J. Smith; Leon Bennun; Stuart H.M. Butchart; Simon Ferrier; Ruud P.B. Foppen; Lucas Joppa; Diego Juffe‐Bignoli; et al. (Conservation Biology, 2016)
World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.

Portrayal of sustainability principles in the mission statements and on home pages of the world's largest organizations - Stephen T. Garnett; Michael J. Lawes; Robyn James; Kristen Bigland; Kerstin K. Zander (Conservation Biology, 2016)
Conservation can be achieved only if sustainability is embraced as core to organizational cultures. To test the extent to which the related concepts of sustainability, conservation, response to climate change, poverty alleviation, and gender equity have been incorporated into organizational culture, we compared mission statements published from 1990 to 2000 with those published in 2014 for 150 organzations, including conservation nongovernmental organizations (NGOs), aid NGOs, government development agencies, resource extraction companies, and retailers (30 in each category). We also analyzed the 2014 home web pages of each organization. Relative to the earlier period, the frequency with which mission statements mentioned poverty alleviation, biodiversity conservation, and a range of sustainable practices increased only slightly by 2014, particularly among resource extractors and retail companies. Few organizations in any sector had embedded either climate change or gender equity into their mission statements. In addition, the proportional intensity with which any of the aspirations were expressed did not change between periods. For current home pages, conservation NGOs, resource extractors, and government agencies were significantly more likely to acknowledge the importance of matters that were not part of their core business, but few aid agencies or retail companies promoted goals beyond alleviation of crises and profit maximization, respectively. Overall, there has been some progress in recognizing poverty alleviation, biodiversity conservation, and sustainable practices, but gender equity and a determination to reduce impacts on climate change are still rarely promoted as central institutional concerns. Sustainability in general, and biodiversity conservation in particular, will not be achieved unless their importance is more widely apparent in core communication products of organizations.

Value of intelligence applied to networks - Christopher M. Smith; William T. Scherer; Stephen Carr (Environment Systems and Decisions, 2016)

Dissolution Similarity Requirements: How Similar or Dissimilar Are the Global Regulatory Expectations? - Dorys Argelia Diaz; Stephen T. Colgan; Connie S. Langer; Nagesh T. Bandi; Michael D. Likar; Leslie Van Alstine (The AAPS Journal, 2016)

Organic and inorganic mercurials have distinct effects on cellular thiols, metal homeostasis, and Fe-binding proteins in Escherichia coli - Stephen P. LaVoie; Daphne T. Mapolelo; Darin M. Cowart; Benjamin J. Polacco; Michael K. Johnson; Robert A. Scott; Susan M. Miller; Anne O. Summers (JBIC Journal of Biological Inorganic Chemistry, 2015)

Population genetic structure at the northern range limit of the threatened eastern hog-nosed snake (Heterodon platirhinos) - Amanda T. J. Xuereb; Jeremy D. Rouse; Glenn Cunnington; Stephen C. Lougheed (Conservation Genetics, 2015)

A reply to ‘A meta-database of Holocene sediment cores for England: missing data’ (Tooley 2015) - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

A meta-database of Holocene sediment cores for England - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

Expression and function of the epithelial sodium channel δ-subunit in human respiratory epithelial cells in vitro - Elena Schwagerus; Svenja Sladek; Stephen T. Buckley; Natalia Armas-Capote; Diego Alvarez de la Rosa; Brian J. Harvey; Horst Fischer; Beate Illek; Hanno Huwer; Nicole Schneider-Daum; Claus-Michael Lehr; Carsten Ehrhardt (Pflügers Archiv - European Journal of Physiology, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

A Pilot Study of Gait Function in Farmworkers in Eastern North Carolina - Ha T. Nguyen; Stephen B. Kritchevsky; Judy L. Foxworth; Sara A. Quandt; Phillip Summers; Francis O. Walker; Thomas A. Arcury (Journal of Agromedicine, 2015)

Maternal hypertension programs increased cerebral tissue damage following stroke in adult offspring - Nicole M. Ventura; Albert Y. Jin; M. Yat Tse; Nichole T. Peterson; R. David Andrew; Jeffrey D. Mewburn; Stephen C. Pang (Molecular and Cellular Biochemistry, 2015)

The contribution of sensory nerves to cutaneous vasodilatation of the forearm and leg to local skin heating - Gary J. Hodges; Andrew T. Del Pozzi; Gregory W. McGarr; Matthew M. Mallette; Stephen S. Cheung (European Journal of Applied Physiology, 2015)

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

Developing Critical Loads of Nitrate and Sulfate Deposition to Watersheds of the Great Smoky Mountains National Park, USA - Qingtao Zhou; Charles T. Driscoll; Stephen E. Moore; Matt A. Kulp; James R. Renfro; John S. Schwartz; Meijun Cai; Jason A. Lynch (Water, Air, & Soil Pollution, 2015)

Erratum to: The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

Genetic analysis and phenotypic characterization of leaf photosynthetic capacity in a sorghum (Sorghum spp.) diversity panel - Maria G. Salas Fernandez; Katie Strand; Martha T. Hamblin; Mark Westgate; Emily Heaton; Stephen Kresovich (Genetic Resources and Crop Evolution, 2015)

In Vitro, Pharmacokinetic, Pharmacodynamic, and Safety Comparisons of Single and Combined Administration of Tiotropium and Salmeterol in COPD Patients Using Different Dry Powder Inhalers - Stephen T. Horhota; Jan A. van Noord; Cynthia B. Verkleij; Loek J. Bour; Ashish Sharma; Michael Trunk; Piet J. G. Cornelissen (The AAPS Journal, 2015)

Diverse phenotypic consequences of mutations affecting the C-terminus of FLNA - Margriet van Kogelenberg; Alice R. Clark; Zandra Jenkins; Tim Morgan; Ananda Anandan; Gregory M. Sawyer; Matthew Edwards; Tracy Dudding; Tessa Homfray; Bruce Castle; John Tolmie; Fiona Stewart; et al. (Journal of Molecular Medicine, 2015)

Genetic signatures indicate widespread antibiotic resistance and phage infection in microbial communities of the McMurdo Dry Valleys, East Antarctica - Sean T. S. Wei; Colleen M. Higgins; Evelien M. Adriaenssens; Don A. Cowan; Stephen B. Pointing (Polar Biology, 2015)

The Domain II S4-S5 Linker in Nav1.9: A Missense Mutation Enhances Activation, Impairs Fast Inactivation, and Produces Human Painful Neuropathy - Chongyang Han; Yang Yang; Bianca T. A. de Greef; Janneke G. J. Hoeijmakers; Monique M. Gerrits; Camiel Verhamme; Jian Qu; Giuseppe Lauria; Ingemar S. J. Merkies; Catharina G. Faber; Sulayman D. Dib-Hajj; Stephen G. Waxman (NeuroMolecular Medicine, 2015)

The Role and Value of Conservation Agency Research - Dirk J. Roux; Richard T. Kingsford; Stephen F. McCool; Melodie A. McGeoch; Llewellyn C. Foxcroft (Environmental Management, 2015)

Heterogeneity of Mitral Leaflet Matrix Composition and Turnover Correlates with Regional Leaflet Strain - Elizabeth H. Stephens; Patrick S. Connell; Monica M. Fahrenholtz; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Cellular and Extracellular Matrix Basis for Heterogeneity in Mitral Annular Contraction - Elizabeth H. Stephens; Monica M. Fahrenholtz; Patrick S. Connell; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Pharmacodynamic Studies to Demonstrate Bioequivalence of Oral Inhalation Products - Leslie Hendeles; Peter T. Daley-Yates; Robert Hermann; Jan De Backer; Sanjeeva Dissanayake; Stephen T. Horhota (The AAPS Journal, 2015)

Dietary supplementation of β-guanidinopropionic acid (βGPA) reduces whole-body and skeletal muscle growth in young CD-1 mice - Bradley L. Baumgarner; Alison M. Nagle; Meagan R. Quinn; A. Elaine Farmer; Stephen T. Kinsey (Molecular and Cellular Biochemistry, 2015)

Diverse metabolic and stress-tolerance pathways in chasmoendolithic and soil communities of Miers Valley, McMurdo Dry Valleys, Antarctica - Sean T. S. Wei; Miguel-Angel Fernandez-Martinez; Yuki Chan; Joy D. Van Nostrand; Asuncion de los Rios-Murillo; Jill M. Y. Chiu; Annapoorna Maitrayee Ganeshram; S. Craig Cary; Jizhong Zhou; Stephen B. Pointing (Polar Biology, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Reply to Comment on “The role of interbasin groundwater transfers in geologically complex terranes, demonstrated by the Great Basin in the western United States”: report published in Hydrogeology Journal (2014) 22:807–828 by Stephen T. Nelson and Alan L. Mayo - Stephen T. Nelson; Alan L. Mayo (Hydrogeology Journal, 2015)

The application of maximal heart rate predictive equations in hypoxic conditions - Carla A. Gallagher; Mark E. T. Willems; Mark P. Lewis; Stephen D. Myers (European Journal of Applied Physiology, 2015)

Molecular adaptations in vasoactive systems during acute stroke in salt-induced hypertension - Nicole M. Ventura; Nichole T. Peterson; M. Yat Tse; R. David Andrew; Stephen C. Pang; Albert Y. Jin (Molecular and Cellular Biochemistry, 2015)

Paisang (Quercus griffithii): A Keystone Tree Species in Sustainable Agroecosystem Management and Livelihoods in Arunachal Pradesh, India - Ranjay K. Singh; Anshuman Singh; Stephen T. Garnett; Kerstin K. Zander; Lobsang; Darge Tsering (Environmental Management, 2015)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Opportunities for Lean Stability Strategies - Stephen T. Colgan; Robert J. Timpano; Matthew Roberts; Roger Weaver; Kevin Ryan; Kevin W. Fields; Garry Scrivens (Journal of Pharmaceutical Innovation, 2014)

Plasma Cytokine Levels are Related to Brain Volumes in HIV-infected Individuals - Assawin Gongvatana; Stephen Correia; Shira Dunsiger; Lynne Gauthier; Kathryn N. Devlin; Skye Ross; Bradford Navia; Karen T. Tashima; Suzanne DeLaMonte; Ronald A. Cohen (Journal of Neuroimmune Pharmacology, 2014)

Urinary bisphenol A-glucuronide and postmenopausal breast cancer in Poland - Britton Trabert; Roni T. Falk; Jonine D. Figueroa; Barry I. Graubard; Montserrat Garcia-Closas; Jolanta Lissowska; Beata Peplonska; Stephen D. Fox; Louise A. Brinton (Cancer Causes & Control, 2014)

Phenotypic variation in shell form in the intertidal acorn barnacle Chthamalus montagui: distribution, response to predators and life history trade-offs - Jefferson Murua; Michael T. Burrows; Roger N. Hughes; Stephen J. Hawkins; Richard C. Thompson; Stuart R. Jenkins (Marine Biology, 2014)

Prolonged isolation and persistence of a common endemic on granite outcrops in both mesic and semi‐arid environments in south‐western Australia - Sarah‐Louise Tapper; Margaret Byrne; Colin J. Yates; Gunnar Keppel; Stephen D. Hopper; Kimberly Van Niel; Antonius G. T. Schut; Laco Mucina; Grant W. Wardell‐Johnson (Journal of Biogeography, 2014)
Aim Granite outcrops may be able to act as refugia for species during adverse climate change, owing to their topographic complexity. We assessed this hypothesis by examining phylogeographical patterns in a common, geographically widespread granite endemic, Stypandra glauca (Hemerocallidaceae). Location Granite outcrops of the Southwest Australian Floristic Region, Western Australia. Methods Twenty‐four tetraploid individuals of the granite endemic Stypandra glauca were sampled from each of 12 granite outcrops: 7 from a mesic environment and 5 from the semi‐arid region. Phylogenetic reconstruction and divergence‐dating was achieved using Bayesian and parsimony analyses of chloroplast haplotypes from 90 individuals. Nuclear diversity and population differentiation were analysed across all individuals using 10 microsatellite loci. Results Stypandra glauca exhibited high (chloroplast) or moderate (nuclear) levels of divergence among, and low diversity within, outcrops. Haplotype diversity was high in both sampling regions, and each haplotype was unique to one outcrop. There was little correlation between geographical and genetic distance. Both nuclear and chloroplast diversity were higher in southern (mesic) outcrops than in northern (semi‐arid) outcrops, although the level of chloroplast divergence among outcrops was similar for both climatic regions. Main conclusions The levels of divergence and low diversity revealed in S. glauca support a scenario of prolonged isolation and persistence on granite outcrops in both mesic and semi‐arid climatic regions, with no evidence of contraction–expansion dynamics across the outcrop network. The higher levels of diversity in the southern populations may result from the maintenance of a larger effective population size in southern regions, which retained more mesic climates during drier glacial periods. Although the climatic conditions differ between outcrops in this study, our results indicate that outcrops in both regions have harboured S. glauca throughout climatic changes, accentuating the value of these habitats to biodiversity conservation under future changing climate.

Microscale sulfur cycling in the phototrophic pink berry consortia of the S ippewissett S alt M arsh - Elizabeth G. Wilbanks; Ulrike Jaekel; Verena Salman; Parris T. Humphrey; Jonathan A. Eisen; Marc T. Facciotti; Daniel H. Buckley; Stephen H. Zinder; Gregory K. Druschel; David A. Fike; Victoria J. Orphan (Environmental Microbiology, 2014)
Summary Microbial metabolism is the engine that drives global biogeochemical cycles, yet many key transformations are carried out by microbial consortia over short spatiotemporal scales that elude detection by traditional analytical approaches. We investigate syntrophic sulfur cycling in the ‘pink berry’ consortia of the S ippewissett S alt M arsh through an integrative study at the microbial scale. The pink berries are macroscopic, photosynthetic microbial aggregates composed primarily of two closely associated species: sulfide‐oxidizing purple sulfur bacteria ( PB ‐ PSB 1) and sulfate‐reducing bacteria ( PB ‐ SRB 1). Using metagenomic sequencing and 34 S ‐enriched sulfate stable isotope probing coupled with nanoSIMS , we demonstrate interspecies transfer of reduced sulfur metabolites from PB ‐ SRB 1 to PB ‐ PSB 1. The pink berries catalyse net sulfide oxidation and maintain internal sulfide concentrations of 0–500 μ m . Sulfide within the berries, captured on silver wires and analysed using secondary ion mass spectrometer, increased in abundance towards the berry interior, while δ 34 S‐ sulfide decreased from 6‰ to −31‰ from the exterior to interior of the berry. These values correspond to sulfate–sulfide isotopic fractionations (15–53‰) consistent with either sulfate reduction or a mixture of reductive and oxidative metabolisms. Together this combined metagenomic and high‐resolution isotopic analysis demonstrates active sulfur cycling at the microscale within well‐structured macroscopic consortia consisting of sulfide‐oxidizing anoxygenic phototrophs and sulfate‐reducing bacteria.

Consideration of a comprehensive animal model of addiction: the limitations of modeling a counterfeit condition - Stephen T. Tiffany (Psychopharmacology, 2014)

GFR may not accurately predict aspects of proximal tubule drug handling - T. L. Putt; Stephen B. Duffull; J. B. W. Schollum; R. J. Walker (European Journal of Clinical Pharmacology, 2014)

Effect of age and disturbance on decadal changes in carbon stocks in managed forest landscapes in central Canada - Michael T. Ter-Mikaelian; Stephen J. Colombo; Jiaxin Chen (Mitigation and Adaptation Strategies for Global Change, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Changing forest water yields in response to climate warming: results from long‐term experimental watershed sites across North America - Irena F. Creed; Adam T. Spargo; Julia A. Jones; Jim M. Buttle; Mary B. Adams; Fred D. Beall; Eric G. Booth; John L. Campbell; Dave Clow; Kelly Elder; Mark B. Green; Nancy B. Grimm; et al. (Global Change Biology, 2014)
Climate warming is projected to affect forest water yields but the effects are expected to vary. We investigated how forest type and age affect water yield resilience to climate warming. To answer this question, we examined the variability in historical water yields at long‐term experimental catchments across Canada and the United States over 5‐year cool and warm periods. Using the theoretical framework of the Budyko curve, we calculated the effects of climate warming on the annual partitioning of precipitation ( P ) into evapotranspiration ( ET ) and water yield. Deviation ( d ) was defined as a catchment's change in actual ET divided by P [ AET / P ; evaporative index ( EI )] coincident with a shift from a cool to a warm period – a positive d indicates an upward shift in EI and smaller than expected water yields, and a negative d indicates a downward shift in EI and larger than expected water yields. Elasticity was defined as the ratio of interannual variation in potential ET divided by P ( PET / P ; dryness index) to interannual variation in the EI – high elasticity indicates low d despite large range in drying index (i.e., resilient water yields), low elasticity indicates high d despite small range in drying index (i.e., nonresilient water yields). Although the data needed to fully evaluate ecosystems based on these metrics are limited, we were able to identify some characteristics of response among forest types. Alpine sites showed the greatest sensitivity to climate warming with any warming leading to increased water yields. Conifer forests included catchments with lowest elasticity and stable to larger water yields. Deciduous forests included catchments with intermediate elasticity and stable to smaller water yields. Mixed coniferous/deciduous forests included catchments with highest elasticity and stable water yields. Forest type appeared to influence the resilience of catchment water yields to climate warming, with conifer and deciduous catchments more susceptible to climate warming than the more diverse mixed forest catchments.

Cimetidine, acetaminophen, and 1,7-dimethylxanthine, as indicators of wastewater pollution in marine sediments from Masan Bay, Korea - Minkyu Choi; Edward T. Furlong; Stephen L. Werner; Anthony S. Pait; In-Seok Lee; Hee-Gu Choi (Ocean Science Journal, 2014)

Beef cattle body temperature during climatic stress: a genome-wide association study - Jeremy T. Howard; Stephen D. Kachman; Warren M. Snelling; E. John Pollak; Daniel C. Ciobanu; Larry A. Kuehn; Matthew L. Spangler (International Journal of Biometeorology, 2014)

Relaxed selection causes microevolution of seawater osmoregulation and gene expression in landlocked Alewives - Jonathan P. Velotta; Stephen D. McCormick; Rachel J. O’Neill; Eric T. Schultz (Oecologia, 2014)

Effect of acute normobaric hypoxia on the ventilatory threshold - Carla A. Gallagher; Mark E. T. Willems; Mark P. Lewis; Stephen D. Myers (European Journal of Applied Physiology, 2014)

Expression of a wolf spider toxin in tobacco inhibits the growth of microbes and insects - Eric T. Johnson; Patrick F. Dowd; Stephen R. Hughes (Biotechnology Letters, 2014)

Multiple factors determine the effect of anthropogenic barriers to connectivity on riverine fish - Robert J. Rolls; Ben Stewart-Koster; Tanya Ellison; Stephen Faggotter; David T. Roberts (Biodiversity and Conservation, 2014)

Conflicting natural and anthropogenic threats reduce nest success in centrarchid fishes - Stephen M. Selego; George T. Merovich; James T. Anderson (Hydrobiologia, 2014)

Creating new evolutionary pathways through bioinvasion: the population genetics of brushtail possums in N ew Z ealand - Stephen D. Sarre; Nicola Aitken; Aaron T. Adamack; Anna J. MacDonald; Bernd Gruber; Phil Cowan (Molecular Ecology, 2014)
Rapid increases in global trade and human movement have created novel mixtures of organisms bringing with them the potential to rapidly accelerate the evolution of new forms. The common brushtail possum ( T richosurus vulpecula ), introduced into N ew Z ealand from A ustralia in the 19th century, is one such species having been sourced from multiple populations in its native range. Here, we combine microsatellite DNA ‐ and GIS ‐based spatial data to show that T . vulpecula originating from at least two different Australian locations exhibit a population structure that is commensurate with their introduction history and which cannot be explained by landscape features alone. Most importantly, we identify a hybrid zone between the two subspecies which appears to function as a barrier to dispersal. When combined with previous genetic, morphological and captive studies, our data suggest that assortative mating between the two subspecies may operate at a behavioural or species recognition level rather than through fertilization, genetic incompatibility or developmental inhibition. Nevertheless, hybridization between the two subspecies of possum clearly occurs, creating the opportunity for novel genetic combinations that would not occur in their natural ranges and which is especially likely given that multiple contact zones occur in N ew Z ealand. This discovery has implications for wildlife management in N ew Z ealand because multiple contact zones are likely to influence the dispersal patterns of possums and because differential susceptibility to baiting with sodium fluoroacetate between possums of different origins may promote novel genetic forms.

Wetland Ecosystem Response to Hydrologic Restoration and Management: The Everglades and its Urban-Agricultural Boundary (FL, USA) - Pamela L. Sullivan; Evelyn E. Gaiser; Donatto Surratt; David T. Rudnick; Stephen E. Davis; Fred H. Sklar (Wetlands, 2014)

The role of interbasin groundwater transfers in geologically complex terranes, demonstrated by the Great Basin in the western United States - Stephen T. Nelson; Alan L. Mayo (Hydrogeology Journal, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Examining the effects of initial smoking abstinence on response to smoking-related stimuli and response inhibition in a human laboratory model - Matthew P. Bradstreet; Stephen T. Higgins; F. Joseph McClernon; Rachel V. Kozink; Joan M. Skelly; Yukiko Washio; Alexa A. Lopez; Marie A. Parry (Psychopharmacology, 2014)

Effectiveness of ecosystem-based approaches for adaptation: review of the evidence-base - N. Doswald; R. Munroe; D. Roe; A. Giuliani; I. Castelli; J. Stephens; I. Möller; T. Spencer; B. Vira; H. Reid (Climate and Development, 2014)

Quantification of Vibrio vulnificus in an Estuarine Environment: a Multi-Year Analysis Using QPCR - Jennifer J. Wetz; A. Denene Blackwood; J. Stephen Fries; Zachary F. Williams; Rachel T. Noble (Estuaries and Coasts, 2014)

New microsatellite loci for the threatened eastern hog-nosed snake (Heterodon platirhinos) in Ontario, Canada - Amanda T. J. Xuereb; James D. Austin; Stephen C. Lougheed (Conservation Genetics Resources, 2014)

Mapping bedrock lithologies through in situ regolith using retained element ratios: a case study from the Agnew-Lawlers area, Western Australia - Stephen J. Barnes; L. A. Fisher; R. Anand; T. Uemoto (Australian Journal of Earth Sciences, 2014)

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

The equine CD1 gene family is the largest and most diverse yet identified - Robson G. Dossa; Debra C. Alperin; Melissa T. Hines; Stephen A. Hines (Immunogenetics, 2014)

Integrated stratigraphy and palaeoenvironment of the P/E boundary interval, Rakhi Nala section, Indus Basin (Pakistan) - Muhammad Hanif; Malcolm B. Hart; Stephen T. Grimes; Melanie J. Leng (Arabian Journal of Geosciences, 2014)

Fertilization and plant diversity accelerate primary succession and restoration of dune communities - Zachary T. Long; Stephen R. Fegley; Charles H. Peterson (Plant Ecology, 2013)

Maternal Care, Iteroparity and the Evolution of Social Behavior: A Critique of the Semelparity Hypothesis - Stephen T. Trumbo (Evolutionary Biology, 2013)

The Threat of Disease Increases as Species Move Toward Extinction - MATTHEW J. HEARD; KATHERINE F. SMITH; KELSEY J. RIPP; MELANIE BERGER; JANE CHEN; JUSTIN DITTMEIER; MAGGIE GOTER; STEPHEN T. MCGARVEY; ELIZABETH RYAN (Conservation Biology, 2013)
At local scales, infectious disease is a common driver of population declines, but globally it is an infrequent contributor to species extinction and endangerment. For species at risk of extinction from disease important questions remain unanswered, including when does disease become a threat to species and does it co‐occur, predictably, with other threats? Using newly compiled data from the International Union for Conservation of Nature (IUCN) Red List, we examined the relative role and co‐occurrence of threats associated with amphibians, birds, and mammals at 6 levels of extinction risk (i.e., Red List status categories: least concern, near threatened, vulnerable, endangered, critically endangered, and extinct in the wild/extinct). We tested the null hypothesis that the proportion of species threatened by disease is the same in all 6 Red List status categories. Our approach revealed a new method for determining when disease most frequently threatens species at risk of extinction. The proportion of species threatened by disease varied significantly between IUCN status categories and linearly increased for amphibians, birds, and all species combined as these taxa move from move from least concern to critically endangered. Disease was infrequently the single contributing threat. However, when a species was negatively affected by a major threat other than disease (e.g., invasive species, land‐use change) that species was more likely to be simultaneously threatened by disease than species that had no other threats. Potential drivers of these trends include ecological factors, clustering of phylogenetically related species in Red List status categories, discovery bias among species at greater risk of extinction, and availability of data. We echo earlier calls for baseline data on the presence of parasites and pathogens in species when they show the first signs of extinction risk and arguably before. La Amenaza de Enfermedades Incrementa a Medida que las Especies se Aproximan a la Extinción

Biodiversity Offsets and the Challenge of Achieving No Net Loss - TOBY A. GARDNER; AMREI VON HASE; SUSIE BROWNLIE; JONATHAN M. M. EKSTROM; JOHN D. PILGRIM; CONRAD E. SAVY; R. T. THEO STEPHENS; JO TREWEEK; GRAHAM T. USSHER; GERRI WARD; KERRY TEN KATE (Conservation Biology, 2013)
Businesses, governments, and financial institutions are increasingly adopting a policy of no net loss of biodiversity for development activities. The goal of no net loss is intended to help relieve tension between conservation and development by enabling economic gains to be achieved without concomitant biodiversity losses. biodiversity offsets represent a necessary component of a much broader mitigation strategy for achieving no net loss following prior application of avoidance, minimization, and remediation measures. However, doubts have been raised about the appropriate use of biodiversity offsets. We examined what no net loss means as a desirable conservation outcome and reviewed the conditions that determine whether, and under what circumstances, biodiversity offsets can help achieve such a goal. We propose a conceptual framework to substitute the often ad hoc approaches evident in many biodiversity offset initiatives. The relevance of biodiversity offsets to no net loss rests on 2 fundamental premises. First, offsets are rarely adequate for achieving no net loss of biodiversity alone. Second, some development effects may be too difficult or risky, or even impossible, to offset. To help to deliver no net loss through biodiversity offsets, biodiversity gains must be comparable to losses, be in addition to conservation gains that may have occurred in absence of the offset, and be lasting and protected from risk of failure. Adherence to these conditions requires consideration of the wider landscape context of development and offset activities, timing of offset delivery, measurement of biodiversity, accounting procedures and rule sets used to calculate biodiversity losses and gains and guide offset design, and approaches to managing risk. Adoption of this framework will strengthen the potential for offsets to provide an ecologically defensible mechanism that can help reconcile conservation and development. Balances de Biodiversidad y el Reto de No Obtener Pérdida Neta

Testing the Effects of Constraints on Climate Change–Friendly Behavior among Groups of Australian Residents - Jee In Yoon; Gerard T. Kyle; Carena J. van Riper; Stephen G. Sutton (Coastal Management, 2013)

Top‐down control of soil fungal community composition by a globally distributed keystone consumer - Thomas W. Crowther; David W. G. Stanton; Stephen M. Thomas; A. Donald A'Bear; Jennifer Hiscox; T. Hefin Jones; Jana Voříšková; Petr Baldrian; Lynne Boddy (Ecology, 2013)
The relative contribution of top‐down and bottom‐up processes regulating primary decomposers can influence the strength of the link between the soil animal community and ecosystem functioning. Although soil bacterial communities are regulated by bottom‐up and top‐down processes, the latter are considered to be less important in structuring the diversity and functioning of fungal‐dominated ecosystems. Despite the huge diversity of mycophagous (fungal‐feeding) soil fauna, and their potential to reverse the outcomes of competitive fungal interactions, top‐down grazing effects have never been found to translate to community‐level changes. We constructed soil mesocosms to investigate the potential of isopods grazing on cord‐forming basidiomycete fungi to influence the community composition and functioning of a complex woodland soil microbial community. Using metagenomic sequencing we provide conclusive evidence of direct top‐down control at the community scale in fungal‐dominated woodland soil. By suppressing the dominant cord‐forming basidiomycete fungi, isopods prevented the competitive exclusion of surrounding litter fungi, increasing diversity in a community containing several hundred fungal species. This isopod‐induced modification of community composition drove a shift in the soil enzyme profile, and led to a restructuring of the wider mycophagous invertebrate community. We highlight characteristics of different soil ecosystems that will give rise to such top‐down control. Given the ubiquity of isopods and basidiomycete fungi in temperate and boreal woodland ecosystems, such top‐down community control could be of widespread significance for global carbon and nutrient cycling.

A combined geological, hydrochemical, and geophysical approach to understanding a disease contamination hazard in groundwaters at a state fish hatchery - Alan L. Mayo; Stephen T. Nelson; John H. McBride; Camille Durrant Mease; David G. Tingey; Dan Aubrey (Natural Hazards, 2013)

Cardiac glutaminolysis: a maladaptive cancer metabolism pathway in the right ventricle in pulmonary hypertension - Lin Piao; Yong-Hu Fang; Kishan Parikh; John J. Ryan; Peter T. Toth; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Suppressed recovery of plant community composition and biodiversity on dredged fill of a hurricane-induced inlet through a barrier island - Zachary T. Long; Stephen R. Fegley; Charles H. Peterson (Journal of Coastal Conservation, 2013)

Epigenomic association analysis identifies smoking-related DNA methylation sites in African Americans - Yan V. Sun; Alicia K. Smith; Karen N. Conneely; Qiuzhi Chang; Weiyan Li; Alicia Lazarus; Jennifer A. Smith; Lynn M. Almli; Elisabeth B. Binder; Torsten Klengel; Dorthie Cross; Stephen T. Turner; et al. (Human Genetics, 2013)

Does increasing the spatial resolution of a regional climate model improve the simulated daily precipitation? - Steven C. Chan; Elizabeth J. Kendon; Hayley J. Fowler; Stephen Blenkinsop; Christopher A. T. Ferro; David B. Stephenson (Climate Dynamics, 2013)

Fluvial trace fossils in the Middle Siwalik (Sarmatian-Pontian) of Darjeeling Himalayas, India - ABHIJIT CHAKRABORTY; STEPHEN T HASIOTIS; BHASKAR GHOSH; HARENDRA NATH BHATTACHARYA (Journal of Earth System Science, 2013)

Plant functional types and traits as biodiversity indicators for tropical forests: two biogeographically separated case studies including birds, mammals and termites - Andrew N. Gillison; David E. Bignell; Kenneth R. W. Brewer; Erick C. M. Fernandes; David T. Jones; Douglas Sheil; Peter H. May; Allan D. Watt; Reginaldo Constantino; Eduardo G. Couto; Kurniatun Hairiah; Paul Jepson; et al. (Biodiversity and Conservation, 2013)

Paths to selection on life history loci in different natural environments across the native range of A rabidopsis thaliana - Alexandre Fournier‐Level; Amity M. Wilczek; Martha D. Cooper; Judith L. Roe; Jillian Anderson; Deren Eaton; Brook T. Moyers; Renee H. Petipas; Robert N. Schaeffer; Bjorn Pieper; Matthieu Reymond; Maarten Koornneef; et al. (Molecular Ecology, 2013)
Selection on quantitative trait loci ( QTL ) may vary among natural environments due to differences in the genetic architecture of traits, environment‐specific allelic effects or changes in the direction and magnitude of selection on specific traits. To dissect the environmental differences in selection on life history QTL across climatic regions, we grew a panel of interconnected recombinant inbred lines ( RIL s) of Arabidopsis thaliana in four field sites across its native European range. For each environment, we mapped QTL for growth, reproductive timing and development. Several QTL were pleiotropic across environments, three colocalizing with known functional polymorphisms in flowering time genes ( CRY 2 , FRI and MAF 2‐5 ), but major QTL differed across field sites, showing conditional neutrality. We used structural equation models to trace selection paths from QTL to lifetime fitness in each environment. Only three QTL directly affected fruit number, measuring fitness. Most QTL had an indirect effect on fitness through their effect on bolting time or leaf length. Influence of life history traits on fitness differed dramatically across sites, resulting in different patterns of selection on reproductive timing and underlying QTL . In two oceanic field sites with high prereproductive mortality, QTL alleles contributing to early reproduction resulted in greater fruit production, conferring selective advantage, whereas alleles contributing to later reproduction resulted in larger size and higher fitness in a continental site. This demonstrates how environmental variation leads to change in both QTL effect sizes and direction of selection on traits, justifying the persistence of allelic polymorphism at life history QTL across the species range.

Quantifying the production of dissolved organic nitrogen in headwater streams using 15 N tracer additions - Laura T. Johnson; Jennifer L. Tank; Robert O. Hall, Jr.; Patrick J. Mulholland; Stephen K. Hamilton; H. Maurice Valett; Jackson R. Webster; Melody J. Bernot; William H. McDowell; Bruce J. Peterson; Suzanne M. Thomas (Limnology and Oceanography, 2013)
Most nitrogen (N) assimilation in lake and marine ecosystems is often subsequently released via autochthonous dissolved organic nitrogen (DON) production, but autochthonous DON production has yet to be quantified in flowing waters. We measured in‐stream DON production following 24 h 15 N‐nitrate () tracer additions in 36 headwater streams, a subset of sites from the second Lotic Intersite Nitrogen eXperiment. Streams were located in five North American ecoregions and drained basins dominated by native vegetation, agriculture, or urban land use. Using a two‐compartment model, we could quantify DON production in 15 streams as a function of DO 15 N derived from 15 N tracer in biomass compartments. The streams with detectable DON production had higher % modified land use (agriculture + urban) in their basins than did streams with undetectable DON production. Median DON production represented 8% of total uptake when we used N biomass estimates based on N assimilated over 1 d (measured directly from the 15 N additions). Median DON production was 17% of total uptake when we used N assimilated over 42 d (extrapolated from previous 15 N tracer studies). Variation in DON production was positively correlated with ecosystem respiration, indicating that stream heterotrophy may influence DON production. In‐stream DON production was similar in magnitude to stream denitrification and nitrification, indicating that the production of autochthonous DON can represent a substantial transformation of stream N. Our results confirm that headwater streams can quickly convert inorganic N into organic forms, although the ultimate fate of DON remains unclear.

Stay or leave? Potential climate change adaptation strategies among Aboriginal people in coastal communities in northern Australia - Kerstin K. Zander; Lisa Petheram; Stephen T. Garnett (Natural Hazards, 2013)

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Cryptic phenotypic plasticity in populations of the freshwater prosobranch snail, Pleurocera canaliculata - Robert T. Dillon; Stephen J. Jacquemin; Mark Pyron (Hydrobiologia, 2013)

Association of germline microRNA SNPs in pre-miRNA flanking region and breast cancer risk and survival: the Carolina Breast Cancer Study - Jeannette T. Bensen; Chiu Kit Tse; Sarah J. Nyante; Jill S. Barnholtz-Sloan; Stephen R. Cole; Robert C. Millikan (Cancer Causes & Control, 2013)

Development and characterization of an exposure generation system to investigate the health effects of particles from fresh and aged traffic emissions - Vasileios Papapostolou; Joy E. Lawrence; Stephen T. Ferguson; Jack M. Wolfson; Edgar A. Diaz; John J. Godleski; Petros Koutrakis (Air Quality, Atmosphere & Health, 2013)

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Modelling the effects of dispersal mechanisms and hydrodynamic regimes upon the structure of microbial communities within fluvial biofilms - Stephen Woodcock; Katharina Besemer; Tom J. Battin; Thomas P. Curtis; William T. Sloan (Environmental Microbiology, 2013)
Summary The spatial distribution of microbial taxa is determined primarily by physical and chemical environments and by dispersal. In a homogeneous landscape with limited dispersal, the similarity in abundance of taxa in samples declines with separation distance. We present a one‐dimensional model for the spatial autocorrelation in abundances arising from immigration from some remote community and dispersal between environmentally similar landscape patches. Spatial correlation in taxa abundances were calculated from biofilms from the beds of two flumes which differed only in their bedform profiles; one flat and the other a periodic sawtooth shape. The hydraulic regime is approximately uniform over the flat bed, whereas the sawtooth induces fast flow over the peaks and recirculation in the troughs. On the flat bed, the correlation decline between samples was reproduced by a model using one biologically reasonable parameter. A decline was apparent in the other flume; however, a better fit was achieved when dispersal was not assumed constant everywhere. However, analysis of finer‐resolution data for the heterogeneous flume suggested even this model did not adequately capture the community's complexity. We conclude that hydrodynamics are a strong driver of taxa‐abundance patterns in stream biofilms. However, local adaptability must also be considered to build up a complete mechanistic model.

QTL involved in the modification of cyanidin compounds in black and red raspberry fruit - J. M. Bushakra; C. Krieger; D. Deng; M. J. Stephens; A. C. Allan; R. Storey; V. V. Symonds; D. Stevenson; T. McGhie; D. Chagné; E. J. Buck; S. E. Gardiner (Theoretical and Applied Genetics, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Intertidal habitat composition and regional-scale shoreline morphology along the Benguela coast - Linda Harris; Stephen Holness; Ronel Nel; Amanda T. Lombard; David Schoeman (Journal of Coastal Conservation, 2013)

Polysaccharides of Dendrobium officinale inhibit TNF-α-induced apoptosis in A-253 cell line - L. Xiang; C. W. Stephen Sze; T. B. Ng; Y. Tong; P. C. Shaw; C. W. Sydney Tang; Y. B. Kalin Zhang (Inflammation Research, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Development of microsatellite loci for the western slimy salamander (Plethodon albagula) using 454 sequencing - Brett N. Spatola; William E. Peterman; Nathan T. Stephens; Grant M. Connette; Donald B. Shepard; Kenneth H. Kozak; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics Resources, 2013)

Zooplankton provide early warnings of a regime shift in a whole lake manipulation - Michael L. Pace; Stephen R. Carpenter; Robert A. Johnson; Jason T. Kurtzweil (Limnology and Oceanography, 2013)
Regime shifts are massive changes among alternate ecosystem states. Predicting regime shifts is difficult, but statistical indicators such as increasing variance or autocorrelation may provide early warnings of their impending onset. We conducted a 4 yr lake manipulation to test for early warnings prior to a food‐web transition by adding largemouth bass ( Micropterus salmoides ) to a lake dominated by small fishes, and thereby drive a trophic cascade that altered zooplankton biomass, community composition, and body size. Declining catches of small fishes were associated with shifts to larger bodied species of Daphnia . We measured zooplankton biomass daily in a reference and manipulated lake and calculated variance and autocorrelation of the zooplankton time series using 28 d rolling windows. We asked whether the variance in the manipulated lake (relative to the reference lake) increased and whether autocorrelation approached unity (a value suggested by theory) prior to the food‐web regime shift. The variance and autocorrelation of zooplankton biomass were similar between the two lakes in the first 2 yr of the manipulation. During the third year, variance was much higher and autocorrelation approached unity for sustained periods in the manipulated but not in the reference lake. Variance and autocorrelation were similar between the two lakes during the fourth year as the food‐web transition moved to completion. The joint response of variance and autocorrelation in year 3 provided an early warning of the food‐web transition consistent with theoretical expectation.

Contributions of long‐distance dispersal to population growth in colonising Pinus ponderosa populations - Mark R. Lesser; Stephen T. Jackson (Ecology Letters, 2013)
Long‐distance dispersal is an integral part of plant species migration and population development. We aged and genotyped 1125 individuals in four disjunct populations of Pinus ponderosa that were initially established by long‐distance dispersal in the 16th and 17th centuries. Parentage analysis was used to determine if individuals were the product of local reproductive events (two parents present), long‐distance pollen dispersal (one parent present) or long‐distance seed dispersal (no parents present). All individuals established in the first century at each site were the result of long‐distance dispersal. Individuals reproduced at younger ages with increasing age of the overall population. These results suggest Allee effects, where populations were initially unable to expand on their own, and were dependent on long‐distance dispersal to overcome a minimum‐size threshold. Our results demonstrate that long‐distance dispersal was not only necessary for initial colonisation but also to sustain subsequent population growth during early phases of expansion.

A summary of the use of electronic tagging to provide insights into salmon migration and survival - A. Peter Klimley; R. Bruce MacFarlane; Phillip T. Sandstrom; Stephen T. Lindley (Environmental Biology of Fishes, 2013)

Net Present Biodiversity Value and the Design of Biodiversity Offsets - Jacob McC. Overton; R. T. Theo Stephens; Simon Ferrier (Ambio, 2013)

Agricultural Injury in California Hispanic Farm Workers: MICASA Follow-up Survey - Stephen A. McCurdy; Hong Xiao; Tamara E. Hennessy-Burt; Maria T. Stoecklin-Marois; Daniel J. Tancredi; Deborah H. Bennett; Marc B. Schenker (Journal of Agromedicine, 2013)

Breeding together: modeling synchrony in productivity in a seabird community - José J. Lahoz-Monfort; Byron J. T. Morgan; Michael P. Harris; Francis Daunt; Sarah Wanless; Stephen N. Freeman (Ecology, 2013)
With environmental conditions changing rapidly, there is a need to move beyond single‐species models and consider how communities respond to environmental drivers. We present a modeling approach that allows estimation of multispecies synchrony in productivity, or its components, and the contribution of environmental covariates as synchronizing and desynchronizing agents. We apply the model to long‐term breeding success data for five seabird species at a North Atlantic colony. Our Bayesian analysis reveals varying degrees of synchrony in overall productivity, with a common signal indicating a significant decline in productivity between 1986 and 2009. Productivity in seabirds reflects conditions in the marine ecosystem so the estimated synchronous component is a useful indicator of local marine environment health. For the two species for which we have most data, the environmental contribution to overall productivity synchrony is driven principally by effects operating at the chick stage rather than during incubation. Our results emphasize the importance of studying together species that coexist in a community. The framework, which accommodates interspecific clutch‐size variation, is readily applicable to any species assemblage in any ecosystem where long‐term productivity data are available.

G Protein-Coupled Receptor 124 (GPR124) Gene Polymorphisms and Risk of Brain Arteriovenous Malformation - Shantel Weinsheimer; Ari D. Brettman; Ludmila Pawlikowska; D. Christine Wu; Michael R. Mancuso; Frank Kuhnert; Michael T. Lawton; Stephen Sidney; Jonathan G. Zaroff; Charles E. McCulloch; William L. Young; Calvin Kuo; et al. (Translational Stroke Research, 2012)

Erratum to: Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

The Application of Science- and Risk-Based Concepts to Drug Substance Stability Strategies - Stephen T. Colgan; Timothy J. Watson; Robert D. Whipple; Roger Nosal; Jon V. Beaman; David M. De Antonis (Journal of Pharmaceutical Innovation, 2012)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

Expression of stromal genes associated with the angiogenic response are not differentiated between human tumour xenografts with divergent vascular morphologies - Matthew Farren; Susie Weston; Helen Brown; Nicola Broadbent; Steve Powell; Robert Shaw; Neil R. Smith; Rachael Inglis; Alex Graham; Sue Ashton; Stephen R. Wedge; Simon T. Barry (Angiogenesis, 2012)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Contest behavior and other reproductive efforts in aging breeders: a test of residual reproductive value and state-dependent models - Stephen T. Trumbo (Behavioral Ecology and Sociobiology, 2012)

Local and Landscape Associations Between Wintering Dabbling Ducks and Wetland Complexes in Mississippi - Aaron T. Pearse; Richard M. Kaminski; Kenneth J. Reinecke; Stephen J. Dinsmore (Wetlands, 2012)

Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

Using energy dispersive x-ray fluorescence microchemistry to infer migratory life history of Atlantic sturgeon - Matthew T. Balazik; Stephen P. McIninch; Greg C. Garman; Michael L. Fine; Clint B. Smith (Environmental Biology of Fishes, 2012)

Impact of varenicline on cue-specific craving assessed in the natural environment among treatment-seeking smokers - Julie C. Gass; Jennifer M. Wray; Larry W. Hawk; Martin C. Mahoney; Stephen T. Tiffany (Psychopharmacology, 2012)

Integrating field and laboratory evidence for environmental sex determination in the amphipod, Echinogammarus marinus - Yasmin Guler; Stephen Short; Peter Kile; Alex T. Ford (Marine Biology, 2012)

Amphibian Community Richness in Cropland and Grassland Playas in the Southern High Plains, USA - Louise S. Venne; Jo-Szu Tsai; Stephen B. Cox; Loren M. Smith; Scott T. McMurry (Wetlands, 2012)

Decomposing the mid‐Holocene Tsuga decline in eastern North America - Robert K. Booth; Simon Brewer; Maarten Blaauw; Thomas A. Minckley; Stephen T. Jackson (Ecology, 2012)
The mid‐Holocene decline of Tsuga canadensis (hereafter Tsuga ) populations across eastern North America is widely perceived as a synchronous event, driven by pests/pathogens, rapid climate change, or both. Pattern identification and causal attribution are hampered by low stratigraphic density of pollen‐sampling and radiometric dates at most sites, and by absence of highly resolved, paired pollen and paleoclimate records from single sediment cores, where chronological order of climatic and vegetational changes can be assessed. We present an intensely sampled (contiguous 1‐cm intervals) record of pollen and water table depth (inferred from testate amoebae) from a single core spanning the Tsuga decline at Irwin Smith Bog in Lower Michigan, with high‐precision chronology. We also present an intensively sampled pollen record from Tower Lake in Upper Michigan. Both sites show high‐magnitude fluctuations in Tsuga pollen percentages during the pre‐decline maximum. The terminal decline is dated at both sites ca. 5000 cal yr BP, some 400 years later than estimates from other sites and data compilations. The terminal Tsuga decline was evidently heterochronous across its range. A transient decline ca. 5350 cal yr BP at both sites may correspond to the terminal decline at other sites in eastern North America. At Irwin Smith Bog, the terminal Tsuga decline preceded an abrupt and persistent decline in water table depths by ∼200 years, suggesting the decline was not directly driven by abrupt climate change. The Tsuga decline may best be viewed as comprising at least three phases: a long‐duration pre‐decline maximum with high‐magnitude and high‐frequency fluctuations, followed by a terminal decline at individual sites, followed in turn by two millennia of persistently low Tsuga populations. These phases may not be causally linked, and may represent dynamics taking place at multiple temporal and spatial scales. Further progress toward understanding the phenomenon requires an expanded network of high‐resolution pollen and paleoclimate chronologies.

Mass Spectrometry-Based Quantification of CYP Enzymes to Establish In Vitro/In Vivo Scaling Factors for Intestinal and Hepatic Metabolism in Beagle Dog - Aki T. Heikkinen; Arno Friedlein; Jens Lamerz; Peter Jakob; Paul Cutler; Stephen Fowler; Tara Williamson; Roberto Tolando; Thierry Lave; Neil Parrott (Pharmaceutical Research, 2012)

Early life sun exposure, vitamin D-related gene variants, and risk of non-Hodgkin lymphoma - Jennifer L. Kelly; Matthew T. Drake; Zachary S. Fredericksen; Yan W. Asmann; Mark Liebow; Tait D. Shanafelt; Andrew L. Feldman; Stephen M. Ansell; William R. Macon; Megan M. Herr; Alice H. Wang; Grzegorz S. Nowakowski; et al. (Cancer Causes & Control, 2012)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Balancing the edge effects budget: bay scallop settlement and loss along a seagrass edge - John M. Carroll; Bradley T. Furman; Stephen T. Tettelbach; Bradley J. Peterson (Ecology, 2012)
Edge effects are a dominant subject in landscape ecology literature, yet they are highly variable and poorly understood. Often, the literature suggests simple models for edge effects—positive (enhancement at the edge), negative (enhancement at the interior), or no effect (neutral)—on a variety of metrics, including abundance, diversity, and mortality. In the marine realm, much of this work has focused on fragmented seagrass habitats due to their importance for a variety of commercially important species. In this study, the settlement, recruitment, and survival of bay scallops was investigated across a variety of seagrass patch treatments. By simultaneously collecting settlers (those viable larvae available to settle and metamorphose) and recruits (those settlers that survive some period of time, in this case, 6 weeks) on the same collectors, we were able to demonstrate a “balance” between positive and negative edge effects, resulting in a net neutral effect. Scallop settlement was significantly enhanced along seagrass edges, regardless of patch type while survival was elevated within patch interiors. However, recruitment (the net result of settlement and post‐settlement loss) did not vary significantly from edge to center, representing a neutral effect. Further, results suggest that post‐settlement loss, most likely due to predation, appears to be the dominant mechanism structuring scallop abundance, not patterns in settlement. These data illustrate the complexity of edge effects, and suggest that the metric used to investigate the effect (be it abundance, survival, or other metrics) can often influence the magnitude and direction of the perceived effect. Traditionally, high predation along a habitat edge would have indicated an “ecological trap” for the species in question; however, this study demonstrates that, at the population level, an ecological trap may not exist.

Use of Biosolids for Phytocapping of Landfill Soil - Dane T. Lamb; Stephen Heading; Nanthi Bolan; Ravi Naidu (Water, Air, & Soil Pollution, 2012)

Human cardiac autonomic responses to head-up tilting during 72-h starvation - Stephen J. Brown; M. Bryant; T. Mündel; S. R. Stannard (European Journal of Applied Physiology, 2012)

Differential gene expression in Alternaria gaisen exposed to dark and light - Rodney G. Roberts; Joseph F. Bischoff; Stephen T. Reymond (Mycological Progress, 2012)

Bacterial community profiles from sediments of the Anacostia River using metabolic and molecular analyses - Karen L. Bushaw-Newton; Evan C. Ewers; David J. Velinsky; Jeffrey T. F. Ashley; Stephen E. MacAvoy (Environmental Science and Pollution Research, 2012)

Climate Zone Delineation: Evaluating Approaches for Use in Natural Resource Management - Michael T. Tercek; Stephen T. Gray; Christopher M. Nicholson (Environmental Management, 2012)

Nuclear DNA content variation associated with muscle fiber hypertrophic growth in fishes - Ana Gabriela Jimenez; Stephen T. Kinsey (Journal of Comparative Physiology B, 2012)

Extensive sympatry, cryptic diversity and introgression throughout the geographic distribution of two coral species complexes - JASON T. LADNER; STEPHEN R. PALUMBI (Molecular Ecology, 2012)
The identification of species is one of the most basic, and yet critically important, issues in biology with far‐reaching potential implications for fields such as biodiversity conservation, population ecology and epidemiology. Morphology has long been the primary tool biologists have used to categorize life. However, we now know that a significant portion of natural diversity is morphologically hidden, and therefore, we must integrate nonmorphological tools into the description of biodiversity. Here, we demonstrate the utility of multilocus population genetic data for identifying and characterizing cryptic species complexes, even when species share large amounts of genetic variability. Specifically, we have used DNA sequence data from 12 genomic regions to characterize two widespread species complexes in the coral genus Acropora : A. cytherea and A. hyacinthus . These two morphospecies have each been sampled from 5 to 7 locations throughout their Indo‐Pacific distributions, and with the use of structure and hierarchical clustering, we demonstrate the presence of at least six widespread cryptic species within these two morphospecies complexes. After identifying cryptic lineages, we then utilize the genetic data to examine the history of introgressive hybridization within and between these morphospecies complexes. Our data indicate that these two complexes form a global syngameon with consistent patterns of introgression between species across large geographic distributions.

Different evolutionary histories underlie congruent species richness gradients of birds and mammals - Bradford A. Hawkins; Christy M. McCain; T. Jonathan Davies; Lauren B. Buckley; Brian L. Anacker; Howard V. Cornell; Ellen I. Damschen; John‐Arvid Grytnes; Susan Harrison; Robert D. Holt; Nathan J. B. Kraft; Patrick R. Stephens (Journal of Biogeography, 2012)
Aim The global species richness patterns of birds and mammals are strongly congruent. This could reflect similar evolutionary responses to the Earth’s history, shared responses to current climatic conditions, or both. We compare the geographical and phylogenetic structures of both richness gradients to evaluate these possibilities. Location Global. Methods Gridded bird and mammal distribution databases were used to compare their species richness gradients with the current environment. Phylogenetic trees (resolved to family for birds and to species for mammals) were used to examine underlying phylogenetic structures. Our first prediction is that both groups have responded to the same climatic gradients. Our phylogenetic predictions include: (1) that both groups have similar geographical patterns of mean root distance, a measure of the level of the evolutionary development of faunas, and, more directly, (2) that richness patterns of basal and derived clades will differ, with richness peaking in the tropics for basal clades and in the extra‐tropics for derived clades, and that this difference will hold for both birds and mammals. We also explore whether alternative taxonomic treatments for mammals can generate patterns matching those of birds. Results Both richness gradients are associated with the same current environmental gradients. In contrast, neither of our evolutionary predictions is met: the gradients have different phylogenetic structures, and the richness of birds in the lowland tropics is dominated by many basal species from many basal groups, whereas mammal richness is attributable to many species from both few basal groups and many derived groups. Phylogenetic incongruence is robust to taxonomic delineations for mammals. Main conclusions Contemporary climate can force multiple groups into similar diversity patterns even when evolutionary trajectories differ. Thus, as widely appreciated, our understanding of biodiversity must consider responses to both past and present climates, and our results are consistent with predictions that future climate change will cause major, correlated changes in patterns of diversity across multiple groups irrespective of their evolutionary histories.

Making a stand: five centuries of population growth in colonizing populations of Pinus ponderosa - Mark R. Lesser; Stephen T. Jackson (Ecology, 2012)
The processes underlying the development of new populations are important for understanding how species colonize new territory and form viable long‐term populations. Life‐history‐mediated processes such as Allee effects and dispersal capability may interact with climate variability and site‐specific factors to govern population success and failure over extended time frames. We studied four disjunct populations of ponderosa pine in the Bighorn Basin of north‐central Wyoming to examine population growth spanning more than five centuries. The study populations are separated from continuous ponderosa pine forest by distances ranging from 15 to >100 km. Strong evidence indicates that the initial colonizing individuals are still present, yielding a nearly complete record of population history. All trees in each population were aged using dendroecological techniques. The populations were all founded between 1530 and 1655 cal yr CE. All show logistic growth patterns, with initial exponential growth followed by a slowing during the mid to late 20th century. Initial population growth was slower than expectations from a logistic regression model at all four populations, but increased during the mid‐18th century. Initial lags in population growth may have been due to strong Allee effects. A combination of overcoming Allee effects and a transition to favorable climate conditions may have facilitated a mid‐18th century pulse in population growth rate.

Comparative mapping of the oat Dw6/dw6 dwarfing locus using NILs and association with vacuolar proton ATPase subunit H - Stephen J. Molnar; Julie T. Chapados; Sivakala Satheeskumar; Charlene P. Wight; Bonnie Bancroft; Winson Orr; Doris E. Luckert; Solomon Kibite (Theoretical and Applied Genetics, 2012)

MEG-SIM: A Web Portal for Testing MEG Analysis Methods using Realistic Simulated and Empirical Data - C. J. Aine; L. Sanfratello; D. Ranken; E. Best; J. A. MacArthur; T. Wallace; K. Gilliam; C. H. Donahue; R. Montaño; J. E. Bryant; A. Scott; J. M. Stephen (Neuroinformatics, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Identification and Synthesis of a Male-Produced Pheromone for the Neotropical Root Weevil Diaprepes abbreviatus - Stephen L. Lapointe; Rocco T. Alessandro; Paul S. Robbins; Ashot Khrimian; Ales Svatos; Joseph C. Dickens; Fernando Otálora-Luna; Fatma Kaplan; Hans T. Alborn; Peter E. Teal (Journal of Chemical Ecology, 2012)

Refugia: identifying and understanding safe havens for biodiversity under climate change - Gunnar Keppel; Kimberly P. Van Niel; Grant W. Wardell‐Johnson; Colin J. Yates; Margaret Byrne; Ladislav Mucina; Antonius G. T. Schut; Stephen D. Hopper; Steven E. Franklin (Global Ecology and Biogeography, 2012)
Aim Identifying and protecting refugia is a priority for conservation under projected anthropogenic climate change, because of their demonstrated ability to facilitate the survival of biota under adverse conditions. Refugia are habitats that components of biodiversity retreat to, persist in and can potentially expand from under changing environmental conditions. However, the study and discussion of refugia has often been ad hoc and descriptive in nature. We therefore: (1) provide a habitat‐based concept of refugia, and (2) evaluate methods for the identification of refugia. Location Global. Methods We present a simple conceptual framework for refugia and examine the factors that describe them. We then demonstrate how different disciplines are contributing to our understanding of refugia, and the tools that they provide for identifying and quantifying refugia. Results Current understanding of refugia is largely based on Quaternary phylogeographic studies on organisms in North America and Europe during significant temperature fluctuations. This has resulted in gaps in our understanding of refugia, particularly when attempting to apply current theory to forecast anthropogenic climate change. Refugia are environmental habitats with space and time dimensions that operate on evolutionary time‐scales and have facilitated the survival of biota under changing environmental conditions for millennia. Therefore, they offer the best chances for survival under climate change for many taxa, making their identification important for conservation under anthropogenic climate change. Several methods from various disciplines provide viable options for achieving this goal. Main conclusions The framework developed for refugia allows the identification and description of refugia in any environment. Various methods provide important contributions but each is limited in scope; urging a more integrated approach to identify, define and conserve refugia. Such an approach will facilitate better understanding of refugia and their capacity to act as safe havens under projected anthropogenic climate change.

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Population genetic structure of protected allis shad (Alosa alosa) and twaite shad (Alosa fallax) - Marc T. Jolly; Miran W. Aprahamian; Stephen J. Hawkins; Peter A. Henderson; Rob Hillman; Niall O’Maoiléidigh; Peter S. Maitland; Rayner Piper; Martin J. Genner (Marine Biology, 2012)

The NLRP3 inflammasome is active but not essential in endotoxin-induced uveitis - Holly L. Rosenzweig; April Woods; Jenna S. Clowers; Stephen R. Planck; James T. Rosenbaum (Inflammation Research, 2012)

Frontogenesis and Frontal Progression of a Trapping-Generated Estuarine Convergence Front and Its Influence on Mixing and Stratification - Sarah N. Giddings; Derek A. Fong; Stephen G. Monismith; C. Chris Chickadel; Kathleen A. Edwards; William J. Plant; Bing Wang; Oliver B. Fringer; Alexander R. Horner-Devine; Andrew T. Jessup (Estuaries and Coasts, 2012)

A multi-model ensemble of downscaled spatial climate change scenarios for the Dommel catchment, Western Europe - Michelle T. H. van Vliet; Stephen Blenkinsop; Aidan Burton; Colin Harpham; Hans Peter Broers; Hayley J. Fowler (Climatic Change, 2012)

Bangladesh Needs a “Blue–Green Revolution” to Achieve a Green Economy - Nesar Ahmed; James F. Muir; Stephen T. Garnett (Ambio, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Evaluating release alternatives for a long-lived bird species under uncertainty about long-term demographic rates - Clinton T. Moore; Sarah J. Converse; Martin J. Folk; Michael C. Runge; Stephen A. Nesbitt (Journal of Ornithology, 2012)

Multi‐decadal drought and amplified moisture variability drove rapid forest community change in a humid region - Robert K. Booth; Stephen T. Jackson; Valerie A. Sousa; Maura E. Sullivan; Thomas A. Minckley; Michael J. Clifford (Ecology, 2012)
Climate variability, particularly the frequency of extreme events, is likely to increase in the coming decades, with poorly understood consequences for terrestrial ecosystems. Hydroclimatic variations of the Medieval Climate Anomaly (MCA) provide a setting for studying ecological responses to recent climate variability at magnitudes and timescales comparable to expectations of coming centuries. We examined forest response to the MCA in the humid western Great Lakes region of North America, using proxy records of vegetation, fire, and hydroclimate. Multi‐decadal moisture variability during the MCA was associated with a widespread, episodic decline in Fagus grandifolia (beech) populations. Spatial patterns of drought and forest changes were coherent, with beech declining only in areas where proxy‐climate records indicate that severe MCA droughts occurred. The occurrence of widespread, drought‐induced ecological changes in the Great Lakes region indicates that ecosystems in humid regions are vulnerable to rapid changes in drought magnitude and frequency.

Tolerance to cannabinoid-induced behaviors in mice treated chronically with ethanol - Matthew J. Pava; Emily M. Blake; Stephen T. Green; Brandon J. Mizroch; Patrick J. Mulholland; John J. Woodward (Psychopharmacology, 2012)

Investigations into the Fate of Inhaled Salmon Calcitonin at the Respiratory Epithelial Barrier - Leonie Baginski; Frederic Tewes; Stephen T. Buckley; Anne Marie Healy; Udo Bakowsky; Carsten Ehrhardt (Pharmaceutical Research, 2012)

Therapeutic inhibition of fatty acid oxidation in right ventricular hypertrophy: exploiting Randle’s cycle - Yong-Hu Fang; Lin Piao; Zhigang Hong; Peter T. Toth; Glenn Marsboom; Peter Bache-Wiig; Jalees Rehman; Stephen L. Archer (Journal of Molecular Medicine, 2012)

Nitrogen transformations in a through‐flow wetland revealed using whole‐ecosystem pulsed 15 N additions - Jonathan M. O'Brien; Stephen K. Hamilton; Lauren E. Kinsman-Costello; Jay T. Lennon; Nathaniel E. Ostrom (Limnology and Oceanography, 2012)
We used pulsed and continuous additions of 15 N together with whole‐ecosystem metabolism measurements to elucidate the mechanisms of nitrogen (N) transformations in a small (1170 m 2 ) through‐flow wetland situated along a stream. From measurements of the wetland inflow and outflow, we observed a consistent decrease in nitrate (by 10% of inflow concentrations), while ammonium increased by an order of magnitude. Outflow ammonium concentrations oscillated in a diel cycle, inverse to the concentration of dissolved oxygen (i.e., greater ammonium export at night). The pulsed 15 N additions showed little uptake of nitrate over time in the wetland and rapid daytime uptake of ammonium from the water column (rate constant, k t = 0.11 h −1 ). A steady‐state 15 N‐ammonium addition demonstrated a similar rate of ammonium uptake (k t = 0.067 h −1 ), no detectable nitrification, and highlighted the spatial pattern of ammonium and nitrate uptake within the wetland. Porewater concentration profiles suggest high rates of net ammonium diffusion from the sediments. Ecosystem metabolism measurements indicate that release was attenuated during the day by autotrophic uptake, resulting in lower ammonium export during the day. Denitrification rates were modeled from dissolved N 2 : Ar ratios, but they were not sufficient to account for the observed loss in nitrate. Nitrate was removed near the pond inflow but not actively cycled throughout the pond, while the balance between sediment release and subsequent uptake of ammonium from the water‐column dominated N cycling in this wetland.

Hexachlorocyclohexanes in the Environment: Mechanisms of Dechlorination - Shaolin Li; Daniel W. Elliott; Stephen T. Spear; Luming Ma; Wei-Xian Zhang (Critical Reviews in Environmental Science and Technology, 2011)

Transport of NOX Emissions from Sugarcane Fertilisation into the Great Barrier Reef Lagoon - Clare Paton-Walsh; Stephen R. Wilson; Travis Naylor; David W. T. Griffith; O. T. Denmead (Environmental Modeling & Assessment, 2011)

Purification and characterization of arabinofuranosidase from the corn endophyte Acremonium zeae - Kenneth M. Bischoff; Sebastiao T. de Rezende; Troy M. Larson; Siqing Liu; Stephen R. Hughes; Joseph O. Rich (Biotechnology Letters, 2011)

Clinical contributors to cerebral white matter integrity in HIV-infected individuals - Assawin Gongvatana; Ronald A. Cohen; Stephen Correia; Kathryn N. Devlin; Jadrian Miles; Hakmook Kang; Hernando Ombao; Bradford Navia; David H. Laidlaw; Karen T. Tashima (Journal of NeuroVirology, 2011)

Characterisation and predicted genome locations of Leach’s storm-petrel (Oceanodroma leucorhoa) microsatellite loci (Procellariidae, Aves) - Anthony W. J. Bicknell; Deborah A. Dawson; Gavin J. Horsburgh; Mairi E. Knight; David T. Bilton; Stephen C. Votier (Conservation Genetics Resources, 2011)

The social viability and environmental sustainability of direct action land reform settlements in the Amazon - Flávia L. Leite; Marcellus M. Caldas; Cynthia Simmons; Stephen G. Perz; Stephen Aldrich; Robert T. Walker (Environment, Development and Sustainability, 2011)

Utility of high-density plantings in bay scallop, Argopecten irradians irradians, restoration - Stephen T. Tettelbach; Debra Barnes; John Aldred; Gregg Rivara; Dennis Bonal; Andrew Weinstock; Chelsea Fitzsimons-Diaz; Josh Thiel; M. Chase Cammarota; Adam Stark; Katherine Wejnert; Richard Ames; et al. (Aquaculture International, 2011)

A morphologic criterion to distinguish bird tracks - Amanda R. Falk; Larry D. Martin; Stephen T. Hasiotis (Journal of Ornithology, 2011)

Spatial Distribution and Temporal Trends of Polycyclic Aromatic Hydrocarbons (PAHs) in Sediments from Lake Maryut, Alexandria, Egypt - Assem Omar. Barakat; Alaa Mostafa; Terry L. Wade; Stephen T. Sweet; Nadia B. El Sayed (Water, Air, & Soil Pollution, 2011)

Cysteine residue 911 in C-terminal tail of human BKCaα channel subunit is crucial for its activation by carbon monoxide - Vsevolod Telezhkin; Stephen P. Brazier; Ruth Mears; Carsten T. Müller; Daniela Riccardi; Paul J. Kemp (Pflügers Archiv - European Journal of Physiology, 2011)

Validation of annual periodicity in otoliths of red snapper, Lutjanus campechanus - Stephen T. Szedlmayer; Sabrina G. Beyer (Environmental Biology of Fishes, 2011)

Integrated rice-fish farming in Bangladesh: meeting the challenges of food security - Nesar Ahmed; Stephen T. Garnett (Food Security, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Microsporidia infections in the amphipod, Echinogammarus marinus (Leach): suggestions of varying causal mechanisms to intersexuality - Gongda Yang; Stephen Short; Peter Kille; Alex T. Ford (Marine Biology, 2011)

Erratum: Design and Analysis of Line Transect Surveys for Primates - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2011)

Erratum: Line Transect Sampling of Primates: Can Animal-to-Observer Distance Methods Work? - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2011)

Genetic transformation of the codling moth, Cydia pomonella L., with piggyBac EGFP - Holly J. Ferguson; Lisa G. Neven; Stephen T. Thibault; Ahmed Mohammed; Malcolm Fraser (Transgenic Research, 2011)

Effects of acute pramipexole on preference for gambling-like schedules of reinforcement in rats - Patrick S. Johnson; Gregory J. Madden; Adam T. Brewer; Jonathan W. Pinkston; Stephen C. Fowler (Psychopharmacology, 2011)

FAP, gastric cancer, and genetic counseling featuring children and young adults: a family study and review - Henry T. Lynch; Carrie Snyder; Janine M. Davies; Stephen Lanspa; Jane Lynch; Zoran Gatalica; Victoria Graeve; Jason Foster (Familial Cancer, 2010)

Placental growth factor neutralising antibodies give limited anti-angiogenic effects in an in vitro organotypic angiogenesis model - Sandra R. Brave; Cath Eberlein; Masabumi Shibuya; Stephen R. Wedge; Simon T. Barry (Angiogenesis, 2010)

Sub‐fossil Chironomidae as indicators of palaeoflow regimes: integration into the PalaeoLIFE flow index - Lynda C. Howard; Paul J. Wood; Malcolm T. Greenwood; Helen M. Rendell; Stephen J. Brooks; Patrick D. Armitage; Chris A. Extence (Journal of Quaternary Science, 2010)
The sub‐fossil head capsules of larval Chironomidae have been widely exploited as palaeoecological indicators of lentic ecosystems but their value in the interpretation of the evolution of lotic systems has been underutilised by comparison. Recent research has demonstrated that the remains of Chironomidae are abundant within fluvial sequences and that they offer a valuable record of channel change and floodplain evolution that may complement that derived from existing biological and sedimentological techniques. This paper demonstrates the use of Chironomidae in characterising the palaeoflow regime of a large mid–late Holocene floodplain palaeochannel (5470–4960 to 1530–1350 cal. a BP) of the River Trent (Derbyshire, UK). Using expert knowledge and published information regarding flow preferences, larval Chironomidae were incorporated into the PalaeoLIFE (Lotic‐invertebrate Index for Flow Evaluation) methodology. The results clearly demonstrate that the sub‐fossil record provided by Chironomidae can be used to characterise changes in the flow regime within palaeochannel sections. At the scale of the channel section, species‐ and generic‐level ecological associations can provide useful information regarding habitat characteristics, including the presence of instream vegetation, mineral substrates and woody debris. The ability to undertake environmental reconstruction and channel evolution history was significantly enhanced through the application of a multi‐proxy approach, by incorporating other aquatic insect groups (Trichoptera and Coleoptera) into the PalaeoLIFE metric, together with sedimentological data. Copyright © 2010 John Wiley & Sons, Ltd.

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Exploitation of walleye in a Great Plains reservoir: harvest patterns and management scenarios - M. C. QUIST; J. L. STEPHEN; S. T. LYNOTT; J. M. GOECKLER; R. D. SCHULTZ (Fisheries Management and Ecology, 2010)
This study assessed exploitation and evaluated management options for walleye, Sander vitreus (Mitchill), in Glen Elder Reservoir, Kansas. A total of 2429 walleye varying from 240 to 687 mm was tagged with Carlin dangler tags during 2000–2003. After correcting for tag loss and non‐reporting, exploitation of walleye was estimated as 68.3%. More than 85% of the tagged walleye were harvested during April to June and 75% were harvested within 6 months after tagging. A Beverton‐Holt yield‐per‐recruit model was used to evaluate six minimum length limits varying from 250 to 610 mm. Given current exploitation rates, population demographics and harvest regulations (381‐mm minimum length limit), the walleye population is probably experiencing recruitment overfishing. Model results suggested that a 610‐mm minimum length limit would be required to prevent growth overfishing and a 533‐mm or longer minimum length limit would prevent recruitment overfishing.

The use of otolith shape analysis for ageing juvenile red snapper, Lutjanus campechanus - Sabrina G. Beyer; Stephen T. Szedlmayer (Environmental Biology of Fishes, 2010)

Oriented Markov Random Field Based Dendritic Spine Segmentation for Fluorescence Microscopy Images - Jie Cheng; Xiaobo Zhou; Eric L. Miller; Veronica A. Alvarez; Bernardo L. Sabatini; Stephen T. C. Wong (Neuroinformatics, 2010)

Design and Analysis of Line Transect Surveys for Primates - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2010)

Spatial distribution of lead concentrations in urban surface soils of New Orleans, Louisiana USA - Michael T. Abel; Burton Suedel; Steven M. Presley; Thomas R. Rainwater; Galen P. Austin; Stephen B. Cox; Les N. McDaniel; Richard Rigdon; Timothy Goebel; Richard Zartman; Blair D. Leftwich; Todd A. Anderson; et al. (Environmental Geochemistry and Health, 2010)

Genetic diversity and differentiation of three Brazilian populations of Scarlet ibis (Eudocimus ruber) - Evonnildo C. Gonçalves; Stephen F. Ferrari; Tibério César T. Burlamaqui; Leonardo Miranda; Marcelo S. Santos; Artur Silva; Maria Paula C. Schneider (Journal of Ornithology, 2010)

Scaling with body mass of mitochondrial respiration from the white muscle of three phylogenetically, morphologically and behaviorally disparate teleost fishes - Jessica L. Burpee; Elise L. Bardsley; Richard M. Dillaman; Wade O. Watanabe; Stephen T. Kinsey (Journal of Comparative Physiology B, 2010)

Differential susceptibility to epithelial-mesenchymal transition (EMT) of alveolar, bronchial and intestinal epithelial cells in vitro and the effect of angiotensin II receptor inhibition - Stephen T. Buckley; Carlos Medina; Carsten Ehrhardt (Cell and Tissue Research, 2010)

Niche conservatism as an emerging principle in ecology and conservation biology - John J. Wiens; David D. Ackerly; Andrew P. Allen; Brian L. Anacker; Lauren B. Buckley; Howard V. Cornell; Ellen I. Damschen; T. Jonathan Davies; John‐Arvid Grytnes; Susan P. Harrison; Bradford A. Hawkins; Robert D. Holt; et al. (Ecology Letters, 2010)
The diversity of life is ultimately generated by evolution, and much attention has focused on the rapid evolution of ecological traits. Yet, the tendency for many ecological traits to instead remain similar over time [niche conservatism (NC)] has many consequences for the fundamental patterns and processes studied in ecology and conservation biology. Here, we describe the mounting evidence for the importance of NC to major topics in ecology (e.g. species richness, ecosystem function) and conservation (e.g. climate change, invasive species). We also review other areas where it may be important but has generally been overlooked, in both ecology (e.g. food webs, disease ecology, mutualistic interactions) and conservation (e.g. habitat modification). We summarize methods for testing for NC, and suggest that a commonly used and advocated method (involving a test for phylogenetic signal) is potentially problematic, and describe alternative approaches. We suggest that considering NC: (1) focuses attention on the within‐species processes that cause traits to be conserved over time, (2) emphasizes connections between questions and research areas that are not obviously related (e.g. invasives, global warming, tropical richness), and (3) suggests new areas for research (e.g. why are some clades largely nocturnal? why do related species share diseases?).

Can ocean acidification affect population dynamics of the barnacle Semibalanus balanoides at its southern range edge? - Helen S. Findlay; Michael T. Burrows; Michael A. Kendall; John I. Spicer; Stephen Widdicombe (Ecology, 2010)
The global ocean and atmosphere are warming. There is increasing evidence suggesting that, in addition to other environmental factors, climate change is affecting species distributions and local population dynamics. Additionally, as a consequence of the growing levels of atmospheric carbon dioxide (CO 2 ), the oceans are taking up increasing amounts of this CO 2 , causing ocean pH to decrease (ocean acidification). The relative impacts of ocean acidification on population dynamics have yet to be investigated, despite many studies indicating that there will be at least a sublethal impact on many marine organisms, particularly key calcifying organisms. Using empirical data, we forced a barnacle ( Semibalanus balanoides ) population model to investigate the relative influence of sea surface temperature (SST) and ocean acidification on a population nearing the southern limit of its geographic distribution. Hindcast models were compared to observational data from Cellar Beach (southwestern United Kingdom). Results indicate that a declining pH trend (−0.0017 unit/yr), indicative of ocean acidification over the past 50 years, does not cause an observable impact on the population abundance relative to changes caused by fluctuations in temperature. Below the critical temperature (here T crit = 13.1°C), pH has a more significant affect on population dynamics at this southern range edge. However, above this value, SST has the overriding influence. At lower SST, a decrease in pH (according to the National Bureau of Standards, pH NBS ) from 8.2 to 7.8 can significantly decrease the population abundance. The lethal impacts of ocean acidification observed in experiments on early life stages reduce cumulative survival by ~25%, which again will significantly alter the population level at this southern limit. Furthermore, forecast predictions from this model suggest that combined acidification and warming cause this local population to die out 10 years earlier than would occur if there was only global warming and no concomitant decrease in pH.

The Response of Bone Marrow-Derived Mesenchymal Stem Cells to Dynamic Compression Following TGF-β3 Induced Chondrogenic Differentiation - Stephen D. Thorpe; Conor T. Buckley; Tatiana Vinardell; Fergal J. O’Brien; Veronica A. Campbell; Daniel J. Kelly (Annals of Biomedical Engineering, 2010)

Considering spatial and temporal scale in landscape‐genetic studies of gene flow - COREY DEVIN ANDERSON; BRYAN K. EPPERSON; MARIE‐JOSÉE FORTIN; ROLF HOLDEREGGER; PATRICK M. A. JAMES; MICHAEL S. ROSENBERG; KIM T. SCRIBNER; STEPHEN SPEAR (Molecular Ecology, 2010)
Landscape features exist at multiple spatial and temporal scales, and these naturally affect spatial genetic structure and our ability to make inferences about gene flow. This article discusses how decisions about sampling of genotypes (including choices about analytical methods and genetic markers) should be driven by the scale of spatial genetic structure, the time frame that landscape features have existed in their current state, and all aspects of a species’ life history. Researchers should use caution when making inferences about gene flow, especially when the spatial extent of the study area is limited. The scale of sampling of the landscape introduces different features that may affect gene flow. Sampling grain should be smaller than the average home‐range size or dispersal distance of the study organism and, for raster data, existing research suggests that simplifying the thematic resolution into discrete classes may result in low power to detect effects on gene flow. Therefore, the methods used to characterize the landscape between sampling sites may be a primary determinant for the spatial scale at which analytical results are applicable, and the use of only one sampling scale for a particular statistical method may lead researchers to overlook important factors affecting gene flow. The particular analytical technique used to correlate landscape data and genetic data may also influence results; common landscape‐genetic methods may not be suitable for all study systems, particularly when the rate of landscape change is faster than can be resolved by common molecular markers.

Persistence and expansion of ponderosa pine woodlands in the west‐central Great Plains during the past two centuries - Margot W. Kaye; Connie A. Woodhouse; Stephen T. Jackson (Journal of Biogeography, 2010)
Aim Woody plant expansion and infilling in grasslands and savannas are occurring across a broad range of ecosystems around the globe and are commonly attributed to fire suppression, livestock grazing, nutrient enrichment and/or climate variability. In the western Great Plains, ponderosa pine ( Pinus ponderosa ) woodlands are expanding across broad geographical and environmental gradients. The objective of this study was to reconstruct the establishment of ponderosa pine in woodlands in the west‐central Great Plains and to identify whether it was mediated by climate variability. Location Our study took place in a 400‐km wide region from the base of the Front Range Mountains ( c . 105° W) to the central Great Plains ( c . 100° W) and from Nebraska (43° N) to northern New Mexico (36° N), USA. Methods Dates for establishment of ponderosa pine were reconstructed with tree rings in 11 woodland sites distributed across the longitudinal and latitudinal gradients of the study area. Temporal trends in decadal pine establishment were compared with summer Palmer Drought Severity Index (PDSI). Annual trends in pine establishment from 1985 to 2005 were compared with seasonal PDSI, temperature and moisture availability. Results Establishment of ponderosa pine occurred in the study area in all but one decade (1770s) between the 1750s and the early 2000s, with over 35% of establishment in the region occurring after 1980. Pine establishment was highly variable among sites. Across the region, decadal pine establishment was persistently low from 1940 to 1960, when PDSI was below average. Annual pine establishment from 1985 to 2005 was positively correlated with summer PDSI and inversely correlated with minimum spring temperatures. Main conclusions Most ponderosa pine woodlands pre‐date widespread Euro‐American settlement of the region around c . ad 1860 and currently have stable tree populations. High variability in the timing of establishment of pine among sites highlights the multiplicity of factors that can drive woodland dynamics, including land use, fire history, CO 2 enrichment, tree population dynamics and climate. Since the 1840s, the influence of climate was most notable across the study area during the mid‐20th century, when the establishment of pine was suppressed by two significant droughts. The past sensitivity of establishment of ponderosa pine to drought suggests that woodland expansion will be negatively affected by predicted increases in temperature and drought in the Great Plains.

A GIS-based Approach to Identify and Map Playa Wetlands on the High Plains, Kansas, USA - Mark W. Bowen; William C. Johnson; Stephen L. Egbert; Scott T. Klopfenstein (Wetlands, 2010)

Line Transect Sampling of Primates: Can Animal-to-Observer Distance Methods Work? - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2010)

Comparison of the DNA methylation profiles of human peripheral blood cells and transformed B-lymphocytes - Yan V. Sun; Stephen T. Turner; Jennifer A. Smith; Pamela I. Hammond; Alicia Lazarus; Jodie L. Van De Rostyne; Julie M. Cunningham; Sharon L. R. Kardia (Human Genetics, 2010)

Release of Plasmid DNA-Encoding IL-10 from PLGA Microparticles Facilitates Long-Term Reversal of Neuropathic Pain Following a Single Intrathecal Administration - Ryan Gene Soderquist; Evan M. Sloane; Lisa C. Loram; Jacqueline A. Harrison; Ellen C. Dengler; Scott M. Johnson; Luke D. Amer; Courtney S. Young; Makenzie T. Lewis; Stephen Poole; Matthew G. Frank; Linda R. Watkins; et al. (Pharmaceutical Research, 2010)

Genetic variation in the IL7RA/IL7 pathway increases multiple sclerosis susceptibility - Rebecca L. Zuvich; Jacob L. McCauley; Jorge R. Oksenberg; Stephen J. Sawcer; Philip L. De Jager; Cristin Aubin; Anne H. Cross; Laura Piccio; Neelum T. Aggarwal; Denis Evans; David A. Hafler; Alastair Compston; et al. (Human Genetics, 2010)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

Design of a Miniature Tissue Culture System to Culture Mouse Heart Valves - Samuel C. Lieber; Boudewijn P. T. Kruithof; Nadine Aubry; Stephen F. Vatner; Vinciane Gaussin (Annals of Biomedical Engineering, 2010)

The metabolic demands of swimming behavior influence the evolution of skeletal muscle fiber design in the brachyuran crab family Portunidae - Kristin M. Hardy; Sean C. Lema; Stephen T. Kinsey (Marine Biology, 2010)

Comparative survival of bay scallops in eelgrass and the introduced alga, Codium fragile, in a New York estuary - John M. Carroll; Bradley J. Peterson; Dennis Bonal; Andrew Weinstock; Christopher F. Smith; Stephen T. Tettelbach (Marine Biology, 2010)

A new clade of archaic large-bodied predatory dinosaurs (Theropoda: Allosauroidea) that survived to the latest Mesozoic - Roger B. J. Benson; Matthew T. Carrano; Stephen L. Brusatte (The Science of Nature, 2010)

The inhibition of pyruvate dehydrogenase kinase improves impaired cardiac function and electrical remodeling in two models of right ventricular hypertrophy: resuscitating the hibernating right ventricle - Lin Piao; Yong-Hu Fang; Virgilio J. J. Cadete; Christian Wietholt; Dalia Urboniene; Peter T. Toth; Glenn Marsboom; Hannah J. Zhang; Idith Haber; Jalees Rehman; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2010)

A comprehensive resequence analysis of the KLK15–KLK3–KLK2 locus on chromosome 19q13.33 - Hemang Parikh; Zuoming Deng; Meredith Yeager; Joseph Boland; Casey Matthews; Jinping Jia; Irene Collins; Ariel White; Laura Burdett; Amy Hutchinson; Liqun Qi; Jennifer A. Bacior; et al. (Human Genetics, 2010)

A numerical study of inferred rockfish ( Sebastes spp.) larval dispersal along the central California coast - CHRISTINE H. PETERSEN; PATRICK T. DRAKE; CHRISTOPHER A. EDWARDS; STEPHEN RALSTON (Fisheries Oceanography, 2010)
Successful recruitment of marine fishes depends on survival during early life‐history stages, which is influenced by oceanic advection due to its impact on coastal trophodynamics and transport processes. Here we evaluate the influence of ocean circulation on the dispersal of rockfish ( Sebastes spp.) larvae along the central California coast using an implementation of the Regional Ocean Modeling System, driven at the surface by output from the Coupled Ocean Atmosphere Mesoscale Prediction System. Thousands of floats simulating rockfish larval propagules, constrained to follow fixed depths, were released over a broad coastal area at 2‐day intervals, and transported by simulated ocean currents at depths of 1, 7, 20, 40, and 70 m. Trajectory statistics are averaged across the 4‐yr period from January 2000 through December 2003 to reveal mean trajectory direction, net displacement, fractional cross‐shore loss, and duration of retention for different seasons. On average, near‐surface propagules originating nearshore are transported offshore during the upwelling season, whereas deeper propagules move alongshore to the north. This vertical shear vanishes during winter, with most floats moving alongshore to the north, regardless of depth. After 35 days in the water column, typical transport distances were ∼50 km for floats remaining nearshore and ∼150 km for floats over the midshelf and slope. Implications for performance of marine reserves for rockfish conservation are discussed. Our results also provide evidence for a strong semiannual pattern of coastal retention rates, with high export of near‐surface drifters during the upwelling season. In contrast, high rates of shelf retention occurred for releases at 20 m and deeper during summer, and at all depths during winter.

Molecular characterization of global maize breeding germplasm based on genome-wide single nucleotide polymorphisms - Yanli Lu; Jianbing Yan; Claudia T. Guimarães; Suketoshi Taba; Zhuanfang Hao; Shibin Gao; Shaojiang Chen; Jiansheng Li; Shihuang Zhang; Bindiganavile S. Vivek; Cosmos Magorokosho; Stephen Mugo; et al. (Theoretical and Applied Genetics, 2009)

What is “fallback”?: metrics needed to assess telemetry tag effects on anadromous fish behavior - Holly J. Frank; Martha E. Mather; Joseph M. Smith; Robert M. Muth; John T. Finn; Stephen D. McCormick (Hydrobiologia, 2009)

Is it possible to identify habitat for a rare species? Shortjaw Cisco (Coregonus zenithicus) in Lake Huron as a case study - Benjamin T. Naumann; Stephen S. Crawford (Environmental Biology of Fishes, 2009)

Nodulation of Sesbania species by Rhizobium ( Agrobacterium ) strain IRBG74 and other rhizobia - Stephen P. Cummings; Prasad Gyaneshwar; Pablo Vinuesa; Frank T. Farruggia; Mitchell Andrews; David Humphry; Geoffrey N. Elliott; Andrew Nelson; Caroline Orr; Deborah Pettitt; Gopit R. Shah; Scott R. Santos; et al. (Environmental Microbiology, 2009)
Summary Concatenated sequence analysis with 16S rRNA, rpoB and fusA genes identified a bacterial strain (IRBG74) isolated from root nodules of the aquatic legume Sesbania cannabina as a close relative of the plant pathogen Rhizobium radiobacter (syn. Agrobacterium tumefaciens ). However, DNA:DNA hybridization with R. radiobacter , R. rubi , R. vitis and R. huautlense gave only 44%, 5%, 8% and 8% similarity respectively, suggesting that IRBG74 is potentially a new species. Additionally, it contained no vir genes and lacked tumour‐forming ability, but harboured a sym ‐plasmid containing nifH and nodA genes similar to those in other Sesbania symbionts. Indeed, IRBG74 effectively nodulated S. cannabina and seven other Sesbania spp. that nodulate with Ensifer ( Sinorhizobium )/ Rhizobium strains with similar nodA genes to IRBG74, but not species that nodulate with Azorhizobium or Mesorhizobium . Light and electron microscopy revealed that IRBG74 infected Sesbania spp. via lateral root junctions under flooded conditions, but via root hairs under non‐flooded conditions. Thus, IRBG74 is the first confirmed legume‐nodulating symbiont from the Rhizobium ( Agrobacterium ) clade. Cross‐inoculation studies with various Sesbania symbionts showed that S. cannabina could form fully effective symbioses with strains in the genera Rhizobium and Ensifer , only ineffective ones with Azorhizobium strains, and either partially effective ( Mesorhizobium huakii ) or ineffective ( Mesorhizobium plurifarium ) symbioses with Mesorhizobium . These data are discussed in terms of the molecular phylogeny of Sesbania and its symbionts.

Lymphocyte recruitment into the tumor site is altered in patients with MSI-H colon cancer - Kristen M. Drescher; Poonam Sharma; Patrice Watson; Zoran Gatalica; Stephen N. Thibodeau; Henry T. Lynch (Familial Cancer, 2009)

Changes in the relative reinforcing effects of cigarette smoking as a function of initial abstinence - Jin H. Yoon; Stephen T. Higgins; Matthew P. Bradstreet; Gary J. Badger; Colleen S. Thomas (Psychopharmacology, 2009)

Identification of human sperm transcripts as candidate markers of male fertility - Claudia Lalancette; Adrian E. Platts; Graham D. Johnson; Benjamin R. Emery; Douglas T. Carrell; Stephen A. Krawetz (Journal of Molecular Medicine, 2009)

An Automated Pipeline for Dendrite Spine Detection and Tracking of 3D Optical Microscopy Neuron Images of In Vivo Mouse Models - Jing Fan; Xiaobo Zhou; Jennifer G. Dy; Yong Zhang; Stephen T. C. Wong (Neuroinformatics, 2009)

The Biogeographical Distribution of Duncecap Larkspur (Delphinium occidentale) Chemotypes and Their Potential Toxicity - Daniel Cook; Dale R. Gardner; James A. Pfister; Kevin D. Welch; Benedict T. Green; Stephen T. Lee (Journal of Chemical Ecology, 2009)

Discovery and characterization of chemical signals for citrus root weevil, Diaprepes abbreviatus - Fernando Otálora-Luna; Jennifer A. Hammock; Rocco T. Alessandro; Stephen L. Lapointe; Joseph C. Dickens (Arthropod-Plant Interactions, 2009)

Extracellular Hemicellulolytic Enzymes from the Maize Endophyte Acremonium zeae - Kenneth M. Bischoff; Donald T. Wicklow; Douglas B. Jordan; Sebastiao T. de Rezende; Siqing Liu; Stephen R. Hughes; Joseph O. Rich (Current Microbiology, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

‘That which does not kill us only makes us stronger’: the role of carbon monoxide in thermophilic microbial consortia - Stephen M. Techtmann; Albert S. Colman; Frank T. Robb (Environmental Microbiology, 2009)
Summary Carbon monoxide (CO), while a potent toxin, is also a key intermediate in major autotrophic pathways such as methanogenesis and acetogenesis. The ability of purple sulfur bacteria to use CO as an energy source was first described by Uffen in 1976. The prototype extremely thermophilic carboxydotroph Carboxydothermus hydrogenoformans was described in 1991. Eight bacteria and one archaeon that utilize CO have since been isolated and described from diverse geothermal environments. They derive energy from the oxidation of CO with water to form CO 2 and H 2 . Most of these isolates thrive with headspace CO partial pressures around 1 atm, which is grossly elevated relative to CO concentrations in geothermal effluents. To account for this, we suggest that under consortial growth conditions the carboxydotrophs occupy microniches in which biogenic CO accumulates locally to high concentrations. CO oxidizers dissipate these potentially toxic CO hot spots with the production of H 2 , CO 2 and acetate whose subsequent oxidation fuels other thermophiles. The identification of genes related to anaerobic CO oxidation in many metagenomic databases attests to widespread distribution of carboxydotrophs. Current evidence suggests that CO‐oxidizing bacteria and archaea hold a vital niche in thermophilic ecosystems.

Spatial scales of variance in abundance of intertidal species: effects of region, dispersal mode, and trophic level - Michael T. Burrows; Robin Harvey; Linda Robb; Elvira S. Poloczanska; Nova Mieszkowska; Pippa Moore; Rebecca Leaper; Stephen J. Hawkins; Lisandro Benedetti-Cecchi (Ecology, 2009)
Determination of the pattern of variation in population abundance among spatial scales offers much insight into the potential regulating factors. Here we offer a method of quantifying spatial variance on a range of scales derived by sampling of irregularly spaced sites along complex coastlines. We use it to determine whether the nature of spatial variance depends on the trophic level or the mode of dispersal of the species involved and the role of the complexity of the underlying habitat. A least‐cost distance model was used to determine distances by sea between all pairs of sites. Ordination of this distance matrix using multidimensional scaling allowed estimation of variance components with hierarchical ANOVA at nested spatial scales using spatial windows. By repeatedly moving these spatial windows and using a second set of spatial scales, average variance scale functions were derived for 50+ species in the UK rocky intertidal. Variance spectra for most species were well described by the inverse power law (1/ f β ) for noise spectra, with values for the exponent ranging from 0 to 1.1. At higher trophic levels (herbivores and carnivores), those species with planktonic dispersal had significantly higher β values, indicating greater large‐ than small‐scale variability, as did those on simpler coastlines (southwestern England and Wales vs. western Scotland). Average abundance and proportional incidence of species had the strongest influence on β values, with those of intermediate abundance and incidence having much greater large‐scale variance (β ≈ 0.5) than rare or ubiquitous species (β ≈ 0).

Paleoenvironmental conditions in the Spanish Miocene–Pliocene boundary: isotopic analyses of Hipparion dental enamel - Laura Domingo; Stephen T. Grimes; M. Soledad Domingo; M. Teresa Alberdi (The Science of Nature, 2009)

Automated Axon Tracking of 3D Confocal Laser Scanning Microscopy Images Using Guided Probabilistic Region Merging - Ranga Srinivasan; Xiaobo Zhou; Eric Miller; Ju Lu; Jeff W. Lichtman; Stephen T. C. Wong (Neuroinformatics, 2009)

Estuarine and Coastal Habitat Use of Gulf Sturgeon (Acipenser oxyrinchus desotoi) in the North-Central Gulf of Mexico - Stephen T. Ross; W. Todd Slack; Ryan J. Heise; Mark A. Dugo; Howard Rogillio; Bryant R. Bowen; Paul Mickle; Richard W. Heard (Estuaries and Coasts, 2009)

Manganese in coastal rainwater: speciation, photochemistry and deposition to seawater - Joan D. Willey; Michael T. Inscore; Robert J. Kieber; Stephen A. Skrabal (Journal of Atmospheric Chemistry, 2009)

Long‐term disease dynamics in lakes: causes and consequences of chytrid infections in Daphnia populations - Pieter T. J. Johnson; Anthony R. Ives; Richard C. Lathrop; Stephen R. Carpenter (Ecology, 2009)
Understanding the drivers and consequences of disease epidemics is an important frontier in ecology. However, long‐term data on hosts, their parasites, and the corresponding environmental conditions necessary to explore these interactions are often unavailable. We examined the dynamics of Daphnia pulicaria , a keystone zooplankter in lake ecosystems, to explore the long‐term causes and consequences of infection by a chytridiomycete parasitoid ( Polycaryum laeve ). After quantifying host–pathogen dynamics from vouchered samples collected over 15 years, we used autoregressive models to evaluate (1) hypothesized drivers of infection, including host density, water temperature, dissolved oxygen, host‐food availability, and lake mixing; and (2) the effects of epidemics on host populations. Infection was present in most years but varied widely in prevalence, from P. laeve transmission, such that epidemics occurred primarily during periods of water mixing. Development of the thermocline likely reduced transmission by spatially separating susceptible hosts from infectious zoospores. Among years, ice duration and cumulative snowfall correlated negatively with infection prevalence, likely because of reductions in spring phytoplankton and D. pulicaria density in years with extended winters. Epidemics also influenced dynamics of the host population. Infected D. pulicaria rarely ( P. laeve prevalence was positively correlated with sexual reproduction in D. pulicaria . Analyses of D. pulicaria density‐dependent population dynamics predicted that, in the absence of P. laeve infection, host abundance would be 11–50% higher than what was observed. By underscoring the importance of complex physical processes in controlling host–parasite interactions and of epidemic disease in influencing host populations, our results highlight the value of long‐term data for understanding wildlife disease dynamics.

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

MODELING THE RESPONSE OF POPULATIONS OF COMPETING SPECIES TO CLIMATE CHANGE - Elvira S. Poloczanska; Stephen J. Hawkins; Alan J. Southward; Michael T. Burrows (Ecology, 2008)
Biotic interactions will modulate species' responses to climate change. Many approaches to predicting the impacts of climate change on biodiversity so far have been based purely on a climate envelope approach and have not considered direct and indirect species interactions. Using a long‐term observational data set (>30 years) of competing intertidal barnacle species, we built a hierarchy of age‐structured two‐taxa population models ( Semibalanus balanoides vs. Chthamalus montagui and C. stellatus combined as one taxon) to test if the presence of a dominant competitor can mediate climatic influence on the subordinate species. Models were parameterized using data from populations on the south coast of southwest England and verified by hindcasting using independent north coast population data. Recruitment of the dominant competitor, S. balanoides , is driven by temperature. The mechanisms of competition explored included simple space preemption and temperature‐driven interference competition. The results indicate that interspecific competition between juvenile barnacles is important in regulating chthamalid density but not that of the dominant competitor S. balanoides . Simulations were carried out using alternative future climate scenarios to predict barnacle population abundance over the next century. Under all emission scenarios, the cold‐water S. balanoides is predicted to virtually disappear from southwest England by the 2050s, leading to the competitive release of Chthamalus throughout the entire region and thereby substantially increasing its abundance and occupied habitat (by increasing vertical range on the shore). Our results demonstrate that climate change can profoundly affect the abundance and distribution of species through both the direct effects of temperature on survival, and also by altering important negative interactions through shifting competitive balances and essentially removing dominant competitors or predators. Climate change impacts on organisms are unlikely to lead only to straightforward, easily predictable changes in population size and distribution. The complex, indirect effects of climate change need to be taken into account if we are to accurately forecast the long‐term effects of global warming.

Considerations for Assessments of Wadable Drainage Systems in the Agriculturally Dominated Deltas of Arkansas and Mississippi - W. W. Stephens; M. T. Moore; J. L. Farris; J. L. Bouldin; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 2008)

Preparation of Active Proteins, Vaccines and Pharmaceuticals as Fine Powders using Supercritical or Near-Critical Fluids - Stephen P. Cape; Joseph A. Villa; Edward T. S. Huang; Tzung-Horng Yang; John F. Carpenter; Robert E. Sievers (Pharmaceutical Research, 2008)

Reproductive status of Octopus pallidus, and its relationship to age and size - Stephen C. Leporati; Gretta T. Pecl; Jayson M. Semmens (Marine Biology, 2008)

Comprehensive resequence analysis of a 136 kb region of human chromosome 8q24 associated with prostate and colon cancers - Meredith Yeager; Nianqing Xiao; Richard B. Hayes; Pascal Bouffard; Brian Desany; Laura Burdett; Nick Orr; Casey Matthews; Liqun Qi; Andrew Crenshaw; Zdenek Markovic; Karin M. Fredrikson; et al. (Human Genetics, 2008)

Spatially-averaged flow statistics within a canopy of large bluff bodies: Results from direct numerical simulations - Omduth Coceal; T. Glyn Thomas; Stephen E. Belcher (Acta Geophysica, 2008)

The Mordor Alkaline Igneous Complex, Central Australia: PGE-enriched disseminated sulfide layers in cumulates from a lamprophyric magma - Stephen J. Barnes; J. A. C. Anderson; T. R. Smith; L. Bagas (Mineralium Deposita, 2008)

Hydrostatic constraints on morphological exploitation of light in tall Sequoia sempervirens trees - Hiroaki T. Ishii; Gregory M. Jennings; Stephen C. Sillett; George W. Koch (Oecologia, 2008)

Estuaries and Coasts as an Outlet for Research in Coastal Ecosystems: A Bibliometric Study - James W. Fourqurean; Carlos M. Duarte; Mark D. Kershaw; Stephen T. Threlkeld (Estuaries and Coasts, 2008)

A structural motif in the C-terminal tail of slo1 confers carbon monoxide sensitivity to human BKCa channels - Sandile E. Williams; Stephen P. Brazier; Nian Baban; Vsevolod Telezhkin; Carsten T. Müller; Daniela Riccardi; Paul J. Kemp (Pflügers Archiv - European Journal of Physiology, 2008)

Workflow and Methods of High-Content Time-Lapse Analysis for Quantifying Intracellular Calcium Signals - Fuhai Li; Xiaobo Zhou; Jinmin Zhu; Weiming Xia; Jinwen Ma; Stephen T. C. Wong (Neuroinformatics, 2008)

Scaling environmental change through the community‐level: a trait‐based response‐and‐effect framework for plants - KATHARINE N. SUDING; SANDRA LAVOREL; F. S. CHAPIN; JOHANNES H. C. CORNELISSEN; SANDRA DÍAZ; ERIC GARNIER; DEBORAH GOLDBERG; DAVID U. HOOPER; STEPHEN T. JACKSON; MARIE‐LAURE NAVAS (Global Change Biology, 2008)
Predicting ecosystem responses to global change is a major challenge in ecology. A critical step in that challenge is to understand how changing environmental conditions influence processes across levels of ecological organization. While direct scaling from individual to ecosystem dynamics can lead to robust and mechanistic predictions, new approaches are needed to appropriately translate questions through the community level. Species invasion, loss, and turnover all necessitate this scaling through community processes, but predicting how such changes may influence ecosystem function is notoriously difficult. We suggest that community‐level dynamics can be incorporated into scaling predictions using a trait‐based response–effect framework that differentiates the community response to environmental change (predicted by response traits) and the effect of that change on ecosystem processes (predicted by effect traits). We develop a response‐and‐effect functional framework, concentrating on how the relationships among species' response, effect, and abundance can lead to general predictions concerning the magnitude and direction of the influence of environmental change on function. We then detail several key research directions needed to better scale the effects of environmental change through the community level. These include (1) effect and response trait characterization, (2) linkages between response‐and‐effect traits, (3) the importance of species interactions on trait expression, and (4) incorporation of feedbacks across multiple temporal scales. Increasing rates of extinction and invasion that are modifying communities worldwide make such a research agenda imperative.

Ecology and management of northern pike in Wisconsin - Terry L. Margenau; Steven P. AveLallemant; David Giehtbrock; Stephen T. Schram (Hydrobiologia, 2008)

An Automated Method for Cell Detection in Zebrafish - Tianming Liu; Gang Li; Jingxin Nie; Ashley Tarokh; Xiaobo Zhou; Lei Guo; Jarema Malicki; Weiming Xia; Stephen T. C. Wong (Neuroinformatics, 2008)

Ecological stability in a changing world? Reassessment of the palaeoenvironmental history of Cuatrociénegas, Mexico - Thomas A. Minckley; Stephen T. Jackson (Journal of Biogeography, 2008)
Previous work on the palaeoenvironmental history of Cuatrociénegas, Coahuila, Mexico, suggests that the local environments of the basin have been relatively stable since the last glacial period. Reassessment of the palaeoenvironmental record from Cuatrociénegas, combined with the analysis of a glacial‐age packrat midden (∼ 16,900 cal yr bp ), shows that this region has experienced substantial climatic and ecological changes during the Late Quaternary. Woodlands occurred near the valley floor until ca. 11,000 years ago, migrating upslope as climate warmed. The apparent lack of change in the flora of the basin floor may be attributable to high soil salinity. This edaphic control led to earlier interpretations that the region was environmentally stable.

Dynamics and predictive modelling of Vibrio spp. in the Neuse River Estuary, North Carolina, USA - Jennifer L. Hsieh; J. Stephen Fries; Rachel T. Noble (Environmental Microbiology, 2008)
Summary Vibrio spp. are naturally occurring bacteria in marine and estuarine environments around the world. The genus includes several human and animal pathogens that can negatively impact human health, seafood and aquaculture. Vibrio spp. populations are capable of rapid adaptation in response to changing environmental conditions, making them dynamic over short‐term and seasonal scales. Temperature, vertical mixing, tidal flushing, climate, precipitation and nutrient loading can change the estuarine environment and subsequently alter microbial community structure, including Vibrio spp., affecting estuarine water quality and public health. To describe these dynamics, Vibrio spp. concentrations and a range of microbial, physical and chemical measures were monitored every 2 weeks and after storm events for 19 months in the Neuse River Estuary (NRE). Results showed clear seasonal and geographic trends in Vibrio spp. abundance. Multiple regression analysis revealed a strong relationship to temperature and salinity, with additional minor influences of chlorophyll a and dissolved organic carbon. Similar models based on easily measured environmental parameters should be pursued for individual Vibrio species in the NRE and other estuarine environments. Predictive models provide useful information for managers, researchers and modellers of estuarine ecosystems.

Harnessing hypoxic adaptation to prevent, treat, and repair stroke - Rajiv R. Ratan; Ambreena Siddiq; Natalya Smirnova; Ksenia Karpisheva; Renee Haskew-Layton; Stephen McConoughey; Brett Langley; Alvaro Estevez; Patricio T. Huerta; Bruce Volpe; Sashwati Roy; Chandan K. Sen; et al. (Journal of Molecular Medicine, 2007)

Hepatitis B awareness, knowledge, and screening among Asian Americans - Tung T. Nguyen; Vicky Taylor; Moon S. Chen; Roshan Bastani; Annette E. Maxwell; Stephen J. Mcphee (Journal of Cancer Education, 2007)

Modelling to forestall extinction of Australian tropical birds - Stephen T. Garnett; Barry W. Brook (Journal of Ornithology, 2007)

Development of vegetation in dune slack wetlands of Cape Cod National Seashore (Massachusetts, USA) - Stephen M. Smith; Marybeth Hanley; Keith T. Killingbeck (Plant Ecology, 2007)

Modelling adaptive management strategies for coping with the impacts of climate variability and change on riverine algal blooms - NEIL R. VINEY; BRYSON C. BATES; STEPHEN P. CHARLES; IAN T. WEBSTER; MYRIAM BORMANS (Global Change Biology, 2007)
The impact of climate change on hydrology and water resources is one of the most critical issues facing the world in the next few decades. In particular, there is a need to quantify the risks associated with maintaining the security of resource quantity and quality, and to assess the effectiveness of potential management strategies. In this paper, we assess the impacts of climate variability and change on one aspect of river health. A simple model of Anabaena algal bloom occurrence at a weir pool in the lower Murrumbidgee River, Australia, has been coupled to a catchment model that is used to simulate streamflow, irrigation demand and diversions, dam water storage and releases, and decision‐making by both irrigators and managers. Long‐term climate data are obtained from a statistical downscaling algorithm, which, when applied to global climate model predictions can provide climate data suitable for driving the coupled model under a variety of climatic scenarios. The coupled model is then used to assess the impact of climate variability and projected climate change on the frequency, duration and magnitude of Anabaena blooms. The impact of two management strategies for bloom control are also assessed and it is shown that even a single, quite simple, resource‐neutral, adaptive management strategy has the potential to substantially reduce the occurrence and impact of algal blooms and to more than compensate for the deleterious impacts of climate change. This result supports the notion that planning for the future can lead to positive outcomes in the present.

Spatial Variability of Flow Statistics within Regular Building Arrays - Omduth Coceal; T. Glyn Thomas; Stephen E. Belcher (Boundary-Layer Meteorology, 2007)

Genetic population structure of the sagebrush Brewer’s sparrow, Spizella breweri breweri, in a fragmented landscape at the northern range periphery - Emily K. Croteau; Stephen C. Lougheed; Pamela G. Krannitz; Nancy A. Mahony; Brett L. Walker; Peter T. Boag (Conservation Genetics, 2007)

Automated Axon Tracking of 3D Confocal Laser Scanning Microscopy Images Using Guided Probabilistic Region Merging - Ranga Srinivasan; Xiaobo Zhou; Eric Miller; Ju Lu; Jeff Litchman; Stephen T. C. Wong (Neuroinformatics, 2007)

The climatic impact of supervolcanic ash blankets - Morgan T. Jones; R. Stephen J. Sparks; Paul J. Valdes (Climate Dynamics, 2007)

The nicotinic acetylcholine receptor antagonist mecamylamine prevents escalation of cocaine self-administration in rats with extended daily access - Stephen T. Hansen; Gregory P. Mark (Psychopharmacology, 2007)

Does terrestrial organic carbon subsidize the planktonic food web in a clear‐water lake? - Michael L. Pace; Stephen R. Carpenter; Jonathan J. Cole; James J. Coloso; James F. Kitchell; James R. Hodgson; Jack J. Middelburg; Nicholas D. Preston; Christopher T. Solomon; Brian C. Weidel (Limnology and Oceanography, 2007)
Allochthonous organic carbon can subsidize consumers in aquatic systems, but this subsidy may only be significant in relatively small systems with high organic matter loading. We tested the importance of allochthonous carbon to consumers in a relatively large (258,000 m 2 ) clear‐water lake by adding H 13 CO 3 daily for 56 d. Dissolved inorganic carbon (DIC) was substantially enriched in 13 C by the addition, but it was also variable over diel cycles because of exchange with the atmosphere and photosynthesis. By measuring the δ 13 C value of a physically separated phytoplankton concentrate as well as the δ 13 C of phospholipid fatty acids, we were able to follow 13 C‐labeling dynamics of specific groups of phytoplankton and bacteria. The δ 13 C values of particulate organic carbon (POC), dissolved organic carbon (DOC), phytoplankton, bacteria, zooplankton, and the invertebrate predator, Chaoborus spp. all increased to a maximum during the addition and declined once the addition ceased. Autochthony (% C derived from internal primary production) of carbon pools (POC, DOC) and consumers was assessed by fitting dynamic models to time series of δ 13 C. Autochthonous carbon was the dominant source (88‐100%) for POC, gram‐positive bacteria, a copepod, zooplankton biomass, and Chaoborus spp. Autochthonous carbon provided a lower fraction (

Spatial patterns of flow and their modification within and around a giant kelp forest - Brian Gaylord; Johanna H. Rosman; Daniel C. Reed; Jeffrey R. Koseff; Jonathan Fram; Sally MacIntyre; Katie Arkema; Cameron McDonald; Mark A. Brzezinski; John L. Largier; Stephen G. Monismith; Peter T. Raimondi; et al. (Limnology and Oceanography, 2007)
We present findings from two sets of measurements that quantified currents around and over the full extent of a giant kelp ( Macrocystis pyrifera ) forest located at Mohawk Reef, Santa Barbara, California. Velocities were damped inside this 200‐m X 300‐m forest, but not to the extent reported for larger (kilometer‐scale) kelp beds, suggesting that alongshore currents may play a greater role in exchange than has often been assumed. Secondary flow features that bear on the performance of forest organisms were observed, including a region along the forest’s outer boundary where velocities exceeded incident speeds by up to 200%. An offshore current on the order of 1 cm s −1 developed within the kelp bed, likely due to pressure gradients established across the forest coupled with topography. Wake recirculations that might have facilitated leeward retention of waterborne subsidies were not apparent. Calculations suggest that kelp beds can interact with (and thus potentially filter) substantial portions of impinging waters; in our study, 40–90% of arriving waters entered the upstream end, and 20–70% reached the center of the forest. Seasonal changes in the size and density of the forest modified the levels of flow damping and filtration. The sum of these effects suggests potential influences on organisms throughout the forest community.

A substance flow analysis in the southern hemisphere: cadmium in the Australian economy - Suphaphat Kwonpongsagoon; David T. Waite; Stephen J. Moore; Paul H. Brunner (Clean Technologies and Environmental Policy, 2007)

Scale-specific correlations between habitat heterogeneity and soil fauna diversity along a landscape structure gradient - Adam J. Vanbergen; Allan D. Watt; Ruth Mitchell; Anne-Marie Truscott; Stephen C. F. Palmer; Eva Ivits; Paul Eggleton; T. Hefin Jones; José Paulo Sousa (Oecologia, 2007)

Defending young biparentally: female risk-taking with and without a male in the burying beetle, Nicrophorus pustulatus - Stephen T. Trumbo (Behavioral Ecology and Sociobiology, 2007)

Yawning and hypothermia in rats: effects of dopamine D3 and D2 agonists and antagonists - Gregory T. Collins; Amy Hauck Newman; Peter Grundt; Kenner C. Rice; Stephen M. Husbands; Cédric Chauvignac; Jianyong Chen; Shaomeng Wang; James H. Woods (Psychopharmacology, 2007)

Alterations in presenilin 1 processing by amyloid-β peptide in the rat retina - Helena R. Watts; Valerie Vince; Desmond T. Walsh; Laura G. Bresciani; Stephen M. Gentleman; Ling-Sun Jen; Peter J. B. Anderson (Experimental Brain Research, 2007)

Approaches to resolving cephalopod movement and migration patterns - Jayson M. Semmens; Gretta T. Pecl; Bronwyn M. Gillanders; Claire M. Waluda; Elizabeth K. Shea; Didier Jouffre; Taro Ichii; Karsten Zumholz; Oleg N. Katugin; Stephen C. Leporati; Paul W. Shaw (Reviews in Fish Biology and Fisheries, 2007)

Season mediates herbivore effects on litter and soil microbial abundance and activity in a semi-arid woodland - Aimée T. Classen; Steven T. Overby; Stephen C. Hart; George W. Koch; Thomas G. Whitham (Plant and Soil, 2007)

Simulation of high-frequency sinusoidal electrical block of mammalian myelinated axons - Niloy Bhadra; Emily A. Lahowetz; Stephen T. Foldes; Kevin L. Kilgore (Journal of Computational Neuroscience, 2007)

An investigation of genome-wide associations of hypertension with microsatellite markers in the family blood pressure program (FBPP) - C. Charles Gu; Steven C. Hunt; Sharon Kardia; Stephen T. Turner; Aravinda Chakravarti; Nicholas Schork; Richard Olshen; David Curb; Cashell Jaquish; Eric Boerwinkle; D. C. Rao (Human Genetics, 2007)

The role of histone ubiquitylation and deubiquitylation in gene expression as determined by the analysis of an HTB1 K123R Saccharomyces cerevisiae strain - A. Irina Mutiu; Stephen M. T. Hoke; Julie Genereaux; Gaoyang Liang; Christopher J. Brandl (Molecular Genetics and Genomics, 2007)

Cephalopod hatchling growth: the effects of initial size and seasonal temperatures - Stephen C. Leporati; Gretta T. Pecl; Jayson M. Semmens (Marine Biology, 2007)

Particle suspensions and their regions of effect in the Neuse River Estuary: Implications for water quality monitoring - J. Stephen Fries; Rachel T. Noble; Hans W. Paerl; Gregory W. Characklis (Estuaries and Coasts, 2007)

Expression of the cytoskeleton linker protein ezrin in human cancers - Benjamin Bruce; Gaurav Khanna; Ling Ren; Goran Landberg; Karin Jirström; Charles Powell; Alain Borczuk; Evan T. Keller; Kirk J. Wojno; Paul Meltzer; Kristin Baird; Andrea McClatchey; et al. (Clinical & Experimental Metastasis, 2007)

Provider knowledge and practice regarding hepatitis B screening in Chinese-speaking patients - Cindy J. Lai; Tung T. Nguyen; Jimmy Hwang; Susan L. Stewart; Anson Kwan; Stephen J. McPhee (Journal of Cancer Education, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Resolving the genetic basis of invasiveness and predicting invasions - Cynthia Weinig; Marcus T. Brock; Jenny A. Dechaine; Stephen M. Welch (Genetica, 2007)

Nitrogen fertilizer and gender effects on the secondary metabolism of yaupon, a caffeine-containing North American holly - Matthew J. Palumbo; Francis E. Putz; Stephen T. Talcott (Oecologia, 2007)

Family-based association study of matrix metalloproteinase-3 and -9 haplotypes with susceptibility to ischemic white matter injury - Myriam Fornage; Thomas H. Mosley; Clifford R. Jack; Mariza de Andrade; Sharon L. R. Kardia; Eric Boerwinkle; Stephen T. Turner (Human Genetics, 2007)

DNA banking for plant breeding, biotechnology and biodiversity evaluation - Trevor R. Hodkinson; Stephen Waldren; John A. N. Parnell; Colin T. Kelleher; Karine Salamin; Nicolas Salamin (Journal of Plant Research, 2007)

Alkaloid Profiles, Concentration, and Pools in Velvet Lupine (Lupinus leucophyllus) Over the Growing Season - Stephen T. Lee; Michael H. Ralphs; Kip E. Panter; Daniel Cook; Dale R. Gardner (Journal of Chemical Ecology, 2007)

Significant linkage to airway responsiveness on chromosome 12q24 in families of children with asthma in Costa Rica - Juan C. Celedón; Manuel E. Soto-Quiros; Lydiana Avila; Stephen L. Lake; Catherine Liang; Eduardo Fournier; Mitzi Spesny; Craig P. Hersh; Jody S. Sylvia; Thomas J. Hudson; Andrei Verner; Barbara J. Klanderman; et al. (Human Genetics, 2006)

Carbon and Nitrogen Cycling in Southwestern Ponderosa Pine Forests - Stephen C. Hart; Paul C. Selmants; Sarah I. Boyle; Steven T. Overby (Forest Science, 2006)
Ponderosa pine forests of the southwestern United States were historically characterized by relatively open, parklike stands with a bunchgrass-dominated understory. This forest structure was maintained by frequent, low-intensity surface fires. Heavy livestock grazing, fire suppression, and favorable weather conditions following Euro-American settlement in the late 19th century resulted in a dramatic increase in pine regeneration. Today, many of these forest stands have high stand densities with low understory production, and are susceptible to infrequent, stand-replacing fires. The primary objective of our study was to better characterize the contemporary carbon (C) and nitrogen (N) cycling processes in relatively unmanaged southwestern ponderosa pine stands. We then compared these ecosystem conditions with those of an adjacent stand that had received an ecological restoration treatment that included thinning and prescribed burning. Our results suggest that N availability and aboveground net primary productivity (ANPP) of trees in these forests are low compared to other forests. Restoration treatments decreased ANPP but increased the proportion of ANPP in woody tissues. These treatments also increased soil respiration, water availability, temperature, and net nitrification, but had no effect on net N mineralization and microbial N. We speculate that the understory response to restoration treatments is a key factor affecting the overall ecosystem response in these forests.

Biocolloid retention in partially saturated soils - Tammo S. Steenhuis; Annette Dathe; Yuniati Zevi; Jennifer L. Smith; Bin Gao; Stephen B. Shaw; Dilkushi DeAlwis; Samary Amaro-Garcia; Rosemarie Fehrman; M. Ekrem Cakmak; Ian C. Toevs; Benjamin M. Liu; et al. (Biologia, 2006)

Tolerance of striped trumpeter Latris lineata embryos to ozonated seawater - Stephen C. Battaglene; David T. Morehead (Aquaculture International, 2006)

See globally, spike locally: oscillations in a retinal model encode large visual features - Greg J. Stephens; Sergio Neuenschwander; John S. George; Wolf Singer; Garrett T. Kenyon (Biological Cybernetics, 2006)

The Populus homeobox gene ARBORKNOX1 reveals overlapping mechanisms regulating the shoot apical meristem and the vascular cambium - Andrew T. Groover; Shawn D. Mansfield; Stephen P. DiFazio; Gayle Dupper; Joseph R. Fontana; Ryan Millar; Yvonne Wang (Plant Molecular Biology, 2006)

Zebra Mussel Antifouling Activity of the Marine Natural Product Aaptamine and Analogs - Jeffrey A. Diers; John J. Bowling; Stephen O. Duke; Subagus Wahyuono; Michelle Kelly; Mark T. Hamann (Marine Biotechnology, 2006)

A comparison of low-latitude cloud properties and their response to climate change in three AGCMs sorted into regimes using mid-tropospheric vertical velocity - Matthew C. Wyant; Christopher S. Bretherton; Julio T. Bacmeister; Jeffrey T. Kiehl; Isaac M. Held; Ming Zhao; Stephen A. Klein; Brian J. Soden (Climate Dynamics, 2006)

Taxa–area relationships for microbes: the unsampled and the unseen - Stephen Woodcock; Thomas P. Curtis; Ian M. Head; Mary Lunn; William T. Sloan (Ecology Letters, 2006)
The recent observation of a power–law relationship, S ∝ A z , between number of taxa, S , and area, A , for microbial eukaryotes and bacteria suggests that this is one of the few generic relationships in ecology, applicable to plants, animals and microbes. However, the rate of increase in the number of species with area varies from approximately the fourth ( z = 0.26) to as little as the 50th root ( z = 0.0019) in microbes. This is an enormous range for which no quantitative explanation has been proffered. We show by sampling from synthetic populations that the disparity between sample and community sizes in microbial community surveys means z can be considerably underestimated and accrual of rare taxa with increasing area will not be detectable. Significant microbial taxa–area relationships will only be observed when changes in community structure within samples correlate with area. Thus, the very low z values observed recently cannot be used as the sole evidence in support of any particular community theory of community assembly. More generally, this suggests that our search for patterns and laws in the microbial world will be profoundly influenced and, potentially distorted by the sample sizes that are typical of microbial community surveys.

The Influence of Habitat Complexity on Reef Fish Communities in the Northeastern Gulf of Mexico - Mark E. Lingo; Stephen T. Szedlmayer (Environmental Biology of Fishes, 2006)

Genetic Control of the Enantiomeric Composition of Ipsdienol in the Pine Engraver, Ips pini - Michael J. Domingue; William T. Starmer; Stephen A. Teale (Journal of Chemical Ecology, 2006)

Genetic alterations in caspase-10 may be causative or protective in autoimmune lymphoproliferative syndrome - Shigui Zhu; Amy P. Hsu; Marla M. Vacek; Lixin Zheng; Alejandro A. Schäffer; Janet K. Dale; Joie Davis; Roxanne E. Fischer; Stephen E. Straus; Donna Boruchov; Frank T. Saulsbury; Michael J. Lenardo; et al. (Human Genetics, 2006)

Quantifying the roles of immigration and chance in shaping prokaryote community structure - William T. Sloan; Mary Lunn; Stephen Woodcock; Ian M. Head; Sean Nee; Thomas P. Curtis (Environmental Microbiology, 2006)
Summary Naturally occurring populations of bacteria and archaea are vital to life on the earth and are of enormous practical significance in medicine, engineering and agriculture. However, the rules governing the formation of such communities are still poorly understood, and there is a need for a usable mathematical description of this process. Typically, microbial community structure is thought to be shaped mainly by deterministic factors such as competition and niche differentiation. Here we show, for a wide range of prokaryotic communities, that the relative abundance and frequency with which different taxa are observed in samples can be explained by a neutral community model (NCM). The NCM, which is a stochastic, birth–death immigration process, does not explicitly represent the deterministic factors and therefore cannot be a complete or literal description of community assembly. However, its success suggests that chance and immigration are important forces in shaping the patterns seen in prokaryotic communities.

AnnouncingEstuaries and Coasts, Journal of the Estuarine Research Federation - Stephen T. Threlkeld (Estuaries and Coasts, 2006)

Classification tree and minimum‐volume ellipsoid analyses of the distribution of ponderosa pine in the western USA - Jodi R. Norris; Stephen T. Jackson; Julio L. Betancourt (Journal of Biogeography, 2006)
Aim Ponderosa pine ( Pinus ponderosa Douglas ex Lawson & C. Lawson) is an economically and ecologically important conifer that has a wide geographic range in the western USA, but is mostly absent from the geographic centre of its distribution – the Great Basin and adjoining mountain ranges. Much of its modern range was achieved by migration of geographically distinct Sierra Nevada ( P. ponderosa var. ponderosa ) and Rocky Mountain ( P. ponderosa var. scopulorum ) varieties in the last 10,000 years. Previous research has confirmed genetic differences between the two varieties, and measurable genetic exchange occurs where their ranges now overlap in western Montana. A variety of approaches in bioclimatic modelling is required to explore the ecological differences between these varieties and their implications for historical biogeography and impending changes in western landscapes. Location Western USA. Methods We used a classification tree analysis and a minimum‐volume ellipsoid as models to explain the broad patterns of distribution of ponderosa pine in modern environments using climatic and edaphic variables. Most biogeographical modelling assumes that the target group represents a single, ecologically uniform taxonomic population. Classification tree analysis does not require this assumption because it allows the creation of pathways that predict multiple positive and negative outcomes. Thus, classification tree analysis can be used to test the ecological uniformity of the species. In addition, a multidimensional ellipsoid was constructed to describe the niche of each variety of ponderosa pine, and distances from the niche were calculated and mapped on a 4‐km grid for each ecological variable. Results The resulting classification tree identified three dominant pathways predicting ponderosa pine presence. Two of these three pathways correspond roughly to the distribution of var. ponderosa , and the third pathway generally corresponds to the distribution of var. scopulorum . The classification tree and minimum‐volume ellipsoid model show that both varieties have very similar temperature limitations, although var. ponderosa is more limited by the temperature extremes of the continental interior. The precipitation limitations of the two varieties are seasonally different, with var. ponderosa requiring significant winter moisture and var. scopulorum requiring significant summer moisture. Great Basin mountain ranges are too cold at higher elevations to support either variety of ponderosa pine, and at lower elevations are too dry in summer for var. scopulorum and too dry in winter for var. ponderosa . Main conclusions The classification tree analysis indicates that var. ponderosa is ecologically as well as genetically distinct from var. scopulorum . Ecological differences may maintain genetic separation in spite of a limited zone of introgression between the two varieties in western Montana. Two hypotheses about past and future movements of ponderosa pine emerge from our analyses. The first hypothesis is that, during the last glacial period, colder and/or drier summers truncated most of the range of var. scopulorum in the central Rockies, but had less dramatic effects on the more maritime and winter‐wet distribution of var. ponderosa . The second hypothesis is that, all other factors held constant, increasing summer temperatures in the future should produce changes in the distribution of var. scopulorum that are likely to involve range expansions in the central Rockies with the warming of mountain ranges currently too cold but sufficiently wet in summer for var. scopulorum . Finally, our results underscore the growing need to focus on genotypes in biogeographical modelling and ecological forecasting.

Animal behavior in urban ecosystems: Modifications due to human-induced stress - Stephen S. Ditchkoff; Sarah T. Saalfeld; Charles J. Gibson (Urban Ecosystems, 2006)

Water, salt, and nutrient exchanges in San Francisco Bay - Stephen V. Smith; James T. Hollibaugh (Limnology and Oceanography, 2006)
We constructed water, salt, and nutrient budgets for San Francisco Bay and used them to analyze the net biogeochemical performance of the bay. The bay was subdivided into three sectors, North, Central, and South Bay, with the Central Bay serving as a proxy for the oceanic end member. Separate budgets were constructed for the wet (October—March) and dry (April—October) seasons of each year for 6 yr (1990–1995). This period of record contained 2 yr of above normal runoff (1993, 1995) and 4 yr of below average runoff. Effluent from sewage treatment plants accounts for approximately 50% of the nutrient loading to the bay in winter and 80% of the summer loading. Both arms of the bay were apparently net heterotrophic during the winter, with this signal being strongest during the wet winters of 1993 and 1995. We conclude that overall the bay is slightly net autotrophic (production of new organic matter in the bay by plant growth exceeds respiratory demands); however, this varies seasonally (strongest in summer) and is complicated by the possibility of significant abiotic P adsorption in the North Bay.

Relating precipitation and water management to nutrient concentrations in the oligotrophic “upside‐down” estuaries of the Florida Everglades - Daniel L. Childers; Joseph N. Boyer; Stephen E. Davis; Christopher J. Madden; David T. Rudnick; Fred H. Sklar (Limnology and Oceanography, 2006)
We present 8 yr of long‐term water quality, climatological, and water management data for 17 locations in Everglades National Park, Florida. Total phosphorus (P) concentration data from freshwater sites (typically −1 , or 8 µg L −1 ) indicate the oligotrophic, P‐limited nature of this large freshwater—estuarine landscape. Total P concentrations at estuarine sites near the Gulf of Mexico (average ~0.5 µmol L −1 ) demonstrate the marine source for this limiting nutrient. This “upside down” phenomenon, with the limiting nutrient supplied by the ocean and not the land, is a defining characteristic of the Everglade landscape. We present a conceptual model of how the seasonality of precipitation and the management of canal water inputs control the marine P supply, and we hypothesize that seasonal variability in water residence time controls water quality through internal biogeochemical processing. Low freshwater inflows during the dry season increase estuarine residence times, enabling local processes to control nutrient availability and water quality. El Ni#x00F1;o—Southern Oscillation (ENSO) events tend to mute the seasonality of rainfall without altering total annual precipitation inputs. The Niño3 ENSO index (which indicates an ENSO event when positive and a La Niña event when negative) was positively correlated with both annual rainfall and the ratio of dry season to wet season precipitation. This ENSO‐driven disruption in seasonal rainfall patterns affected salinity patterns and tended to reduce marine inputs of P to Everglades estuaries. ENSO events also decreased dry season residence times, reducing the importance of estuarine nutrient processing. The combination of variable water management activities and interannual differences in precipitation patterns has a strong influence on nutrient and salinity patterns in Everglades estuaries.

Comparing and evaluating process‐based ecosystem model predictions of carbon and water fluxes in major European forest biomes - Pablo Morales; Martin T. Sykes; I. Colin Prentice; Pete Smith; Benjamin Smith; Harald Bugmann; Bärbel Zierl; Pierre Friedlingstein; Nicolas Viovy; Santi Sabaté; Anabel Sánchez; Eduard Pla; et al. (Global Change Biology, 2005)
Process‐based models can be classified into: (a) terrestrial biogeochemical models (TBMs), which simulate fluxes of carbon, water and nitrogen coupled within terrestrial ecosystems, and (b) dynamic global vegetation models (DGVMs), which further couple these processes interactively with changes in slow ecosystem processes depending on resource competition, establishment, growth and mortality of different vegetation types. In this study, four models – RHESSys, GOTILWA+, LPJ‐GUESS and ORCHIDEE – representing both modelling approaches were compared and evaluated against benchmarks provided by eddy‐covariance measurements of carbon and water fluxes at 15 forest sites within the EUROFLUX project. Overall, model‐measurement agreement varied greatly among sites. Both modelling approaches have somewhat different strengths, but there was no model among those tested that universally performed well on the two variables evaluated. Small biases and errors suggest that ORCHIDEE and GOTILWA+ performed better in simulating carbon fluxes while LPJ‐GUESS and RHESSys did a better job in simulating water fluxes. In general, the models can be considered as useful tools for studies of climate change impacts on carbon and water cycling in forests. However, the various sources of variation among models simulations and between models simulations and observed data described in this study place some constraints on the results and to some extent reduce their reliability. For example, at most sites in the Mediterranean region all models generally performed poorly most likely because of problems in the representation of water stress effects on both carbon uptake by photosynthesis and carbon release by heterotrophic respiration ( R h ). The use of flux data as a means of assessing key processes in models of this type is an important approach to improving model performance. Our results show that the models have value but that further model development is necessary with regard to the representation of the some of the key ecosystem processes.

Effect of sustained-release (SR) bupropion on craving and withdrawal in smokers deprived of cigarettes for 72 h - Vincenzo Teneggi; Stephen T. Tiffany; Lisa Squassante; Stefano Milleri; Luigi Ziviani; Alan Bye (Psychopharmacology, 2005)

Methylphenidate increases cigarette smoking - Craig R. Rush; Stephen T. Higgins; Andrea R. Vansickel; William W. Stoops; Joshua A. Lile; Paul E. A. Glaser (Psychopharmacology, 2005)

Influence of the duration of abstinence on the relative reinforcing effects of cigarette smoking - Jennifer Plebani Lussier; Stephen T. Higgins; Gary J. Badger (Psychopharmacology, 2005)

Comparison of the Pharmacokinetics of Oxycodone and Noroxycodone in Male Dark Agouti and Sprague–Dawley Rats: Influence of Streptozotocin-Induced Diabetes - Lillian Huang; Stephen R. Edwards; Maree T. Smith (Pharmaceutical Research, 2005)

New Insights into Old Lemurs: The Trophic Adaptations of the Archaeolemuridae - Laurie R. Godfrey; Gina M. Semprebon; Gary T. Schwartz; David A. Burney; William L. Jungers; Erin K. Flanagan; Frank P. Cuozzo; Stephen J. King (International Journal of Primatology, 2005)

A 40,000‐year woodrat‐midden record of vegetational and biogeographical dynamics in north‐eastern Utah, USA - Stephen T. Jackson; Julio L. Betancourt; Mark E. Lyford; Stephen T. Gray; Kate Aasen Rylander (Journal of Biogeography, 2005)
Aim A conspicuous climatic and biogeographical transition occurs at 40–45° N in western North America. This pivot point marks a north–south opposition of wet and dry conditions at interannual and decadal time‐scales, as well as the northern and southern limits of many dominant western plant species. Palaeoecologists have yet to focus on past climatic and biotic shifts along this transition, in part because it requires comparisons across dissimilar records [i.e. pollen from lacustrine sediments to the north and plant macrofossils from woodrat ( Neotoma ) middens to the south]. To overcome these limitations, we are extending the woodrat‐midden record northward into the lowlands of the central Rocky Mountains. Location Woodrat middens were collected from crevices and rock shelters on south‐facing slopes of Dutch John Mountain (2000–2200 m, 40°57′ N, 109°25′ W), situated on the eastern flanks of the Uinta Mountains in north‐eastern Utah. The site is near the regional limits for Pinus ponderosa , P. edulis , P. contorta , Cercocarpus ledifolius var. intricatus , Abies concolor , Ephedra viridis and other important western species. Methods We analysed pollen and plant macrofossils from the 40,000‐year midden sequence. The middens represent brief, depositional episodes (mostly years to decades). Four middens represent the early to full‐glacial period (40,000–18,000 cal‐yr bp ), eight middens are from the late‐glacial/early Holocene transition (13,500–9000 cal yr bp ), and 33 middens span the mid‐to‐late Holocene (last 7500 years). Temporal density of our Holocene middens (one every c. 210 years) is comparable with typical Holocene pollen sequences from lake sediments. Results Early to full‐glacial assemblages are characterized by low diversity and occurrence of montane conifers ( Picea pungens , Pseudotsuga menziesii , P. flexilis , Juniperus communis ) absent from the site today. Diversity increases in the late‐glacial samples with the addition of J. scopulorum , J. horizontalis , C. montanus , C. ledifolius var. intricatus and mesic understory species. The coniferous trees and J. communis declined and J. osteosperma appeared during the late‐glacial/Holocene transition. Juniperus osteosperma populations have occupied the site throughout the Holocene. Pinus ponderosa was established by 7500 cal‐yr bp , and has occurred at least locally ever since. Montane conifers and J. horizontalis persisted until c. 5500 cal‐yr bp . The signature events of the late Holocene were the invasions of P. edulis and Ephedra viridis and establishment of pinyon–juniper woodland in the last 800 years. Main conclusions The Dutch John Mountain midden record adds to an emerging picture in which mid‐elevation conifers ( P. flexilis , Pseudotsuga menziesii , Picea pungens , J. scopulorum , J. communis ) dominated vegetation over a wide area of the Colorado Plateau and adjacent Rocky Mountains. Rather than being fragmented, as often assumed in phylogeographical studies, these species had broader and more‐connected distributions than they do in the region today. Paradoxically, subalpine conifers ( Picea engelmannii , A. lasiocarpa ) occurred at higher elevations to the south, possibly representing declining precipitation from south to north owing to southward displacement of the polar jet stream. The Dutch John Mountain record displays a series of extinction and invasion events. Most of the extinctions were local in scale; nearly all constituents of fossil midden assemblages occur within a few kilometres of Dutch John Mountain, and some occur at least locally on its slopes. The sole exception is J. horizontalis , which is regionally extinct. In contrast to extinctions, Holocene invasions were regional in scale; J. osteosperma , P. ponderosa , P. edulis and Ephedra viridis immigrated from glacial‐age source populations far to the south.

Long‐term potential ecosystem responses to greenhouse gas‐induced thermohaline circulation collapse - Paul A. T. Higgins; Stephen H. Schneider (Global Change Biology, 2005)
Abrupt climate change, such as could occur with significant thermohaline circulation (THC) weakening, appears throughout the palaeoclimate record and in many model experiments. We examine potential responses of ecosystem structure and function to the combined influence of THC collapse and greenhouse gas increase in Central England using a broad range of temperature scenarios. We demonstrate that biological communities in the North Atlantic region could be heavily influenced by THC collapse, but that the pattern of ecosystem responses depends upon the seasonal pattern of temperature changes. Plausible THC collapse scenarios threaten the remnant habitat fragments, upon which much of England's remaining biodiversity depends, by causing shifts away from the currently dominant temperate broadleaf cold deciduous tree type. Furthermore, some ecosystem responses, particularly of energy partitioning between sensible and latent heat fluxes, constitute potentially substantial feedbacks to the local climate system. However, accurate assessment of biotic responses to THC collapse requires far better confidence of the resulting seasonal temperature cycle than climate models currently provide.

Nitrogen pools and fluxes in grassland soils sequestering carbon - Richard T. Conant; Keith Paustian; Stephen J. Del Grosso; William J. Parton (Nutrient Cycling in Agroecosystems, 2005)

Intrasexual Competition and Mating Behavior in Ptomascopus morio (Coleoptera: Silphidae Nicrophorinae) - Seizi Suzuki; Masahiro Nagano; Stephen T. Trumbo (Journal of Insect Behavior, 2005)

Monitoring perchlorate exposure and thyroid hormone status among raccoons inhabiting a perchlorate-contaminated site - Philip N. Smith; Sarah J. Utley; Stephen B. Cox; Todd A. Anderson; Scott T. McMurry (Environmental Monitoring and Assessment, 2005)

Distribution Patterns of Mercury in Lakes and Rivers of Northeastern North America - Ian F. Dennis; Thomas A. Clair; Charles T. Driscoll; Neil Kamman; Ann Chalmers; Jamie Shanley; Stephen A. Norton; Steve Kahl (Ecotoxicology, 2005)

Deconstruction of Historic Mercury Accumulation in Lake Sediments, Northeastern United States - Ethan Perry; Stephen A. Norton; Neil C. Kamman; P. M. Lorey; Charles T. Driscoll (Ecotoxicology, 2005)

Intensively Managed Forest Plantations in the Pacific Northwest: Conclusions - W. T. Adams; Stephen Hobbs; Norm Johnson (Journal of Forestry, 2005)

Intensively Managed Forest Plantations in the Pacific Northwest: Introduction - W. T. Adams; Stephen Hobbs; Norm Johnson (Journal of Forestry, 2005)

On the effects of topography on wind and the generation of currents in a large multi-basin lake - Francisco J. Rueda; S. Geoffrey Schladow; Stephen G. Monismith; Mark T. Stacey (Hydrobiologia, 2005)

Magnesian andesite and dacite lavas from Mt. Shasta, northern California: products of fractional crystallization of H2O-rich mantle melts - Timothy L. Grove; Michael B. Baker; Richard C. Price; Stephen W. Parman; Linda T. Elkins-Tanton; Nilanjan Chatterjee; Othmar Mntener (Contributions to Mineralogy and Petrology, 2005)

Shoreline tufa and tufaglomerate from Pleistocene Lake Bonneville, Utah, USA: stable isotopic and mineralogical records of lake conditions, processes, and climate - Stephen T. Nelson; M. Jay Wood; Alan L. Mayo; David G. Tingey; Dennis Eggett (Journal of Quaternary Science, 2005)
Shoreline carbonate deposits of Pleistocene Lake Bonneville record the conditions and processes within the lake, including the evaporative balance as well as vertical and lateral chemical and isotopic gradients. Tufas (swash‐zone) and tufaglomerates (cemented, subaqueous colluvium or beachrock) on multiple, well‐developed shorelines near the Silver Island Range, Utah, also present an opportunity to examine physicochemical lake processes through time. Three shorelines are represented by carbonate deposits, including the 23–20 ka Stansbury stage, 15–14.5 ka Bonneville stage, and 14.5–14 ka Provo stage. Mean δ 18 O VSMOW values of all three shorelines are statistically indistinguishable ( ∼ 27 ± 1‰), when a few Bonneville samples of unusual composition are neglected. However, differences in primary carbonate mineralogy indicate that the correspondence is an artefact of the different fractionation factors between calcite or aragonite and water. Second, in order to sustain a much smaller, shallower lake during the colder Stansbury stage, the climate must have also been relatively dry. Third, δ 18 O values in tufa are higher than tufaglomerate by ∼ 0.5‰, consistent with greater evaporative enrichment of lake water in the swash zone. Fourth, mean δ 13 C values for the Provo, Stansbury and Bonneville shorelines (4.4, 5.0 and 5.2‰, respectively) show that carbon species were dominated by atmospheric exchange, with the variations produced by differences in the oxidation of organic matter. Comparisons of shoreline carbonates with deep‐lake marls of the same approximate age indicate that shoreline carbonate was much higher in δ 13 C and δ 18 O values (both ∼ 2.5‰) during Bonneville time, whereas isotopic differences were minor (both ∼ 1‰) in Stansbury time. In particular, the Bonneville stage may have sustained large vertical or lateral isotopic gradients due to evaporative enrichment effects on δ 18 O values. In contrast, the lake during the much shallower Stansbury stage may have been well mixed. Differences in the primary mineralogy (Stansbury and Bonneville, aragonite > calcite; Provo, calcite > aragonite) reflect profound differences in lake chemistry in terms of open versus closed‐basin lakes. The establishment of a continuous outlet during Provo time probably reduced the Mg 2+ /Ca 2+ ratio of lake water. Curiously, regardless of primary mineralogy, tufaglomerate cements are enriched in Na + and Cl − and depleted in Mg 2+ relative to capping tufa of the same age. This probably reflects vital or kinetic effects in the swash zone (tufa). We suspect that ‘abiotic’ effects may have been important in the dark pore space of developing tufaglomerate, where the absence of light suppressed photosynthesis. Copyright © 2005 John Wiley & Sons, Ltd.

Komatiites and nickel sulfide ores of the Black Swan area, Yilgarn Craton, Western Australia. 3: Komatiite geochemistry, and implications for ore forming processes - Stephen J. Barnes; Robin E. T. Hill; Noreen J. Evans (Mineralium Deposita, 2004)

Plant Tissue Extraction Method for Complexed and Free Cyanide - Joseph T. Bushey; Stephen D. Ebbs; David A. Dzombak (Water, Air, & Soil Pollution, 2004)

Comparison of national administrative and commercial databases to monitor expenditure and costs of statins across Europe - T. Walley; P. Folino-Gallo; U. Schwabe; E. Van Ganse; P. Stephens (European Journal of Clinical Pharmacology, 2004)

Discussion of “Tectonic controls of Mississippi Valley-type lead-zinc mineralization in orogenic forelands” by D.C. Bradley and D.L. Leach - Stephen E. Kesler; John T. Chesley; John N. Christensen; Richard D. Hagni; Wouter Heijlen; J. Richard Kyle; Phillipe Muchez; Kula C. Misra; Rob van der Voo (Mineralium Deposita, 2004)

Deriving Grassland Management Factors for a Carbon Accounting Method Developed by the Intergovernmental Panel on Climate Change - Stephen M. Ogle; Richard T. Conant; Keith Paustian (Environmental Management, 2004)

Analysis of the Maize Polyubiquitin-1 Promoter Heat Shock Elements and Generation of Promoter Variants with Modified Expression Characteristics - Stephen J. Streatfield; Maria E. Magallanes-Lundback; Katherine K. Beifuss; Christopher A. Brooks; Robin L. Harkey; Robert T. Love; Jeff Bray; John A. Howard; Joseph M. Jilka; Elizabeth E. Hood (Transgenic Research, 2004)

Diversity and Productivity in Grassland Ecosystems - EMILY T. CLOYD; MELISSA S. LUCASH; NICOLE E. MUIR HOTALING; J. HOPE HORNBECK; HEATHER N. JENSEN; BYRON J. NORELIUS; STEPHEN H. REYNOLDS; JACOB D. WICKHAM (Conservation Biology, 2004)

North Atlantic phylogeography and large‐scale population differentiation of the seagrass Zostera marina L. - JEANINE L. OLSEN; WYTZE T. STAM; JAMES A. COYER; THORSTEN B. H. REUSCH; MARTIN BILLINGHAM; CHRISTOFFER BOSTRÖM; ELIZABETH CALVERT; HARTVIG CHRISTIE; STEPHEN GRANGER; RICHARD LA LUMIÈRE; NATALIYA MILCHAKOVA; MARIE‐PIERRE OUDOT‐LE SECQ; et al. (Molecular Ecology, 2004)
As the most widespread seagrass in temperate waters of the Northern Hemisphere, Zostera marina provides a unique opportunity to investigate the extent to which the historical legacy of the last glacial maximum (LGM18 000–10 000 years bp ) is detectable in modern population genetic structure. We used sequences from the nuclear rDNA–internal transcribed spacer (ITS) and chloroplast mat K‐intron, and nine microsatellite loci to survey 49 populations (> 2000 individuals) from throughout the species’ range. Minimal sequence variation between Pacific and Atlantic populations combined with biogeographical groupings derived from the microsatellite data, suggest that the trans ‐Arctic connection is currently open. The east Pacific and west Atlantic are more connected than either is to the east Atlantic. Allelic richness was almost two‐fold higher in the Pacific. Populations from putative Atlantic refugia now represent the southern edges of the distribution and are not genetically diverse. Unexpectedly, the highest allelic diversity was observed in the North Sea–Wadden Sea–southwest Baltic region. Except for the Mediterranean and Black Seas, significant isolation‐by‐distance was found from ~150 to 5000 km. A transition from weak to strong isolation‐by‐distance occurred at ~150 km among northern European populations suggesting this scale as the natural limit for dispersal within the metapopulation. Links between historical and contemporary processes are discussed in terms of the projected effects of climate change on coastal marine plants. The identification of a high genetic diversity hotspot in Northern Europe provides a basis for restoration decisions.

Vertical Distribution, Size Structure, and Habitat Associations of Four Blenniidae Species on Gas Platforms in the Northcentral Gulf of Mexico - Marek F. Topolski; Stephen T. Szedlmayer (Environmental Biology of Fishes, 2004)

Mitochondrial DNA phylogeography of western lowland gorillas ( Gorilla gorilla gorilla ) - Stephen L. Clifford; Nicola M. Anthony; Mireille Bawe‐Johnson; Kate A. Abernethy; Caroline E. G. Tutin; Lee J. T. White; Magdelena Bermejo; Michelle L. Goldsmith; Kelley McFarland; Kathryn J. Jeffery; Michael W. Bruford; E. Jean Wickings (Molecular Ecology, 2004)
The geographical distribution of genetic variation within western lowland gorillas ( Gorilla gorilla gorilla ) was examined to clarify the population genetic structure and recent evolutionary history of this group. DNA was amplified from shed hair collected from sites across the range of the three traditionally recognized gorilla subspecies: western lowland ( G. g. gorilla ), eastern lowland ( G. g. graueri ) and mountain ( G. g. beringei ) gorillas. Nucleotide sequence variation was examined in the first hypervariable domain of the mitochondrial control region and was much higher in western lowland gorillas than in either of the other two subspecies. In addition to recapitulating the major evolutionary split between eastern and western lowland gorillas, phylogenetic analysis indicates a phylogeographical division within western lowland gorillas, one haplogroup comprising gorilla populations from eastern Nigeria through to southeast Cameroon and a second comprising all other western lowland gorillas. Within this second haplogroup, haplotypes appear to be partitioned geographically into three subgroups: (i) Equatorial Guinea, (ii) Central African Republic, and (iii) Gabon and adjacent Congo. There is also evidence of limited haplotype admixture in northeastern Gabon and southeast Cameroon. The phylogeographical patterns are broadly consistent with those predicted by current Pleistocene refuge hypotheses for the region and suggest that historical events have played an important role in shaping the population structure of this subspecies.

The effect of introgressions of wheat D-genome chromosomes into 'Presto' triticale - Hikmet Budak; P. Stephen Baenziger; Brian S. Beecher; Robert A. Graybosch; Benjamin T. Campbell; Marry J. Shipman; Mustafa Erayman; Kent M. Eskridge (Euphytica, 2004)

Cardiorespiratory reflexes and aquatic surface respiration in the neotropical fish tambaqui ( Colossoma macropomum ): acute responses to hypercarbia - Luiz H. Florindo; Stephen G. Reid; Ana L. Kalinin; William K. Milsom; Francisco T. Rantin (Journal of Comparative Physiology B, 2004)

Detection of Human Immunodeficiency Virus Type 1 Envelope Peptide- Stimulated T-helper Cell Responses and Variations in the Corresponding Regions of Viral Isolates among Vertically Infected Children - Stephen Meddows-Taylor; Maria A. Papathanasopoulos; Louise Kuhn; Tammy M. Meyers; Caroline T. Tiemessen (Virus Genes, 2004)

A Late‐glacial chironomid record from Hawes Water, northwest England - Alan Bedford; Richard. T. Jones; Barbara Lang; Stephen Brooks; Jim D. Marshall (Journal of Quaternary Science, 2004)
This paper presents the results of a high‐resolution Late‐glacial chironomid stratigraphy from Hawes Water, a small carbonate lake in northern Lancashire. The samples were from a core taken from the terrestrialised margin of the present lake, which represents an intermediate depth between the true littoral and the profundal. The chironomid assemblage showed a high degree of sensitivity to both broad‐scale and short‐term temperature changes. Comparison with an existing proxy temperature record (δ 18 O) for the site confirmed the presence of four temperature inversions within the Late‐glacial Interstadial. A mean July air temperature inference model, derived from acid, soft‐water lakes in Norway and Svalbard, was applied to the data. Despite the absence of carbonate lakes within the Norwegian training set, there was a close similarity between trends in estimated July air temperature and the δ 18 O trace, with a particularly strong correspondence in the periods of clay deposition. This suggests that this model is highly robust. The inferred maximum Interstadial temperature was 13.4°C, dropping initially to 7.5°C in the Loch Lomond Stadial. Temperatures reach a maximum of nearly 10°C in this period, cool for a short period before rising rapidly to 13.2°C at the start of the Holocene. These temperatures are similar to but slightly higher than those estimated for Whitrig Bog, southeast Scotland, and lower than those inferred from coleopteran‐based models for sites in South Wales. Copyright © 2004 John Wiley & Sons, Ltd.

The DY genes of the cattle MHC: expression and comparative analysis of an unusual class II MHC gene pair - Keith T. Ballingall; Shirley A. Ellis; Niall D. MacHugh; Stephen D. Archibald; Declan J. McKeever (Immunogenetics, 2004)

Validating the use of woodrat ( Neotoma ) middens for documenting natural invasions - Mark E. Lyford; Stephen T. Jackson; Stephen T. Gray; Robert G. Eddy (Journal of Biogeography, 2004)
Aim Plant macrofossils in fossil woodrat ( Neotoma ) middens are the primary source of information on late Quaternary biogeographical history of plants in arid and semi‐arid regions of North America. Macrofossil records from middens are playing particularly important roles in documenting spatial and temporal patterns of plant migrations and invasions since the last glacial maximum 21,000 years ago. However, relatively few actualistic studies comparing contents of modern middens with surrounding flora and vegetation have been carried out. The primary aim of this study is to assess the reliability of midden assemblages in detecting the presence of tree, shrub and several other plant species growing on the surrounding landscape. The secondary aims are to determine whether probability of occurrence of species in middens is related to abundance in vegetation, and whether representation of individual species in middens is contingent on presence/absence or abundance of other species. Location Our five study sites were bedrock escarpments or canyons in the central Rocky Mountains (north‐eastern Utah, central Wyoming and south‐central Montana). All sites were in conifer woodland or forest/woodland variously dominated by Juniperus osteosperma , J. scopulorum , Pinus edulis , P. flexilis and Pseudotsuga menziesii . Neotoma cinerea is the only woodrat species in the region. Methods Macrofossil assemblages from 59 modern middens (all showing clear signs of recent or ongoing woodrat activity) were compared with floristic composition of vegetation within 50 m of the middens, and with percent cover of vegetation within 30 m of the middens. Results Coniferous trees and shrubs were well‐represented in middens, occurring consistently even when abundance in the local vegetation was very low. Juniperus osteosperma and J. scopulorum were particularly well‐represented, occurring in middens regardless of local abundance. Other conifers ( P. edulis , P. flexilis , P. ponderosa , Pseudotsuga menziesii ) were occasionally absent from middens when abundance in vegetation was low ( Main conclusions Middens constructed by N. cinerea are highly reliable sensors of presence/absence of J. osteosperma and J. scopulorum , and hence can be used to infer invasions and past biogeographical distributions of these species. The middens are also reliable in registering populations of other conifers, although presence in middens may be contingent on local abundance. Additional comparative studies are needed to develop a sound empirical basis for using middens of N. cinerea and other species to infer past presence/absence of plant species on the landscape, and to explore the vegetation‐sensing properties of midden assemblages.

The potential to mitigate global warming with no‐tillage management is only realized when practised in the long term - Johan Six; Stephen M. Ogle; F. Jay breidt; Rich T. Conant; Arvin R. Mosier; Keith Paustian (Global Change Biology, 2004)
No‐tillage (NT) management has been promoted as a practice capable of offsetting greenhouse gas (GHG) emissions because of its ability to sequester carbon in soils. However, true mitigation is only possible if the overall impact of NT adoption reduces the net global warming potential (GWP) determined by fluxes of the three major biogenic GHGs (i.e. CO 2 , N 2 O, and CH 4 ). We compiled all available data of soil‐derived GHG emission comparisons between conventional tilled (CT) and NT systems for humid and dry temperate climates. Newly converted NT systems increase GWP relative to CT practices, in both humid and dry climate regimes, and longer‐term adoption (>10 years) only significantly reduces GWP in humid climates. Mean cumulative GWP over a 20‐year period is also reduced under continuous NT in dry areas, but with a high degree of uncertainty. Emissions of N 2 O drive much of the trend in net GWP, suggesting improved nitrogen management is essential to realize the full benefit from carbon storage in the soil for purposes of global warming mitigation. Our results indicate a strong time dependency in the GHG mitigation potential of NT agriculture, demonstrating that GHG mitigation by adoption of NT is much more variable and complex than previously considered, and policy plans to reduce global warming through this land management practice need further scrutiny to ensure success.

What is represented by vertical shifts in self-administration dose?response curves? - Jonathan L. Katz; Stephen T. Higgins (Psychopharmacology, 2004)

Detection of Huanglongbing (citrus greening disease) in Timor-Leste (East Timor) and in Papua New Guinea - M. P. Weinert; S. C. Jacobson; J. F. Grimshaw; G. A. Bellis; P. M. Stephens; T. G. Gunua; M. F. Kame; R. I. Davis (Australasian Plant Pathology, 2004)

Cytosolic Ca2+ pulses and protein kinase activation in the signal transduction pathways leading to the plant oxidative burst - Stephen G. Cessna; Jitae Kim; Ann T. S. Taylor (Journal of Plant Biology, 2003)

Genetic evidence for female‐biased dispersal in the bullfrog, Rana catesbeiana (Ranidae) - James D. Austin; José A. Dávila; Stephen C. Lougheed; Peter T. Boag (Molecular Ecology, 2003)
Sex‐biased dispersal is an important but unexplored area of amphibian ecology. We predicted female‐biased dispersal in the bullfrog ( Rana catesbeiana ) based on aspects of their mating system and tested this prediction using data from seven polymorphic DNA microsatellite loci. Allelic ( F ‐statistics) and genotypic [assignment index, ( AIc )] frequencies from nine Ontario populations support our prediction, although significant sex differences in inbreeding and variance of AIc were not detected. The diversity of mating systems found in amphibians represents an important avenue for investigating the relationship between reproductive systems, dispersal and phylogeny.

Fractional crystallization and mantle-melting controls on calc-alkaline differentiation trends - Timothy L. Grove; Linda T. Elkins-Tanton; Stephen W. Parman; Nilanjan Chatterjee; Othmar Mntener; Glenn A. Gaetani (Contributions to Mineralogy and Petrology, 2003)

The validity of the reinstatement model of craving and relapse to drug use - Jonathan L. Katz; Stephen T. Higgins (Psychopharmacology, 2003)

Erratum to The validity of the reinstatement model of craving and relapse to drug use - Jonathan L. Katz; Stephen T. Higgins (Psychopharmacology, 2003)

Effects of elevated carbon dioxide on green leaf tissue and leaf litter quality in an intact Mojave Desert ecosystem - SHARON A. BILLINGS; STEPHEN F. ZITZER; HEATHER WEATHERLY; SEAN M. SCHAEFFER; T. CHARLET; JOHN A. ARNONE; R. D. EVANS (Global Change Biology, 2003)
The effects of elevated carbon dioxide (CO 2 ) on plant litter are critical determinants of ecosystem feedback to changing atmospheric CO 2 concentrations. We measured concentrations of nitrogen (N) and carbon (C) and calculated C : N ratios of green leaves of two desert perennial shrubs, and the same quality parameters plus lignin and cellulose content of leaf litter from four shrub species exposed to elevated CO 2 (FACE technology; Hendrey & Kimball, 1994 ) for 3 years in an intact Mojave Desert ecosystem. Shrubs tested were Larrea tridentata , Lycium pallidum , Lycium andersonii and Ambrosia dumosa . We calculated resorption efficiency from green tissue and leaf litter N data and measured lignin and cellulose content in litter in the last year study. Green leaves of L. tridentata grown under elevated CO 2 had significantly lower N concentrations and higher C : N ratios than shrubs grown in ambient conditions in 1999 ( P Lycium pallidum green leaves grown under elevated CO 2 had significantly lower N concentrations and higher C : N ratios than shrubs grown under ambient conditions in 2000 ( P 2 effect on C content of either species. We found no effect of CO 2 on N or C content, C : N ratios, or lignin or cellulose concentrations in leaf litter of L. tridentata , L. pallidum , L. andersonii , or A. dumosa . There was no significant effect of CO 2 on estimates of shrub resorption efficiency. There was a seasonal effect on green tissue and litter tissue quality for L. tridentata , with lower tissue N content in summer than in spring or winter months. These data suggest that any productivity increases with elevated CO 2 in desert ecosystems may not be limited by lower leaf litter quality and that resorption efficiency calculations are best performed on an individual leaf basis.

Assessment of antimicrobial activity of hydrophilic betaines in osmotically stressed bacteria. - Barbara A. Peddie; Jacqueline E. Wood; Michael Lever; D. Alan R. Happer; Frederick de Zwart; Stephen T. Chambers (Antonie van Leeuwenhoek, 2003)

Comparison of Beach Bacterial Water Quality Indicator Measurement Methods - Rachel T. Noble; Stephen B. Weisberg; Molly K. Leecaster; Charles D. McGee; Kerry Ritter; Kathy O. Walker; Patricia M. Vainik (Environmental Monitoring and Assessment, 2003)

Managing Troubled Data: Coastal Data Partnerships Smooth Data Integration - Stephen S. Hale; Anne Hale Miglarese; M. Patricia Bradley; Thomas J. Belton; Larry D. Cooper; Michael T. Frame; Christopher A. Friel; Linda M. Harwell; Robert E. King; William K. Michener; David T. Nicolson; Bruce G. Peterjohn (Environmental Monitoring and Assessment, 2003)

Optical remote sensing of benthic habitats and bathymetry in coastal environments at Lee Stocking Island, Bahamas: A comparative spectral classification approach - Eric M. Louchard; R. Pamela Reid,; F. Carol Stephens; Curtiss O. Davis,; Robert A. Leathers; Downes T. Valerie (Limnology and Oceanography, 2003)
Remote sensing is a valuable tool for rapid identification of benthic features in coastal environments. Past applications have been limited, however, by multispectral models that are typically difficult to apply when bottom types are heterogeneous and complex. We attempt to overcome these limitations by using a spectral library of remote sensing reflectance (R rs ), generated through radiative transfer computations, to classify image pixels according to bottom type and water depth. R rs spectra were calculated for water depths ranging from 0.5 to 20 m at 0.5− to 1.0−m depth intervals using measured reflectance spectra from sediment, seagrass, and pavement bottom types and inherent optical properties of the water. To verify the library, computed upwelling radiance and downwelling irradiance spectra were compared to field measurements obtained with a hyperspectral tethered spectral radiometer buoy (TSRB). Comparisons between simulated spectra and TSRB data showed close matches in signal shape and magnitude. The library classification method was tested on hyperspectral data collected using a portable hyperspectral imager for low light spectroscopy (PHILLS) airborne sensor near Lee Stocking Island, Bahamas. Two hyperspectral images were classified using a minimum‐distance method. Comparisons with ground truth data indicate that library classification can be successful at identifying bottom type and water depth information from hyperspectral imagery. With the addition of diverse sediments types and different species of corals, seagrass, and algae, spectral libraries will have the potential to serve as valuable tools for identifying characteristic wavelengths that can be incorporated into bottom classification and bathymetry algorithms.

A genome screen for linkage disequilibrium in HLA-DRB1*15-positive Germans with multiple sclerosis based on 4666 microsatellite markers - Rene Goedde; Stephen Sawcer; Stefan Boehringer; Bianca Miterski; Eckhart Sindern; Michael Haupts; Sebastian Schimrigk; Alastair Compston; Joerg T. Epplen (Human Genetics, 2002)

Reproduction of hatchery-reared and transplanted wild bay scallops, Argopecten irradians irradians, relative to natural populations - Stephen T. Tettelbach; Christopher F. Smith; Peter Wenczel; Edward Decort (Aquaculture International, 2002)

Genetic diversity and evolution of the human leptin locus tetranucleotide repeat - Susan Moffett; Jeremy Martinson; Mark D. Shriver; Ranjan Deka; Stephen T. McGarvey; Ramiro Barrantes; Robert E. Ferrell (Human Genetics, 2002)

A high resolution, multiproxy Late‐glacial record of climate change and intrasystem responses in northwest England - Richard T. Jones; Jim D. Marshall; Stephen F. Crowley; Alan Bedford; Nigel Richardson; Jan Bloemendal; Frank Oldfield (Journal of Quaternary Science, 2002)
A lacustrine carbonate sequence from Hawes Water, Lancashire, UK, has been studied using stable isotopic, lithological, pollen and mineral magnetic analysis. The data reveal four abrupt climatic oscillations in the Late‐glacial Interstadial leading up to the onset of the Loch Lomond Stadial. The data also point to climatic warming relatively early within the stadial, ca. 12 500 GRIP yr, prior to the onset of the Holocene. The oxygen isotope record is taken as a signature of climate forcing against which the response of the lake‐system can be monitored. By adopting this approach it is revealed that the response of the biological system to the rapid climatic oscillations is non‐linear and primarily a function of the antecedent conditions. A significant end‐Devensian isotopic excursion (A) is matched by only minor changes in the cold‐adapted floras and faunas. During the warmer interstadial, the response of the biological ecosystem (events B–D) is clearly influenced by thresholds: major changes in the catchment vegetation associated with relatively minor oscillations in the isotopic signature. The stratigraphical patterns reveal significant lag effects between the onset of climate deterioration and resulting changes in vegetation. Copyright © 2002 John Wiley & Sons, Ltd.

Conservation genetics of the loggerhead shrike (Lanius ludovicianus) in central and eastern North America - Mary Vallianatos; Stephen C. Lougheed; Peter T. Boag (Conservation Genetics, 2002)

Buffer‐Zone Distances to Protect Foraging and Loafing Waterbirds from Disturbance by Personal Watercraft and Outboard‐Powered Boats - James A. Rodgers; Stephen T. Schwikert (Conservation Biology, 2002)
Outdoor recreation and ecotourism can have negative effects on wildlife species, so it is important to determine buffer zones within which activities near critical wildlife areas are limited. We exposed 23 species of waterbirds ( Pelecaniformes, Ciconiiformes, Falconiformes, Charadriiformes) to the direct approach of a personal watercraft ( PWC) and an outboard‐powered boat to determine their flush distances. We used 11 sites with a mixture of low, moderate, and high amounts of human activity along the east and west coasts of Florida during September–November 1998 and April–June 1999. We detected considerable variation in flush distances among individuals within the same species and among species in response to both types of vessels. Average flush distances for the PWC ranged from 19.5 m ( Least Tern [ Sterna antillarum ]) to 49.5 m (Osprey [ Pandion haliaetus ]), whereas average flush distances for the outboard‐powered boat ranged from 23.4 m ( Forster's Tern [ S. forsteri ]) to 57.9 m (Osprey). Larger species generally exhibited greater average flush distances for both types of watercraft. A comparison of the flush distances elicited by each watercraft indicated that only the Great Blue Heron ( Ardea herodias ) exhibited significantly larger flush distances ( t test, p Anhinga anhinga ], Little Blue Heron [ Egretta caerulea ], Willet [ Catoptrophorus semipalmatus ], and Osprey) exhibited significantly larger flush distances ( t test, p t test, p > 0.05) in their flush distances in response to the fast‐moving PWC and the outboard‐powered boat. Our data suggest that a single buffer‐zone distance can be developed for both PWC and outboard‐powered vessels. Buffer zones of 180 m for wading birds, 140 m for terns and gulls, 100 m for plovers and sandpipers, and 150 m for ospreys would minimize their disturbance at foraging and loafing sites in Florida.

Catecholamine neuron groups in rat brain slices differ in their susceptibility to excitatory amino acid induced dendritic degeneration - Petra T. Bywood; Stephen M. Johnson (Neurotoxicity Research, 2001)

A low dose alcohol drug discrimination in social drinkers: relationship with subjective effects - Anne Jackson; Stephens D.; Duka T. (Psychopharmacology, 2001)

Physiology, biochemistry and taxonomy of deep-sea nitrile metabolising Rhodococcus strains - Stephen C. Heald; Pedro F.B. Brandão; Richard Hardicre; Alan T. Bull (Antonie van Leeuwenhoek, 2001)

Comparison of Tissue Concentrations After Intramuscular and Topical Administration of Ketoprofen - Irmgard Tegeder; Jörn Lötsch; Martina Kinzig-Schippers; Fritz Sörgel; Gary R. Kelm; Stephen T. Meller; Gerd Geisslinger (Pharmaceutical Research, 2001)

Gender- and age-dependent relationships between the E-selectin S128R polymorphism and coronary artery calcification - Darrell L. Ellsworth; Lawrence F. Bielak; Stephen T. Turner; Patrick F. Sheedy; Eric Boerwinkle; Patricia A. Peyser (Journal of Molecular Medicine, 2001)

Feeding, egg production, and egg hatching success of the copepods Acartia tonsa and Temora longicornis on diets of the toxic diatom Pseudo-nitzschia multiseries and the non-toxic diatom Pseudo-nitzschia pungens - Jean A. Lincoln; Jefferson T. Turner; Stephen S. Bates; Claude Léger; David A. Gauthier (Hydrobiologia, 2001)

Dynamic bacterial and viral response to an algal bloom at subzero temperatures - Patricia L. Yager; Tara L. Connelly; Behzad Mortazavi; K. Eric Wommack; Nasreen Bano; James E. Bauer; Stephen Opsahl; James T. Hollibaugh (Limnology and Oceanography, 2001)
New evidence suggests that cold‐loving (psychrophilic) bacteria may be a dynamic component of the episodic bloom events of high‐latitude ecosystems. Here we report the results of an unusually early springtime study of pelagic microbial activity in the coastal Alaskan Arctic. Heterotrophic bacterioplankton clearly responded to an algal bloom by doubling cell size, increasing the fraction of actively respiring cells (up to an unprecedented 84% metabolically active using redox dye CTC), shifting substrate‐uptake capabilities from kinetic parameters better adapted to lower substrate concentrations to those more suited for higher concentrations, and more than doubling cell abundance. Community composition (determined by polymerase chain reaction/DGGE and nucleotide sequence analysis) also shifted over the bloom. Results support, for the first time with modern molecular methods, previous culture‐based observations of bacterial community succession during Arctic algal blooms and confirm that previously observed variability in pelagic microbial activity can be linked to changes in community structure. During early bloom stages, virioplankton and bacterial abundance were comparable, suggesting that mortality due to phage infection was low at that time. The virus‐to‐bacteria ratio (VBR) increased 10‐fold at the height of the bloom, however, suggesting an increased potential for bacterioplankton mortality resulting from viral infection. The peak in VBR coincided with observed shifts in both microbial activity and community structure. These early‐season data suggest that substrate and virioplankton interactions may control the active microbial carbon cycling of this region.

Evidence for Holocene climate variability from the sediments of a Scottish remote mountain lake - Richard W. Battarbee; Nigel G. Cameron; Paul Golding; Stephen J. Brooks; Roy Switsur; Doug Harkness; Peter Appleby; Frank Oldfield; Roy Thompson; Don T. Monteith; Andrew McGovern (Journal of Quaternary Science, 2001)
High resolution sampling of sediment cores covering approximately the last 4000 yr from Lochan Uaine, a small corrie loch in the Scottish Cairngorm Mountains, show quasi‐periodic cycles in organic matter (measured as percentage loss on ignition). Analysis of these cycles show correspondences between loss on ignition, δ 13 C values and chironomid head capsule abundance. We interpret the changes as reflecting changes in lake productivity and hypothesise that they are driven by climate variability. However, it is not yet clear whether the periods of relatively high organic matter production and preservation are associated with colder or with warmer conditions. Nevertheless the results indicate the value of using sediments from remote, undisturbed mountain lakes as recorders of Holocene climate variability. Copyright © 2001 John Wiley & Sons, Ltd.

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

Trends in wood density and structure are linked to prevention of xylem implosion by negative pressure - Uwe G. Hacke; John S. Sperry; William T. Pockman; Stephen D. Davis; Katherine A. McCulloh (Oecologia, 2001)

d -Amphetamine increases choice of cigarette smoking over monetary reinforcement - Jennifer W. Tidey; Stephen T. Higgins; Suzanne C. O'Neill (Psychopharmacology, 2000)

Habitat Fragmentation and Burying Beetle Abundance and Success - Stephen T. Trumbo; Philip L. Bloch (Journal of Insect Conservation, 2000)

Reproductive and hormonal factors associated with mammographic breast density by age (United States) - Amira Y. El-Bastawissi; Emily White; Margaret T. Mandelson; Stephen H. Taplin (Cancer Causes & Control, 2000)

Using size distributions to detect nutrient and sediment effects within and between habitats - Robert M. Baca; Stephen T. Threlkeld (Hydrobiologia, 2000)

A Regional Survey of the Microbiological Water Quality along the Shoreline of the Southern California Bight - Rachel T. Noble; John H. Dorsey; Molly Leecaster; Victoria Orozco-Borbón; Daniel Reid; Kenneth Schiff; Stephen B. Weisberg (Environmental Monitoring and Assessment, 2000)

Frequency-Magnitude Relationships for seismic areas around the capital cities of Solomon, Vanuatu, Tonga and Fiji Islands - A. Hofstetter; A. Shapira; K. Bulehite; T. Jones; K. Mafi; A. Malitzky; A. Papabatu; G. Prasad; M. Regnier; G. Shorten; A. Singh6; M. Stephen; et al. (Journal of Seismology, 2000)

Regioselective alkylation at the N4 positionof a 3-oxo-1,4-benzodiazepine on solid support - Fadia E. Ali; Catherine C.K. Yuan; Stephen T. Ross; Leon B. Hall (Molecular Diversity, 2000)

An axonemal dynein at the Hybrid Sterility 6 locus: implications for t haplotype-specific male sterility and the evolution of species barriers - John Fossella; Sadhana A. Samant; Lee M. Silver; Stephen M. King; Kevin T. Vaughan; Patricia Olds-Clarke; Karl A. Johnson; Atsushi Mikami; Richard B. Vallee; Stephen H. Pilder (Mammalian Genome, 2000)

Nitrogen deficiency, phosphorus sufficiency, and the invasion of Lake Kinneret, Israel, by the N2-fixing cyanobacterium Aphanizomenon ovalisporum - Moshe Gophen; Val H. Smith; Aminadav Nishri; Stephen T. Threlkeld (Aquatic Sciences, 1999)

An in vitro model of angiogenesis: Basic features - Eileen T. Bishop; Graham T. Bell; Stephen Bloor; I.J. Broom; Neil F.K. Hendry; Denys N. Wheatley (Angiogenesis, 1999)

Genetic variation at twentythree microsatellite loci in sixteen human populations - Ranjan Deka; Mark D. Shriver; Ling Mei Yu; Elisa Mueller Heidreich; Li Jin; Yixi Zhong; Stephen T. Mcgarvey; Shyam Swarup Agarwal; Clareann H. Bunker; Tetsuro Miki; Joachim Hundrieser; Shih-Jiun Yin; et al. (Journal of Genetics, 1999)

Osmoprotective activity, urea protection, and accumulation of hydrophilic betaines in Escherichia coli and Staphylococcus aureus - Barbara A. Peddie; Michael Lever; Kelly Randall; Stephen T. Chambers (Antonie van Leeuwenhoek, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Pollen dispersal models in Quaternary plant ecology: Assumptions, parameters, and prescriptions - Stephen T. Jackson; Mark E. Lyford (The Botanical Review, 1999)

Nitrogen deficiency, phosphorus sufficiency, and the invasion of Lake Kinneret, Israel, by the N - Moshe Gophen; Val H. Smith; Aminadav Nishri; Stephen T. Threlkeld (Aquatic Sciences, 1999)

Taxonomy and biotransformation activities of some deep-sea actinomycetes - Joy A. Colquhoun; Stephen C. Heald; Lina Li; J. Tamaoka; Chiaki Kato; Koki Horikoshi; A. T. Bull (Extremophiles, 1998)

The toxic mechanism and metabolic effects of atractyloside in precision-cut pig kidney and liver slices - David K. Obatomi; Nguyen T. K. Thanh; Stephen Brant; Peter H. Bach (Archives of Toxicology, 1998)

ELISA detection of restriction site polymorphisms in the pig ryanodine receptor locus - Gary E. Truett; Jerilyn A. Walker; Joanie B. Wilson; Stephen M. Redmann, Jr.; Richard T. Tulley; Gregg R. Eckardt; Graham Plastow; Michael Lefevre (Mammalian Genome, 1998)

Defined medium for normal adult human prostatic stromal cells - Donna M. Peehl; Robert G. Sellers; Stephen T. Wong (In Vitro Cellular & Developmental Biology - Animal, 1998)

Species richness patterns of amphibians in southwestern Ontario ponds - Stephen J. Hecnar; Robert T. M'Closkey (Journal of Biogeography, 1998)
In southwestern Ontario amphibian species richness (α‐diversity) was investigated at 180 ponds from 1992 to 1994. Patterns of species richness were compared among regions and the relationship between species richness and local habitat and regional landscape variables was investigated. Patterns of incidence differed among regions, with species that use woodlands being rare in one of the regions. Repeated measures analysis of variance indicated that species richness differed significantly among regions but not among sub‐regions nested within regions. Species richness did not change significantly over time and there was no region by year effect. Species richness was highly correlated with local variables related to fish predation and to regional variables related to forest cover. Multiple regression indicated that a combination of local and regional variables best accounted for the variance in species richness, but the amount of regional woodlands was the single most important variable. The pattern of species richness can be explained by historical deforestation as the primary process.

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Discriminative stimulus properties of low doses of ethanol in humans - T. Duka; D. N. Stephens; C. Russell; R. Tasker (Psychopharmacology, 1998)

Alternate-day buprenorphine dosing is preferred to daily dosing by opioid-dependent humans - L. Amass; Warren K. Bickel; John P. Crean; Joan Blake; Stephen T. Higgins (Psychopharmacology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Application of life cycle inventory analysis to fuel tank system design - Gregory A. Keoleian; Sabrina Spatari; Robb T. Beal; Robert D. Stephens; Ronald L. Williams (The International Journal of Life Cycle Assessment, 1998)

Spectral karyotyping refines cytogenetic diagnostics of constitutional chromosomal abnormalities - E. Schröck; T. Veldman; Hesed Padilla-Nash; Y. Ning; Jack Spurbeck; Syed Jalal; Lisa G. Shaffer; Peter Papenhausen; Chahira Kozma; Mary C. Phelan; Eigil Kjeldsen; Stephen A. Schonberg; et al. (Human Genetics, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Substrate preference in age-0 red snapper, Lutjanus campechanus - Stephen T. Szedlmayer; Jeffrey C. Howe (Environmental Biology of Fishes, 1997)

Division of labor between undertaker specialists and other middle-aged workers in honey bee colonies - Stephen T. Trumbo; Zhi-Yong Huang; Gene E. Robinson (Behavioral Ecology and Sociobiology, 1997)

Genetic mapping of lysyl oxidase-2 (Loxl) on mouse Chromosome 9 - Velizar T. Tchernev; Tom P. Yang; Stephen F. Kingsmore (Mammalian Genome, 1997)

Mating in bighorn sheep: frequent male reproduction via a high-risk "unconventional" tactic - John T. Hogg; Stephen H. Forbes (Behavioral Ecology and Sociobiology, 1997)

Response - Mark A. Batzer; Stephen T. Sherry; Prescott L. Deininger; Mark Stoneking (Journal of Molecular Evolution, 1997)

Conformational analysis of galanin using end to end distance distribution observed by Förster resonance energy transfer - T. Kulinski; Anders B. A. Wennerberg; R. Rigler; Stephen W. Provencher; M. Pooga; Ü. Langel; Tamas Bartfai (European Biophysics Journal, 1997)

Isolation and Characterization of an Acetylated Impurity in Escherichia coli-Derived Recombinant Human Interleukin-10 (IL-10) Drug Substance - Mollie N. Pflumm; Stephen C. Gruber; Anthony Tsarbopoulos; David Wylie; Birendra Pramanik; James N. Bausch; Suman T. Patel (Pharmaceutical Research, 1997)

Spatial Scale and Determination of Species Status of the Green Frog. Escala Espacial y Determinacion del Estatus de la Especie de Rana Verde - Stephen J. Hecnar; Robert T. M'Closkey (Conservation Biology, 1997)

Isolation and characterization of the complete mouse emerin gene - Kersten Small; Maylene Wagener; Stephen T. Warren (Mammalian Genome, 1997)

A natural "Benchmark" for Ecosystem Function - Yrjö Haila; Patrick J. Comer; Malcolm Hunter; Michael J. Samways; Clive Hambler; Martin R. Speight; Paul Hendricks; Stephen Herrero; F. Stephen Dobson; Andrew T. Smith; Jinping Yu (Conservation Biology, 1997)

The coleoptile chloroplast: Distinct distribution of xanthophyll cycle pigments, and enrichment in Photosystem II - Jianxin Zhu; Stephen M. Gómez; Bruce T. Mawson; Xiangqun Jin; Eduardo Zeiger (Photosynthesis Research, 1997)

Molecular modeling parameters predict antioxidant efficacy of 3-indolyl compounds - H. G. Shertzer; M. Wilson Tabor; I. T. D. Hogan; Stephen J. Brown; Malcolm Sainsbury (Archives of Toxicology, 1996)

Extra-pair paternity and the opportunity for sexual selection in a socially monogamous bird (Dendroica petechia) - Stephen M. Yezerinac; Patrick J. Weatherhead; Peter T. Boag (Behavioral Ecology and Sociobiology, 1995)

Extra-pair paternity and the opportunity for sexual selection in a socially monogamous bird ( Dendroica petechia ) - Stephen M. Yezerinac; P. J. Weatherhead; Peter T. Boag (Behavioral Ecology and Sociobiology, 1995)

Membrane potential fluctuations of human T-lymphocytes have fractal characteristics of fractional brownian motion - Albert M. Churilla; Wolfram A. Gottschalke; Larry S. Liebovitch; Lev Y. Selector; Angelo T. Todorov; Stephen Yeandle (Annals of Biomedical Engineering, 1995)

Family structure influences mate choice in white-fronted bee-eaters - Peter H. Wrege; Stephen T. Emlen (Behavioral Ecology and Sociobiology, 1994)

Family structure influences mate choice in white-fronted bee-eaters - P. H. Wrege; Stephen T. Emlen (Behavioral Ecology and Sociobiology, 1994)

Nodulation of soybean roots by an isolate of Bradyrhizobium japonicum with reduced firm attachment capability - Stephen J. Vesper; T. V. Bhuvaneswari (Archives of Microbiology, 1988)

Experimental Rift Valley fever in rhesus macaques - C. J. Peters; D. Jones; R. Trotter; J. Donaldson; J. White; E. Stephen; T. W. Slone (Archives of Virology, 1988)

Biochemical determination of parental uncertainty in white-fronted bee-eaters - Peter H. Wrege; Stephen T. Emlen (Behavioral Ecology and Sociobiology, 1987)

Reproductive, immunologie, and cytogenetic effects of dietary 3,3?,4,4?-tetrachloroazoxybenzene exposure to mice - Michael R. Bleavins; Ronald D. Hinsdill; M. T. Stephen Hsia; Lorraine F. Meisner; John E. Wiley (Archives of Environmental Contamination and Toxicology, 1985)

Effects of 3,3?,4,4?-tetrachloroazoxybenzene on selected immune parameters of the mouse - Michael R. Bleavins; Ronald D. Hinsdill; John R. Hochstein; M. T. Stephen Hsia (Archives of Environmental Contamination and Toxicology, 1985)

Neurospora glucamylase and a mutant affected in its regulation - Rita D. Sigmund; Mark T. McNally; Deborah B. Lee; Stephen J. Free (Biochemical Genetics, 1985)

Sex-limited genetic variation in a mouse salivary protein - Robert C. Karn; Stephen R. Dlouhy; Kenneth R. Springer; J. Peter Hjorth; J. Tnnes Nielsen (Biochemical Genetics, 1982)

Embryotoxicity of 3,3?,4,4?-tetrachloroazobenzene and 3,3?,4,4?-tetrachioroazoxybenzene in the chick embryo - Kenneth R. Schrankel; Bill L. Kreamer; M. T. Stephen Hsia (Archives of Environmental Contamination and Toxicology, 1982)

Renal perfusion dynamics during preservation - Stephen W. Flax; John G. Webster; Stuart J. Updike; David T. Uehling (Annals of Biomedical Engineering, 1978)

Dimethyl sulfoxide as an electron acceptor for anaerobic growth - Stephen H. Zinder; T. D. Brock (Archives of Microbiology, 1978)

A pharmacokinetic model for predicting pesticide residues in fish - Stephen F. Krzeminski; Joseph T. Gilbert; John A. Ritts (Archives of Environmental Contamination and Toxicology, 1977)

Lek organization and mating strategies in the bullfrog - Stephen T. Emlen (Behavioral Ecology and Sociobiology, 1976)